Development and future of droplet microfluidics - Nan, Lang; Zhang, Huidan; Weitz, DavidA.; Shum, Ho Cheung (Lab on a Chip, 2024)
Over the past two decades, advances in droplet-based microfluidics have facilitated new approaches to process and analyze samples with unprecedented levels of precision and throughput. A wide variety of applications has been inspired across multiple disciplines ranging from materials science to biology. Understanding the dynamics of droplets enables optimization of microfluidic operations and design of new techniques tailored to emerging demands. In this review, we discuss the underlying physics behind high-throughput generation and manipulation of droplets. We also summarize the applications in droplet-derived materials and droplet-based lab-on-a-chip biotechnology. In addition, we offer perspectives on future directions to realize wider use of droplet microfluidics in industrial production and biomedical analyses.

Spatially non-uniform condensates emerge from dynamically arrested phase separation - Erkamp, Nadia A.; Sneideris, Tomas; Ausserwöger, Hannes; Qian, Daoyuan; Qamar, Seema; Nixon-Abell, Jonathan; St George-Hyslop, Peter; Schmit, Jeremy D.; Weitz, DavidA.; Knowles, Tuomas P. J. (Nature Communications, 2023)
The formation of biomolecular condensates through phase separation from proteins and nucleic acids is emerging as a spatial organisational principle used broadly by living cells. Many such biomolecular condensates are not, however, homogeneous fluids, but possess an internal structure consisting of distinct sub-compartments with different compositions. Notably, condensates can contain compartments that are depleted in the biopolymers that make up the condensate. Here, we show that such double-emulsion condensates emerge via dynamically arrested phase transitions. The combination of a change in composition coupled with a slow response to this change can lead to the nucleation of biopolymer-poor droplets within the polymer-rich condensate phase. Our findings demonstrate that condensates with a complex internal architecture can arise from kinetic, rather than purely thermodynamic driving forces, and provide more generally an avenue to understand and control the internal structure of condensates in vitro and in vivo.

High Throughput Microfluidics Platform to Assess Synthetic Lethality and Novel Therapeutic Drug Combinations - Soltis, Anthony; Zhelyazkova, Boryana; Drake, Pascal; Eleftheriadis, Efstathios; Ventresco, Andrew; Weitz, DavidA.; Iafrate, Anthony J.; Lee, Arlinda (Blood, 2023)

Multichannel Multijunction Droplet Microfluidic Device to Synthesize Hydrogel Microcapsules with Different Core-Shell Structures and Adjustable Core Positions - Wu, Qiong; Huang, Xing; Liu, Ran; Yang, Xinzhu; Xiao, Gao; Jiang, Nan; Weitz, DavidA.; Song, Yukon (Langmuir, 2023)
Core–shell hydrogel microcapsules have sparked great interest due to their unique characteristics and prospective applications in the medical, pharmaceutical, and cosmetic fields. However, complex synthetic procedures and expensive costs have limited their practical application. Herein, we designed and prepared several multichannel and multijunctional droplet microfluidic devices based on soft lithography for the effective synthesis of core–shell hydrogel microcapsules for different purposes. Additionally, two different cross-linking processes (ultraviolet (UV) exposure and interfacial polymerization) were used to synthesize different types of core–shell structured hydrogel microcapsules. Hydrogel microcapsules with gelatin methacryloyl (GelMA) as the core and polyacrylamide (PAM) as the thin shell were synthesized using UV cross-linking. Using an interfacial polymerization process, another core–shell structured microcapsule with GelMA as the core and Ca2+ cross-linked alginate with polyethylenimine (PEI) as the shell was constructed, and the core diameter and total droplet diameter were flexibly controlled by carving. Noteworthy, these hydrogel microcapsules exhibit stimuli-responsiveness and controlled release ability. Overall, a novel technique was developed to successfully synthesize various hydrogel microcapsules with core–shell microstructures. The hydrogel microcapsules possess a multilayered structure that facilitates the coassembly of cells and drugs, as well as the layered assembly of multiple drugs, to develop synergistic therapeutic regimens. These adaptable and controllable hydrogel microdroplets shall held great promise for multicell or multidrug administration as well as for high-throughput drug screening.

The Rapid Generation of Cell-Laden, FACS-CompatibleCollagen Gels - Xiao, Yi; Huang, Qiaoling; Collins, Jesse W.; Brouchon, Julie; Nelson, Jeffery A.; Zachary Niziolek; O'Neil, Alison; Ye, Fangfu; Weitz, DavidA.; Heyman, John A. (Organoids, 2023)
A three-dimensional cell culture in hydrogel beads can support cell growth and differentiation into multi-cellular structures, and these gel beads could be used as building blocks for more complex three-dimensional assemblies. This requires hydrogel beads that are robust enough to sort via FACS yet can be degraded by cell-secreted enzymes. Collagen polymers form hydrogels that are excellent cell growth substrates; however, collagen-containing hydrogel beads typically include additional polymers that limit their degradation. Here, we introduce a simple microfluidic method to generate robust, sortable, cell-laden collagen hydrogel beads. We use on-device pH control to trigger collagen gelation without exposing cells to low pH, ensuring high cell viability. We fabricate microfluidic devices to generate droplets with a wide size range, as demonstrated by production of both small (~55 µm diameter) and large (~300 µm diameter) collagen gels. All hydrogels are sufficiently robust to allow for sorting using FACS. Moreover, high cell viability is maintained throughout the process.

Anomalous crystalline ordering of particles in a viscoelastic fluid under high shear - Sun, Sijie; Xue, Nan; Aime, Stefano; Kim, Hyoungsoo; Tang, Jizhou; Gareth H. McKinley; Stone, A.; Weitz, DavidA. (PNAS, 2023)
Addition of particles to a viscoelastic suspension dramatically alters the properties of the mixture, particularly when it is sheared or otherwise processed. Shear-induced stretching of the polymers results in elastic stress that causes a substantial increase in measured viscosity with increasing shear, and an attractive interaction between particles, leading to their chaining. At even higher shear rates, the flow becomes unstable, even in the absence of particles. This instability makes it very difficult to determine the properties of a particle suspension. Here, we use a fully immersed parallel plate geometry to measure the high-shear-rate behavior of a suspension of particles in a viscoelastic fluid. We find an unexpected separation of the particles within the suspension resulting in the formation of a layer of particles in the center of the cell. Remarkably, monodisperse particles form a crystalline layer which dramatically alters the shear instability. By combining measurements of the velocity field and torque fluctuations, we show that this solid layer disrupts the flow instability and introduces a single-frequency component to the torque fluctuations that reflects a dominant velocity pattern in the flow. These results highlight the interplay between particles and a suspending viscoelastic fluid at very high shear rates.

The liquid-to-solid transition of FUS is promoted by the condensate surface - Shen, Yi; Chen, Anqi; Wang, Wenyun; Shen, Yinan; Ruggeri, Francesco S.; Aime, Stefano; Wang, Zizhao; Qamar, Seema; Espinosa, Jorge R.; Garaizar, Adiran; St. George-Hyslop, Peter; Collepardo-Guevara, Rosana; et al. (PNAS, 2023)
A wide range of macromolecules can undergo phase separation, forming biomolecular condensates in living cells. These membraneless organelles are typically highly dynamic, formed reversibly, and carry out essential functions in biological systems. Crucially, however, a further liquid-to-solid transition of the condensates can lead to irreversible pathological aggregation and cellular dysfunction associated with the onset and development of neurodegenerative diseases. Despite the importance of this liquid-to-solid transition of proteins, the mechanism by which it is initiated in normally functional condensates is unknown. Here we show, by measuring the changes in structure, dynamics, and mechanics in time and space, that single-component FUS condensates do not uniformly convert to a solid gel, but rather that liquid and gel phases coexist simultaneously within the same condensate, resulting in highly inhomogeneous structures. Furthermore, our results show that this transition originates at the interface between the condensate and the dilute continuous phase, and once initiated, the gelation process propagates toward the center of the condensate. To probe such spatially inhomogeneous rheology during condensate aging, we use a combination of established micropipette aspiration experiments together with two optical techniques, spatial dynamic mapping and reflective confocal dynamic speckle microscopy. These results reveal the importance of the spatiotemporal dimension of the liquid-to-solid transition and highlight the interface of biomolecular condensates as a critical element in driving pathological protein aggregation.

Droplet-based high-throughput single microbe RNA sequencing by smRandom-seq - Xu, Ziye; Wang, Yuting; Sheng, Kuanwei; Rosenthal, Raoul; Liu, Nan; Hua, Xiaoting; Zhang, Tianyu; Chen, Jiaye; Song, Mengdi; Lv, Yuexiao; Zhang, Shunji; Huang, Yingjuan; et al. (Nature Communications, 2023)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen50443292_562="398" data-gtm-vis-first-on-screen50443292_563="398" data-gtm-vis-polling-id50443292_562="5197" data-gtm-vis-polling-id50443292_563="5198" data-gtm-vis-recent-on-screen50443292_562="56230413" data-gtm-vis-recent-on-screen50443292_563="56230413" data-gtm-vis-total-visible-time50443292_562="2400" data-gtm-vis-total-visible-time50443292_563="2400" data-title="Abstract" lang="en"> Bacteria colonize almost all parts of the human body and can differ significantly. However, the population level transcriptomics measurements can only describe the average bacteria population behaviors, ignoring the heterogeneity among bacteria. Here, we report a droplet-based high-throughput single-microbe RNA-seq assay (smRandom-seq), using random primers for in situ cDNA generation, droplets for single-microbe barcoding, and CRISPR-based rRNA depletion for mRNA enrichment. smRandom-seq showed a high species specificity (99%), a minor doublet rate (1.6%), a reduced rRNA percentage (32%), and a sensitive gene detection (a median of ~1000 genes per single E. coli). Furthermore, smRandom-seq successfully captured transcriptome changes of thousands of individual E. coli and discovered a few antibiotic resistant subpopulations displaying distinct gene expression patterns of SOS response and metabolic pathways in E. coli population upon antibiotic stress. smRandom-seq provides a high-throughput single-microbe transcriptome profiling tool that will facilitate future discoveries in microbial resistance, persistence, microbe-host interaction, and microbiome research.

Dislocation interactions during plastic relaxation of epitaxial colloidal crystals - Svetlizky, Ilya; Kim, Seongsoo; Weitz, DavidA.; Spaepen, Frans (Nature Communications, 2023)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-50443292_562="227" data-gtm-vis-first-on-screen-50443292_563="227" data-gtm-vis-has-fired-50443292_562="1" data-gtm-vis-has-fired-50443292_563="1" data-gtm-vis-total-visible-time-50443292_562="10000" data-gtm-vis-total-visible-time-50443292_563="10000" data-title="Abstract" lang="en"> The severe difficulty to resolve simultaneously both the macroscopic deformation process and the dislocation dynamics on the atomic scale limits our understanding of crystal plasticity. Here we use colloidal crystals, imaged on the single particle level by high-speed three-dimensional (3D) confocal microscopy, and resolve in real-time both the relaxation of the epitaxial misfit strain and the accompanying evolution of dislocations. We show how dislocation interactions give rise to the formation of complex dislocation networks in 3D and to unexpectedly sharp plastic relaxation. The sharp relaxation is facilitated by attractive interactions that promote the formation of new dislocations that are more efficient in mediating strain. Dislocation networks form fragmented structures, as dislocation growth is blocked by either attractive interactions, which result in the formation of sessile dislocation junctions, or by repulsion from perpendicular segments. The strength of these blocking mechanisms decreases with the thickness of the crystal film. These results reveal the critical role of dislocation interactions in plastic deformation of thin films and can be readily generalized from the colloidal to the atomic scale.

Positional influence on cellular transcriptional identity revealed through spatially segmented single-cell transcriptomics - Morse, David B.; Michalowski, Aleksandra M.; Ceribelli, Michele; De Jonghe, Joachim; Vias, Maria; Riley, Deanna; Davies-Hill, Theresa; Voss, Ty; Pittaluga, Stefania; Muus, Christoph; Liu, Jiamin; Boyle, Samantha; et al. (Cell Systems, 2023)
Single-cell RNA sequencing (scRNA-seq) is a powerful technique for describing cell states. Identifying the spatial arrangement of these states in tissues remains challenging, with the existing methods requiring niche methodologies and expertise. Here, we describe segmentation by exogenous perfusion (SEEP), a rapid and integrated method to link surface proximity and environment accessibility to transcriptional identity within three-dimensional (3D) disease models. The method utilizes the steady-state diffusion kinetics of a fluorescent dye to establish a gradient along the radial axis of disease models. Classification of sample layers based on dye accessibility enables dissociated and sorted cells to be characterized by transcriptomic and regional identities. Using SEEP, we analyze spheroid, organoid, and in vivo tumor models of high-grade serous ovarian cancer (HGSOC). The results validate long-standing beliefs about the relationship between cell state and position while revealing new concepts regarding how spatially unique microenvironments influence the identity of individual cells within tumors.

Controlled Continuous Evolution of Enzymatic Activity Screened at Ultrahigh Throughput Using Drop-Based Microfluidics - Rosenthal, Raoul G.; Zhang, Xinge Diana; Durdic, Karla Ilic; Collins, J.J.; Weitz, DavidA. (Angewandte Chemie, 2023)
Enzymes are highly specific catalysts delivering improved drugs and greener industrial processes. Naturally occurring enzymes must typically be optimized which is often accomplished through directed evolution; however, this is still a labor- and capital-intensive process, due in part to multiple molecular biology steps including DNA extraction, in vitro library generation, transformation, and limited screening throughput. We present an effective and broadly applicable continuous evolution platform that enables controlled exploration of fitness landscape to evolve enzymes at ultrahigh throughput based on direct measurement of enzymatic activity. This drop-based microfluidics platform cycles cells between growth and mutagenesis followed by screening with minimal human intervention, relying on the nCas9 chimera with mutagenesis polymerase to produce in vivo gene diversification using sgRNAs tiled along the gene. We evolve alditol oxidase to change its substrate specificity towards glycerol, turning a waste product into a valuable feedstock. We identify a variant with a 10.5-fold catalytic efficiency.

Rock-on-a-chip: “Seeing” the association/disassociation of an adaptive polymer in solutions flowing through porous media - Zhang, Yan; Zhao, Xuezhi; Han, Peihui; He, Tianlei; Yin, Hongyao; Zhang, Liyuan; Feng, Yujun; Weitz, DavidA. (Lab on a Chib, 2023)
The flow and transport of polymer solutions through porous media are ubiquitous in myriad scientific and engineering applications. With escalating interest in adaptive polymers, understanding the flow dynamics of their solutions is indispensable (yet lacking). Here, the hydrophobic-effect-driven reversible associations in a self-adaptive polymer (SAP) solution and its flow characteristics in a microfluidic-based “rock-on-a-chip” device have been analyzed. The hydrophobic aggregates were fluorescent labeled; this enabled a direct visualization of the in situ association/disassociation of the polymer supramolecular assemblies in pore spaces and throats. Furthermore, the influence of this adaptation on the macroscopic flow behavior of the SAP solution was analyzed by comparing its flow with that of two partially-hydrolyzed polyacrylamide (the molecular weight (MW)-equivalent HPAM-1 and ultrahigh-MW HPAM-2) solutions in the semi-dilute regime with similar initial viscosities. At low flow rates (with shear predominance), the SAP solution showed a low shear viscosity compared to HPAM-1, indicating a higher shear susceptibility for association than chain entanglement. Although the SAP exhibited the same elastic instability as the non-adaptive polymers above a threshold flow rate, the adaptable structure of the former advanced the onset of its viscoelastic-governed flow, providing a stronger flow resistance, possibly through an extension resistance. Furthermore, 3D-media analysis indicated that the reversible association/disassociation of SAP increased the accessible pore space during nonaqueous-liquid displacement, facilitating oil production.

Kinetics of formation of a macroscale binary Coulombic material - Battat, Sarah; Nagarkar, Amit A.; Spaepen, Frans; Weitz, DavidA.; George M. Whitesides (Physical Review Materials, 2023)
The electrostatic self-assembly of charged Brownian objects typically occurs in cases of short-range interactions. The objects form Coulombic materials that are close-packed and have long-range order. Here, we present a system in which two kinds of non-Brownian millimeter-sized beads tribocharge differently, experience long-range electrostatic interactions, and still form ordered two-dimensional structures. We provide a complete characterization of the kinetics of formation of these materials, as the total number of beads is held constant and the relative number of beads that tribocharge negatively or positively is modified. We agitate the beads by shaking the dish in which they are contained. We show that the beads commonly adopt a transient structure that we call a rosette. A rosette consists of a central bead surrounded by six close-packed neighbors of a different kind. The symmetry of the final structure depends on the relative number of negatively and positively charged beads, and it is not necessarily the same as that of the transient structure. Our results bear important implications in the de novo design of Coulombic materials given our ability to isolate transient structures, identify the moment of their appearance, and quantify the impact of agitation, tribocharging, and Coulombic energy minimization on their persistence.

Visualization of adaptive polymer flow and displacement in medium-permeable 3D core-on-a-chip - Zhang, Yan; Zhao, Xue-Zhi; Han, Pei-Hui; Zhang, Li-Yuan; Weitz, DavidA.; Feng, Yu-Jun (Petroleum Science, 2023)
Polymer flooding has been witnessed an effective technology for enhancing oil recovery from medium-to low-permeability reservoirs; however, direct visualization of polymer solution flow in such reservoir condition is still lacking. In this work, a three-dimensional (3D) core-on-a-chip device with a permeability of around 200 mD was prepared and employed to visualize the pore-scale flow and displacement of a self-adaptive polymer (SAP, 8.7 × 106 g·mol−1)−whose microscopic association structure and macroscopic viscosity can reversibly change in response to shear action−versus partially hydrolyzed polyacrylamide(HPAM), by recording their flow curves, monitoring dynamic transportation process via particle imaging velocimetry, and building 3D structure of remaining oil. The results show that, in single-phase flow, all polymer solutions exhibit flow thinning and then thickening regions as flow rate increases, but the transition between two regimes occurs at a small Weissenberg number (10−3−10−1) in this medium-permeable condition. In contrast to HPAM-1 with close weight-average molecular weight (Mw), the adaptive character not only extends SAP's shear-govern region, allowing SAP to propagate piece by piece and achieve higher accessible pore volume, but it also enhances the elastic resistibility of polymer in the extension-dominated regime, increasing the microscopic displacement efficiency. These two effects result in 1.5–3 times more oil recovery factor for SAP than for HPAM-1. Regarding ultra-high-Mw HPAM-2 (25 × 106 g·mol−1), plugging and chain degradation do occur, thus producing lower oil recovery than SAP. This work provides a direct approach for in-situ assessment of polymer-based displacing system under a more authentic condition of practical reservoirs.

Melting of a macroscale binary Coulombic crystal - Battat, Sarah; Weitz, DavidA.; George M. Whitesides (Soft Matter, 2023)
The question of melting has been addressed theoretically and experimentally for two-dimensional crystals in thermal equilibrium. However, as it pertains to out-of-equilibrium systems, the question is unresolved. Here, we present a platform to study the melting of a two-dimensional, binary Coulombic crystal composed of equal numbers of nylon and polytetrafluoroethylene (PTFE) beads that measure a couple of millimeters in diameter. The beads are tribocharged—nylon positively and PTFE negatively—and they experience long-range electrostatic interactions. They form a square crystal in which nylon and PTFE beads sit at alternating sites on a checkerboard lattice. We melt the crystal by agitating the dish in which it resides using an orbital shaker. We compare the melting behavior of the crystal without impurities to that of the crystal with impurities, where we use gold-coated nylon beads as impurities because they tribocharge negligibly. Our results reveal that impurities do not influence the melting of the crystal. Instead, the crystal undergoes shear-induced melting, beginning from its edges, due to its collisions with the dish. As a result of repetitive collisions, the beads acquire kinetic energy, undergo rearrangements, and become disordered. Unlike most examples of shear-induced melting, portions of the crystal remain locally ordered given the persistence of electrostatic interactions and the occurrence of some collisions that are favorable to ordering clusters of beads. Our work clarifies the melting behavior of sheared crystals whose constituents have persistent long-range interactions. It may prove valuable in determining the conditions under which such materials are immune to disorder.

Matrix viscoelasticity controls spatiotemporal tissue organization - Elosegui-Artola, Alberto; Anupam Gupta; Najibi, Alexander J.; Seo, Bo Ri; Garry, Ryan; Tringides, Christina M.; de Lázaro, Irene; Darnell, Max; Gu, Wei; Zhou, Qiao; Weitz, DavidA.; Mahadevan, L.; et al. (Nature Materials, 2023)
Biomolecular and physical cues of the extracellular matrix environment regulate collective cell dynamics and tissue patterning. Nonetheless, how the viscoelastic properties of the matrix regulate collective cell spatial and temporal organization is not fully understood. Here we show that the passive viscoelastic properties of the matrix encapsulating a spheroidal tissue of breast epithelial cells guide tissue proliferation in space and in time. Matrix viscoelasticity prompts symmetry breaking of the spheroid, leading to the formation of invading finger-like protrusions, YAP nuclear translocation and epithelial-to-mesenchymal transition both in vitro and in vivo in a Arp2/3-complex-dependent manner. Computational modelling of these observations allows us to establish a phase diagram relating morphological stability with matrix viscoelasticity, tissue viscosity, cell motility and cell division rate, which is experimentally validated by biochemical assays and in vitro experiments with an intestinal organoid. Altogether, this work highlights the role of stress relaxation mechanisms in tissue growth dynamics, a fundamental process in morphogenesis and oncogenesis.

Stimuli-Triggered Multishape, Multimode, and Multistep Deformations Designed by Microfluidic 3D Droplet Printing - Yang, Chenjing; Xiao, Yao; Hu, Lingjie; Chen, Jingyi; Zhao, Chun-Xia; Zhao, Peng; Ruan, Jian; Wu, Ziliang; Yu, Haifeng; Weitz, DavidA.; Chen, Dong (small, 2023)
Elastomers generally possess low Young's modulus and high failure strain, which are widely used in soft robots and intelligent actuators. However, elastomers generally lack diverse functionalities, such as stimulated shape morphing, and a general strategy to implement these functionalities into elastomers is still challenging. Here, a microfluidic 3D droplet printing platform is developed to design composite elastomers architected with arrays of functional droplets. Functional droplets with controlled size, composition, position, and pattern are designed and implemented in the composite elastomers, imparting functional performances to the systems. The composited elastomers are sensitive to stimuli, such as solvent, temperature, and light, and are able to demonstrate multishape (bow- and S-shaped), multimode (gradual and sudden), and multistep (one- and two-step) deformations. Based on the unique properties of droplet-embedded composite elastomers, a variety of stimuli-responsive systems are developed, including designable numbers, biomimetic flowers, and soft robots, and a series of functional performances are achieved, presenting a facile platform to impart diverse functionalities into composite elastomers by microfluidic 3D droplet printing.

Phase separation-induced nanoprecipitation for making polymer nanoparticles with high drug loading - Yang, Guangze; Liu, Yun; Song Jin; Hui, Yue; Wang, Xing; Xu, Letao; Chen, Dong; Weitz, DavidA.; Zhao, Chun-Xiao (Aggregate, 2023)
Increasing drug loading remains a critical challenge in the development and translation of nanomedicine. High drug-loading nanoparticles have demonstrated unique advantages such as less carrier material used, better-controlled drug release, and improved efficacy and safety. Herein, we report a simple and efficient salt concentration screening method for making polymer nanoparticles with exceptionally high drug loading (up to 66.5 wt%) based on phase separation-induced nanoprecipitation. Upon addition of salt, phase separation occurs in a miscible solvent-water solution delaying the precipitation time of drugs and polymers to different extents, facilitating their co-precipitation thus the formation of high drug-loading nanoparticles with high encapsulation efficiency (>90%) and excellent stability (>1 month). This technology is versatile and easy to be adapted to various hydrophobic drugs, different polymers, and solvents. This salt-induced nanoprecipitation strategy offers a novel approach to fabricating polymer nanoparticles with tunable drug loading, and opens great potentials for future nanomedicines.

Droplet-based transcriptome profiling of individual synapses - Niu, Muchun; Cao, Wenjian; Wang, Yongcheng; Zhu, Qiangyuan; Luo, Jiayi; Wang, Baiping; Zheng, Hui; Weitz, DavidA.; Zong, Chenghang (Nature Biotechnology, 2023)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-50443292_562="695" data-gtm-vis-first-on-screen-50443292_563="695" data-gtm-vis-has-fired-50443292_562="1" data-gtm-vis-has-fired-50443292_563="1" data-gtm-vis-total-visible-time-50443292_562="10000" data-gtm-vis-total-visible-time-50443292_563="10000" data-title="Abstract" lang="en"> Synapses are crucial structures that mediate signal transmission between neurons in complex neural circuits and display considerable morphological and electrophysiological heterogeneity. So far we still lack a high-throughput method to profile the molecular heterogeneity among individual synapses. In the present study, we develop a droplet-based single-cell (sc) total-RNA-sequencing platform, called Multiple-Annealing-and-Tailing-based Quantitative scRNA-seq in Droplets, for transcriptome profiling of individual neurites, primarily composed of synaptosomes. In the synaptosome transcriptome, or ‘synaptome’, profiling of both mouse and human brain samples, we detect subclusters among synaptosomes that are associated with neuronal subtypes and characterize the landscape of transcript splicing that occurs within synapses. We extend synaptome profiling to synaptopathy in an Alzheimer’s disease (AD) mouse model and discover AD-associated synaptic gene expression changes that cannot be detected by single-nucleus transcriptome profiling. Overall, our results show that this platform provides a high-throughput, single-synaptosome transcriptome profiling tool that will facilitate future discoveries in neuroscience.

Bioinspired Tough and Strong Fibers with Hierarchical Core-Shell Structure - Xiao, Yao; Yang, Chenjing; Zhai, Xiaowei; Zhao, Lai; Zhao, Peng; Ruan, Jian; Chen, Dong; Weitz, DavidA.; Liu, Kai (Advanced Materials Interfaces, 2023)
Strong and tough bio-based fibers are attractive for both fundamental research and practical applications. In this work, strong and tough hierarchical core–shell fibers with cellulose nanofibrils (CNFs) in the core and regenerated silk fibroins (RSFs) in the shell are designed and prepared, mimicking natural spider silks. CNF/RSF core–shell fibers with precisely controlled morphology are continuously wet-spun using a co-axial microfluidic device. Highly-dense non-covalent interactions are introduced between negatively-charged CNFs in the core and positively-charged RSFs in the shell, diminishing the core/shell interface and forming an integral hierarchical fiber. Meanwhile, shearing by microfluidic channels and post-stretching induce a better ordering of CNFs in the core and RSFs in the shell, while ordered CNFs and RSFs are more densely packed, thus facilitating the formation of non-covalent interactions within the fiber matrix. Therefore, CNF/RSF core–shell fibers demonstrate excellent mechanical performances; especially after post-stretching, their tensile strength, tensile strain, Young's modulus, and toughness are up to 635 MPa, 22.4%, 24.0 GPa, and 110 MJ m−3, respectively. In addition, their mechanical properties are barely compromised even at −40 and 60 °C. Static load and dynamic impact tests suggest that CNF/RSF core–shell fibers are strong and tough, making them suitable for advanced structural materials.

Visualization of Flow-Induced Strain Using Structural Color in Channel-Free Polydimethylsiloxane Devices - Shiba, Kota; Zhuang, Chao; Minami, Kosuke; Imamura, Gaku; Tamura, Ryo; Samitsu, Sadaki; Idei, Takumi; Yoshikawa, Genki; Sun, Luyi; Weitz, DavidA. (Advanced Science, 2023)
Measuring flow of gases is of fundamental importance yet is typically done with complex equipment. There is, therefore, a longstanding need for a simple and inexpensive means of flow measurement. Here, gas flow is measured using an extremely simple device that consists of an Ar plasma-treated polydimethylsiloxane (PDMS) slab adhered on a glass substrate with a tight seal. This device does not even have a channel, instead, gas can flow between the PDMS and the glass by deforming the PDMS wall, in other words, by making an interstice as a temporary path for the flow. The formation of the temporary path results in a compressive bending stress at the inner wall of the path, which leads to the formation of well-ordered wrinkles, and hence, the emergence of structural color that changes the optical transmittance of the device. Although it is very simple, this setup works sufficiently well to measure arbitrary gases and analyzes their flow rates, densities, and viscosities based on the change in color. It is also demonstrated that this technique is applicable to the flow-induced display of a pattern such as a logo for advanced applications.

Rapid parallel generation of a fluorescently barcoded drop library from a microtiter plate using the plate-interfacing parallel encapsulation (PIPE) chip - Zath, Geoffrey K.; Sperling, Ralph A.; Hoffman, Carter W.; Bikos, Dimitri A.; Abbasi, Reha; Abate, Adam R.; Weitz, DavidA.; Chang, Connie B. (Lab on a Chip, 2022)
In drop-based microfluidics, an aqueous sample is partitioned into drops using individual pump sources that drive water and oil into a drop-making device. Parallelization of drop-making devices is necessary to achieve high-throughput screening of multiple experimental conditions, especially in time-sensitive studies. Here, we present the plate-interfacing parallel encapsulation (PIPE) chip, a microfluidic chip designed to generate 50 to 90 μm diameter drops of up to 96 different conditions in parallel by interfacing individual drop makers with a standard 384-well microtiter plate. The PIPE chip is used to generate two types of optically barcoded drop libraries consisting of two-color fluorescent particle combinations: a library of 24 microbead barcodes and a library of 192 quantum dot barcodes. Barcoded combinations in the drop libraries are rapidly measured within a microfluidic device using fluorescence detection and distinct barcoded populations in the fluorescence drop data are identified using DBSCAN data clustering. Signal analysis reveals that particle size defines the source of dominant noise present in the fluorescence intensity distributions of the barcoded drop populations, arising from Poisson loading for microbeads and shot noise for quantum dots. A barcoded population from a drop library is isolated using fluorescence-activated drop sorting, enabling downstream analysis of drop contents. The PIPE chip can improve multiplexed high-throughput assays by enabling simultaneous encapsulation of barcoded samples stored in a microtiter plate and reducing sample preparation time.

Multidisciplinary endeavors make future medicine smart - Shang, Luoran; Cao, Yihai; Weitz, DavidA. (Smart Medicine, 2022)
Humans suffer from thousands of diseases, and many of them lack effective methods for diagnosis and treatment. To address these unmet medical needs, basic research in multiple areas can provide important clinical contributions. The breathtaking discoveries in fundamental life sciences not only enhance our understanding of the human body but also lead to the creation of new diagnostics and pharmaceuticals. Innovations in medically relevant technologies, drawing on a wide range of disciplines, bring hope to previously intractable illnesses. All these lead to the dramatic transformation of medicine toward “Smart Medicine.” We foresee the future of medicine to be nourished with cutting-edge ideas from many different fields. We also anticipate specially designed methods that help translate these ideas and make them fit for specific healthcare purposes.

Visualization of adaptive polymer flow and displacement in medium-permeable 3D core-on-a-chip - Zhang, Yan; Zhao, Xue-Zhi; Han, Pei-Hui; Zhang, Li-Yuan; Weitz, DavidA.; Feng, Yu-Jun Feng (Petroleum Science, 2022)
Polymer flooding has been witnessed an effective technology for enhancing oil recovery from medium-to low-permeability reservoirs; however, direct visualization of polymer solution flow in such reservoir condition is still lacking. In this work, a three-dimensional (3D) core-on-a-chip device with a permeability of around 200 mD was prepared and employed to visualize the pore-scale flow and displacement of a self-adaptive polymer (SAP, 8.7 × 106 g∙mol−1)−whose microscopic association structure and macroscopic viscosity can reversibly change in response to shear action−versus partially hydrolyzed polyacrylamide (HPAM), by recording their flow curves, monitoring dynamic transportation process via particle imaging velocimetry, and building 3D structure of remaining oil. The results show that, in single-phase flow, all polymer solutions exhibit flow thinning and then thickening regions as flow rate increases, but the transition between two regimes occurs at a small Weissenberg number (10−3−10−1) in this medium-permeable condition. In contrast to HPAM-1 with close weight-average molecular weight (Mw), the adaptive character not only extends SAP's shear-govern region, allowing SAP to propagate piece by piece and achieve higher accessible pore volume, but it also enhances the elastic resistibility of polymer in the extension-dominated regime, increasing the microscopic displacement efficiency. These two effects result in 1.5–3 times more oil recovery factor for SAP than for HPAM-1. Regarding ultra-high-Mw HPAM-2 (25 × 106 g∙mol−1), plugging and chain degradation do occur, thus producing lower oil recovery than SAP. This work provides a direct approach for in-situassessment of polymer-based displacing system under a more authentic condition of practical reservoirs.

‘Phase transitions’ in bacteria – From structural transitions in free living bacteria to phenotypic transitions in bacteria within biofilms - Wang, Xiaoling; Blumenfeld, Raphael; Feng, Xi-Qiao; Weitz, DavidA. (Physics of Life Reviews, 2022)
Phase transitions are common in inanimate systems and have been studied extensively in natural sciences. Less explored are the rich transitions that take place at the micro- and nano-scales in biological systems. In conventional phase transitions, large-scale properties of the media change discontinuously in response to continuous changes in external conditions. Such changes play a significant role in the dynamic behaviours of organisms. In this review, we focus on some transitions in both free-living and biofilms of bacteria. Particular attention is paid to the transitions in the flagellar motors and filaments of free-living bacteria, in cellular gene expression during the biofilm growth, in the biofilm morphology transitions during biofilm expansion, and in the cell motion pattern transitions during the biofilm formation. We analyse the dynamic characteristics and biophysical mechanisms of these phase transition phenomena and point out the parallels between these transitions and conventional phase transitions. We also discuss the applications of some theoretical and numerical methods, established for conventional phase transitions in inanimate systems, in bacterial biofilms.

Research Progress in High-Throughput Screening of CO2 Reduction Catalysts - Wu, Qinglin; Pan, Meidie; Zhang, Shikai; Sun, Dongpeng; Yang Yang; Chen, Dong; Weitz, DavidA.; Gao, Xiang (Energies, 2022)
The conversion and utilization of carbon dioxide (CO2) have dual significance for reducing carbon emissions and solving energy demand. Catalytic reduction of CO2 is a promising way to convert and utilize CO2. However, high-performance catalysts with excellent catalytic activity, selectivity and stability are currently lacking. High-throughput methods offer an effective way to screen high-performance CO2 reduction catalysts. Here, recent advances in high-throughput screening of electrocatalysts for CO2reduction are reviewed. First, the mechanism of CO2 reduction reaction by electrocatalysis and potential catalyst candidates are introduced. Second, high-throughput computational methods developed to accelerate catalyst screening are presented, such as density functional theory and machine learning. Then, high-throughput experimental methods are outlined, including experimental design, high-throughput synthesis, in situ characterization and high-throughput testing. Finally, future directions of high-throughput screening of CO2 reduction electrocatalysts are outlooked. This review will be a valuable reference for future research on high-throughput screening of CO2 electrocatalysts.

Soft materials evolution and revolution - Weitz, DavidA. (Nature Materials, 2022)
Soft matter has evolved considerably since it became recognized as a unified field. This has been driven by new experimental, numerical and theoretical methods to probe soft matter, and by new ways of formulating soft materials. These advances have driven a revolution in knowledge and expansion into biological and active matter.

Line optical tweezers as controllable micromachines: techniques and emerging trends - Shen, Yinan; Weitz, DavidA.; Forde, Nancy R.; Shayegan, Marjan (Soft Matter, 2022)
In the past three decades, the technology of optical tweezers has made significant contributions in various scientific areas, including optics, photonics, and nanosciences. Breakthroughs include manipulating particles in both static and dynamic ways, particle sorting, and constructing controllable micromachines. Advances in shaping and controlling the laser beam profile enable control over the position and location of the trap, which has many possible applications. A line optical tweezer (LOT) can be created by rapidly moving a spot optical tweezer using a tool such as a galvanometer mirror or an acousto-optic modulator. By manipulating the intensity profile along the beam line to be asymmetric or non-uniform, the technique can be adapted to various specific applications. Among the many exciting applications of line optical tweezers, in this work, we discuss in detail applications of LOT, including probing colloidal interactions, transporting and sorting of colloidal microspheres, self-propelled motions, trapping anisotropic particles, exploring colloidal interactions at fluid-fluid interfaces, and building optical thermal ratchets. We further discuss prospective applications in each of these areas of soft matter, including polymeric and biological soft materials.

High-throughput, single-microbe genomics with strain resolution, applied to a human gut microbiome - Zheng, Wenshan; Zhao, Shijie; Yin, Yehang; Zhang, Huidan; Needham, David M.; Evans, Ethan D.; Dai, Chengzhen L.; Lu, Peter J.; Alm, Eric J.; Weitz, DavidA. (Science, 2022)
Single-cell methods are the state of the art in biological research. Zheng et al. developed a high-throughput technique called Microbe-seq designed to analyze single bacterial cells from a microbiota. Microbe-seq uses microfluidics to separate individual bacterial cells within droplets and then extract, amplify, and barcode their DNA, which is then subject to pooled Illumina sequencing. The technique was tested by sequencing multiple human fecal samples to generate barcoded reads for thousands of single amplified genomes (SAGs) per sample. Pooling the SAGs corresponding to the same bacterial species allowed consensus assemblies of these genomes to provide insights into strain-level diversity and revealed a phage association and the limits on horizontal gene-transfer events between strains.

A high-throughput multiparameter screen for accelerated development and optimization of soluble genetically encoded fluorescent biosensors - Koveal, Dorothy; Rosen, Paul C.; Meyer, Dylan J.; Diaz-Garcia, Carlos Manlio; Wang, Yongcheng; Cai, Li-Heng; Chou, Peter J.; Weitz, DavidA.; Yellen, Gary (Nature Communications, 2022)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-50443292_562="598" data-gtm-vis-first-on-screen-50443292_563="599" data-gtm-vis-has-fired-50443292_562="1" data-gtm-vis-has-fired-50443292_563="1" data-gtm-vis-total-visible-time-50443292_562="10000" data-gtm-vis-total-visible-time-50443292_563="10000" data-title="Abstract" lang="en"> Genetically encoded fluorescent biosensors are powerful tools used to track chemical processes in intact biological systems. However, the development and optimization of biosensors remains a challenging and labor-intensive process, primarily due to technical limitations of methods for screening candidate biosensors. Here we describe a screening modality that combines droplet microfluidics and automated fluorescence imaging to provide an order of magnitude increase in screening throughput. Moreover, unlike current techniques that are limited to screening for a single biosensor feature at a time (e.g. brightness), our method enables evaluation of multiple features (e.g. contrast, affinity, specificity) in parallel. Because biosensor features can covary, this capability is essential for rapid optimization. We use this system to generate a high-performance biosensor for lactate that can be used to quantify intracellular lactate concentrations. This biosensor, named LiLac, constitutes a significant advance in metabolite sensing and demonstrates the power of our screening approach.

Large-scale single-cell encapsulation in microgels through metastable droplet-templating combined with microfluidic-integration - Zhang, Haoyue; Zhang, Liyuan; An, Chuanfeng; Zhang, Yang; Zhao, Fei; Gao, Yijie; Zhang, Yonghao; Li, Hanting; Zhang, Yujie; Ren, Changle; Sun, Kai; He, Wei; et al. (Biofabrication, 2022)
Current techniques for the generation of cell-laden microgels are limited by numerous challenges, including poorly uncontrolled batch-to-batch variations, processes that are both labor- and time-consuming, the high expense of devices and reagents, and low production rates; this hampers the translation of laboratory findings to clinical applications. To address these challenges, we develop a droplet-based microfluidic strategy based on metastable droplet-templating and microchannel integration for the substantial large-scale production of single cell-laden alginate microgels. Specifically, we present a continuous processing method for microgel generation by introducing amphiphilic perfluoronated alcohols to obtain metastable emulsion droplets as sacrificial templates. In addition, to adapt to the metastable emulsion system, integrated microfluidic chips containing 80 drop-maker units are designed and optimized based on the computational fluid dynamics simulation. This strategy allows single cell encapsulation in microgels at a maximum production rate of 10 ml h−1 of cell suspension while retaining cell viability and functionality. These results represent a significant advance toward using cell-laden microgels for clinical-relevant applications, including cell therapy, tissue regeneration and 3D bioprinting.

Adsorption of Polar Species at Crude Oil-Water Interfaces: the Chemoelastic Behavior - Saad, Ahmed M.; Aime, Stefano; Mahavadi, Sharath Chandra; Song, Yi-Qiao; Yutkin, Maxim P.; Weitz, DavidA.; Patzek, Tadeusz W. (Langmuir, 2022)
We investigate the formation and properties of crude oil/water interfacial films. The time evolution of interfacial tension suggests the presence of short and long timescale processes reflecting the competition between different populations of surface-active molecules. We measure both the time-dependent shear and extensional interfacial rheology moduli. Late-time interface rheology is dominated by elasticity, which results in visible wrinkles on the crude oil drop surface upon interface disturbance. We also find that the chemical composition of the interfacial films is affected by the composition of the aqueous phase that it has contacted. For example, sulfate ions promote films enriched with carboxylic groups and condensed aromatics. Finally, we perform solution exchange experiments and monitor the late-time film composition upon the exchange. We detect the film composition change upon replacing chloride solutions with sulfate-enriched ones. To the best of our knowledge, we are the first to report the composition alteration of aged crude oil films. This finding might foreshadow an essential crude oil recovery mechanism.

Correlation Tracking: Using simulations to interpolate highly correlated particle tracks - King, Ella M.; Wang, Zizhao; Weitz, DavidA.; Spaepen, Frans; Michael P. Brenner (Physical Review E, 2022)
Despite significant advances in particle imaging technologies over the past two decades, few advances have been made in particle tracking, i.e., linking individual particle positions across time series data. The state-of-the-art tracking algorithm is highly effective for systems in which the particles behave mostly independently. However, these algorithms become inaccurate when particle motion is highly correlated, such as in dense or strongly interacting systems. Accurate particle tracking is essential in the study of the physics of dense colloids, such as the study of dislocation formation, nucleation, and shear transformations. Here, we present a method for particle tracking that incorporates information about the correlated motion of the particles. We demonstrate significant improvement over the state-of-the-art tracking algorithm in simulated data on highly correlated systems.

Dielectrophoretic Characterization of Dynamic Microcapsules and Their Magnetophoretic Manipulation - Elkeles, Tom; Park, Sinwook; Werner, Joerg G.; Weitz, DavidA.; Yossifon, Gilad (ACS Appl. Mater. Interfaces, 2022)
In this work, we present dielectrophoresis (DEP) and in situ electrorotation (ROT) characterization of reversibly stimuli-responsive “dynamic” microcapsules that change the physicochemical properties of their shells under varying pH conditions and can encapsulate and release (macro)molecular cargo on demand. Specifically, these capsules are engineered to open (close) their shell under high (low) pH conditions and thus to release (retain) their encapsulated load or to capture and trap (macro)molecular samples from their environment. We show that the steady-state DEP and ROT spectra of these capsules can be modeled using a single-shell model and that the conductivity of their shells is influenced most by the pH. Furthermore, we measured the transient response of the angular velocity of the capsules under rotating electric field conditions, which allows us to directly determine the characteristic time scales of the underlying physical processes. In addition, we demonstrate the magnetic manipulation of microcapsules with embedded magnetic nanoparticles for lab-on-chip tasks such as encapsulation and release at designated locations and the in situ determination of their physicochemical state using on-chip ROT. The insight gained will enable the advanced design and operation of these dynamic drug delivery and smart lab-on-chip transport systems.

Regulation of cell attachment, spreading, and migration by hydrogel substrates with independently tunable mesh size - Xia, Jing; Liu, Zong-Yuan; Han, Zheng-Yuan; Yuan, Yuan; Shao, Yue; Feng, Xi-Qiao; Weitz, DavidA. (Acta Biomaterialia, 2022)
Hydrogels are widely used as substrates to investigate interactions between cells and their microenvironment as they mimic many attributes of the extracellular matrix. The stiffness of hydrogels is an important property that is known to regulate cell behavior. Beside stiffness, cells also respond to structural cues such as mesh size. However, since the mesh size of hydrogel is intrinsically coupled to its stiffness, its role in regulating cell behavior has never been independently investigated. Here, we report a hydrogel system whose mesh size and stiffness can be independently controlled. Cell behavior, including spreading, migration, and formation of focal adhesions is significantly altered on hydrogels with different mesh sizes but with the same stiffness. At the transcriptional level, hydrogel mesh size affects cellular mechanotransduction by regulating nuclear translocation of yes-associated protein. These findings demonstrate that the mesh size of a hydrogel plays an important role in cell-substrate interactions.

Vimentin intermediate filaments and filamentous actin form unexpected interpenetrating networks that redefine the cell cortex - Huayin Wu; Shen, Yinan; Sivagurunathan, Suganya; Weber, Miriam Sarah; Adam, Stephen A.; Shin, Jennifer H.; Jeffrey J. Fredberg; Medalia, Ohad; Goldman, Robert; Weitz, DavidA. (PNAS, 2022)
The cytoskeleton of eukaryotic cells is primarily composed of networks of filamentous proteins, F-actin, microtubules, and intermediate filaments. Interactions among the cytoskeletal components are important in determining cell structure and in regulating cell functions. For example, F-actin and microtubules work together to control cell shape and polarity, while the subcellular organization and transport of vimentin intermediate filament (VIF) networks depend on their interactions with microtubules. However, it is generally thought that F-actin and VIFs form two coexisting but separate networks that are independent due to observed differences in their spatial distribution and functions. In this paper, we present a closer investigation of both the structural and functional interplay between the F-actin and VIF cytoskeletal networks. We characterize the structure of VIFs and F-actin networks within the cell cortex using structured illumination microscopy and cryo-electron tomography. We find that VIFs and F-actin form an interpenetrating network (IPN) with interactions at multiple length scales, and VIFs are integral components of F-actin stress fibers. From measurements of recovery of cell contractility after transient stretching, we find that the IPN structure results in enhanced contractile forces and contributes to cell resilience. Studies of reconstituted networks and dynamic measurements in cells suggest direct and specific associations between VIFs and F-actin. From these results, we conclude that VIFs and F-actin work synergistically, both in their structure and in their function. These results profoundly alter our understanding of the contributions of the components of the cytoskeleton, particularly the interactions between intermediate filaments and F-actin.

Nonlinear Phenomena in Microfluidics - Battat, Sarah; Weitz, DavidA.; Whitesides, George (Chemical Reviews, 2022)
This review focuses on experimental work on nonlinear phenomena in microfluidics, which for the most part are phenomena for which the velocity of a fluid flowing through a microfluidic channel does not scale proportionately with the pressure drop. Examples include oscillations, flow-switching behaviors, and bifurcations. These phenomena are qualitatively distinct from laminar, diffusion-limited flows that are often associated with microfluidics. We explore the nonlinear behaviors of bubbles or droplets when they travel alone or in trains through a microfluidic network or when they assemble into either one- or two-dimensional crystals. We consider the nonlinearities that can be induced by the geometry of channels, such as their curvature or the bas-relief patterning of their base. By casting posts, barriers, or membranes─situated inside channels─from stimuli-responsive or flexible materials, the shape, size, or configuration of these elements can be altered by flowing fluids, which may enable autonomous flow control. We also highlight some of the nonlinearities that arise from operating devices at intermediate Reynolds numbers or from using non-Newtonian fluids or liquid metals. We include a brief discussion of relevant practical applications, including flow gating, mixing, and particle separations.

The correlation between cell and nucleus size is explained by an eukaryotic cell growth model - Wu, Yufei; Adrian F. Pegoraro; Weitz, DavidA.; Paul Janmey; Sun, Sean X. (PLOS Computational Biology, 2022)
In eukaryotes, the cell volume is observed to be strongly correlated with the nuclear volume. The slope of this correlation depends on the cell type, growth condition, and the physical environment of the cell. We develop a computational model of cell growth and proteome increase, incorporating the kinetics of amino acid import, protein/ribosome synthesis and degradation, and active transport of proteins between the cytoplasm and the nucleoplasm. We also include a simple model of ribosome biogenesis and assembly. Results show that the cell volume is tightly correlated with the nuclear volume, and the cytoplasm-nucleoplasm transport rates strongly influence the cell growth rate as well as the cell/nucleus volume ratio (C/N ratio). Ribosome assembly and the ratio of ribosomal proteins to mature ribosomes also influence the cell volume and the cell growth rate. We find that in order to regulate the cell growth rate and the cell/nucleus volume ratio, the cell must optimally control groups of kinetic and transport parameters together, which could explain the quantitative roles of canonical growth pathways. Finally, although not explicitly demonstrated in this work, we point out that it is possible to construct a detailed proteome distribution using our model and RNAseq data, provided that a quantitative cell division mechanism is known.

Cell-Inspired Hydrogel Microcapsules with a Thin Oil Layer of Enhanced Retention of Highly Reactive Antioxidants - Chu, Jin-Ok; Choi, Yoon; Kim, Do-Wan; Jeong, Hye-Seon; Park, Jong Pil; Weitz, DavidA.; Kee, Sei-Jung; Hyomin Lee; Choi, Chang-Hyung (ACS Appl. Mater. Interfaces, 2022)
In nature, individual cells are compartmentalized by a membrane that protects the cellular elements from the surrounding environment while simultaneously equipped with an antioxidant defense system to alleviate the oxidative stress resulting from light, oxygen, moisture, and temperature. However, this mechanism has not been realized in cellular mimics to effectively encapsulate and retain highly reactive antioxidants. Here, we report cell-inspired hydrogel microcapsules with an interstitial oil layer prepared by utilizing triple emulsion drops as templates to achieve enhanced retention of antioxidants. We employ ionic gelation for the hydrogel shell to prevent exposure of the encapsulated antioxidants to free radicals typically generated during photopolymerization. The interstitial oil layer in the microcapsule serves as an stimulus-responsive diffusion barrier, enabling efficient encapsulation and retention of antioxidants by providing an adequate pH microenvironment until osmotic pressure is applied to release the cargo on-demand. Moreover, addition of a lipophilic reducing agent in the oil layer induces a complementary reaction with the antioxidant, similar to the nonenzymatic antioxidant defense system in cells, leading to enhanced retention of the antioxidant activity. Furthermore, we show the complete recovery and even further enhancement in antioxidant activity by lowering the storage temperature, which decreases the oxidation rate while retaining the complementary reaction with the lipophilic reducing agent.

An outlook on microfluidics: the promise and the challenge - Battat, Sarah; Weitz, DavidA.; Whitesides, George (Lab on a Chip, 2022)
This perspective considers ways in which the field of microfluidics can increase its impact by improving existing technologies and enabling new functionalities. We highlight applications where microfluidics has made or can make important contributions, including diagnostics, food safety, and the production of materials. The success of microfluidics assumes several forms, including fundamental innovations in fluid mechanics that enable the precise manipulation of fluids at small scales and the development of portable microfluidic chips for commercial purposes. We identify outstanding technical challenges whose resolution could increase the accessibility of microfluidics to users with both scientific and non-technical backgrounds. They include the simplification of procedures for sample preparation, the identification of materials for the production of microfluidic devices in both laboratory and commercial settings, and the replacement of auxiliary equipment with automated components for the operation of microfluidic devices.

Local high-density distributions of phospholipids induced by the nucleation and growth of smectic liquid crystals at the interface - Yang, Chenjing; Chen, Li; Zhang, Rui; Chen, Dong; Arriaga, Laura R.; Weitz, DavidA. (Chinese Chemical Letters, 2022)
Amphiphilic molecules adsorbed at the interface could control the orientation of liquid crystals (LCs) while LCs in turn could influence the distributions of amphiphilic molecules. The studies on the interactions between liquid crystals and amphiphilic molecules at the interface are important for the development of molecular sensors. In this paper, we demonstrate that the development of smectic LC ordering from isotropic at the LC/water interface could induce local high-density distributions of amphiphilic phospholipids. Mixtures of liquid crystals and phospholipids in chloroform are first emulsified in water. By fluorescently labeling the phospholipids adsorbed at the interface, their distributions are visualized under fluorescent confocal microscope. Interestingly, local high-density distributions of phospholipids showing a high fluorescent intensity are observed on the surface of LC droplets. Investigations on the correlation between phospholipid density, surface tension and smectic LC ordering suggest that when domains of smectic LC layers nucleate and grow from isotropic at the LC/water interface as chloroform slowly evaporates at room temperature, phospholipids transition from liquid-expanded to liquid-condensed phases in response to the smectic ordering, which induces a higher surface tension at the interface. The results will provide an important insight into the interactions between liquid crystals and amphiphilic molecules at the interface.

Pickering emulsions stabilized by colloidal surfactants: Role of solid particles - Sun, Zhu; Yan, Xiaoxiao; Xiao, Yao; Hu, Lingjie; Eggersdorfer, Max; Chen, Dong; Yang, Zhenzhong; Weitz, DavidA. (Particuology, 2022)
Pickering emulsions are emulsions stabilized by colloidal surfactants, i.e. solid particles. Compared with traditional molecular surfactant-stabilized emulsions, Pickering emulsions show many advantages, such as high resistance to coalescence, long-term stability, good biocompatibility and tunable properties. In recent years, Pickering emulsions are widely applied in scientific researches and industrial applications. In this review, we focus on the influences of particle properties on Pickering emulsions, including particle amphiphilicity, concentration, size and shape, and summarize the strategies developed for the preparation of amphiphilic Janus particles. The applications of Pickering emulsions in food industry, cosmetic industry, material science, drug delivery, biomedical research and vaccine adjuvant will also be covered. Pickering emulsions are a unique system for multi-disciplinary studies and will become more and more important in the future.

Advanced microfluidic devices for fabricating multi-structural hydrogel microsphere - Chen, Zehao; Lv, Zhendong; Zhen Zhang; Weitz, DavidA.; Zhang, Hongbo; Zhang, Yuhui; Cui, Wenguo (Exploration, 2021)
Hydrogel microspheres are a novel functional material, arousing much attention in various fields. Microfluidics, a technology that controls and manipulates fluids at the micron scale, has emerged as a promising method for fabricating hydrogel microspheres due to its ability to generate uniform microspheres with controlled geometry. With the development of microfluidic devices, more complicated hydrogel microspheres with multiple structures can be constructed. This review presents an overview of advances in microfluidics for designing and engineering hydrogel microspheres. It starts with an introduction to the features of hydrogel microspheres and microfluidic techniques, followed by a discussion of material selection for fabricating microfluidic devices. Then the progress of microfluidic devices for single-component and composite hydrogel microspheres is described, and the method for optimizing microfluidic devices is also given. Finally, this review discusses the key research directions and applications of microfluidics for hydrogel microsphere in the future.

Programmable microbial ink for 3D printing of living materials produced from genetically engineered protein nanofibers - Duraj-Thatte, Anna M.; Manjula-Basavanna, Avinash; Rutledge, Jarod; Xia, Jing; Hassan, Shabir; Sourlis, Arjirios; Rubio, Andres G.; Lesha, Ami; Zenkl, Michael; Kan, Anton; Weitz, DavidA.; Zhang, Yu Shrike; et al. (Nature Communications, 2021)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-50443292_562="700" data-gtm-vis-first-on-screen-50443292_563="700" data-gtm-vis-has-fired-50443292_562="1" data-gtm-vis-has-fired-50443292_563="1" data-gtm-vis-total-visible-time-50443292_562="10000" data-gtm-vis-total-visible-time-50443292_563="10000" data-title="Abstract" lang="en"> Living cells have the capability to synthesize molecular components and precisely assemble them from the nanoscale to build macroscopic living functional architectures under ambient conditions. The emerging field of living materials has leveraged microbial engineering to produce materials for various applications but building 3D structures in arbitrary patterns and shapes has been a major challenge. Here we set out to develop a bioink, termed as “microbial ink” that is produced entirely from genetically engineered microbial cells, programmed to perform a bottom-up, hierarchical self-assembly of protein monomers into nanofibers, and further into nanofiber networks that comprise extrudable hydrogels. We further demonstrate the 3D printing of functional living materials by embedding programmed Escherichia coli (E. coli) cells and nanofibers into microbial ink, which can sequester toxic moieties, release biologics, and regulate its own cell growth through the chemical induction of rationally designed genetic circuits. In this work, we present the advanced capabilities of nanobiotechnology and living materials technology to 3D-print functional living architectures.

Synthesis of nanomedicine hydrogel microcapsules by droplet microfluidic process and their pH and temperature dependent release. - Liu, R.; Wu, Q.; X. Huang; Zhao, X.; Chen, X.; Chen, Y.; Weitz, D. A.; Song, Y. (RSC Advances, 2021)
Chitosan and alginate hydrogels are attractive because they are highly biocompatible and suitable for developing nanomedicine microcapsules. Here we fabricated a polydimethylsiloxane-based droplet microfluidic reactor to synthesize nanomedicine hydrogel microcapsules using Au@CoFeB–Rg3 as a nanomedicine model and a mixture of sodium alginate and PEG-g-chitosan crosslinked by genipin as a hydrogel model. The release kinetics of nanomedicines from the hydrogel were evaluated by simulating the pH and temperature of the digestive tract during drug transport and those of the target pathological cell microenvironment. Their pH and temperature-dependent release kinetics were studied by measuring the mass loss of small pieces of thin films formed by the nanomedicine-encapsulating hydrogels in buffers of pH 1.2, 7.4, and 5.5, which replicate the pH of the stomach, gut and blood, and cancer microenvironment, respectively, at 20 °C and 37 °C, corresponding to the storage temperature of hydrogels before use and normal body temperature. Interestingly, nanomedicine-encapsulating hydrogels can undergo rapid decomposition at pH 5.5 and are relatively stable at pH 7.4 at 37 °C, which are desirable qualities for drug delivery, controlled release, and residue elimination after achieving target effects. These results indicate that the designed nanomedicine hydrogel microcapsule system is suitable for oral administration.

Emulsion Designer Using Microfluidic Three-Dimensional Droplet Printing in Droplet - Chen, Li; Xiao, Yao; Wu, Qinglin; Yan, Xiaoxiao; Zhao, Peng; Ruan, Jing; Shan, Jianzhen; Chen, Dong; Weitz, DavidA.; Ye, Fangfu (Small, 2021)
Hierarchical emulsions are interesting for both scientific researches and practical applications. Hierarchical emulsions prepared by microfluidics require complicated device geometry and delicate control of flow rates. Here, a versatile method is developed to design hierarchical emulsions using microfluidic 3D droplet printing in droplet. The process of droplet printing in droplet mimics the dragonfly laying eggs and has advantages of easy processing and flexible design. To demonstrate the capability of the method, double emulsions and triple emulsions with tunable core number, core size, and core composition are prepared. The hierarchical emulsions are excellent templates for the developments of functional materials. Flattened crescent-moon-shaped particles are then fabricated using double emulsions printed in confined 2D space as templates. The particles are excellent delivery vehicles for 2D interfaces, which can load and transport cargos through a well-defined trajectory under external magnetic steering. Microfluidic 3D droplet printing in droplet provides a powerful platform with improved simplicity and flexibility for the design of hierarchical emulsions and functional materials.

Effects of Vimentin Intermediate Filaments on the Structure and Dynamics of In Vitro Multicomponent Interpenetrating Cytoskeletal Networks - Shen, Yinan; Huayin Wu; Lu, Peter J.; Wang, Dianzhuo; Shayegan, Marjan; Li, Hui; Shi, Weichao; Wang, Zizhao; Cai, Liheng; Xia, Jing; Zhang, Meng; Ding, Ruihua; et al. (Physical Review Letters, 2021)
We investigate the rheological properties of interpenetrating networks reconstituted from the main cytoskeletal components: filamentous actin, microtubules, and vimentin intermediate filaments. The elastic modulus is determined largely by actin, with little contribution from either microtubules or vimentin. However, vimentin dramatically impacts the relaxation, with even small amounts significantly increasing the relaxation time of the interpenetrating network. This highly unusual decoupling between dissipation and elasticity may reflect weak attractive interactions between vimentin and actin networks.

Unexpected scaling of interstitial velocities with permeability due to polymer retention in porous media - Parsa, Shima; Ahmad Zareei; Santanach-Carreras, Enric; Morris, Eliza J.; Amir, Ariel; Xiao, Lizhi; Weitz, DavidA. (Physical Review Fluids, 2021)
Polymer retention from the flow of a polymer solution through porous media results in substantial decrease of the permeability; however, the underlying physics of this effect is unknown. While the polymer retention leads to a decrease in pore volume, here we show that this cannot cause the full reduction in permeability. Instead, to determine the origin of this anomalous decrease in permeability, we use confocal microscopy to measure the pore-level velocities in an index-matched model porous medium. We show that they exhibit an exponential distribution and, upon polymer retention, this distribution is broadened yet retains the same exponential form. Surprisingly, the velocity distributions are scaled by the inverse square root of the permeabilities. We combine experiment and simulation to show these changes result from diversion of flow in the random porous-medium network rather than reduction in pore volume upon polymer retention.

Dynamic Speckle Holography - Aime, Stefano; Sabato, Matteo; Xiao, Lizhi; Weitz, DavidA. (Physical Review Letters, 2021)
We introduce dynamic speckle holography, a new technique that combines imaging and scattering to measure three-dimensional maps of displacements as small as ten nanometers over several centimeters, greatly extending the capabilities of traditional imaging systems. We attain this sensitivity by imaging speckle patterns of light collected at three scattering angles and measuring the decay in the temporal correlation due to local motion. We use dynamic speckle holography to measure the strain field of a colloidal gel undergoing fracture and establish the surprising role of internal tension in driving the fracture.

Tumorigenic mesenchymal clusters are less sensitive to moderate osmotic stresses due to low amounts of junctional E-cadherin - Mohammed, Danahe; Park, Chan Young; Jeffrey J. Fredberg; Weitz, DavidA. (Scientific Reports, 2021)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="311" data-gtm-vis-first-on-screen-10482319_401="311" data-gtm-vis-has-fired-10482319_393="1" data-gtm-vis-has-fired-10482319_401="1" data-gtm-vis-total-visible-time-10482319_393="10000" data-gtm-vis-total-visible-time-10482319_401="10000" data-title="Abstract" lang="en"> The migration of tumorigenic cells is a critical step for metastatic breast cancer progression. Although the role of the extracellular matrix in breast cancer cell migration has been extensively described, the effect of osmotic stress on the migration of tumor breast cohorts remains unclear. Most of our understanding on the effect of osmotic stresses on cell migration comes from studies at the level of the single cell in isolation and does not take cell–cell interactions into account. Here, we study the impact of moderate osmotic stress on the migration of cell clusters composed of either non-tumorigenic or tumorigenic cells. We observe a decrease in migration distance and speed for non-tumorigenic cells but not for tumorigenic ones. To explain these differences, we investigate how osmotic stress impacts the mechanical properties of cell clusters and affects their volumes. Our findings show that tumorigenic mesenchymal cells are less sensitive to osmotic stress than non-tumorigenic cells and suggest that this difference is associated with a lower expression of E-cadherin. Using EGTA treatments, we confirm that the establishment of cell–cell adhesive interactions is a key component of the behavior of cell clusters in response to osmotic stress. This study provides evidence on the low sensitivity of mesenchymal tumorigenic clusters to moderate osmotic stress and highlights the importance of cadherin-based junctions in the response to osmotic stress.

Millifluidics, microfluidics, and nanofluidics: manipulating fluids at varying length scales - L. Chen; Yang, C.; Xiao, Y.; Yan, X.; Hu, L.; Eggersdorfer, M.; D. Chen; Weitz, D. A.; Ye, F. (Materials Today Nano, 2021)
Manipulating fluids at varying length scales and understanding their underlying mechanisms are significant for interdisciplinary studies of physics, chemistry, biology, and engineering; fluid manipulation plays an important role in both scientific research and industrial applications. Here, we systematically review millifluidics, microfluidics, and nanofluidics with dimensions ranging from millimeters to nanometers. The major physics associated with flow property and interactions of millifluidics, microfluidics, and nanofluidics are discussed in detail, especially the differences arising from different length scales. Device fabrication techniques are summarized including additive and nonadditive manufacturing methods for millifluidics and microfluidics and top-down and bottom-up strategies for nanofluidics. Recent developments and applications of millifluidics, microfluidics, and nanofluidics are described to provide an overview on current researches. Outlooks of millifluidics, microfluidics, and nanofluidics are discussed at the end.​​​​​​

Attractive Pickering Emulsion Gels - Wu, Baiheng; Yang, Chenjing; Xin, Qi; Kong, Linlin; Eggersdorfer, Max; Ruan, Jan; Zhao, Peng; Shan, Jianzhen; Liu, Kai; Chen, Dong; Weitz, DavidA.; Gao, Xiang (Advanced Materials, 2021)
Properties of emulsions highly depend on the interdroplet interactions and, thus, engineering interdroplet interactions at molecular scale are essential to achieve desired emulsion systems. Here, attractive Pickering emulsion gels (APEGs) are designed and prepared by bridging neighboring particle-stabilized droplets via telechelic polymers. In the APEGs, each telechelic molecule with two amino end groups can simultaneously bind to two carboxyl functionalized nanoparticles in two neighboring droplets, forming a bridged network. The APEG systems show typical shear-thinning behaviors and their viscoelastic properties are tunable by temperature, pH, and molecular weight of the telechelic polymers, making them ideal for direct 3D printing. The APEGs can be photopolymerized to prepare APEG-templated porous materials and their microstructures can be tailored to optimize their performances, making the APEG systems promising for a wide range of applications.

Linear triglycerol-based fluorosurfactants show high potential for droplet-microfluidics-based biochemical assays - Chowdhury, Mohammad S.; Zheng, Wenshan; Singh, Abhishek K.; Ong, Irvine L.H.; Hou, Yong; Heyman, John A.; Faghani, Abbas; Amstad, Esther; Weitz, DavidA.; Haag, Rainer (Soft Matter, 2021)
Fluorosurfactants have expanded the landscape of high-value biochemical assays in microfluidic droplets, but little is known about how the spatial geometries and polarity of the head group contribute to the performance of fluorosurfactants. To decouple this, we design, synthesize, and characterize two linear and two dendritic glycerol- or tris-based surfactants with a common perfluoropolyether tail. To reveal the influence of spatial geometry, we choose inter-droplet cargo transport as a stringent test case. Using surfactants with linear di- and triglycerol, we show that the inter-droplet cargo transport is minimal compared with their dendritic counterparts. When we encapsulated a less-leaky sodium fluorescent dye into the droplets, quantitatively, we find that the mean fluorescence intensity of the PFPE-dTG stabilized PBS-only droplets after 72 h was ∼3 times that of the signal detected in PBS-only droplets stabilized by PFPE-lTG. We also demonstrate that the post-functionalization of PFPE-lTG having a linear geometry and four hydroxy groups enables the ‘from-Droplet’ fishing of the biotin–streptavidin protein complex without the trade-off between fishing efficiency and droplet stability. Thus, our approach to design user-friendly surfactants reveals the aspects of spatial geometry and facile tunability of the polar head groups that have not been captured or exploited before.

Microchannel measurements of viscosity for both gases and liquids - Shiba, Kota; Li, Guangming; Emmanuel Virot; Yoshikawa, Genki; Weitz, DavidA. (Lab on a Chip, 2021)
Quantifying the viscosity of a fluid is of great importance in determining its properties and can even be used to identify what the fluid is. While many techniques exist for measuring the viscosity of either gases or liquids, it is very challenging to probe both gases and liquids with a single approach because of the significant difference in their nature, and the vast difference in the values of their viscosities. We introduce a facile approach to measuring the viscosity of a Newtonian fluid, either a gas or a liquid, by flowing it through a deformable microchannel where the deformation depends on the pressure required to induce the flow, which, in turn, depends on the fluid viscosity. A strain gauge embedded just above and across the microchannel transduces the flow-induced deformation into strain. The strain is proportional to the square of the flow-induced deformation enabling us to precisely discriminate not only gases but also liquids based on their viscosities with the same device.

Implications of Quenching-to-Dequenching Switch in Quantitative Cell Uptake and Biodistribution of Dye-Labeled Nanoparticles - Yang, Guangzhe; Liu, Yun; Hui, Yue; Tengjisi; Chen, Dong; Weitz, DavidA.; Zhao, Chun-Xia (Angewandte Chemie, 2021)
A general strategy to carry out cell uptake and biodistribution studies is to label nanoparticles (NPs) with a fluorescent dye. However, the comparative study of different dye‐loaded NPs remains difficult owing to uncontrolled dye quenching and de‐quenching. Here we compared two types of dye‐labeled NPs and demonstrated their distinct properties. NPs with dye molecules at a solid state suffer from dye quenching, so the dye release and/or NP degradation in biological environments leads to a several‐fold increase of fluorescence intensity despite the same amount of NPs, owing to the state switch from quenching to de‐quenching. In contrast, NPs with dye molecules at a soluble state exhibit no quenching effect. To standardize the comparative study, we propose two possible solutions: using lower dye loading or using medium analysis for quantifying cell uptake of NPs. This work provides valuable insights into selecting valid quantification methods for bio‐nano studies.

Sequencing-Based Protein Analysis of Single Extracellular Vesicles - Ko, Jina; Wang, Yongcheng; Sheng, Kuanwei; Weitz, DavidA.; Weissleder, Ralph (ACS Nano, 2021)
Circulating extracellular vesicles (EVs)—biological nanomaterials shed from most mammalian cells—have emerged as promising biomarkers, drug delivery vesicles, and treatment modulators. While different types of vesicles are being explored for these applications, it is becoming clear that human EVs are quite heterogeneous even in homogeneous or monoclonal cell populations. Since it is the surface EV protein composition that will largely dictate their biological behavior, high-throughput single EV profiling methods are needed to better define EV subpopulations. Here, we present an antibody-based immunosequencing method that allows multiplexed measurement of protein molecules from individual nanometer-sized EVs. We use droplet microfluidics to compartmentalize and barcode individual EVs. The barcodes/antibody-DNA are then sequenced to determine protein composition. Using this highly sensitive technology, we detected specific proteins at the single EV level. We expect that this technology can be further adapted for multiplexed protein analysis of any nanoparticle.

Anomalous mechanics of Zn2+-modified fibrin networks - Xia, Jing; Cai, Liheng; Huayin Wu; Mackintosh, Frederick C.; Weitz, DavidA. (PNAS, 2021)
Fibrin is the main component of blood clots. The mechanical properties of fibrin are therefore of critical importance in successful hemostasis. One of the divalent cations released by platelets during hemostasis is Zn2+; however, its effect on the network structure of fibrin gels and on the resultant mechanical properties remains poorly understood. Here, by combining mechanical measurements with three-dimensional confocal microscopy imaging, we show that Zn2+ can tune the fibrin network structure and alter its mechanical properties. In the presence of Zn2+, fibrin protofibrils form large bundles that cause a coarsening of the fibrin network due to an increase in fiber diameter and reduction of the total fiber length. We further show that the protofibrils in these bundles are loosely coupled to one another, which results in a decrease of the elastic modulus with increasing Zn2+ concentrations. We explore the elastic properties of these networks at both low and high stress: At low stress, the elasticity originates from pulling the thermal slack out of the network, and this is consistent with the thermal bending of the fibers. By contrast, at high stress, the elasticity exhibits a common master curve consistent with the stretching of individual protofibrils. These results show that the mechanics of a fibrin network are closely correlated with its microscopic structure and inform our understanding of the structure and physical mechanisms leading to defective or excessive clot stiffness.

Single-Cell Transcriptomics Reveals a Heterogeneous Cellular Response to BK Virus Infection - An, Ping; Cantalupo, Paul G.; Zheng, Wenshan; Saenz-Robles, Maria Teresa; Duray, Alexis M.; Weitz, DavidA.; Pipas, James M. (Journal of Virology, 2021)
BK virus (BKV) is a human polyomavirus that is generally harmless but can cause devastating disease in immunosuppressed individuals. BKV infection of renal cells is a common problem for kidney transplant patients undergoing immunosuppressive therapy. In cultured primary human renal proximal tubule epithelial (RPTE) cells, BKV undergoes a productive infection. The BKV-encoded large T antigen (LT) induces cell cycle entry, resulting in the upregulation of numerous genes associated with cell proliferation. Consistently, microarray and transcriptome sequencing (RNA-seq) experiments performed on bulk infected cell populations identified several proliferation-related pathways that are upregulated by BKV. These studies revealed few genes that are downregulated. In this study, we analyzed viral and cellular transcripts in single mock- or BKV-infected cells. We found that the levels of viral mRNAs vary widely among infected cells, resulting in different levels of LT and viral capsid protein expression. Cells expressing the highest levels of viral transcripts account for approximately 20% of the culture and have a gene expression pattern that is distinct from that of cells expressing lower levels of viral mRNAs. Surprisingly, cells expressing low levels of viral mRNA do not progress with time to high expression, suggesting that the two cellular responses are determined prior to or shortly following infection. Finally, comparison of cellular gene expression patterns of cells expressing high levels of viral mRNA with those of mock-infected cells or cells expressing low levels of viral mRNA revealed previously unidentified pathways that are downregulated by BKV. Among these are pathways associated with drug metabolism and detoxification, tumor necrosis factor (TNF) signaling, energy metabolism, and translation.

A New Ensemble Machine-Learning Framework for Searching Sweet Spots in Shale Reservoirs - Tang, Jizhou; Fan, Bo; Xiao, Lizhi; Tian, Shouceng; Zhang, Fengshou; Zhang, Liyuan; Weitz, DavidA. (SPE Journal, 2021)
Knowing the location of sweet spots benefits the horizontal well drilling and the selection of perforation clusters. Generally, geoscientists determine sweet spots from the well-logging interpretation. In this paper, a group of prevalent classifiers [extreme gradient boosting (XGBoost), unbiased boosting with categorical features (CatBoost), and light gradient boosting machine (LightGBM)] based on gradient-boosting decision trees (GBDTs) are introduced to automatically determine sweet spots based on well-log data sets. Compared with linear support vector machines (SVMs), these robust algorithms can deal with comparative scales of features and learn nonlinear decision boundaries. Moreover, they are less influenced by the presence of outliers. Another prevailing approach, named generative adversarial networks (GANs), is implemented to augment the training data set by using a small number of training samples. An extensive application has been built for the field cases in a certain oilfield. We randomly select 73 horizontal wells for training, and 13 features are chosen from well-log data sets. Compared with conventional SVMs, the agreement rates of interpretation by XGBoost and CatBoost are significantly improved. Without special preprocessing of the input data sets and conditional tabular GAN (CTGAN) model fine tuning, the fake data set could still bring a relatively low agreement rate for all detections. Finally, we propose an ensemble-learning framework concatenating multilevels of classifiers and improve agreement rate. In this paper, we illustrate a new tool for categorizing the reservoir quality by using GBDTs and ensemble models, which further helps search and identify sweet spots automatically. This tool enables us to integrate experts’ knowledge to the developed model, identify logging curves more efficiently, and cover more sweet spots during the drilling and completion treatment, which immensely decrease the cost of log interpretation.

Ordered Mesoporous Microcapsules from Double Emulsion Confined Block Copolymer Self-Assembly - Werner, Joerg G.; Hyomin Lee; Wiesner, Ulrich; Weitz, DavidA. (ACS Nano, 2021)
Polymeric microcapsules with shells containing homogeneous pores with uniform diameter on the nanometer scale are reported. The mesoporous microcapsules are obtained from confined self-assembly of amphiphilic block copolymers with a selective porogen in the shell of water-in-oil-in-water double emulsion drops. The use of double emulsion drops as a liquid template enables the formation of homogeneous capsules of 100s of microns in diameter, with aqueous cores encapsulated in a shell membrane with a tunable thickness of 100s of nanometers to 10s of microns. Microcapsules with shells that exhibit an ordered gyroidal morphology and three-dimensionally connected mesopores are obtained from the triblock terpolymer poly(isoprene)-block-poly(styrene)-block-poly(4-vinylpyridine) coassembled with pentadecylphenol as a porogen. The bicontinuous shell morphology yields nanoporous paths connecting the inside to the outside of the microcapsule after porogen removal; by contrast, one-dimensional hexagonally packed cylindrical pores, obtained from a traditional diblock copolymer system with parallel alignment to the surface, would block transport through the shell. To enable the mesoporous microcapsules to withstand harsh conditions, such as exposure to organic solvents, without rupture of the shell, we develop a cross-linking method of the nanostructured triblock terpolymer shell after its self-assembly. The microcapsules exhibit pH-responsive permeability to polymeric solutes, demonstrating their potential as a filtration medium for actively tunable macromolecular separation and purification. Furthermore, we report a tunable dual-phase separation method to fabricate microcapsules with hierarchically porous shells that exhibit ordered mesoporous membrane walls within sponge-like micron-sized macropores to further control shell permeability.

The vortex-driven dynamics of droplets within droplets - Tiribocchi, A.; Montessori, A.; Lauricella, M.; Bonaccorso, F.; Succi, S.; Aime, Stefano; Milani, M.; Weitz, DavidA. (Nature Communications, 2021)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="13133" data-gtm-vis-first-on-screen-10482319_401="13133" data-gtm-vis-has-fired-10482319_393="1" data-gtm-vis-has-fired-10482319_401="1" data-gtm-vis-total-visible-time-10482319_393="10000" data-gtm-vis-total-visible-time-10482319_401="10000" data-title="Abstract" lang="en"> Understanding the fluid-structure interaction is crucial for an optimal design and manufacturing of soft mesoscale materials. Multi-core emulsions are a class of soft fluids assembled from cluster configurations of deformable oil-water double droplets (cores), often employed as building-blocks for the realisation of devices of interest in bio-technology, such as drug-delivery, tissue engineering and regenerative medicine. Here, we study the physics of multi-core emulsions flowing in microfluidic channels and report numerical evidence of a surprisingly rich variety of driven non-equilibrium states (NES), whose formation is caused by a dipolar fluid vortex triggered by the sheared structure of the flow carrier within the microchannel. The observed dynamic regimes range from long-lived NES at low core-area fraction, characterised by a planetary-like motion of the internal drops, to short-lived ones at high core-area fraction, in which a pre-chaotic motion results from multi-body collisions of inner drops, as combined with self-consistent hydrodynamic interactions. The onset of pre-chaotic behavior is marked by transitions of the cores from one vortex to another, a process that we interpret as manifestations of the system to maximize its entropy by filling voids, as they arise dynamically within the capsule.

Single Extracellular Vesicle Protein Analysis Using Immuno-Digital Droplet Polymerase Chain Reaction Amplification - Ko, Jina; Wang, Yongcheng; Carlson, Jonathan C.T.; Marquard, Angela; Gungabeesoon, Jeremy; Charest, Alain; Weitz, DavidA.; Pittet, Mikael J.; Weissleder, Ralph (Advanced Biosystems, 2020)
There is a need for novel analytical techniques to study the composition of single extracellular vesicles (EV). Such techniques are required to improve the understanding of heterogeneous EV populations, to allow identification of unique subpopulations, and to enable earlier and more sensitive disease detection. Because of the small size of EV and their low protein content, ultrahigh sensitivity technologies are required. Here, an immuno‐droplet digital polymerase chain reaction (iddPCR) amplification method is described that allows multiplexed single EV protein profiling. Antibody–DNA conjugates are used to label EV, followed by stochastic microfluidic incorporation of single EV into droplets. In situ PCR with fluorescent reporter probes converts and amplifies the barcode signal for subsequent read‐out by droplet imaging. In these proof‐of‐principle studies, it is shown that multiplex protein analysis is possible in single EV, opening the door for future analyses.

Rapid isolation of antigen-specific B-cells using droplet microfluidics - Ding, Ruihua; Hung, Kuo-Chan; Mitra, Anindita; Ung, Lloyd W.; Lightwood, Daniel; Tu, Ran; Starkie, Dale; Cai, Liheng; Mazutis, Linas; Chong, Shaorong; Weitz, DavidA.; Heyman, John A. (RSC Advances, 2020)
Monoclonal antibodies are powerful tools for scientific research and are the basis of numerous therapeutics. However, traditional approaches to generate monoclonal antibodies against a desired target, such as hybridoma-based techniques and display library methods, are laborious and suffer from fusion inefficiency and display bias, respectively. Here we present a platform, featuring droplet microfluidics and a bead-based binding assay, to rapidly identify and verify antigen-binding antibody sequences from primary cells. We used a defined mixture of hybridoma cells to characterize the system, sorting droplets at up to 100 Hz and isolating desired hybridoma cells, comprising 0.1% of the input, with a false positive rate of less than 1%. We then applied the system to once-frozen primary B-cells to isolate rare cells secreting target-binding antibody. We performed RT-PCR on individual sorted cells to recover the correctly paired heavy- and light-chain antibody sequences, and we used rapid cell-free protein synthesis to generate single-chain variable fragment-format (scFv) antibodies from fourteen of the sorted cells. Twelve of these showed antigen-specific binding by ELISA. Our platform facilitates screening animal B-cell repertoires within days at low cost, increasing both rate and range of discovering antigen-specific antibodies from living organisms. Further, these techniques can be adapted to isolate cells based on virtually any secreted product.

Hydrogel Microcapsules with a Thin Oil Layer: Smart Triggered Release via Diverse Stimuli - Jeong, Hye-Seon; Kim, Eunseo; Nam, Changwoo; Choi, Yoon; Lee, You-Jeong; Weitz, DavidA.; Hyomin Lee; Choi, Chang-Hyung (Advanced Functional Materials, 2020)
A hydrogel microcapsule with an intermediate thin oil layer is presented to achieve smart release of a broad range of cargoes triggered via diverse stimuli. A microfluidic technique is used to produce triple emulsion droplets with a thin oil layer that separates the innermost aqueous phase from the hydrogel prepolymer phase, which transforms into a hydrogel shell via photopolymerization. The intermediate oil layer within the hydrogel microcapsule acts as an effective diffusion barrier, allowing encapsulation of various small cargoes within a porous hydrogel shell until a stimulus is applied to destabilize the oil layer. It is demonstrated that diverse stimuli including chemical dissolution, mechanical stress, and osmotic pressure can be utilized to release the encapsulated cargo on‐demand. In addition, osmotic pressure and the hydrogel shell thickness can be independently tuned to control the onset time of release as well as the release behavior of multi‐cargo encapsulated hydrogel microcapsule. The release can be either simultaneous or selective.

Tunable Nanochannels Connected in Series for Dynamic Control of Multiple Concentration-Polarization Layers and Preconcentrated Molecule Plugs - Sabbagh, Barak; Stolovicki, Elad; Park, Sinwook; Weitz, DavidA.; Yossifon, Gilad (Nano Letters, 2020)
Integration of ionic permselective medium (e.g., nanochannels, membranes) within microfluidic channels has been shown to enable on-chip desalination, sample purification, bioparticle sorting, and biomolecule concentration for enhanced detection sensitivity. However, the ion-permselective mediums are generally of fixed properties and cannot be dynamically tuned. Here we study a microfluidic device consisting of an array of individually addressable elastic membranes connected in series on top of a single microfluidic channel that can be deformed to locally reduce the channel cross-section into a nanochannel. Dynamic tunability of the ion-permselective medium, as well as controllability of its location and ionic permselectivity, introduces a new functionality to microfluidics-based lab-on-a-chip devices, for example, dynamic localization of preconcentrated biomolecule plugs at different sensing regions for multiplex detection. Moreover, the ability to simultaneously form a series of preconcentrated plugs at desired locations increases parallelization of the system and the trapping efficiency of target analytes.

Microfluidic fabrication of Phase-Inverted Microcapsules with Asymmetric Shell Membranes with Graded Porosity - Wu, Zhang; Werner, Joerg G.; Weitz, DavidA. (ACS Macro Letters, 2020)
Microcapsules with liquid cores and solid shells are attractive as dispersible protective micron-sized containers. Applications that rely on molecular mass transport often require a combination of size selectivity, high permeability, and mechanical stability. Capsule architectures that combine all these features represent a material property, design, and fabrication challenge. In this work, the design of an asymmetric microcapsule shell architecture is reported to achieve a good combination of the desired features. Poly(methyl methacrylate) phase-inverted microcapsules featuring an asymmetric graded macroporous shell covered with a dense skin separation layer are obtained from water-in-oil-in-water double emulsion drops that are phase-inverted in a water-based coagulation bath. The phase-inverted microcapsules exhibit good mechanical stability and allow for high permeability of its shell membrane with molecular size dependence.

Stiffness of the interface between a colloidal body-centered cubic crystal and its liquid - Hwang, Hierin; Weitz, DavidA.; Spaepen, Frans (PNAS, 2020)
Equilibrium interfaces were established between body-centered cubic (BCC) crystals and their liquid using charged colloidal particles in an electric bottle. By measuring a time series of interfacial positions and computing the average power spectrum, their interfacial stiffness was determined according to the capillary fluctuation method. For the (100) and the (114) interfaces, the stiffnesses were 0.15 and 0.18 kBT/σ2 (σ: particle diameter), respectively, and were isotropic in the plane of the interface. For comparison, similar charged colloids were used to create an interface between a face-centered cubic (FCC) crystal and its liquid. Its stiffness was significantly larger: 0.26 kBT/σ2. This result gives experimental support to the explanations offered for the preferential nucleation of BCC over FCC in metallic alloys.

Science and Cooking: Physics Meets Food, From Homemade to Haute Cuisine - Brenner, Michael; Sorensen, Pia; David Weitz (W.W. Norton, 2020)

Diverse Particle Carriers Prepared by Co-Precipitation and Phase Separation: Formation and Applications - Sun, Zhu; Wu, Baiheng; Ren, Yixin; Wang, Zhongzheng; Zhao, Chun‐Xia; Hai, Mingtan; Weitz, DavidA.; Chen, Dong (ChemPlusChem, 2020)
Nanoparticles with diverse structures and unique properties have attracted increasing attention for their widespread applications. Co‐precipitation under rapid mixing is an effective method to obtained biocompatible nanoparticles and diverse particle carriers are achieved by controlled phase separation via interfacial tensions. In this Minireview, we summarize the underlying mechanism of co‐precipitation and show that rapid mixing is important to ensure co‐precipitation. In the binary polymer system, the particles can form four different morphologies, including occluded particle, core‐shell capsule, dimer particle, and heteroaggregate, and we demonstrate that the final morphology could be controlled by surface tensions through surfactant, polymer composition, molecular weight, and temperature. The applications of occluded particles, core‐shell capsules and dimer particles prepared by co‐precipitation or microfluidics upon the regulation of interfacial tensions are discussed in detail, and show great potential in the areas of functional materials, colloidal surfactants, drug delivery, nanomedicine, bio‐imaging, displays, and cargo encapsulation.

J-Aggregate-Based FRET Monitoring of Drug Release from Polymer Nanoparticles with High Drug Loading - Liu, Yun; Yang, Guangze; Song Jin; Zhang, Run; Chen, Peng; Tengjisi; Wang, Lianzhou; Chen, Dong; Weitz, DavidA.; Zhao, Chun‐Xia (Angewandte Chemie, 2020)
Understanding drug‐release kinetics is critical for the development of drug‐loaded nanoparticles. We developed a J‐aggregate‐based Förster‐resonance energy‐transfer (FRET) method to investigate the release of novel high‐drug‐loading (50 wt %) nanoparticles in comparison with low‐drug‐loading (0.5 wt %) nanoparticles. Single‐dye‐loaded nanoparticles form J‐aggregates because of the high dye‐loading (50 wt %), resulting in a large red‐shift (≈110 nm) in the fluorescence spectrum. Dual‐dye‐loaded nanoparticles with high dye‐loading using FRET pairs exhibited not only FRET but also a J‐aggregate red‐shift (116 nm). Using this J‐aggregate‐based FRET method, dye‐core–polymer‐shell nanoparticles showed two release processes intracellularly: the dissolution of the dye aggregates into dye molecules and the release of the dye molecules from the polymer shell. Also, the high‐dye‐loading nanoparticles (50 wt %) exhibited a slow release kinetics in serum and relatively quick release in cells, demonstrating their great potential in drug delivery.

Universal Statistical Laws for the Velocities of Collective Migrating Cells - Lin, Shao‐Zhen; Chen, Peng‐Cheng; Guan, Liu‐Yuan; Shao, Yue; Hao, Yu-Kun; Li, Qunyang; Bo Li; Weitz, DavidA.; Feng, Xi‐Qiao (Advanced Biosystems, 2020)
Migratory dynamics of collective cells is central to the morphogenesis of biological tissues. The statistical distribution of cell velocities in 2D confluent monolayers is measured through large‐scale and long‐term experiments of various cell types lying on different substrates. A linear relation is discovered between the variability and the mean of cell speeds during the jamming process of confluent cell monolayers, suggesting time‐invariant distribution profile of cell velocities. It is further found that the probability density function of cell velocities obeys the non‐canonical q‐Gaussian statistics, regardless of cell types and substrate stiffness. It is the Tsallis entropy, instead of the classical Boltzmann–Gibbs entropy, that dictates the universal statistical laws of collective cell migration. The universal statistical law stems from cell–cell interactions, as demonstrated by the wound healing experiments. This previously unappreciated finding provides a linkage between cell‐level heterogeneity and tissue‐level ensembles in embryonic development and tumor growth.

Propagation and adsorption of nanoparticles in porous medium as traveling waves - Gerber, Gaetan; Weitz, DavidA.; Coussot, P. (Physical Review Research, 2020)
Generally, one attempts to globally predict or interpret, from numerical simulations, the history of the effluents exiting porous media (i.e., the breakthrough curve), without a clear view of the detailed evolutions of deposition inside the medium. We developed a simple physical frame of description of the colloidal particle transport and adsorption, which allows to predict the main characteristics of transport and deposition in porous media from a set of directly measurable (macroscopic) physical parameters. More precisely, we show that the deposition distribution is basically a traveling wave propagating in the medium with a shape (frontal or extended) and velocity depending on the flow rate and the availability of particles with regards to the adsorption capacity. This in particular makes it possible to predict or interpret the breakthrough curve shape from a physical approach. We also show that additional effects may be included, such as a multiporosity leading to confinement effects (delayed deposition in less accessible regions). The validity of the model is checked from original direct visualizations by confocal microscopy of particle adsorption in time and space for nanoparticle suspensions flowing through a bead packing. This makes it possible to measure the evolution of the deposition profiles in time distinguishing the deposition in confined regions. The model appears to successfully predict the different trends: traveling wave, global deposition profile shape, profiles of deposition in confined regions.

Core-Shell Nanohydrogels with Programmable Swelling for Conformance Control in Porous Media - Zhang, Liyuan; Abbaspourrad, Alireza; Parsa, Shima; Tang, Jizhou; Cassiola, Flavia; Zhang, Meng; Tian, Shouceng; Dai, Caili; Xiao, Lizhi; Weitz, DavidA. (ACS Applied Materials & Interfaces, 2020)
Conformance control during waterflooding in an oil reservoir is utilized to redistribute water and increase the sweep efficiency and hence oil production. Using preformed gel particles can effectively redirect the flow by blocking the high-permeability zones and forcing water into low-permeability zones where the oil is trapped. However, the size of such gel particles can limit their applications deeper within the reservoir and can result in shear-induced degradation near the well bore. Here, we fabricate core–shell nanohydrogels with delayed swelling behavior; their volume increases by a factor of 200 after about 30 days in brine under reservoir conditions. We study their effect on the flow behavior in a three-dimensional porous medium micromodel consisting of randomly packed glass beads. Using confocal microscopy, we directly visualize the spatial variations of flow in the micromodel before and after nanohydrogel injection and swelling. The swollen nanohydrogels block some pores reducing the permeability of the micromodel and diverting the water into low-permeability regions. A core flood experiment further confirms that the nanohydrogels can significantly reduce the permeability of a reservoir sample and divert the fluid flow. Our results demonstrate that these core–shell nanohydrogels might be useful for flow control in porous media and can be used as a conformance control agent.

Dissolvable Polyacrylamide Beads for High-Throughput Droplet DNA Barcoding - Wang, Yongcheng; Cao, Ting; Ko, Jina; Shen, Yinan; Zong, Will; Sheng, Kuanwei; Cao, Wenjian; Sun, Sijie; Cai, Liheng; Zhou, Ying‐Lin; Zhang, Xin‐Xiang; Zong, Chenghang; et al. (Advanced Science, 2020)
Droplet‐based single cell sequencing technologies, such as inDrop, Drop‐seq, and 10X Genomics, are catalyzing a revolution in the understanding of biology. Barcoding beads are key components for these technologies. What is limiting today are barcoding beads that are easy to fabricate, can efficiently deliver primers into drops, and thus achieve high detection efficiency. Here, this work reports an approach to fabricate dissolvable polyacrylamide beads, by crosslinking acrylamide with disulfide bridges that can be cleaved with dithiothreitol. The beads can be rapidly dissolved in drops and release DNA barcode primers. The dissolvable beads are easy to synthesize, and the primer cost for the beads is significantly lower than that for the previous barcoding beads. Furthermore, the dissolvable beads can be loaded into drops with >95% loading efficiency of a single bead per drop and the dissolution of beads does not influence reverse transcription or the polymerase chain reaction (PCR) in drops. Based on this approach, the dissolvable beads are used for single cell RNA and protein analysis.

Stable Polymer Nanoparticles with Exceptionally High Drug Loading by Sequential Nanoprecipitation - Liu, Yun; Yang, Guangze; Baby, Thejus; Tengjisi; Chen, Dong; Weitz, DavidA.; Zhao, Chun‐Xia (Angewandte Chemie, 2020)
Poor solubility often leads to low drug efficacy. Encapsulation of water‐insoluble drugs in polymeric nanoparticles offers a solution. However, low drug loading remains a critical challenge. Now, a simple and robust sequential nanoprecipitation technology is used to produce stable drug‐core polymer‐shell nanoparticles with high drug loading (up to 58.5 %) from a wide range of polymers and drugs. This technology is based on tuning the precipitation time of drugs and polymers using a solvent system comprising multiple organic solvents, which allows the formation of drug nanoparticles first followed by immediate precipitation of one or two polymers. This technology offers a new strategy to manufacture polymeric nanoparticles with high drug loading having good long‐term stability and programmed release and opens a unique opportunity for drug delivery applications.

The Fourth Decade of Microfluidics - Kong, Tiantian; Shum, Ho C.; Weitz, DavidA. (Small, 2020)

Microfluidics-Assisted Assembly of Injectable Photonic Hydrogels Toward Reflective Cooling - Zhu, Zhijie; Liu, Ji-Dong; Liu, Chang; Wu, Xingjiang; Li, Qing; Chen, Su; Zhao, Xin; Weitz, DavidA. (Small, 2020)
Development of fast curing and easy modeling of colloidal photonic crystals is highly desirable for various applications. Here, a novel type of injectable photonic hydrogel (IPH) is proposed to achieve self‐healable structural color by integrating microfluidics‐derived photonic supraballs with supramolecular hydrogels. The supramolecular hydrogel is engineered via incorporating β‐cyclodextrin/poly(2‐hydroxypropyl acrylate‐co‐N‐vinylimidazole) (CD/poly(HPA‐co‐VI)) with methacrylated gelatin (GelMA), and serves as a scaffold for colloidal crystal arrays. The photonic supraballs derived from the microfluidics techniques, exhibit excellent compatibility with the hydrogel scaffolds, leading to enhanced assembly efficiency. By virtue of hydrogen bonds and host–guest interactions, a series of self‐healable photonic hydrogels (linear, planar, and spiral assemblies) can be facilely assembled. It is demonstrated that the spherical symmetry of the photonic supraballs endows them with identical optical responses independent of viewing angles. In addition, by taking the advantage of angle independent spectrum characteristics, the IPH presents beneficial effects in reflective cooling, which can achieve up to 17.4 °C in passive solar reflective cooling. The strategy represents an easy‐to‐perform platform for the construction of IPH, providing novel insights into macroscopic self‐assembly toward thermal management applications.

Origin of anomalous polymer-induced fluid displacement in porous media - Parsa, Shima; Santanach-Carreras, Enric; Xiao, Lizhi; Weitz, DavidA. (Physical Review Fluids, 2020)
Immiscible displacement of fluids with large viscosity mismatch is inherently unstable due to viscous fingering, even in porous media where capillary forces dominate. Adding polymer to the displacing fluid reduces the viscosity mismatch and suppresses the viscous fingering instability thereby increasing the fluid displacement leading to extensive use in applications such as oil recovery. Surprisingly, however, an increase in displacement occurs even for very large viscosity mismatches. Moreover, significant additional displacement is observed when the polymer solution is followed by additional water flow. Thus, the fundamental physics of this phenomenon remains unclear. To understand this behavior, we use confocal microscopy to visualize the displacement of oil in a three-dimensional micromodel of a porous medium and simultaneously measure the local flow velocities of the displacing fluid. We find that the increased displacement results from a counterintuitive effect: polymer retention in the medium and the resultant local changes in flow. Typically retention is avoided since it reduces the permeability of the medium; instead, we find that large and heterogeneous local changes in flow lead to sufficiently large enough viscous forces at the interface of the immiscible fluids resulting in increased displacement.

MAFG-driven astrocytes promote CNS inflammation - Wheeler, Michael A.; Clark, Iain C.; Tjon, Emily C.; Li, Zhaorong; Zandee, Stephanie E.J.; Couturier, Charles P.; Watson, Brianna R.; Scalisi, Giulia; Alkwai, Sarah; Rothhammer, Veit; Rotem, Assaf; Heyman, John A.; et al. (Nature, 2020)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="10814" data-gtm-vis-first-on-screen-10482319_401="10814" data-gtm-vis-has-fired-10482319_393="1" data-gtm-vis-has-fired-10482319_401="1" data-gtm-vis-recent-on-screen-10482319_393="10814" data-gtm-vis-recent-on-screen-10482319_401="10814" data-gtm-vis-total-visible-time-10482319_393="10000" data-gtm-vis-total-visible-time-10482319_401="10000" data-title="Abstract" lang="en"> Multiple sclerosis is a chronic inflammatory disease of the CNS<a aria-label="Reference 1" data-test="citation-ref" data-track="click" data-track-action="reference anchor" data-track-label="link" href="https://www.nature.com/articles/s41586-020-1999-0#ref-CR1" id="ref-link-section-d58481e837" title="Reich, D. S., Lucchinetti, C. F. & Calabresi, P. A. Multiple sclerosis. N. Engl. J. Med. 378, 169–180 (2018).">1. Astrocytes contribute to the pathogenesis of multiple sclerosis<a aria-label="Reference 2" data-test="citation-ref" data-track="click" data-track-action="reference anchor" data-track-label="link" href="https://www.nature.com/articles/s41586-020-1999-0#ref-CR2" id="ref-link-section-d58481e841" title="Baecher-Allan, C., Kaskow, B. J. & Weiner, H. L. Multiple sclerosis: mechanisms and immunotherapy. Neuron 97, 742–768 (2018).">2, but little is known about the heterogeneity of astrocytes and its regulation. Here we report the analysis of astrocytes in multiple sclerosis and its preclinical model experimental autoimmune encephalomyelitis (EAE) by single-cell RNA sequencing in combination with cell-specific Ribotag RNA profiling, assay for transposase-accessible chromatin with sequencing (ATAC–seq), chromatin immunoprecipitation with sequencing (ChIP–seq), genome-wide analysis of DNA methylation and in vivo CRISPR–Cas9-based genetic perturbations. We identified astrocytes in EAE and multiple sclerosis that were characterized by decreased expression of NRF2 and increased expression of MAFG, which cooperates with MAT2α to promote DNA methylation and represses antioxidant and anti-inflammatory transcriptional programs. Granulocyte–macrophage colony-stimulating factor (GM-CSF) signalling in astrocytes drives the expression of MAFG and MAT2α and pro-inflammatory transcriptional modules, contributing to CNS pathology in EAE and, potentially, multiple sclerosis. Our results identify candidate therapeutic targets in multiple sclerosis.

Selective cell encapsulation, lysis, pico-injection and size-controlled droplet generation using traveling surface acoustic waves in a microfluidic device - Kirk Mutafopulos; Lu, Peter J.; Garry, Ryan; Pascal Spink; Weitz, David A (Lab on a Chip, 2020)
We generate droplets in a microfluidic device using a traveling surface acoustic wave (TSAW), and control droplet size by adjusting TSAW power and duration. We combine droplet production and fluorescence detection to selectively-encapsulate cells and beads; with this active method, the overwhelming majority of single particles or cells are encapsulated individually into droplets, contrasting the Poisson distribution of encapsulation number that governs traditional, passive microfluidic encapsulation. In addition, we lyse cells before selective encapsulation, and pico-inject new materials into existing droplets.

A High-Throughput Screening System Based on Droplet Microfluidics for Glucose Oxidase Gene Libraries - Prodanović, Radivoje; Ung, W. Lloyd; Đurđić, Karla I.; Fisher, Rainer; Weitz, David A; Ostafe, Raluca (molecules, 2020)
Glucose oxidase (GOx) is an important industrial enzyme that can be optimized for specific applications by mutagenesis and activity-based screening. To increase the efficiency of this approach, we have developed a new ultrahigh-throughput screening platform based on a microfluidic lab-on-chip device that allows the sorting of GOx mutants from a saturation mutagenesis library expressed on the surface of yeast cells. GOx activity was measured by monitoring the fluorescence of water microdroplets dispersed in perfluorinated oil. The signal was generated via a series of coupled enzyme reactions leading to the formation of fluorescein. Using this new method, we were able to enrich the yeast cell population by more than 35-fold for GOx mutants with higher than wild-type activity after two rounds of sorting, almost double the efficiency of our previously described flow cytometry platform. We identified and characterized novel GOx mutants, the most promising of which (M6) contained a combination of six point mutations that increased the catalytic constant kcat by 2.1-fold compared to wild-type GOx and by 1.4-fold compared to a parental GOx variant. The new microfluidic platform for GOx was therefore more sensitive than flow cytometry and supports comprehensive screens of gene libraries containing multiple mutations per gene.

Stimuli responsive Janus microgels with convertible hydrophilicity for controlled emulsion destabilization - Haney, Bobby; Werner, Jörg G.; Weitz, David A; Ramakrishnan, Subramanian (Soft Matter, 2020)
Although the utilization of rigid particles can afford stable emulsions, some applications require eventual emulsion destabilization to release contents captured in the particle-covered droplet. This destabilizing effect is achieved when using stabilizers that respond to controlled changes in environment. Microgels can be synthesized as stimuli responsive polymeric gel networks that adsorb to oil/water interfaces and stabilize emulsions. These particles are commonly hydrogels that swell and collapse in water in response to environmental changes. However, amphiphilic functionality is desired to enhance the adsorption abilities of these hydrogels while maintaining their stimuli responsivity. Microfluidic techniques are used to synthesize Janus microgels with two opposing stimuli responsive hemispheres. The particles have a temperature responsive domain connected to a pH responsive network where each side changes its hydrophilicity in response to a change in temperature or pH, respectively. The Janus microgels are amphiphilic in acidic conditions at 19 °C and alkaline conditions at 40 °C, while the opposite conditions cause a reduction of the amphiphilicity. By stabilizing emulsions with these dual responsive microgels, “smart” droplets that respond to environmental cues are formed. Emulsion droplets remain stable with smaller diameters when aqueous solution conditions favor amphiphilic particles yet, coalesce to larger droplets upon changing pH or temperature. These responsive Janus microgels represent the advancing technology of responsive droplets and demonstrate the applicability of microgels as emulsion stabilizers.

Droplet encapsulation improves accuracy of immune cell cytokine capture assays - Yuan, Yuan; Brouchon, Julie; Calvo-Calle, J. Mauricio; Xia, Jing; Sun, Li; Zhang, Xu; Clayton, Kiera L.; Ye, Fangfu; Weitz, DavidA.; Heyman, John (Lab on a Chip, 2020)
Quantification of cell-secreted molecules, e.g., cytokines, is fundamental to the characterization of immune responses. Cytokine capture assays that use engineered antibodies to anchor the secreted molecules to the secreting cells are widely used to characterize immune responses because they allow both sensitive identification and recovery of viable responding cells. However, if the cytokines diffuse away from the secreting cells, non-secreting cells will also be identified as responding cells. Here we encapsulate immune cells in microfluidic droplets and perform in-droplet cytokine capture assays to limit the diffusion of the secreted cytokines. We use microfluidic devices to rapidly encapsulate single natural killer NK-92 MI cells and their target K562 cells into microfluidic droplets. We perform in-droplet IFN-γ capture assays and demonstrate that NK-92 MI cells recognize target cells within droplets and become activated to secrete IFN-γ. Droplet encapsulation prevents diffusion of secreted products to neighboring cells and dramatically reduces both false positives and false negatives, relative to assays performed without droplets. In a sample containing 1% true positives, encapsulation reduces, from 94% to 2%, the number of true-positive cells appearing as negatives; in a sample containing 50% true positives, the number of non-stimulated cells appearing as positives is reduced from 98% to 1%. After cells are released from the droplets, secreted cytokine remains captured onto secreting immune cells, enabling FACS-isolation of populations highly enriched for activated effector immune cells. Droplet encapsulation can be used to reduce background and improve detection of any single-cell secretion assay.

Hydrogel microcapsules with photocatalytic nanoparticles for removal of organic pollutants - Liu, Jinrun; Chen, Hong; Shi, Xiaojie; Nawar, Saraf; Werner, Jörg; Huang, GaoShan; Ye, Miaomiao; Weitz, DavidA.; Solovev, Alexander A.; Mei, YongFeng (Environmental Science Nano, 2020)
Droplet-based microfluidics is used to fabricate thin shell hydrogel microcapsules for the removal of methylene blue (MB) from aqueous solutions. The microcapsules composed of a poly(methacrylic acid) hydrogel shell exhibit unique properties, including permeation, separation, purification, and reaction of molecular species. Photocatalytic TiO2 and ZnO nanoparticles encapsulated in the microcapsules, i.e. photocatalyst in capsule (PIC), are used to remove organic pollutants using an adsorption–oxidation mechanism. A prototype flow microreactor is assembled to demonstrate a controllable water purification approach in short time using photocatalysts. Our studies of aqueous and homogeneous hydrogel environments for the photocatalysts provide important insights into understanding the effectiveness of MB removal. Hydrogel capsules have MB removal rate comparable to homogeneous particles. Further reduction of both capsule and photocatalyst sizes can potentially aid in quicker water purification.

A General Strategy for One-Step Fabrication of Biocompatible Microcapsules with Controlled Active Release - Sun, Zeyong; Yang, Chenjing; Eggersdorfer, Max; Cui, Jiecheng; Li, Yiwei; Hai, Mingtan; Chen, Dong; Weitz, DavidA. (Chinese Chemical Letters, 2020)
Fabrication of biocompatible core-shell microcapsules in a controllable and scalable manner remains an important but challenging task. Here, we develop a one-step microfluidic approach for the high-throughput production of biocompatible microcapsules, which utilizes single emulsions as templates and controls the precipitation of biocompatible polymer at the water/oil interface. The facile method enables the loading of various oils in the core and the enhancement of polymer shell strength by polyelectrolyte coating. The resulting microcapsules have the advantages of controllability, scalability, biocompatibility, high encapsulation efficiency and high loading capacity. The core-shell microcapsules are ideal delivery vehicles for programmable active release and various controlled release mechanisms are demonstrated, including burst release by vigorous shaking, pH-triggered release for targeted intestinal release and sustained release of perfume over a long period of time. The utility of our technique paves the way for practical applications of core-shell microcapsules.

Absorbent-Adsorbates: Large Amphiphilic Janus Microgels as Droplet Stabilizers - Haney, Bobby; Werner, Joerg G.; Weitz, DavidA.; Ramakrishnan, Subramanian (ACS Applied Materials & Interfaces, 2020)
Microgel particles are cross-linked polymer networks that absorb certain liquids causing network expansion. The type of swelling-fluid and extent of volume change depends on the polymer-liquid interaction and the network’s cross-link density. These colloidal gels can be used to stabilize emulsion drops by adsorbing to the interface of two immiscible fluids. However, to enhance the adsorption abilities of these predominantly hydrophilic gel particles, some degree of hydrophobicity is needed. An amphiphilic Janus microgel with spatially distinct lipophilic and hydrophilic sides is desired. Here, we report the fabrication of polyethylene glycol diacrylate/ polypropylene glycol diacrylate Janus microgels (JM) using microfluidic drop making. The flow streams of the two separate and immiscible monomer solutions are brought into contact and intersected by a third immiscible fluid in a flow-focusing junction to form Janus droplets. The individual droplets are crosslinked via UV irradiation to form monodispersed microgel particles with opposing hydrophilic and hydrophobic 3D-networked polymer matrices. By combining two chemically different polymer gel networks, an amphiphilic emulsion stabilizer is formed that adsorbs to the oil/water interface while its faces absorb their respective water or hydrocarbon solvents. Both particle sides swell at the liquid/liquid interface as water in oil emulsions are stabilized and destabilized via thermal responsive hydrogel. Stimuli responsive droplets are demonstrated by adding a short chain oligo ethylene glycol acrylate molecule to the hydrogel formulation on the Janus microgel particle. Droplets stabilized by these particles experience a sudden increase in droplet diameter around 60˚C. This work with absorbent particles may prove useful for applications in bio catalysis, fuel production, and oil transportation.

Single Molecule Protein Detection with Attomolar Sensitivity Using Droplet Digital Enzyme-Linked Immunosorbent Assay - Cohen, Limor; Cui, Naiwen; Cai, Yamei; Garden, Padric M.; Li, Xiang; Weitz, DavidA.; Walt, David R. (ACS Nano, 2020)
Many proteins are present at low concentrations in biological samples, and therefore, techniques for ultrasensitive protein detection are necessary. To overcome challenges with sensitivity, the digital enzyme-linked immunosorbent assay (ELISA) was developed, which is 1000× more sensitive than conventional ELISA and allows sub-femtomolar protein detection. However, this sensitivity is still not sufficient to measure many proteins in various biological samples, thereby limiting our ability to detect and discover biomarkers. To overcome this limitation, we developed droplet digital ELISA (ddELISA), a simple approach for detecting low protein levels using digital ELISA and droplet microfluidics. ddELISA achieves maximal sensitivity by improving the sampling efficiency and counting more target molecules. ddELISA can detect proteins in the low attomolar range and is up to 25-fold more sensitive than digital ELISA using Single Molecule Arrays (Simoa), the current gold standard tool for ultrasensitive protein detection. Using ddELISA, we measured the LINE1/ORF1 protein, a potential cancer biomarker that has not been previously measured in serum. Additionally, due to the simplicity of our device design, ddELISA is promising for point-of-care applications. Thus, ddELISA will facilitate the discovery of biomarkers that have never been measured before for various clinical applications.

Active Encapsulation in Biocompatible Nanocapsules - Wu, Baiheng; Yang, Chenjing; Bo Li; Feng, Leyun; Hai, Mingtan; Zhao, Chun-Xia; Chen, Dong; Liu, Kai; Weitz, DavidA. (Small, 2020)
Co‐precipitation is generally refers to the co‐precipitation of two solids and is widely used to prepare active‐loaded nanoparticles. Here, it is demonstrated that liquid and solid can precipitate simultaneously to produce hierarchical core–shell nanocapsules that encapsulate an oil core in a polymer shell. During the co‐precipitation process, the polymer preferentially deposits at the oil/water interface, wetting both the oil and water phases; the behavior is determined by the spreading coefficients and driven by the energy minimization. The technique is applicable to directly encapsulate various oil actives and avoid the use of toxic solvent or surfactant during the preparation process. The obtained core–shell nanocapsules harness the advantage of biocompatibility, precise control over the shell thickness, high loading capacity, high encapsulation efficiency, good dispersity in water, and improved stability against oxidation. The applications of the nanocapsules as delivery vehicles are demonstrated by the excellent performances of natural colorant and anti‐cancer drug‐loaded nanocapsules. The core–shell nanocapsules with a controlled hierarchical structure are, therefore, ideal carriers for practical applications in food, cosmetics, and drug delivery.

Effect of divalent cations on the structure and mechanics of vimentin intermediate filaments - Huayin Wu; Shen, Yinan; Wang, Dianzhuo; Herrmann, Harald; Robert D. Goldman; Weitz, DavidA. (Biophysical Journal, 2020)
Divalent cations behave as effective cross-linkers of intermediate filaments (IFs) such as vimentin IF (VIF). These interactions have been mostly attributed to their multivalency. However, ion-protein interactions often depend on the ion species, and these effects have not been widely studied in IFs. Here, we investigate the effects of two biologically important divalent cations, Zn2+ and Ca2+, on VIF network structure and mechanics in vitro. We find that the network structure is unperturbed at micromolar Zn2+ concentrations, but strong bundle formation is observed at a concentration of 100 μM. Microrheological measurements show that network stiffness increases with cation concentration. However, bundling of filaments softens the network. This trend also holds for VIF networks formed in the presence of Ca2+, but remarkably, a concentration of Ca2+ that is two orders higher is needed to achieve the same effect as with Zn2+, which suggests the importance of salt-protein interactions as described by the Hofmeister effect. Furthermore, we find evidence of competitive binding between the two divalent ion species. Hence, specific interactions between VIFs and divalent cations are likely to be an important mechanism by which cells can control their cytoplasmic mechanics.

Microfluidic Synthesis of Multimode Au@CoFeB-Rg3 Nanomedicines and Their Cytotoxicity and Anti-Tumor Effects - Zhang, Weixia; Zhao, Xiaoxiong; Yuan, Yuan; Miao, Fenglin; Li, Wengang; Ji, Shaoxia; Huang, Xing; Chen, Xinhua; Jiang, Tianan; Weitz, DavidA.; Song, Yujun (Chemistry Materials, 2020)
Nanomedicines (i.e., Au@CoFeB-Rg3) were developed by conjugating multimode nanohybrids with active ingredients of natural herbs using Au@CoFeB nanoparticles as one model of multimode nanohybrids and the ginsenoside Rg3 as one model of active ingredients of natural herbs. Au@CoFeB nanoparticles were first synthesized using a temperatureprogrammed microfluidics process. Then, the surface of Au@ CoFeB nanoparticles was modified via an amino-silane coupling agent of (3-aminopropyl) trimethoxysilane (APTMS) and then activated by the bifunctional amine-active cross-linker. They were thereafter conjugated to ginsenosides preactivated by APTMS by cross-linking the surface-activated nanohybrids, forming Au@ CoFeB-Rg3 nanomedicines. Their multimode imaging functions were evaluated with the characterization of their magnetic and optical properties and the response to X-ray radiation. They can be optically detected via dark-field microscopy and can be imaged through X-ray computed tomography. They can also be used as magnetic resonance imaging contrast agents with excellent T2-weighted spin−echo imaging effects. Au@CoFeB-Rg3 nanomedicines exhibited distinct cytotoxicity and inhibitory effects on the proliferation of human hepatocellular carcinoma cells (HepG2/C3) and human chronic myeloid leukemia cells (K562) but were less toxic to 3T3 cells than other cells at concentrations more than 200 μg/ mL. However, Au@CoFeB nanoparticles showed markedly lower cytotoxicity and inhibitory effects on the proliferation of these cell lines, particularly at concentrations <100 μg/mL, than Au@CoFeB-Rg3 nanomedicines. Clearly, there is a distinct synergistic effect between nanohybrids and Rg3. Additionally, Au@CoFeB nanohybrids showed almost no toxicity to Jurkat-CT cells at low concentrations (47 μg/mL), indicating that they may be used as multimode nanoprobes at a suitable concentration. These findings provide an efficient alternative for the synthesis of multifunctional antitumor nanomedicines based on multimode nanohybrids and active ingredients of natural resources.

Decoupling the effects of nanopore size and surface roughness on the attachment, spreading and differentiation of bone marrow-derived stem cells - J. Xia; Yuan, Y.; Wu, H.; Huang, Y.; Weitz, D. A. (Biomaterials, 2020)
The nanopore size and roughness of nanoporous surface are two critical variables in determining stem cell fate, but little is known about the contribution from each cue individually. To address this gap, we use two-dimensional nanoporous membranes with controlled nanopore size and roughness to culture bone marrow-derived mesenchymal stem cells (BMSCs), and study their behaviors such as attachment, spreading and differentiation. We find that increasing the roughness of nanoporous surface has no noticeable effect on cell attachment, and only slightly decreases cell spreading areas and inhibits osteogenic differentiation. However, BMSCs cultured on membranes with larger nanopores have significantly fewer attached cells and larger spreading areas. Moreover, these cells cultured on larger nanopores undergo enhanced osteogenic differentiation by expressing more alkaline phosphatase, osteocalcin, osteopontin, and secreting more collagen type I. These results suggest that although both nanopore size and roughness can affect BMSCs, nanopore size plays a more significant role than roughness in controlling BMSC behavior.

Nanoparticle‐Shelled Catalytic Bubble Micromotor - Adams, Laura L. A.; Lee, Daeyeon; Mei, YongFeng; Weitz, DavidA.; Solovev, Alexander A. (Advanced Materials Interfaces, 2020)
Nanoparticle‐shelled bubbles, prepared with glass capillary microfluidics, are functionalized to produce catalytic micromotors that exhibit novel assembly and disassembly behaviors. Stable microbubble rafts are assembled at an air–solvent interface of nonaqueous propylene carbonate (PC) solvent by creating a meniscus using a glass capillary. Upon the addition of hydrogen peroxide fuel, catalytic microbubbles quickly break free from the bubble raft by repelling from each other and self‐propelling at the air–fuel interface (a mixture of PC and aqueous hydrogen peroxide). While most of micromotors generate oxygen bubbles on the outer catalytic shell, some micromotors contain cracks and eject bubbles from the hollow shells containing air. Nanoparticle‐shelled bubbles with a high buoyancy force are particularly attractive for studying novel propulsion modes and interactions between catalytic bubble micromotors at air–fuel interfaces.

Novel nonequilibrium steady states in multiple emulsions - Tiribocchi, A.; Montessori, A.; Aime, S.; Milani, M.; Lauricella, M.; Succi, S.; Weitz, D. (Physics of Fluids, 2020)
We numerically investigate the rheological response of a noncoalescing multiple emulsion under a symmetric shear flow. We find that the dynamics significantly depends on the magnitude of the shear rate and on the number of the encapsulated droplets, two key parameters whose control is fundamental to accurately select the resulting nonequilibrium steady states. The double emulsion, for instance, attains a static steady state in which the external droplet stretches under flow and achieves an elliptical shape (closely resembling the one observed in a sheared isolated fluid droplet), while the internal one remains essentially unaffected. Novel nonequilibrium steady states arise in a multiple emulsion. Under low/moderate shear rates, for instance, the encapsulated droplets display a nontrivial planetarylike motion that considerably affects the shape of the external droplet. Some features of this dynamic behavior are partially captured by the Taylor deformation parameter and the stress tensor. Besides a theoretical interest on its own, our results can potentially stimulate further experiments, as most of the predictions could be tested in the lab by monitoring droplets’ shapes and position over time.

Parallelizable microfluidic dropmakers with multilayer geometry for the generation of double emulsions - Nawar, Saraf; Stolaroff, Joshuah K.; Ye, Congwang; Huayin Wu; Nguyen, Du Thai; Xin, Feng; Weitz, DavidA. (Lab on a Chip, 2020)
We present a multilayer dropmaker geometry that enables the modular fabrication of microfluidic devices containing precisely patterned channel surface wettability. The platform is used for the scalable production of uniform double emulsion drops. , Microfluidic devices enable the production of uniform double emulsions with control over droplet size and shell thickness. However, the limited production rate of microfluidic devices precludes the use of monodisperse double emulsions for industrial-scale applications, which require large quantities of droplets. To increase throughput, devices can be parallelized to contain many dropmakers operating simultaneously in one chip, but this is challenging to do for double emulsion dropmakers. Production of double emulsions requires dropmakers to have both hydrophobic and hydrophilic channels, requiring spatially precise patterning of channel surface wettability. Precise wettability patterning is difficult for devices containing multiple dropmakers, posing a significant challenge for parallelization. In this paper, we present a multilayer dropmaker geometry that greatly simplifies the process of producing microfluidic devices with excellent spatial control over channel wettability. Wettability patterning is achieved through the independent functionalization of channels in each layer prior to device assembly, rendering the dropmaker with a precise step between hydrophobic and hydrophilic channels. This device geometry enables uniform wettability patterning of parallelized dropmakers, providing a scalable approach for the production of double emulsions.

Spontaneous Creation of Anisotropic Polymer Crystals with Orientation-Sensitive Birefringence in Liquid Drops - Shi, Weichao; Xiaotong Chen; Li, Baihui; Weitz, DavidA. (ACS Applied Materials & Interfaces, 2020)
It remains a grand challenge to prepare anisotropic crystal superstructures with sensitive optical properties in polymer science and materials ﬁeld. This study demonstrates that semicrystalline polymers develop into anisotropic hollow spherulitic crystals spontaneously at interfaces of liquid drops. In contrast to conventional spherulites with centrosymmetric optics and grain boundaries, these anisotropic spherulitic crystals have vanished boundary defects, tunable aspect ratios, and noncentrosymmetric, orientationsensitive birefringence. The experimental ﬁnding is elaborated in poly(L-lactic acid) crystals and is further veriﬁed in a broad class of semicrystalline polymers, irrespective of molecular chirality, chemical constitution, or interfacial modiﬁcation. The facile methods and general mechanism revealed in this study shed light on developing new types of optical microdevices and synthesis of anisotropic semicrystalline particles from liquid emulsions.

DNAzyme-powered nucleic acid release from solid supports - Cao, Ting; Wang, Yongcheng; Tao, Ye; Zhang, Lexiang; Zhou, Ying-Lin; Zhang, Xin-Xiang; Heyman, John A.; Weitz, DavidA. (Chemical Communications, 2020)
Here, we demonstrate use of a Mg 2+ -dependent, site-specific DNA enzyme (DNAzyme) to cleave oligos from polyacrylamide gel beads, which is suitable for use in drop-based assays. , Here, we demonstrate use of a Mg 2+ -dependent, site-specific DNA enzyme (DNAzyme) to cleave oligos from polyacrylamide gel beads, which is suitable for use in drop-based assays. We show that cleavage efficiency is improved by use of a tandem-repeat cleavage site. We further demonstrate that DNAzyme-released oligos function as primers in reverse transcription of cell-released mRNA.

Rapid additive-free bacteria lysis using traveling surface acoustic waves in microfluidic channels - Lu, Haiwei; Kirk Mutafopulos; Heyman, John A.; Pascal Spink; Shen, Liang; Wang, Chaohui; Franke, Thomas; Weitz, DavidA. (Lab on a Chip, 2019)
We report an additive-free method to lyse bacteria and extract nucleic acids and protein using a traveling surface acoustic wave (TSAW) coupled to a microfluidic device. We characterize the effects of the TSAW on E. coli by measuring the viability of cells exposed to the sound waves and find that about 90% are dead. In addition, we measure the protein and nucleic acids released from the cells and show that we recover about 20% of the total material. The lysis method should work for all types of bacteria. These results demonstrate the feasibility of using TSAW to lyse bacteria in a manner that is independent of the type of bacteria.

Preparation of monodisperse hybrid gel particles with various morphologies via flow rate and temperature control - Kanai, Toshimitsu; Nakai, Hiroki; Yamada, Ayaka; Fukuyama, Masafumi; Weitz, DavidA. (Soft Matter, 2019)
We report a facile method for preparing monodisperse hybrid smart gel particles with various morphologies by using microfluidic techniques and the swelling–shrinking phenomenon of thermosensitive poly(N-isopropylacrylamide) (PNIPAM) gel particles. We demonstrate that PNIPAM–polyacrylamide snowman-like, raspberry-like, and dumbbell-like hybrid gel particles can be prepared by controlling the flow rate and temperature.

Traveling surface acoustic wave (TSAW) microfluidic fluorescence activated cell sorter (μFACS) - Kirk Mutafopulos; Pascal Spink; Lofstrom, C. D.; Lu, Peter J.; Lu, H.; Sharpe, J. C.; Franke, T.; Weitz, DavidA. (Lab on a Chip, 2019)
We report a microfluidic fluorescence activated cell-sorting (μFACS) device that employs traveling surface acoustic waves (TSAW) to sort cells at rates comparable to conventional jet-in-air FACS machines, with high purity and viability. The device combines inertial flow focusing and sheath flow to align and evenly space cells, improving the sorting accuracy and screening rate. We sort with an interdigital transducer (IDT) whose tapered geometry allows precise positioning of the TSAW for optimal cell sorting. We sort three different cell lines at several kHz, at cell velocities exceeding one meter per second, while maintaining both sorting purity and cell viability at around 90% simultaneously.

Dendronized fluorosurfactant for highly stable water-in-fluorinated oil emulsions with minimal inter-droplet transfer of small molecules - Chowdhury, Mohammad Suman; Zheng, Wenshan; Kumari, Shalini; Heyman, John; Zhang, Xingcai; Dey, Pradip; Weitz, DavidA.; Haag, Rainer (Nature Communications, 2019)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="1440" data-gtm-vis-first-on-screen-10482319_401="1441" data-gtm-vis-has-fired-10482319_393="1" data-gtm-vis-has-fired-10482319_401="1" data-gtm-vis-total-visible-time-10482319_393="10000" data-gtm-vis-total-visible-time-10482319_401="10000" data-title="Abstract" lang="en"> Fluorosurfactant-stabilized microfluidic droplets are widely used as pico- to nanoliter volume reactors in chemistry and biology. However, current surfactants cannot completely prevent inter-droplet transfer of small organic molecules encapsulated or produced inside the droplets. In addition, the microdroplets typically coalesce at temperatures higher than 80 °C. Therefore, the use of droplet-based platforms for ultrahigh-throughput combination drug screening and polymerase chain reaction (PCR)-based rare mutation detection has been limited. Here, we provide insights into designing surfactants that form robust microdroplets with improved stability and resistance to inter-droplet transfer. We used a panel of dendritic oligo-glycerol-based surfactants to demonstrate that a high degree of inter- and intramolecular hydrogen bonding, as well as the dendritic architecture, contribute to high droplet stability in PCR thermal cycling and minimize inter-droplet transfer of the water-soluble fluorescent dye sodium fluorescein salt and the drug doxycycline.

Self-Limited Accumulation of Colloids in Porous Media - Gerber, G.; Bensouda, M.; Weitz, D. A.; Coussot, P. (Physical Review Letters, 2019)
We present local direct imaging of the progressive adsorption of colloidal particles inside a 3D model porous medium. By varying the interparticle electrostatic interactions, we observe a large range of particle deposition regimes, from a single layer of particles at the surface of the medium to multiple layers and eventually clogging of the system. We derive the complete deposition dynamics and show that colloid accumulation is a self-limited mechanism towards a deposited fraction associated with a balance between the particle interactions and the imposed flow rate. These trends are explained and predicted using a simple probability model considering the particle adsorption energy and the variation of the drag energy with evolving porosity. This constitutes a direct validation of speculated particle transport mechanisms, and a further understanding of accumulation mechanisms.

Controllable Fabrication of Inhomogeneous Microcapsules for Triggered Release by Osmotic Pressure - Zhang, Weixia; Liangliang Qu; Hao Pei; Qin, Zhao; Didier, Jonathan; Wu, Zhengwei; Bobe, Frank; Donald E. Ingber; Weitz, DavidA. (Small, 2019)
Inhomogeneous microcapsules that can encapsulate various cargo for controlled release triggered by osmotic shock are designed and reported. The microcapsules are fabricated using a microfluidic approach and the inhomogeneity of shell thickness in the microcapsules can be controlled by tuning the flow rate ratio of the middle phase to the inner phase. This study demonstrates the swelling of these inhomogeneous microcapsules begins at the thinnest part of shell and eventually leads to rupture at the weak spot with a low osmotic pressure. Systematic studies indicate the rupture fraction of these microcapsules increases with increasing inhomogeneity, while the rupture osmotic pressure decreases linearly with increasing inhomogeneity. The inhomogeneous microcapsules are demonstrated to be impermeable to small probe molecules, which enables long‐term storage. Thus, these microcapsules can be used for long‐term storage of enzymes, which can be controllably released through osmotic shock without impairing their biological activity. The study provides a new approach to design effective carriers to encapsulate biomolecules and release them on‐demand upon applying osmotic shock.

Programmable microencapsulation for enhanced mesenchymal stem cell persistence and immunomodulation - Mao, Angelo S.; Ozkale, Berna; Shah, Nisarg J.; Vining, Kyle H.; Descombes, Tiphaine; Zhang, Liyuan; Tringides, Christina M.; Wong, Sing-Wan; Shin, Jae-Won; Scadden, David T. et al. (Proceedings of the National Academy of Sciences, 2019)
Mesenchymal stem cell (MSC) therapies demonstrate particular promise in ameliorating diseases of immune dysregulation but are hampered by short in vivo cell persistence and inconsistencies in phenotype. Here, we demonstrate that biomaterial encapsulation into alginate using a microfluidic device could substantially increase in vivo MSC persistence after intravenous (i.v.) injection. A combination of cell cluster formation and subsequent cross-linking with polylysine led to an increase in injected MSC half-life by more than an order of magnitude. These modifications extended persistence even in the presence of innate and adaptive immunity-mediated clearance. Licensing of encapsulated MSCs with inflammatory cytokine pretransplantation increased expression of immunomodulatory-associated genes, and licensed encapsulates promoted repopulation of recipient blood and bone marrow with allogeneic donor cells after sublethal irradiation by a ∼2-fold increase. The ability of microgel encapsulation to sustain MSC survival and increase overall immunomodulatory capacity may be applicable for improving MSC therapies in general.

Compression Generated by a 3D Supracellular Actomyosin Cortex Promotes Embryonic Stem Cell Colony Growth and Expression of Nanog and Oct4 - Du, Jing; Fan, Yanlei; Guo, Zheng; Wang, Youguang; Zheng, Xu; Huang, Chong; Liang, Baihui; Gao, Lingyu; Cao, Yanping; Chen, Yunping et al. (Cell Systems, 2019)
Mechanical factors play critical roles in mammalian development. Here, we report that colony-growing mouse embryonic stem cells (mESCs) generate significant tension on the colony surface through the contraction of a three-dimensional supracellular actomyosin cortex (3D-SAC). Disruption of the 3D-SAC, whose organization is dependent on the Rho/Rho-associated kinase (ROCK) signals and E-cadherin, results in mESC colony destruction. Reciprocally, compression force, which is generated by the 3D-SAC, promotes colony growth and expression of Nanog and Oct4 in mESCs and blastocyst development of mouse embryos. These findings suggest that autonomous cell forces regulate embryonic stem cells fate determination and provide insight regarding the biomechanical regulation of embryonic development.

Transparent Impact-Resistant Composite Films with Bioinspired Hierarchical Structure - Chen, Ran; Liu, Junfeng; Yang, Chenjing; Weitz, DavidA.; He, Haonan; Li, Dewen; Chen, Dong; Liu, Kai; Bai, Hao (ACS Applied Materials & Interfaces, 2019)
Inspired by the helicoidally organized microstructure of stomatopods’ smasher dactyl club, a type of impact-resistant composite film reinforced with periodic helicoidal nanofibers is designed and fabricated, which reproduces the structural complexity of the natural material. To periodically align nanofibers in a helicoidal structure, an electrospinning system is developed to better control the alignment of electrospun nanofibers. When the nanofiber scaffold is embedded in an epoxy matrix, the presence of a hierarchical structure allows the composite films to achieve properties well beyond their constituents. The composite film exhibits excellent optical transparency and mechanical properties, such as enhanced tensile strength, ductility, and defect tolerance. With elegant design mimicking nature’s hierarchical structure at multilength scales, the composite films could effectively release the impact energy and greatly increase the impact resistance, suggesting that the transparent composite films are promising protective layers suitable for various applications.

Controlled co-precipitation of biocompatible colorant-loaded nanoparticles by microfluidics for natural color drinks - Kong, Linlin; Chen, Ran; Wang, Xingzheng; Zhao, Chun-Xia; Chen, Qiushui; Hai, Mingtan; Chen, Dong; Yang, Zhenzhong; Weitz, DavidA. (Lab Chip, 2019)
Natural colorants, which impart a vivid color to food and add additional health benefits, are favored over synthetic colorants; however, their applications are limited by their low solubility in water and low stability. Here, we develop a versatile microfluidic strategy to incorporate natural colorants in shellac nanoparticles with controlled physicochemical properties. The rapid mixing in the microfluidic channels ensures that the mixing time is shorter than the aggregation time, thus providing control over the co-precipitation of the colorant and the polymer. By introducing molecular interactions, colorant nanoaggregates are efficiently embedded in the polymer matrix, forming hierarchical colorant-loaded nanoparticles. The colorant-loaded nanoparticles dispersed in water are transparent and stable over a wide pH range and their polymer matrix also provides a favorable microenvironment that greatly improves the shelf life of the colorants. The improved solubility, stability and bioavailability of the natural colorants suggest that shellac nanoparticles are ideal carriers and the stable, transparent dispersions of biocompatible colorant-loaded nanoparticles in water are well-suited for the development of functional foods, such as natural color drinks.

Direct observation of crystallization and melting with colloids - Hwang, Hyerim; Weitz, DavidA.; Spaepen, Frans (Proc. Natl. Acad. Sci. U.S.A., 2019)
We study the kinetics of crystal growth and melting of two types of colloidal crystals: body-centered cubic (BCC) crystals and face-centered cubic (FCC) crystals. A dielectrophoretic “electric bottle” confines colloids, enabling precise control of the motion of the interface. We track the particle motion, and by introducing a structural order parameter, we measure the jump frequencies of particles to and from the crystal and determine from these the free-energy difference between the phases and the interface mobility. We find that the interface is rough in both BCC and FCC cases. Moreover, the jump frequencies correspond to those expected from the random walk of the particles, which translates to collision-limited growth in metallic systems. The mobility of the BCC interface is greater than that of the FCC interface. In addition, contrary to the prediction of some early computer simulations, we show that there is no significant asymmetry between the mobilities for crystallization and melting.

Hydrogel micromotors with catalyst-containing liquid core and shell - Zhu, Hong; Nawar, Saraf; Werner, Jorg G.; Liu, Jinrun; Huang, GaoShan; Mei, YongFeng; Weitz, DavidA.; Solovev, Alexander A. (J. Phys.: Condens. Matter, 2019)
Methacrylic anhydride-derived hydrogel microcapsules have unique properties, including reversibly tunable permeation, purification, and separation of dissolved molecular species. Endowing these dynamic encapsulant systems with autonomous motion will significantly enhance their efficiency and applicability. Here, hydrogel micromotors are realized using complex water-in-oil-in-water double emulsion drops and oil-in-water emulsion drops from glass capillary microfluidics and subsequent photopolymerization. Three hydrogel micromotor strategies are explored: microcapsules with thin shells and liquid cores with dispersed catalytic Pt nanoparticles, as well as water-cored microcapsules and homogeneous microparticles selectively coated with Ti/Pt catalytic layers. Autonomous motion of hydrogel particles and capsules is realized in hydrogen peroxide solutions, where generated oxygen microbubbles propel the dynamically responsive micromotors. The micromotors are balanced by weight, buoyancy, lateral capillary forces and show specific autonomous behaviours that significantly extend short range dynamic responses of hydrogels. Drop-based microfluidics represent a paradigm shift in the integration of multifunctional subsystems and high-throughput design of chemical micromachines in reasonable quantities towards their desired biomedical, environmental and flow/diffusion microreactor applications.

Jetting to dripping transition: Critical aspect ratio in step emulsifiers - Montessori, Andrea; Lauricella, Marco; Stolovicki, Elad; Weitz, DavidA.; Succi, Sauro (Physics of Fluids, 2019)
Fully three-dimensional, time-dependent, direct simulations of the non-ideal Navier-Stokes equations for a two-component fluid shed light into the mechanism which inhibits droplet breakup in step emulsifiers below a critical threshold of the width-to-height (w/h) ratio of the microfluidic nozzle. Below w/h ∼ 2.6, the simulations provide evidence of a smooth topological transition of the fluid from the confined rectangular channel geometry to an isotropic (spherical) expansion of the fluid downstream the nozzle step. Above such threshold, the transition from the inner to the outer space involves a series of dynamical rearrangements which keep the free surface in mechanical balance. Such rearrangements also induce a backflow of the ambient fluid which, in turn, leads to jet pinching and ultimately to its rupture, namely, droplet formation. The simulations show remarkable agreement with the experimental value of the threshold, which is found around w/h ∼ 2.56.

Millimeter-Size Pickering Emulsions Stabilized with Janus Microparticles - Haney, Bobby; Chen, Dong; Cai, Li-Heng; David Weitz; Ramakrishnan, Subramanian (Langmuir, 2019)
The ability to make stable water-in-oil and oil-in-water millimeter-size Pickering emulsions is demonstrated using Janus particles—particles with distinct surface chemistries. The use of a highly cross-linked hydrophobic polymer network and the excellent water-wetting nature of a hydrogel as the hydrophobic and hydrophilic sides, respectively, permit distinct wettability on the Janus particle. Glass capillary microfluidics allows the synthesis of Janus particles with controlled sizes between 128 and 440 μm and control over the hydrophilic-to-hydrophobic domain volume ratio of the particle from 0.36 to 12.77 for a given size. It is shown that the Janus particle size controls the size of the emulsion drops, thus providing the ability to tune the structure and stability of the resulting emulsions. Stability investigations using centrifugation reveal that particles with the smallest size and a balanced hydrophilic-to-hydrophobic volume ratio (Janus ratio) form emulsions with the greatest stability against coalescence. Particles eventually jam at the interface to form nonspherical droplets. This effect is more pronounced as the hydrogel volume is increased. The large Janus particles permit facile visualization of particle-stabilized emulsions, which result in a better understanding of particle stabilization mechanisms of formed emulsions.

Photothermal-responsive nanosized hybrid polymersome as versatile therapeutics codelivery nanovehicle for effective tumor suppression - Zhang, Hongbo; Cui, Wenguo; Qu, Xiangmeng; Huayin Wu; Liangliang Qu; Zhang, Xu; Makila, Ermei; Salonen, Jarno; Yueqi Zhu; Zhou Yang; Chen, Dong; Santos, Helder A.; et al. (Proc. Natl. Acad. Sci. U.S.A., 2019)
Effective cancer therapies often demand delivery of combinations of drugs to inhibit multidrug resistance through synergism, and the development of multifunctional nanovehicles with enhanced drug loading and delivery efficiency for combination therapy is currently a major challenge in nanotechnology. However, such combinations are more challenging to administer than single drugs and can require multipronged approaches to delivery. In addition to being stable and biodegradable, vehicles for such therapies must be compatible with both hydrophobic and hydrophilic drugs, and release drugs at sustained therapeutic levels. Here, we report synthesis of porous silicon nanoparticles conjugated with gold nanorods [composite nanoparticles (cNPs)] and encapsulate them within a hybrid polymersome using double-emulsion templates on a microfluidic chip to create a versatile nanovehicle. This nanovehicle has high loading capacities for both hydrophobic and hydrophilic drugs, and improves drug delivery efficiency by accumulating at the tumor after i.v. injection in mice. Importantly, a triple-drug combination suppresses breast tumors by 94% and 87% at total dosages of 5 and 2.5 mg/kg, respectively, through synergy. Moreover, the cNPs retain their photothermal properties, which can be used to significantly inhibit multidrug resistance upon near-infrared laser irradiation. Overall, this work shows that our nanovehicle has great potential as a drug codelivery nanoplatform for effective combination therapy that is adaptable to other cancer types and to molecular targets associated with disease progression.

Probe Sensitivity to Cortical versus Intracellular Cytoskeletal Network Stiffness - Vahabikashi, Amir; Park, Chan Young; Perkumas, Kristin; Zhang, Zhiguo; Deurloo, Emily K.; Huayin Wu; Weitz, DavidA.; Stamer, W. Daniel; Robert D. Goldman; Jeffrey J. Fredberg; Johnson, Mark (Biophys. J., 2019)
In development, wound healing, and pathology, cell biomechanical properties are increasingly recognized as being of central importance. To measure these properties, experimental probes of various types have been developed, but how each probe reflects the properties of heterogeneous cell regions has remained obscure. To better understand differences attributable to the probe technology, as well as to define the relative sensitivity of each probe to different cellular structures, here we took a comprehensive approach. We studied two cell types—Schlemm’s canal endothelial cells and mouse embryonic fibroblasts (MEFs)—using four different probe technologies: 1) atomic force microscopy (AFM) with sharp tip, 2) AFM with round tip, 3) optical magnetic twisting cytometry (OMTC), and 4) traction microscopy (TM). Perturbation of Schlemm’s canal cells with dexamethasone treatment, α-actinin overexpression, or RhoA overexpression caused increases in traction reported by TM and stiffness reported by sharp-tip AFM as compared to corresponding controls. By contrast, under these same experimental conditions, stiffness reported by round-tip AFM and by OMTC indicated little change. Knockout (KO) of vimentin in MEFs caused a diminution of traction reported by TM, as well as stiffness reported by sharp-tip and round-tip AFM. However, stiffness reported by OMTC in vimentin-KO MEFs was greater than in wild type. Finite-element analysis demonstrated that this paradoxical OMTC result in vimentin-KO MEFs could be attributed to reduced cell thickness. Our results also suggest that vimentin contributes not only to intracellular network stiffness but also cortex stiffness. Taken together, this evidence suggests that AFM sharp tip and TM emphasize properties of the actin-rich shell of the cell, whereas round-tip AFM and OMTC emphasize those of the noncortical intracellular network.

A simple mix-and-read bacteria detection system based on DNAzyme and molecular beacon - Cao, Ting; Wang, Yongcheng; Zhao, Lingli; Wang, Ye; Tao, Ye; Heyman, John A.; Weitz, DavidA.; Zhou, Yinglin; Zhang, Xinxiang (Chem. Commun., 2019)
Here, we describe a simple mix-and-read method for the detection of specific bacterial strains that uses a DNAzyme and a molecular beacon to generate a signal. We have greatly improved upon the previously described DNAzyme-based bacteria detection method by eliminating a tedious preparation step while maintaining detection sensitivity.

Single-step assembly of asymmetric vesicles - Arriaga, Laura R.; Huang, Yuting; Kim, Shin-Hyun; Aragones, Juan L.; Ziblat, Roy; Koehler, Stephan A.; Weitz, DavidA. (Lab Chip, 2019)
Asymmetric vesicles are membranes in which amphiphiles are asymmetrically distributed between each membrane leaflet. This asymmetry dictates chemical and physical properties of these vesicles, enabling their use as more realistic models of biological cell membranes, which also are asymmetric, and improves their potential for drug delivery and cosmetic applications. However, their fabrication is difficult as the self-assembly of amphiphiles always leads to symmetric vesicles. Here, we report the use of water-in-oil-in-oil-in-water triple emulsion drops to direct the assembly of the two leaflets to form asymmetric vesicles. Different compositions of amphiphiles are dissolved in each of the two oil shells of the triple emulsion; the amphiphiles diffuse to the interfaces and adsorb differentially at each of the two oil/water interfaces of the triple emulsion. These middle oil phases dewet from the innermost water cores of the triple emulsion drops, leading to the formation of membranes with degrees of asymmetry up to 70%. The triple emulsion drops are fabricated using capillary microfluidics, enabling production of highly monodisperse drops at rates as high as 300 Hz. Vesicles produced by this method can very efficiently encapsulate many different ingredients; this further enhances the utility of asymmetric vesicles as artificial cells, bioreactors and delivery vehicles.

Single-step microfluidic production of W/O/W double emulsions as templates for β-carotene-loaded giant liposomes formation - Michelon, Mariano; Huang, Yuting; de la Torre, Lucimara Gaziola; Weitz, DavidA.; Cunha, Rosiane Lopes (Chemical Engineering Journal, 2019)
We demonstrated the microfluidic production of W/O/W double emulsion droplets aiming formation of β-carotene-incorporated giant liposomes for food and/or pharmaceutical applications. For this purpose, glass-capillary microfluidic devices were fabricated to create a truly three-dimensional flow aiming production of giant unilamellar liposomes by solvent evaporation process after W/O/W double emulsion droplet templates formation. A great challenge of microfluidic production of monodisperse and stable W/O/W double emulsion templates for this proposal is the replacement of organic solvents potentially toxic for phospholipids dissolution. Besides, the high cost of several semi-synthetic phospholipids commonly used for giant liposome formation remains as a major technological challenge to be overcome. Thus, β-carotene-incorporated giant liposomes were generated using biocompatible solvents with low toxic potential (ethyl acetate and pentane) and non-purified soybean lecithin - a food-grade phospholipid mixture with low cost - by dewetting and evaporation of the solvents forming the oily intermediate phase of W/O/W double emulsion droplet templates. Our results showed monodisperse β-carotene-loaded giant liposomes with diameter ranging between 100 μm and 180 μm and a stability of approximately 7 days. In this way, a single-step microfluidic process with highly accurate control of size distribution was developed. This microfluidic process proposed is potentially useful for a broad range of applications in protection and delivery of active compounds.

Water-Triggered Rapid Release of Biocide with Enhanced Antimicrobial Activity in Biodiesel - Hao Pei; Abbaspourrad, Alireza; Zhang, Weixia; Wu, Zhengwei; Weitz, DavidA. (Macromol. Mater. Eng., 2019)
Biodiesel inherently contains more water than mineral diesel and as a result microbial contamination is a major problem that hinders its widespread application. The current method of removing the microbial contamination is direct addition of biocide. However, this method cannot enrich the water phase with biocide rapidly enough, leading to unavoidable overdosing of biocide and environmental issues. Here, biocide is encapsulated within hydrogel microparticles with a water‐triggered release feature to improve antimicrobial efficiency of biocide in biodiesel. To demonstrate the water‐triggered release mechanism, a green dye is encapsulated within the microparticles. The encapsulated dye remains inside the microparticles for more than 6 weeks when the microparticles are stored in oil phase; however, the dye releases in 4 min when the microparticles contact water. Using this water‐triggered release strategy, biocide is successfully delivered to the water phase in biodiesel. The encapsulated biocide shows higher antimicrobial efficacy than that of free biocide, in both short‐term and long‐term experiments. The possibility of scaling up the production of hydrogel microparticles using bulk emulsification method is also explored. Moreover, the water‐triggered release strategy can be used for releasing other water‐soluble functional materials. This opens opportunities for a wide range of encapsulation and controlled delivery applications.

Initial growth dynamics of 10 nm nanobubbles in the graphene liquid cell - Kim, QHwan; Shin, Dongha; Park, Jungwon; Weitz, DavidA.; Jhe, Wonho (Appl. Nanosci., 2018)
The unexpected long lifetime of nanobubble against the large Laplace pressure is one of the important issues in nanobubble research and a few models have been proposed to explain it. Most studies, however, have been focused on the observation of relatively large nanobubbles over 100 nm and are limited to the equilibrium state phenomena. The study on the sub-100 nm sized nanobubble is still lacking due to the limitation of imaging methods which overcomes the optical resolution limit. Here, we demonstrate the observation of growth dynamics of 10 nm nanobubbles confined in the graphene liquid cell using transmission electron microscopy (TEM). We modified the classical diffusion theory by considering the finite size of the confined system of graphene liquid cell (GLC), successfully describing the temporal growth of nanobubble. Our study shows that the growth of nanobubble is determined by the gas oversaturation, which is affected by the size of GLC.

Macroscopic Self-Assembly: Versatile Hydrogel Ensembles with Macroscopic Multidimensions (Adv. Mater. 52/2018) - Li, Qing; Zhang, Ya-Wen; Wang, Cai-Feng; Weitz, DavidA.; Chen, Su (Adv. Mater., 2018)
A new microfluidic‐assisted self‐healing‐driven assembly strategy enabling continuous and controllable construction of programmed ordered assemblies is developed by Su Chen and co‐workers in article number 1803475. This allows self‐assembly to be carried out on the macroscopic scale toward tissue materials and light‐emitting diode devices.

Reduced Graphene Oxide Membrane Induced Robust Structural Colors toward Personal Thermal Management - Zhu, Zhijie; Zhang, Jing; Tong, Yu-long; Peng, Gang; Cui, Tingting; Wang, Cai-Feng; Chen, Su; Weitz, DavidA. (ACS Photonics, 2018)
Angle-independent structural colors are prepared by membrane separation-assisted assembly (MSAA) method with modified reduced graphene oxide (rGO) as the substrate membrane. We show that the wrinkled and crumpled rGO laminates not only ensure uneven morphology of colloidal film but improve color saturation by decreasing coherent scattering. In addition, we study the influence of stopband position on thermal insulation property of the colloidal film for the first time. High absolute temperature difference of 6.9 °C is achieved comparing with control sample. And films with longer stopband positions indicate better thermal insulation performance because of inherent slow photon effect in photonic structure. This general principle of thermal insulation by colloidal films opens the way to a new generation of thermal management materials.

Topological aspects of jetting to dripping transition in step emulsifiers - Montessori, Andrea; Lauricella, Marco; Stolovicki, Elad; David Weitz; Succi, Sauro (Physics of Fluids, 2018)
Fully three-dimensional, time-dependent, direct simulations of the non-ideal Navier-Stokes equations for a two-component fluid shed light into the mechanism which inhibits droplet breakup in step emulsifiers below a critical threshold of the width-to-height (w/h) ratio of the microfluidic nozzle. Below w/h ∼ 2.6, the simulations provide evidence of a smooth topological transition of the fluid from the confined rectangular channel geometry to an isotropic (spherical) expansion of the fluid downstream the nozzle step. Above such threshold, the transition from the inner to the outer space involves a series of dynamical rearrangements which keep the free surface in mechanical balance. Such rearrangements also induce a backflow of the ambient fluid which, in turn, leads to jet pinching and ultimately to its rupture, namely, droplet formation. The simulations show remarkable agreement with the experimental value of the threshold, which is found around w/h ∼ 2.56.

Versatile Hydrogel Ensembles with Macroscopic Multidimensions - Li, Qing; Zhang, Ya-Wen; Wang, Cai-Feng; Weitz, DavidA.; Chen, Su (Adv. Mater., 2018)
Methods allowing construction of macroscopic programmed materials in a flexible and efficient fashion are highly desirable. However, the existing approaches are far removed from such materials. A new self‐healing‐driven assembly (SHDA) strategy to fabricate various programmed materials by using uniform gel beads (microsize of 212 µm or millimeter size of 4 mm) as building blocks is described here. In virtue of hydrogen bonds and host–guest interactions between gel beads, a series of linear, planar, and 3D beaded assemblies are fabricated via SHDA in microfluidic channels in a continuous and controlled manner. From the perspective of practical applications, the use of gel assemblies is exploited for tissue engineering with controlled cells coculture, as well as light conversion materials toward white‐light‐emitting diodes (WLEDs). The SHDA strategy developed in this study gives a new insight into the facile and rapid fabrication of various programmed materials toward biological tissue and optoelectronic device.

Tumor-Vasculature-on-a-Chip for Investigating Nanoparticle Extravasation and Tumor Accumulation - Wang, Hao-Fei; Ran, Rui; Liu, Yun; Hui, Yue; Zeng, Bijun; Chen, Dong; Weitz, DavidA.; Zhao, Chun-Xia (ACS Nano, 2018)
Nanoparticle tumor accumulation relies on a key mechanism, the enhanced permeability and retention (EPR) effect, but it remains challenging to decipher the exact impact of the EPR effect. Animal models in combination with imaging modalities are useful, but it is impossible to delineate the roles of multiple biological barriers involved in nanoparticle tumor accumulation. Here we report a microfluidic tumor-vasculature-on-a-chip (TVOC) mimicking two key biological barriers, namely, tumor leaky vasculature and 3D tumor tissue with dense extracellular matrix (ECM), to study nanoparticle extravasation through leaky vasculature and the following accumulation in tumor tissues. Intact 3D tumor vasculature was developed with selective permeability of small molecules (20 kDa) but not large ones (70 kDa). The permeability was further tuned by cytokine stimulation, demonstrating the independent control of the leaky tumor vasculature. Combined with tumor spheroids in dense ECM, our TVOC model is capable of predicting nanoparticles’ in vivo tumor accumulation, thus providing a powerful platform for nanoparticle evaluation.

Determining the Lipid Specificity of Insoluble Protein Transmembrane Domains - Ziblat, Roy; Weaver, James; Arriaga, Laura Rodriguez; Chong, Shaorong; Weitz, DavidA. (Lab Chip, 2018)
While the specificity of protein–lipid interactions is a key feature in the function of biological membranes, studying the specifics of these interactions is challenging because most membrane proteins are insoluble in water due to the hydrophobic nature of their transmembrane domains (TMDs). Here, we introduce a method that overcomes this solubility limitation and identifies the affinity profile of protein TMDs to specific lipid formulations. Using 5 human TMDs as a sample group, our results demonstrate that TMDs are highly selective and that these specific lipid–TMD interactions can involve either a single lipid, or the combination of multiple lipid species.

Collective Shape Actuation of Polymer Double Emulsions by Solvent Evaporation - Shi, Weichao; Didier, Jonathan E.; Donald E. Ingber; Weitz, DavidA. (ACS Applied Materials & Interfaces, 2018)
We demonstrate that the shape actuation of waterin-oil-in-water double emulsion droplets can be achieved by controlling solvent evaporation in a model system, where the oil phase consists of hydrophobic homopolymer/amphiphilic block copolymer/solvent. A gradient of interfacial tension is created in the polymer shell, which drives signiﬁcant deformation of the droplets in constant volume. The deformed droplets recover to their initial shape spontaneously, and shape actuation of droplets can be further tuned by osmotic pressure. Our model system provides a new prototype for developing shape-responsive droplets in a solvent environment.

Wetting controls of droplet formation in step emulsification - Eggersdorfer, Maximilian L.; Seybold, Hansjörg; Ofner, Alessandro; Weitz, DavidA.; Studart, André R. (Proceedings of the National Academy of Sciences, 2018)
The formation of droplets is ubiquitous in many natural and industrial processes and has reached an unprecedented level of control with the emergence of milli- and microfluidics. Although important insight into the mechanisms of droplet formation has been gained over the past decades, a sound understanding of the physics underlying this phenomenon and the effect of the fluid’s flow and wetting properties on the droplet size and production rate is still missing, especially for the widely applied method of step emulsification. In this work, we elucidate the physical controls of microdroplet formation in step emulsification by using the wetting of fluidic channels as a tunable parameter to explore a broad set of emulsification conditions. With the help of high-speed measurements, we unequivocally show that the final droplet pinch-off is triggered by a Rayleigh–Plateau-type instability. The droplet size, however, is not determined by the Rayleigh–Plateau breakup, but by the initial wetting regime, where the fluid’s contact angle plays a crucial role. We develop a physical theory for the wetting process, which closely describes our experimental measurements without invoking any free fit parameter. Our theory predicts the initiation of the Rayleigh–Plateau breakup and the transition from dripping to jetting as a function of the fluid’s contact angle. Additionally, the theory solves the conundrum why there is a minimal contact angle of α = 2π/3 = 120° for which droplets can form.

Evolution on the biophysical fitness landscape of an RNA virus - Rotem, Assaf; Serohijos, Adrian W. R.; Chang, Connie B.; Wolfe, Joshua T.; Fischer, Audrey E.; Mehoke, Thomas S.; Zhang, Huidan; Tao, Ye; Ung, W. Lloyd; Choi, Jeong-Mo; Rodrigues, Joıfmmode\tildea\elseã\fi}o V.; Abimbola, O. Kolawole; et al. (Mol. Biol. Evol., 2018)
Viral evolutionary pathways are determined by the fitness landscape, which maps viral genotype to fitness. However, a quantitative description of the landscape and the evolutionary forces on it remain elusive. Here, we apply a biophysical fitness model based on capsid folding stability and antibody binding affinity to predict the evolutionary pathway of norovirus escaping a neutralizing antibody. The model is validated by experimental evolution in bulk culture and in a drop-based microfluidics that propagates millions of independent small viral subpopulations. We demonstrate that along the axis of binding affinity, selection for escape variants and drift due to random mutations have the same direction, an atypical case in evolution. However, along folding stability, selection and drift are opposing forces whose balance is tuned by viral population size. Our results demonstrate that predictable epistatic tradeoffs between molecular traits of viral proteins shape viral evolution.

A Versatile Strategy to Fabricate 3D Conductive Frameworks for Lithium Metal Anodes - Qi, Li-Ya; Shang, Luoran; Chen, Xi; Ye, Luhan; Zhang, Weixia; Feng, Peijian; Zou, Wei; Cao, Naizhen; Zhou, Heng-Hui; Weitz, DavidA.; Li, Xin (Adv. Mater. Interfaces, 2018)
<span style="display: inline !important; float: none; background-color: transparent; color: rgb(28, 29, 30); font-family: Open Sans,sans-serif,icomoon; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">The suppression of lithium dendrite is critical to the realization of lithium metal batteries. 3D conductive framework, among different approaches, has shown very promising results in dendrite suppression. A novel cost‐effective and versatile dip‐coating method is presented here to make 3D conductive framework. Various substrates with different geometries are coated successfully with copper, including electrically insulating glass fiber (GF) or rice paper and conducting Ni foam. In particular, the as‐prepared copper coated GF shows promising results to serve as the lithium metal substrate by the electrochemical battery tests. The method significantly broadens the candidate materials database for 3D conductive framework to include all kinds of intrinsically insulating 3D substrates.

Dynamic Microcapsules with Rapid and Reversible Permeability Switching - Werner, Jorg G.; Deveney, Brendan T.; Nawar, Saraf; Weitz, DavidA. (Adv. Funct. Mater., 2018)
<span style="display: inline !important; float: none; background-color: transparent; color: rgb(28, 29, 30); font-family: Open Sans,sans-serif,icomoon; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Dynamic microcapsules are reported that exhibit shell membranes with fast and reversible changes in permeability in response to external stimuli. A hydrophobic anhydride monomer is employed in the thiol–ene polymerization as a disguised precursor for the acid‐containing shells; this enables the direct encapsulation of aqueous cargo in the liquid core using microfluidic fabrication of water‐in‐oil‐in‐water double emulsion drops. The poly(anhydride) shells hydrolyze in their aqueous environment without further chemical treatment, yielding cross‐linked poly(acid) microcapsules that exhibit trigger‐responsive and reversible property changes. The microcapsule shell can actively be switched numerous times between impermeable and permeable due to the exceptional mechanical properties of the thiol–ene network that prevent rupture or failure of the membrane, allowing it to withstand the mechanical stresses imposed on the capsule during the dynamic property changes. The permeability and molecular weight cutoff of the microcapsules can dynamically be controlled with triggers such as pH and ionic environment. The reversibly triggered changes in permeability of the shell exhibit a response time of seconds, enabling actively adjustable release profiles, as well as on‐demand capture, trapping, and release of cargo molecules with molecular selectivity and fast on‐off rates.

Elucidating the mechanism of step emulsification - Montessori, Andrea; Lauricella, Marco; Succi, Sauro; Stolovicki, Elad; David Weitz (Phys. Rev. Fluids, 2018)
Three-dimensional, time-dependent direct simulations of step emulsification microdevices highlight two essential mechanisms for droplet formation: first, the onset of an adverse pressure gradient driving a backflow of the continuous phase from the external reservoir to the microchannel, and second, the striction of the flowing jet which leads to its subsequent rupture. It is also shown that such a rupture is delayed and eventually suppressed by increasing the flow speed of the dispersed phase within the channel, due to the stabilizing effect of dynamic pressure. This suggests a new criterion for dripping-jetting transition, based on local values of the capillary and Weber numbers.

Hydrogel Microcapsules with Dynamic pH-Responsive Properties from Methacrylic Anhydride - Werner, Jorg; Nawar, Saraf; Solovev, Alexander A.; Weitz, DavidA. (Macromolecules, 2018)
<span style='display: inline !important; float: none; background-color: transparent; color: rgb(0, 0, 0); font-family: "Helvetica","Arial",sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 500; letter-spacing: normal; line-height: 22.4px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px; word-wrap: break-word;'>Dynamic microcapsules are a highly sought-after class of encapsulant for advanced delivery applications with dynamically tunable release profiles, as actively manipulatable microreactors, or as selective microtraps for molecular separation and purification. Such dynamic microcapsules can only be realized with a nondestructive trigger-response mechanism that changes the permeability of the shell membrane reversibly, as found in hydrogels. However, the direct synthesis of a trigger-responsive hydrogel membrane around a water drop without the use of sacrificial templates remains elusive due to the incompatibility of the synthesis chemistry with aqueous emulsion processing. Here, we report on a facile approach to fabricate reversibly responsive hydrogel microcapsules utilizing reactive anhydride chemistry. Cross-linked and hydrophobic poly(methacrylic anhydride) microcapsules are obtained from microfluidic double emulsion drop templating that enables direct encapsulation of hydrophilic, water-suspended cargo within the aqueous core. Hydrolysis in aqueous environment yields microcapsules with a poly(acid) hydrogel shell that exhibit high mechanical and chemical stability for repeated cycling between its swollen and nonswollen states without rupture or fatigue. The permeability of the microcapsules is strongly dependent on the degree of swelling and hence can be actively and dynamically modified, enabling repeated capture, trap, and release of aqueous cargo over numerous cycles.

Microfluidic fabrication of microparticles for biomedical applications - Li, Wen; Zhang, Liyuan; Ge, Xuehui; Xu, Biyi; Zhang, Weixia; Liangliang Qu; Choi, Chang-Hyung; Xu, Jianhong; Zhang, Afang; Hyomin Lee; Weitz, DavidA. (Chem. Soc. Rev., 2018)
<span style="display: inline !important; float: none; background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 300; letter-spacing: -0.32px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Droplet microfluidics offers exquisite control over the flows of multiple fluids in microscale, enabling fabrication of advanced microparticles with precisely tunable structures and compositions in a high throughput manner. The combination of these remarkable features with proper materials and fabrication methods has enabled high efficiency, direct encapsulation of actives in microparticles whose features and functionalities can be well controlled. These microparticles have great potential in a wide range of bio-related applications including drug delivery, cell-laden matrices, biosensors and even as artificial cells. In this review, we briefly summarize the materials, fabrication methods, and microparticle structures produced with droplet microfluidics. We also provide a comprehensive overview of their recent uses in biomedical applications. Finally, we discuss the existing challenges and perspectives to promote the future development of these engineered microparticles.

Single-cell sequencing leads a new era of proﬁling transcriptomic landscape - Zhang, Huidan; Cui, Naiwen; Cai, Yamei; Lei, Fengyang; Weitz, David A (Journal of Bio-X Research, 2018)
Understanding the complexity of biological systems requires a comprehensive analysis of their cell populations. Ideally, this should be done at the single cell level, because bulk analysis of the full population obscured many critical details due to artifacts introduced by averaging. However, this has been technically challenging due to the cumbersome procedure, low throughput, and high costs of performing analysis on a single-cell basis. Excitingly, technical improvements in single-cell RNA sequencing are making it economically practical to proﬁle the transcriptomics of large populations of cells at the single-cell level, and have yielded numerous results that address important biological and medical questions. Further development of the technology and data analysis will signiﬁcantly beneﬁt the biomedical ﬁeld by unraveling the function of individual cells in their microenvironments and modeling their transcriptional dynamics.

High-throughput double emulsion-based microfluidic production of hydrogel microspheres with tunable chemical functionalities toward biomolecular conjugation - Liu, Eric Y.; Jung, Sukwon; Weitz, DavidA.; Yi, Hyunmin; Choi, Chang-Hyung (Lab Chip, 2018)
<span style="display: inline !important; float: none; background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 300; letter-spacing: -0.32px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Chemically functional hydrogel microspheres hold significant potential in a range of applications including biosensing, drug delivery, and tissue engineering due to their high degree of flexibility in imparting a range of functions. In this work, we present a simple, efficient, and high-throughput capillary microfluidic approach for controlled fabrication of monodisperse and chemically functional hydrogel microspheres <em style="background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: italic; font-variant: normal; font-weight: 300; height: auto; letter-spacing: -0.32px; line-height: 24px; margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px; orphans: 2; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">via<span style="display: inline !important; float: none; background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 300; letter-spacing: -0.32px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;"> formation of double emulsion drops with an ultra-thin oil shell as a sacrificial template. This method utilizes spontaneous dewetting of the oil phase upon polymerization and transfer into aqueous solution, resulting in poly(ethylene glycol) (PEG)-based microspheres containing primary amines (chitosan, CS) or carboxylates (acrylic acid, AA) for chemical functionality. Simple fluorescent labelling of the as-prepared microspheres shows the presence of abundant, uniformly distributed and readily tunable functional groups throughout the microspheres. Furthermore, we show the utility of chitosan's primary amine as an efficient conjugation handle at physiological pH due to its low pKa by direct comparison with other primary amines. We also report the utility of these microspheres in biomolecular conjugation using model fluorescent proteins, R-phycoerythrin (R-PE) and green fluorescent protein (GFPuv), <em style="background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: italic; font-variant: normal; font-weight: 300; height: auto; letter-spacing: -0.32px; line-height: 24px; margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px; orphans: 2; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">via<span style="display: inline !important; float: none; background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 300; letter-spacing: -0.32px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;"> tetrazine–<em style="background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: italic; font-variant: normal; font-weight: 300; height: auto; letter-spacing: -0.32px; line-height: 24px; margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px; orphans: 2; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">trans<span style="display: inline !important; float: none; background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 300; letter-spacing: -0.32px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">-cyclooctene (Tz–TCO) ligation for CS-PEG microspheres and carbodiimide chemistry for AA-PEG microspheres, respectively. The results show rapid coupling of R-PE with the microspheres' functional groups with minimal non-specific adsorption. In-depth protein conjugation kinetics studies with our microspheres highlight the differences in reaction and diffusion of R-PE with CS-PEG and AA-PEG microspheres. Finally, we demonstrate orthogonal one-pot protein conjugation of R-PE and GFPuv with CS-PEG and AA-PEG microspheres <em style="background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: italic; font-variant: normal; font-weight: 300; height: auto; letter-spacing: -0.32px; line-height: 24px; margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px; orphans: 2; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">via<span style="display: inline !important; float: none; background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 300; letter-spacing: -0.32px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;"> simple size-based encoding. Combined, these results represent a significant advancement in the rapid and reliable fabrication of monodisperse and chemically functional hydrogel microspheres with tunable properties.

Interaction of spin-labeled HPMA-based nanoparticles with human blood plasma proteins – the introduction of protein-corona-free polymer nanomedicine - Klepac, Damir; Kostkova, Hana; Petrova, Svetlana; Chytil, Petr; Etrych, Tomas; Kereiche, Sami; Raska, Ivan; Weitz, DavidA.; Filippov, Sergey K. (Nanoscale, 2018)
<span style="display: inline !important; float: none; background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 300; letter-spacing: -0.32px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">In this paper, we revised the current understanding of the protein corona that is created on the surface of nanoparticles in blood plasma after an intravenous injection. We have focused on nanoparticles that have a proven therapeutic outcome. These nanoparticles are based on two types of biocompatible amphiphilic copolymers based on <em style="background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: italic; font-variant: normal; font-weight: 300; height: auto; letter-spacing: -0.32px; line-height: 24px; margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px; orphans: 2; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">N<span style="display: inline !important; float: none; background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 300; letter-spacing: -0.32px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">-(2-hydroxypropyl)methacrylamide (HPMA): a block copolymer, poly(ε-caprolactone) (PCL)-<em style="background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: italic; font-variant: normal; font-weight: 300; height: auto; letter-spacing: -0.32px; line-height: 24px; margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px; orphans: 2; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">b<span style="display: inline !important; float: none; background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 300; letter-spacing: -0.32px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">-poly(HPMA), and a statistical HPMA copolymer bearing cholesterol moieties, which have been tested both <em style="background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: italic; font-variant: normal; font-weight: 300; height: auto; letter-spacing: -0.32px; line-height: 24px; margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px; orphans: 2; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">in vitro<span style="display: inline !important; float: none; background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 300; letter-spacing: -0.32px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;"> and <em style="background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: italic; font-variant: normal; font-weight: 300; height: auto; letter-spacing: -0.32px; line-height: 24px; margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px; orphans: 2; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">in vivo<span style="display: inline !important; float: none; background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 300; letter-spacing: -0.32px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">. We studied the interaction of nanoparticles with blood plasma and selected blood plasma proteins by electron paramagnetic resonance (EPR), isothermal titration calorimetry, dynamic light scattering, and cryo-transmission electron microscopy. The copolymers were labeled with TEMPO radicals at the end of hydrophobic PCL or along the hydrophilic HPMA chains to monitor changes in polymer chain dynamics caused by protein adsorption. By EPR and other methods, we were able to probe specific interactions between nanoparticles and blood proteins, specifically low- and high-density lipoproteins, immunoglobulin G, human serum albumin (HSA), and human plasma. It was found that individual proteins and plasma have very low binding affinity to nanoparticles. We observed no hard corona around HPMA-based nanoparticles; with the exception of HSA the proteins showed no detectable binding to the nanoparticles. Our study confirms that a classical “hard corona–soft corona” paradigm is not valid for all types of nanoparticles and each system has a unique protein corona that is determined by the nature of the NP material.

Microfluidic Model Porous Media: Fabrication and Applications - Anbari, Alimohammad; Chien, Hung-Ta; Datta, Sujit S.; Deng, Wen; Weitz, DavidA.; Fan, Jing (Small, 2018)
<span style="display: inline !important; float: none; background-color: transparent; color: rgb(28, 29, 30); font-family: Open Sans,sans-serif,icomoon; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Complex fluid flow in porous media is ubiquitous in many natural and industrial processes. Direct visualization of the fluid structure and flow dynamics is critical for understanding and eventually manipulating these processes. However, the opacity of realistic porous media makes such visualization very challenging. Micromodels, microfluidic model porous media systems, have been developed to address this challenge. They provide a transparent interconnected porous network that enables the optical visualization of the complex fluid flow occurring inside at the pore scale. In this Review, the materials and fabrication methods to make micromodels, the main research activities that are conducted with micromodels and their applications in petroleum, geologic, and environmental engineering, as well as in the food and wood industries, are discussed. The potential applications of micromodels in other areas are also discussed and the key issues that should be addressed in the near future are proposed.

Rapid Patterning of PDMS Microfluidic Device Wettability Using Syringe-Vacuum-Induced Segmented Flow in Nonplanar Geometry - Choi, Chang-Hyung; Hyomin Lee; Weitz, DavidA. (ACS Appl. Mater. Interfaces, 2018)
<span style="display: inline !important; float: none; background-color: transparent; color: rgb(0, 0, 0); font-family: "Helvetica","Arial",sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 500; letter-spacing: normal; line-height: 22.4px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px; word-wrap: break-word;">We present a simple and rapid method to spatially pattern the surface wetting properties of PDMS microfluidic devices by layer-by-layer (LbL) deposition of polyelectrolytes using syringe-vacuum-induced segmented flow in nonplanar geometry. Our technique offers selective surface modification in microfluidic chips with multiple flow-focusing junctions, enabling production of monodisperse double- and triple-emulsion drops.

Tissue and cellular rigidity and mechanosensitive signaling activation in Alexander disease - Wang, Liqun; Xia, Jing; Li, Jonathan; Hagemann, Tracy L.; Jones, Jeffrey R.; Fraenkel, Ernest; Weitz, DavidA.; Zhang, Su-Chun; Messing, Albee; Feany, Mel B. (Nat. Commun., 2018)
<span style="display: inline !important; float: none; background-color: transparent; color: rgb(34, 34, 34); font-family: Lora,Palatino,Times,Times New Roman,serif; font-size: 17px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: 0.17px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px; word-wrap: break-word;">Glial cells have increasingly been implicated as active participants in the pathogenesis of neurological diseases, but critical pathways and mechanisms controlling glial function and secondary non-cell autonomous neuronal injury remain incompletely defined. Here we use models of Alexander disease, a severe brain disorder caused by gain-of-function mutations in GFAP, to demonstrate that misregulation of GFAP leads to activation of a mechanosensitive signaling cascade characterized by activation of the Hippo pathway and consequent increased expression of A-type lamin. Importantly, we use genetics to verify a functional role for dysregulated mechanotransduction signaling in promoting behavioral abnormalities and non-cell autonomous neurodegeneration. Further, we take cell biological and biophysical approaches to suggest that brain tissue stiffness is increased in Alexander disease. Our findings implicate altered mechanotransduction signaling as a key pathological cascade driving neuronal dysfunction and neurodegeneration in Alexander disease, and possibly also in other brain disorders characterized by gliosis.

Microfluidic Templated Multicompartment Microgels for 3D Encapsulation and Pairing of Single Cells - Zhang, Liyuan; Chen, Kaiwen; Zhang, Haoyue; Pang, Bo; Choi, Chang-Hyung; Mao, Angelo S.; Liao, Hongbing; Utech, Stefanie; Mooney, David J.; Wang, Huanan; Weitz, DavidA. (Small, 2018)
Controlled encapsulation and pairing of single cells within a confined 3D matrix can enable the replication of the highly ordered cellular structure of human tissues. Microgels with independently controlled compartments that can encapsulate cells within separately confined hydrogel matrices would provide precise control over the route of pairing single cells. Here, a one‐step microfluidic method is presented to generate monodisperse multicompartment microgels that can be used as a 3D matrix to pair single cells in a highly biocompatible manner. A method is presented to induce microgels formation on chip, followed by direct extraction of the microgels from oil phase, thereby avoiding prolonged exposure of the microgels to the oil. It is further demonstrated that by entrapping stem cells with niche cells within separate but adjacent compartments of the microgels, it can create complex stem cell niche microenvironments in a controlled manner, which can serve as a useful tool for the study of cell–cell interactions. This microfluidic technique represents a significant step toward high‐throughput single cells encapsulation and pairing for the study of intercellular communications at single cell level, which is of significant importance for cell biology, stem cell therapy, and tissue engineering.

Geometric constraints during epithelial jamming - Atia, Lior; Bi, Dapeng; Sharma, Yasha; Jennifer A. Mitchel; Gweon, Bomi; Koehler, Stephan A.; Stephen J. DeCamp; Lan, Bo; Kim, Jae Hun; Hirsch, Rebecca; Adrian F. Pegoraro; Kyu Ha Lee; et al. (Nature Physics, 2018)
As an injury heals, an embryo develops or a carcinoma spreads, epithelial cells systematically change their shape. In each of these processes cell shape is studied extensively whereas variability of shape from cell to cell is regarded most often as biological noise. But where do cell shape and its variability come from? Here we report that cell shape and shape variability are mutually constrained through a relationship that is purely geometrical. That relationship is shown to govern processes as diverse as maturation of the pseudostratified bronchial epithelial layer cultured from non-asthmatic or asthmatic donors, and formation of the ventral furrow in the Drosophila embryo. Across these and other epithelial systems, shape variability collapses to a family of distributions that is common to all. That distribution, in turn, is accounted for by a mechanistic theory of cell–cell interaction, showing that cell shape becomes progressively less elongated and less variable as the layer becomes progressively more jammed. These findings suggest a connection between jamming and geometry that spans living organisms and inert jammed systems, and thus transcends system details. Although molecular events are needed for any complete theory of cell shape and cell packing, observations point to the hypothesis that jamming behaviour at larger scales of organization sets overriding geometric constraints.

Surfactant Variations in Porous Media Localize Capillary Instabilities during Haines Jumps - Yaniv Edery; Steffen Berg; David Weitz (Physical Review Letters, 2018)
We use confocal microscopy to measure velocity and interfacial tension between a trapped wetting phase with a surfactant and a flowing, invading nonwetting phase in a porous medium. We relate interfacial tension variations at the fluid-fluid interface to surfactant concentration and show that these variations localize the destabilization of capillary forces and lead to rapid local invasion of the nonwetting fluid, resulting in a Haines jump. These spatial variations in surfactant concentration are caused by velocity variations at the fluid-fluid interfaces and lead to localization of the Haines jumps even in otherwise very uniform pore structure and pressure conditions. Our results provide new insight into the nature of Haines jumps, one of the most ubiquitous and important instabilities in flow in porous media.

Gold nanorods conjugated porous silicon nanoparticles encapsulated in calcium alginate nano hydrogels using microemulsion templates - Zhang, Hongbo; Yueqi Zhu; Liangliang Qu; Huayin Wu; Haixin Kong; Zhou Yang; Chen, Dong; Mäkilä, Ermei; Salonen, Jarno; Hélder A. Santos; Hai, Mingtan; Weitz, DavidA. (Nano Letters, 2018)
Porous silicon nanoparticles (PSiNPs) and gold nanorods (AuNRs) can be used as biocompatible nanocarriers for delivery of therapeutics but undesired leakage makes them inefficient. By encapsulating the PSiNPs and AuNRs in a hydrogel shell, we create a biocompatible functional nanocarrier that enables sustained release of therapeutics. Here, we report the fabrication of AuNRs-conjugated PSi nanoparticles (AuNRsPSiNPs) through two-step chemical reaction for high-capacity loading of hydrophobic and hydrophilic therapeutics with photothermal property. Furthermore, using water-in-oil microemulsion templates, we encapsulate the AuNRsPSiNPs within a calcium alginate hydrogel nanoshell, creating a versatile biocompatible nanocarrier to codeliver therapeutics for biomedical applications. We find that the functionalized nanohydrogel effectively controls the release rate of the therapeutics while maintaining a high loading efficiency and tunable loading ratios. Notably, combinations of therapeutics coloaded in the functionalized nanohydrogels significantly enhance inhibition of multidrug resistance through synergism and promote faster cancer cell death when combined with photothermal therapy. Moreover, the AuNRs can mediate the conversion of near-infrared laser radiation into heat, increasing the release of therapeutics as well as thermally inducing cell damage to promote faster cancer cell death. Our AuNRsPSiNPs functionalized calcium alginate nanohydrogel holds great promise for photothermal combination therapy and other advanced biomedical applications.

Regularized lattice Boltzmann multicomponent models for low capillary and Reynolds microfluidics flows - Montessori, Andrea; Lauricella, Marco; La Rocca, Michele; Succi, Sauro; Stolovicki, Elad; Zibalt, Roy; David Weitz (Computers & Fluids, 2018)
We present a regularized version of the color gradient lattice Boltzmann (LB) scheme for the simulation of droplet formation in microfluidic devices of experimental relevance. The regularized version is shown to provide computationally efficient access to capillary number regimes relevant to droplet generation via microfluidic devices, such as flow-focusers and the more recent microfluidic step emulsifier devices.

Throughput enhancement of parallel step emulsifier devices by shear-free and efficient nozzle clearance - Stolovicki, Elad; Ziblat, Roy; Weitz, David A (Lab on a Chip, 2018)
Step emulsification is an attractive method for production of monodisperse drops. Its main advantage is the ability to parallelize many step emulsifier nozzles to achieve high production rates. However, step emulsification is sensitive to any obstructions at the nozzle exit. At high production rates, drops can accumulate at nozzle exits, disturb the formation of subsequent drops and impair monodispersity. As a result, parallelized step emulsifier devices typically do not work at maximum productivity. Here a design is introduced that parallelizes hundreds of step emulsifier nozzles, and effectively removes drops from the nozzle exits. The drop clearance is achieved by an open collecting channel, and is aided by buoyancy. Importantly, this clearance method avoids the use of a continuous phase flow for drop clearance and hence no shear is applied on the forming drops. The method works well for a wide range of drops, sizing from 30 to 1000 μm at production rates of 0.03 and 10 L per hour and achieved by 400 and 120 parallelized nozzles respectively.

Reply to the 'Comment on "Robust Scalable High Throughput Production of Monodisperse Drops - Amstad, E.; Weitz, DavidA. (Lab on a Chip, 2017)
This reply to the comment by Nakajima on our article that appeared in Lab on a Chip (E. Amstad, M. Chemama, M. Eggersdorfer, L. R. Arriaga, M. Brenner and D. A. Weitz, Lab Chip, 2016, 16, 4163–4172) highlights the differences between the microchannel step emulsification devices developed by the Nakajima group and the millipede device reported by us in Lab on a Chip.

Correction: Double-emulsion drops with ultra-thin shells for capsule templates - Kim, Shin-Hyun; Kim, Jin Woong; Cho, Jun-Cheol; Weitz, DavidA. (Lab on a Chip, 2017)
Correction for ‘Double-emulsion drops with ultra-thin shells for capsule templates’ by Shin-Hyun Kim et al., Lab Chip, 2011, 11, 3162–3166. In the section “Diameter and shell thickness of double-emulsion drops” there are errors in eqn (2) and in the sentence that begins “In the same fashion, we calculate the thickness of the middle layer of double-emulsion drops which are produced at each values of Q1/Q2 and plot the results in Fig. 3c”. The equation should be<a href="https://pubs.rsc.org/image/article/2017/lc/c6lc90129h/c6lc90129h-t1_hi-res.gif" name="ugt1" onclick="open(this.href, '_blank', 'toolbar=1,scrollbars=yes,resizable=1'); return false;" title="Select to open image in new window"> The sentence should read “In the same fashion, we calculate the thickness of the middle layer of double-emulsion drops which are produced at each values of Q2/Q1 and plot the results in Fig. 3c”. In the caption for Fig. 3c, “Relative thickness of shell to radius of the double-emulsion drops (t/R) as a function of Q1/Q2.” should read “Relative thickness of shell to radius of the double-emulsion drops (t/R) as a function of Q2/Q1.” In addition, the x-axis is incorrectly labelled with “Q1/Q2”. The x-axis should be “Q2/Q1”. A corrected version of Fig. 3c is shown.

Tracking the Structural Deformation of a Sheared Biopolymer Network - Jawerth, Louise M.; Weitz, DavidA. (Functional Analysis, Harmonic Analysis, and Image Processing: A Collection of Papers in Honor of Björn Jawerth, 2017)
Biopolymer networks provide mechanical integrity in many important environments in vivo ranging from the cytoskeleton within a cell to the structural support of cells themselves in tissues and tendons. Rheolog-ical studies have shown that they exhibit many unique material properties. Modelling these properties requires a precise knowledge of how the individual filaments in the network deform locally during a global deformation. Here, we present an image processing method to track the three-dimensional motion of a biopolymer network as a simple shear deformation is applied. We track the structure of the network from one shear position to the next by determining the displacement of each branch point using a cross-correlation. To illustrate the use of this algorithm, we apply it to a fluorescently labelled fibrin network.

Axial Confocal Tomography of Capillary-Contained Colloidal Structures - Liber, Shir R.; Indech, Ganit; van der Wee, Ernest B.; Butenko, Alexander V.; Kodger, Thomas E.; Lu, Peter J.; Schofield, Andrew B.; Weitz, DavidA.; van Blaaderen, Alfons; Sloutskin, Eli (Langmuir, 2017)
<span style='display: inline !important; float: none; background-color: transparent; color: rgb(0, 0, 0); font-family: "Helvetica","Arial",sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 500; letter-spacing: normal; line-height: 22.4px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px; word-wrap: break-word;'>Confocal microscopy is widely used for three-dimensional (3D) sample reconstructions. Arguably, the most significant challenge in such reconstructions is posed by the resolution along the optical axis being significantly lower than in the lateral directions. In addition, the imaging rate is lower along the optical axis in most confocal architectures, prohibiting reliable 3D reconstruction of dynamic samples. Here, we demonstrate a very simple, cheap, and generic method of multiangle microscopy, allowing high-resolution high-rate confocal slice collection to be carried out with capillary-contained colloidal samples in a wide range of slice orientations. This method, realizable with any common confocal architecture and recently implemented with macroscopic specimens enclosed in rotatable cylindrical capillaries, allows 3D reconstructions of colloidal structures to be verified by direct experiments and provides a solid testing ground for complex reconstruction algorithms. In this paper, we focus on the implementation of this method for dense nonrotatable colloidal samples, contained in complex-shaped capillaries. Additionally, we discuss strategies to minimize potential pitfalls of this method, such as the artificial appearance of chain-like particle structures.

Biocompatible Amphiphilic Hydrogel–Solid Dimer Particles as Colloidal Surfactants - Chen, Dong; Amstad, Esther; Zhao, Chun-Xia; Cai, Liheng; Fan, Jing; Chen, Qiushui; Hai, Mingtan; Koehler, Stephan; Zhang, Huidan; Liang, Fuxin; Yang, Zhenzhong; Weitz, DavidA. (ACS Nano, 2017)
<span style='display: inline !important; float: none; background-color: transparent; color: rgb(0, 0, 0); font-family: "Helvetica","Arial",sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 500; letter-spacing: normal; line-height: 22.4px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px; word-wrap: break-word;'>Emulsions of two immiscible liquids can slowly coalesce over time when stabilized by surfactant molecules. Pickering emulsions stabilized by colloidal particles can be much more stable. Here, we fabricate biocompatible amphiphilic dimer particles using a hydrogel, a strongly hydrophilic material, and achieve large contrast in the wetting properties of the two bulbs, resulting in enhanced stabilization of emulsions. We generate monodisperse single emulsions of alginate and shellac solution in oil using a flow-focusing microfluidics device. Shellac precipitates from water and forms a solid bulb at the periphery of the droplet when the emulsion is exposed to acid. Molecular interactions result in amphiphilic dimer particles that consist of two joined bulbs: one hydrogel bulb of alginate in water and the other hydrophobic bulb of shellac. Alginate in the hydrogel compartment can be cross-linked using calcium cations to obtain stable particles. Analogous to surfactant molecules at the interface, the resultant amphiphilic particles stand at the water/oil interface with the hydrogel bulb submerged in water and the hydrophobic bulb in oil and are thus able to stabilize both water-in-oil and oil-in-water emulsions, making these amphiphilic hydrogel–solid particles ideal colloidal surfactants for various applications.

Bioinspired graphene membrane with temperature tunable channels for water gating and molecular separation - Liu, Jingchong; Wang, Nıfmmode\ddotu\elseü\fi}; Yu, Li-Juan; Karton, Amir; Li, Wen; Zhang, Weixia; Guo, Fengyun; Hou, Lanlan; Cheng, Qunfeng; Jiang, Lei; Weitz, DavidA.; Zhao, Yong (Nat. Commun., 2017)
<span style="display: inline !important; float: none; background-color: transparent; color: rgb(34, 34, 34); font-family: Lora,Palatino,Times,Times New Roman,serif; font-size: 17px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: 0.17px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px; word-wrap: break-word;">Smart regulation of substance permeability through porous membranes is highly desirable for membrane applications. Inspired by the stomatal closure feature of plant leaves at relatively high temperature, here we report a nano-gating membrane with a negative temperature-response coefficient that is capable of tunable water gating and precise small molecule separation. The membrane is composed of poly(<i style="background-color: transparent; color: rgb(34, 34, 34); font-family: Lora,Palatino,Times,Times New Roman,serif; font-size: 17px; font-style: italic; font-variant: normal; font-weight: 400; letter-spacing: 0.17px; margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px; orphans: 2; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px; word-wrap: break-word;">N<span style="display: inline !important; float: none; background-color: transparent; color: rgb(34, 34, 34); font-family: Lora,Palatino,Times,Times New Roman,serif; font-size: 17px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: 0.17px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px; word-wrap: break-word;">-isopropylacrylamide) covalently bound to graphene oxide via free-radical polymerization. By virtue of the temperature tunable lamellar spaces of the graphene oxide nanosheets, the water permeance of the membrane could be reversibly regulated with a high gating ratio. Moreover, the space tunability endows the membrane with the capability of gradually separating multiple molecules of different sizes. This nano-gating membrane expands the scope of temperature-responsive membranes and has great potential applications in smart gating systems and molecular separation.

Cell volume change through water efflux impacts cell stiffness and stem cell fate - Guo, Ming; Adrian F. Pegoraro; Mao, Angelo; Zhou, Enhua H.; Arany, Praveen R.; Han, Yulong; Burnette, Dylan T.; Jensen, Mikkel H.; Kasza, Karen E.; Moore, Jeffrey R.; Mackintosh, Frederick C.; Jeffrey J. Fredberg; et al. (Proc. Natl. Acad. Sci. U.S.A., 2017)
<span style='display: inline !important; float: none; background-color: transparent; color: rgb(51, 51, 51); font-family: "Open Sans","HelveticaNeue","Helvetica Neue",Helvetica,Arial,sans-serif; font-size: 15px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;'>Cell volume is thought to be a well-controlled cellular characteristic, increasing as a cell grows, while macromolecular density is maintained. We report that cell volume can also change in response to external physical cues, leading to water influx/efflux, which causes significant changes in subcellular macromolecular density. This is observed when cells spread out on a substrate: Cells reduce their volume and increase their molecular crowding due to an accompanying water efflux. Exploring this phenomenon further, we removed water from mesenchymal stem cells through osmotic pressure and found this was sufficient to alter their differentiation pathway. Based on these results, we suggest cells chart different differentiation and behavioral pathways by sensing/altering their cytoplasmic volume and density through changes in water influx/efflux.

Controlled self-assembly of alginate microgels by rapidly binding molecule pairs - Hu, Yuebi; Mao, Angelo S.; Desai, Rajiv M.; Wang, Huanan; Weitz, DavidA.; Mooney, David J. (Lab Chip, 2017)
<span style="display: inline !important; float: none; background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 300; letter-spacing: -0.32px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Controlled self-assembly of cell-encapsulating microscale polymeric hydrogels (microgels) could be advantageous in a variety of tissue engineering and regenerative medicine applications. Here, a method of assembly by chemical modification of alginate polymer with binding pair molecules (BPM) was explored. Alginate was modified with several types of BPM, specifically biotin and streptavidin and click chemistry compounds, and fabricated into 25–30 μm microgels using a microfluidic platform. These microgels were demonstrated to self-assemble under physiological conditions. By combining complementary microgels at a high ratio, size-defined assemblages were created, and the effects of BPM type and assembly method on the number of microgels per assemblage and packing density were determined. Furthermore, a magnetic process was developed to separate assemblages from single microgels, and allow formation of multilayer spheroids. Finally, cells were singly encapsulated into alginate microgels and assembled using BPM-modified alginate, suggesting potential applications in regenerative medicine.

Deterministic encapsulation of single cells in thin tunable microgels for niche modelling and therapeutic delivery - Mao, Angelo S.; Shin, Jae-Won; Utech, Stefanie; Wang, Huanan; Uzun, Oktay; Li, Weiwei; Cooper, Madeline; Hu, Yuebi; Zhang, Liyuan; Weitz, DavidA.; Mooney, David J. (Nat. Mater., 2017)
<section aria-labelledby="Abs2" data-gtm-vis-first-on-screen-10482319_393="965" data-gtm-vis-first-on-screen-10482319_401="977" data-gtm-vis-has-fired-10482319_393="1" data-gtm-vis-has-fired-10482319_401="1" data-gtm-vis-total-visible-time-10482319_393="10000" data-gtm-vis-total-visible-time-10482319_401="10000" data-title="Abstract" lang="en"> Existing techniques to encapsulate cells into microscale hydrogels generally yield high polymer-to-cell ratios and lack control over the hydrogel’s mechanical properties<a aria-label="Reference 1" data-test="citation-ref" data-track="click" data-track-action="reference anchor" data-track-label="link" href="https://www.nature.com/articles/nmat4781#ref-CR1" id="ref-link-section-d46608e473" title="Selimovic, S., Oh, J., Bae, H., Dokmeci, M. & Khademhosseini, A. Microscale strategies for generating cell-encapsulating hydrogels. Polymers 4, 1554 (2012).">1. Here, we report a microfluidic-based method for encapsulating single cells in an approximately six-micrometre layer of alginate that increases the proportion of cell-containing microgels by a factor of ten, with encapsulation efficiencies over 90%. We show that in vitro cell viability was maintained over a three-day period, that the microgels are mechanically tractable, and that, for microscale cell assemblages of encapsulated marrow stromal cells cultured in microwells, osteogenic differentiation of encapsulated cells depends on gel stiffness and cell density. We also show that intravenous injection of singly encapsulated marrow stromal cells into mice delays clearance kinetics and sustains donor-derived soluble factors in vivo. The encapsulation of single cells in tunable hydrogels should find use in a variety of tissue engineering and regenerative medicine applications.

Dispersing hydrophobic natural colourant β-carotene in shellac particles for enhanced stability and tunable colour - Chen, Dong; Zhao, Chun-Xia; Lagoin, Camille; Hai, Mingtan; Arriaga, Laura R.; Koehler, Stephan; Abbaspourrad, Alireza; Weitz, DavidA. (R. Soc. Open Sci., 2017)
<span style="display: inline !important; float: none; background-color: transparent; color: rgb(0, 0, 0); font-family: "Times New Roman",stixgeneral,serif; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Colour is one of the most important visual attributes of food and is directly related to the perception of food quality. The interest in natural colourants, especially β-carotene that not only imparts colour but also has well-documented health benefits, has triggered the research and development of different protocols designed to entrap these hydrophobic natural molecules to improve their stability against oxidation. Here, we report a versatile microfluidic approach that uses single emulsion droplets as templates to prepare microparticles loaded with natural colourants. The solution of β-carotene and shellac in the solvent is emulsified by microfluidics into droplets. Upon solvent diffusion, β-carotene and shellac co-precipitates, forming solid microparticles of β-carotene dispersed in the shellac polymer matrix. We substantially improve the stability of β-carotene that is protected from oxidation by the polymer matrix and achieve different colour appearances by loading particles with different β-carotene concentrations. These particles demonstrate great promise for practical use in natural food colouring.

Drying regimes in homogeneous porous media from macro- to nanoscale - Thiery, J.; Rodts, S.; Weitz, D. A.; Coussot, P. (Phys. Rev. Fluids, 2017)
<span style="display: inline !important; float: none; background-color: transparent; color: rgb(34, 34, 34); font-family: "Helvetica Neue",Helvetica,Roboto,Arial,sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; line-height: 22.4px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Magnetic resonance imaging visualization down to nanometric liquid films in model porous media with pore sizes from micro- to nanometers enables one to fully characterize the physical mechanisms of drying. For pore size larger than a few tens of nanometers, we identify an initial constant drying rate period, probing homogeneous desaturation, followed by a falling drying rate period. This second period is associated with the development of a gradient in saturation underneath the sample free surface that initiates the inward recession of the contact line. During this latter stage, the drying rate varies in accordance with vapor diffusion through the dry porous region, possibly affected by the Knudsen effect for small pore size. However, we show that for sufficiently small pore size and/or saturation the drying rate is increasingly reduced by the Kelvin effect. Subsequently, we demonstrate that this effect governs the kinetics of evaporation in nanopores as a homogeneous desaturation occurs. Eventually, under our experimental conditions, we show that the saturation unceasingly decreases in a homogeneous manner throughout the wet regions of the medium regardless of pore size or drying regime considered. This finding suggests the existence of continuous liquid flow towards the interface of higher evaporation, down to very low saturation or very small pore size. Paradoxically, even if this net flow is unidirectional and capillary driven, it corresponds to a series of diffused local capillary equilibrations over the full height of the sample, which might explain that a simple Darcy's law model does not predict the effect of scaling of the net flow rate on the pore size observed in our tests.

Massively parallel single-nucleus RNA-seq with DroNc-seq - Habib, Naomi; Avraham-Davidi, Inbal; Anindita Basu; Burks, Tyler; Karthik Shekhar; Hofree, Matan; Choudhury, Sourav R.; Aguet, Francois; Gelfand, Ellen; Ardlie, Kristin; Weitz, DavidA.; Rozenblatt-Rosen, Orit; et al. (Nat. Methods, 2017)
<span style="display: inline !important; float: none; background-color: transparent; color: rgb(34, 34, 34); font-family: Lora,Palatino,Times,Times New Roman,serif; font-size: 17px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: 0.17px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px; word-wrap: break-word;">Single-nucleus RNA sequencing (sNuc-seq) profiles RNA from tissues that are preserved or cannot be dissociated, but it does not provide high throughput. Here, we develop DroNc-seq: massively parallel sNuc-seq with droplet technology. We profile 39,111 nuclei from mouse and human archived brain samples to demonstrate sensitive, efficient, and unbiased classification of cell types, paving the way for systematic charting of cell atlases.

Multistage Transformation and Lattice Fluctuation at AgCl–Ag Interface - Du, Jingshan S.; Park, Jungwon; Kim, QHwan; Jhe, Wonho; Dravid, Vinayak P.; Yang, Deren; Weitz, DavidA. (J. Phys. Chem. Lett., 2017)
<span style='display: inline !important; float: none; background-color: transparent; color: rgb(0, 0, 0); font-family: "Helvetica","Arial",sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 500; letter-spacing: normal; line-height: 22.4px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px; word-wrap: break-word;'>Solid-state transformation between different materials is often accompanied by mechanical expansion and compression due to their volume change and structural evolution at interfaces. However, these two types of dynamics are usually difficult to monitor in the same time. In this work, we use in situ transmission electron microscopy to directly study the reduction transformation at the AgCl–Ag interface. Three stages of lattice fluctuations were identified and correlated to the structural evolution. During the steady state, a quasi-layered growth mode of Ag in both vertical and lateral directions were observed due to the confinement of AgCl lattices. The development of planar defects and depletion of AgCl are respectively associated with lattice compression and relaxation. Topography and structure of decomposing AgCl was further monitored by in situ scanning transmission electron microscopy. Silver species are suggested to originate from both the surface and the interior of AgCl, and be transported to the interface. Such mass transport may have enabled the steady state and lattice compression in this volume-shrinking transformation.

Optically reconfigurable chiral microspheres of self-organized helical superstructures with handedness inversion - Wang, Ling; Chen, Dong; Gutierrez-Cuevas, Karla G.; Bisoyi, Hari Krishna; Fan, Jing; Zola, Rafael S.; Li, Guoqiang; Urbas, Augustine M.; Bunning, Timothy J.; Weitz, DavidA.; Li, Quan (Mater. Horiz., 2017)
<span style="display: inline !important; float: none; background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 300; letter-spacing: -0.32px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Optically reconfigurable monodisperse chiral microspheres of self-organized helical superstructures with dynamic chirality were fabricated <em style="background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: italic; font-variant: normal; font-weight: 300; height: auto; letter-spacing: -0.32px; line-height: 24px; margin-bottom: 0px; margin-left: 0px; margin-right: 0px; margin-top: 0px; orphans: 2; padding-bottom: 0px; padding-left: 0px; padding-right: 0px; padding-top: 0px; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">via<span style="display: inline !important; float: none; background-color: transparent; color: rgba(0, 0, 0, 0.79); font-family: museo_sans300,museo-sans; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 300; letter-spacing: -0.32px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;"> a capillary-based microfluidic technique. Light-driven handedness-invertible transformations between different configurations of microspheres were vividly observed and optically tunable RGB photonic cross-communications among the microspheres were demonstrated.

Perspective on droplet-based single-cell sequencing - Weitz, DavidA. (Lab Chip, 2017)

Polymer Phase Separation in a Microcapsule Shell - Shi, Weichao; Weitz, DavidA. (Macromolecules, 2017)
<span style='display: inline !important; float: none; background-color: transparent; color: rgb(0, 0, 0); font-family: "Helvetica","Arial",sans-serif; font-size: 14px; font-style: normal; font-variant: normal; font-weight: 500; letter-spacing: normal; line-height: 22.4px; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px; word-wrap: break-word;'>Phase separation has been used for engineering microscale fluids and particles with designed structures. But it is challenging to use phase separation to create complicated microcapsules because phase separation in the shell correlates with applied osmotic pressure and affects capsule stability significantly. Here we employ two biodegradable polymers to study the phase separation in microcapsule shells and its effect on the mechanical stability. The dynamic process reveals that phase separation creates a patchy shell with distinct regions transiently, then transports the discrete domains across the shell, and coalesces them at the surface. The equilibrium structure with balanced osmotic pressure is a Janus shell, where one component forms the shell and the other component dewets on the surface. Under slight osmotic pressure to the shell, phase separation reaches a different Janus shape, which consists of two partial shells of each component. We can in further take advantage of phase separation and osmotic pressure to rupture microcapsules at specific locations. Phase separation in the shell provides a facile approach to create versatile capsule structures and affords a reliable strategy to harness the shell mechanics.

Robust mechanobiological behavior emerges in heterogeneous myosin systems - Egan, Paul F.; Moore, Jeffrey R.; Ehrlicher, Allen J.; Weitz, DavidA.; Schunn, Christian; Cagan, Jonathan; LeDuc, Philip (Proc. Natl. Acad. Sci. U.S.A., 2017)
<span style="display: inline !important; float: none; background-color: transparent; color: rgb(51, 51, 51); font-family: "Open Sans","HelveticaNeue","Helvetica Neue",Helvetica,Arial,sans-serif; font-size: 15px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">Biological complexity presents challenges for understanding natural phenomenon and engineering new technologies, particularly in systems with molecular heterogeneity. Such complexity is present in myosin motor protein systems, and computational modeling is essential for determining how collective myosin interactions produce emergent system behavior. We develop a computational approach for altering myosin isoform parameters and their collective organization, and support predictions with in vitro experiments of motility assays with α-actinins as molecular force sensors. The computational approach models variations in single myosin molecular structure, system organization, and force stimuli to predict system behavior for filament velocity, energy consumption, and robustness. Robustness is the range of forces where a filament is expected to have continuous velocity and depends on used myosin system energy. Myosin systems are shown to have highly nonlinear behavior across force conditions that may be exploited at a systems level by combining slow and fast myosin isoforms heterogeneously. Results suggest some heterogeneous systems have lower energy use near stall conditions and greater energy consumption when unloaded, therefore promoting robustness. These heterogeneous system capabilities are unique in comparison with homogenous systems and potentially advantageous for high performance bionanotechnologies. Findings open doors at the intersections of mechanics and biology, particularly for understanding and treating myosin-related diseases and developing approaches for motor molecule-based technologies.

Local Pore Size Correlations Determine Flow Distributions in Porous Media - Alim, Karen; Parsa, Shima; Weitz, David A; Michael P. Brenner (Physical Review Letters, 2017)
The relationship between the microstructure of a porous medium and the observed flow distribution is still a puzzle. We resolve it with an analytical model, where the local correlations between adjacent pores, which determine the distribution of flows propagated from one pore downstream, predict the flow distribution. Numerical simulations of a two-dimensional porous medium verify the model and clearly show the transition of flow distributions from δ-function-like via Gaussians to exponential with increasing disorder. Comparison to experimental data further verifies our numerical approach.

Fabrication of Calcium Phosphate-Based Nanocomposites Incorporating DNA Origami, Gold Nanorods, and Anticancer drugs for Biomedical Applications - Zhang, Hongbo; Qu, Xiangmeng; Chen, Hong; Haixin Kong; Ding, Ruihua; Chen, Dong; Zhang, Xu; Hao Pei; Hélder A. Santos; Hai, Mingtan; Weitz, DavidA. (Advanced Healthcare Materials, 2017)
DNA origami is designed by folding DNA strands at the nanoscale with arbitrary control. Due to its inherent biological nature, DNA origami is used in drug delivery for enhancement of synergism and multidrug resistance inhibition, cancer diagnosis, and many other biomedical applications, where it shows great potential. However, the inherent instability and low payload capacity of DNA origami restrict its biomedical applications. Here, this paper reports the fabrication of an advanced biocompatible nano‐in‐nanocomposite, which protects DNA origami from degradation and facilities drug loading. The DNA origami, gold nanorods, and molecular targeted drugs are co‐incorporated into pH responsive calcium phosphate [Ca3(PO4)2] nanoparticles. Subsequently, a thin layer of phospholipid is coated onto the Ca3(PO4)2 nanoparticle to offer better biocompatibility. The fabricated nanocomposite shows high drug loading capacity, good biocompatibility, and a photothermal and pH‐responsive payload release profile and it fully protects DNA origami from degradation. The codelivery of DNA origami with cancer drugs synergistically induces cancer cell apoptosis, reduces the multidrug resistance, and enhances the targeted killing efficiency toward human epidermal growth factor receptor 2 positive cells. This nanocomposite is foreseen to open new horizons for a variety of clinical and biomedical applications.

Tough Self-Healing Elastomers by Molecular Enforced Integration of Covalent and Reversible Networks - Wu, Jinrong; Cai, Li-Heng; Weitz, DavidA. (Advanced Materials, 2017)
Self‐healing polymers crosslinked by solely reversible bonds are intrinsically weaker than common covalently crosslinked networks. Introducing covalent crosslinks into a reversible network would improve mechanical strength. It is challenging, however, to apply this concept to “dry” elastomers, largely because reversible crosslinks such as hydrogen bonds are often polar motifs, whereas covalent crosslinks are nonpolar motifs. These two types of bonds are intrinsically immiscible without cosolvents. Here, we design and fabricate a hybrid polymer network by crosslinking randomly branched polymers carrying motifs that can form both reversible hydrogen bonds and permanent covalent crosslinks. The randomly branched polymer links such two types of bonds and forces them to mix on the molecular level without cosolvents. This enables a hybrid “dry” elastomer that is very tough with fracture energy 13500 Jm−2 comparable to that of natural rubber. Moreover, the elastomer can self‐heal at room temperature with a recovered tensile strength 4 MPa, which is 30% of its original value, yet comparable to the pristine strength of existing self‐healing polymers. The concept of forcing covalent and reversible bonds to mix at molecular scale to create a homogenous network is quite general and should enable development of tough, self‐healing polymers of practical usage.
Keywords: elastomers; molecular design; self-healing; supramolecular; tough

Mechanical Properties of the Cytoskeleton and Cells - Adrian F. Pegoraro; Paul Janmey; Weitz, DavidA. (Cold Spring Harbor-Perspectives in Biology, 2017)
The cytoskeleton is the major mechanical structure of the cell; it is a complex, dynamic biopolymer network comprising microtubules, actin, and intermediate filaments. Both the individual filaments and the entire network are not simple elastic solids but are instead highly nonlinear structures. Appreciating the mechanics of biopolymer networks is key to under- standing the mechanics of cells. Here, we review the mechanical properties of cytoskeletal polymers and discuss the implications for the behavior of cells.

Enhanced Surface Acoustic Wave Cell Sorting by 3D Microfluidic-Chip Design - Ung, W. Lloyd; Kirk Mutafopulos; Pascal Spink; R. W. Rambach; Franke, Thomas; Weitz, DavidA. (Lab on a Chip, 2017)
We demonstrate an acoustic wave driven microfluidic cell sorter that combines advantages of multilayer device fabrication with planar surface acoustic wave excitation. We harness the strong vertical component of the refracted acoustic wave to enhance cell actuation by using an asymmetric flow field to increase cell deflection. Precise control of the 3-dimensional flow is realized by topographical structures implemented on the top of the microchannel. We experimentally quantify the effect of the structure dimensions and acoustic parameter. The design attains cell sorting rates and purities approaching those of state of the art fluorescence-activated cell sorters with all the advantages of microfluidic cell sorting.

Triple Junction at the Triple Point Resolved on the Individual Particle Level - Chaudhuri, M.; Allahyarov, E.; Löwen, H.; Egelhaaf, S. U.; Weitz, D. A. (Phys. Rev. Lett., 2017)
At the triple point of a repulsive screened Coulomb system, a fcc crystal, a bcc crystal, and a fluid phase coexist. At their intersection, these three phases form a liquid groove, the triple junction. Using confocal microscopy, we resolve the triple junction on a single-particle level in a model system of charged PMMA colloids in a nonpolar solvent. The groove is found to be extremely deep and the incommensurate solid-solid interface to be very broad. Thermal fluctuations hence appear to dominate the solid-solid interface. This indicates a very low interfacial energy. The fcc-bcc interfacial energy is quantitatively determined based on Young’s equation and, indeed, it is only about 1.3 times higher than the fcc-fluid interfacial energy close to the triple point.

Controlled Generation of Ultrathin-Shell Double Emulsions and Studies on Their Stability - Zhao, Chun-Xia; Chen, Dong; Hui, Yue; Weitz, David A; Middelberg, Anton PJ (ChemPhysChem, 2017)
Double emulsions with a hierarchical core-shell structure have great potential in various applications, but their broad use is limited by their instability. To improve stability, water-in-oil-in-water (W/O/W) emulsions with an ultrathin oil layer of several hundred nanometres were produced by using a microcapillary device. The effects of various parameters on the generation of ultrathin-shell double emulsions and their droplet size were investigated, including the proper combinations of inner, middle and outer phases, flow rates and surfactants. The surfactant in the middle oil phase was found to be critical for the formation of the ultrathin-shell double emulsions. Furthermore, the stability of these double emulsions can be notably improved by increasing the concentration of the surfactant, and they can be stable for months. This opens up new opportunities for their future applications in cosmetics, foods and pharmaceuticals.

Physical limits to biomechanical sensing in disordered fibre networks. - Beroz, Farzan; Jawerth, Louise M.; Münster, Stefan; Weitz, David A; Broedersz, Chase P.; Wingreen, Ned S (Nature communications, 2017)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="1288" data-gtm-vis-first-on-screen-10482319_401="1288" data-gtm-vis-has-fired-10482319_393="1" data-gtm-vis-has-fired-10482319_401="1" data-gtm-vis-total-visible-time-10482319_393="10000" data-gtm-vis-total-visible-time-10482319_401="10000" data-title="Abstract" lang="en"> Cells actively probe and respond to the stiffness of their surroundings. Since mechanosensory cells in connective tissue are surrounded by a disordered network of biopolymers, their in vivo mechanical environment can be extremely heterogeneous. Here we investigate how this heterogeneity impacts mechanosensing by modelling the cell as an idealized local stiffness sensor inside a disordered fibre network. For all types of networks we study, including experimentally-imaged collagen and fibrin architectures, we find that measurements applied at different points yield a strikingly broad range of local stiffnesses, spanning roughly two decades. We verify via simulations and scaling arguments that this broad range of local stiffnesses is a generic property of disordered fibre networks. Finally, we show that to obtain optimal, reliable estimates of global tissue stiffness, a cell must adjust its size, shape, and position to integrate multiple stiffness measurements over extended regions of space.

Biocompatible microcapsules with a water core templated from single emulsions - Kong, Linlin; Amstad, Esther; Hai, Mingtan; Ke, Xinyou; Chen, Dong; Zhao, Chun-Xia; Weitz, David A (Chinese Chemical Letters, 2017)
Biocompatible microcapsules with a water core are widely used to encapsulate hydrophilic actives. Here, a facile method to fabricate monodisperse biocompatible microcapsules with a water core in large quantity is reported. Microfluidic technology is utilized to emulsify the inner aqueous phase containing the shell polymer into monodisperse drops in the outer oil phase. As the cosolvent in the inner aqueous phase diffuses into the outer oil phase, the solubility of the shell polymer decreases, which eventually precipitates. Since the shell polymer, shellac, contains both hydrophilic and hydrophobic groups, it tends to wet both the inner aqueous phase and the outer oil phase, thus forming a solid shell at the periphery of the drop. We show that the diffusion rate of hydrophilic molecules encapsulated in the water core decreases as their molecular weight increases and the property of the microcapsules could further be modified by polyelectrolyte multilayer coating. These microcapsules are fabricated using FDA-approved polymer and non-toxic solvents and are of great use in drugs, cosmetics and foods.

Creation of Faceted Polyhedral Microgels from Compressed Emulsions - Fan, Jing; Kim, Shin-Hyun; Chen, Zi; Zhou, Shaobing; Amstad, Esther; Lin, Tina; Weitz, David A (Small, 2017)
Compressed monodisperse emulsions in confined space exhibit highly ordered structures. The influence of the volume fraction and the confinement geometry on the organized structures is investigated and the mechanism by which structural transition occurs is studied. Based on the understanding of ordering behavior of compressed emulsions, a simple and high‐throughput method to fabricate monodisperse polyhedral microgels using the emulsions as the template is developed. By controlling the geometry of the confined spaces, a variety of shapes such as hexagonal prism, Fejes Toth honeycomb prism, truncated octahedron, pyritohedron, and truncated hexagonal trapezohedron are implemented. Moreover, the edge sharpness of each shape is controllable by adjusting the drop volume fraction. This design principle can be readily extended to other shapes and materials, and therefore provides a useful means to create polyhedral microparticles for both fundamental study and practical applications.

Osmotic Pressure Triggered Rapid Release of Encapsulated Enzymes with Enhanced Activity - Zhang, Weixia; Abbaspourrad, Alireza; Chen, Dong; Campbell, Elizabeth; Zhao, Hong; Li, Yiwei; Li, Qingning; Weitz, David A (Advanced Functional Materials, 2017)
In this study, a single‐step microfluidic approach is reported for encapsulation of enzymes within microcapsules with ultrathin polymeric shell for controlled release triggered by an osmotic shock. Using a glass capillary microfluidic device, monodisperse water‐in‐oil‐in‐water double emulsion droplets are fabricated with enzymes in the core and an ultrathin middle oil layer that solidifies to produce a consolidated inert polymeric shell with a thickness of a few tens to hundreds of nanometers. Through careful design of microcapsule membranes, a high percentage of cargo release, over 90%, is achieved, which is triggered by osmotic shock when using poly(methyl methacrylate) as the shell material. Moreover, it is demonstrated that compared to free enzymes, the encapsulated enzyme activity is maintained well for as long as 47 days at room temperature. This study not only extends industrial applications of enzymes, but also offers new opportunities for encapsulation of a wide range of sensitive molecules and biomolecules that can be controllably released upon applying osmotic shock.

Parallelization of microfluidic flow-focusing devices - Amstad, Esther; Chen, Xiaoming; Eggersdorfer, Max; Cohen, Noa; Kodger, Thomas E.; Ren, Carolyn L; Weitz, David A (Physical Review E, 2017)
Microfluidic flow-focusing devices offer excellent control over fluid flow, enabling formation of drops with a narrow size distribution. However, the throughput of microfluidic flow-focusing devices is limited and scale-up through operation of multiple drop makers in parallel often compromises the robustness of their operation. We demonstrate that parallelization is facilitated if the outer phase is injected from the direction opposite to that of the inner phase, because the fluid injection flow rate, where the drop formation transitions from the squeezing into the dripping regime, is shifted towards higher values.

Stable, fluorescent PMMA particles for long-term observation of slow colloidal dynamics - Kodger, Thomas Edward; Lu, Peter James; Wiseman, Gregory Reid; Weitz, David A (Langmuir, 2017)
Suspensions of solid micron-scale colloidal particles in liquid solvents are a foundational model system used to explore a wide range of phase transitions, including crystallization, gelation, spinodal decomposition, and the glass transition. One of the most commonly used systems for these investigations is the fluorescent spherical particles of polymethylmethacrylate (PMMA) suspended in a mixture of nonpolar solvents that match the density and the refractive index of the particles to minimize sedimentation and scattering. However, the particles can swell in these solvents, changing their size and density, and may leak the fluorescent dye over days to weeks; this constrains the exploration of slow and kinetically limited processes, such as near-boundary phase separation or the glass transition. In this paper, we produce PMMA colloidal particles that employ polymerizable and photostable cyanine-based fluorescent monomers spanning the range of visible wavelengths and a polymeric stabilizer prepared from polydimethylsiloxane, PDMS-graft-PMMA. Using microcalorimetry, we characterize the thermodynamics of an accelerated equilibration process for these dispersions in the buoyancy- and refractive-index-matching solvents. We use confocal differential dynamic microscopy to demonstrate that they behave as hard spheres. The suspended particles are stable for months to years, maintaining fixed particle size and density, and do not leak dye. Thus, these particles enable longer term experiments than may have been possible earlier; we demonstrate this by observing spinodal decomposition in a mixture of these particles with a depletant polymer in the microgravity environment of the International Space Station. Using fluorescence microscopy, we observe coarsening over several months and measure the growth of the characteristic length scale to be a fraction of a picometer per second; this rate is among the slowest observed in a phase-separating system. Our protocols should facilitate the synthesis of a variety of particles.

Efficient extraction of oil from droplet microfluidic emulsions - J. R. Haliburton; S. C. Kim; I. C. Clark; Sperling, R. A.; Weitz, D. A.; A. R. Abate (Biomicrofluidics, 2017)
Droplet microfluidic techniques can perform large numbers of single molecule and cell reactions but often require controlled, periodic flow to merge, split, and sort droplets. Here, we describe a simple method to convert aperiodic flows into periodic ones. Using an oil extraction module, we efficiently remove oil from emulsions to readjust the droplet volume fraction, velocity, and packing, producing periodic flows. The extractor acts as a universal adaptor to connect microfluidic modules that do not operate under identical flow conditions, such as droplet generators, incubators, and merger devices.

Scaling by shrinking: empowering single-cell'omics' with microfluidic devices - Prakadan, Sanjay M; Shalek, Alex K; Weitz, David A (Nature Reviews Genetics, 2017)
<section aria-labelledby="Abs3" data-gtm-vis-first-on-screen-10482319_393="25793" data-gtm-vis-first-on-screen-10482319_401="25793" data-gtm-vis-polling-id-10482319_393="842" data-gtm-vis-polling-id-10482319_401="843" data-gtm-vis-recent-on-screen-10482319_393="25793" data-gtm-vis-recent-on-screen-10482319_401="25793" data-gtm-vis-total-visible-time-10482319_393="1400" data-gtm-vis-total-visible-time-10482319_401="1400" data-title="Abstract" lang="en"> Recent advances in cellular profiling have demonstrated substantial heterogeneity in the behaviour of cells once deemed 'identical', challenging fundamental notions of cell 'type' and 'state'. Not surprisingly, these findings have elicited substantial interest in deeply characterizing the diversity, interrelationships and plasticity among cellular phenotypes. To explore these questions, experimental platforms are needed that can extensively and controllably profile many individual cells. Here, microfluidic structures — whether valve-, droplet- or nanowell-based — have an important role because they can facilitate easy capture and processing of single cells and their components, reducing labour and costs relative to conventional plate-based methods while also improving consistency. In this article, we review the current state-of-the-art methodologies with respect to microfluidics for mammalian single-cell 'omics' and discuss challenges and future opportunities.

Ultrafast Nanofiltration through Large-Area Single-layered Graphene Membranes - Qin, Yanzhe; Hu, Yongyou; Koehler, Stephan A.; Cai, Liheng; Wen, Junjie; Tan, Xiaojun; Xu, Weiwei L; Sheng, Qian; Hou, Xu; Xue, Jianming; others (ACS Applied Materials & Interfaces, 2017)
Perforated single-layered graphene has demonstrated selectivity and flux that is orders of magnitude greater than state-of-the-art polymer membranes. However, only individual graphene sheets with sizes up to tens of micrometers have been successfully fabricated for pressurized permeation studies. Scaling-up and reinforcement of these atomic membranes with minimum cracks and pinholes remains a major hurdle for practical applications. We develop a large-area in situ, phase-inversion casting technique to create 63 cm2 high-quality single-layered perforated graphene membranes for ultrafast nanofiltration that can operate at pressures up to 50 bar. This result demonstrates the feasibility of our technique for creating robust large-area, high quality, single-layered graphene and its potential use as a pressurized nanofiltration membrane.

Preparation of microparticles through co-flowing of partially miscible liquids - He, Yinghe; Battat, Sarah; Fan, Jing; Abbaspourrad, Alireza; Weitz, David A (Chemical Engineering Journal, 2017)
Monodisperse microparticles find applications in a wide range of areas. Generation of such particles of several microns in size at a large scale is a difficult task. This paper reports a proof of concept using a microfluidic device that coaxially flows partially miscible liquids for the production of microparticles. The approach makes use of both the physical forces of the process and the chemical properties of the liquid systems that allows for careful control of the mixing and droplet formation processes. Initial results show that, with this approach, particles with a reasonably narrow size distribution can be produced and liquid miscibility can be used as an additional avenue to manipulate the mean particle size and morphology.

Rapid Production of Submicron Drug Substance Particles by Supersonic Spray Drying - Eggersdorfer, Maximilian L; Koren, Vitaly; Stolovicki, Elad; Amstad, Esther; Weitz, David A (Crystal Growth & Design, 2017)
Many newly developed active pharmaceutical ingredients (APIs) are poorly soluble in water and thus have a dissolution-limited bioavailability. The bioavailability of Biopharmaceutical Classification System (BCS) class II APIs increases if they dissolve faster; this can be achieved by increasing their surface-to-volume ratio, for example, through formulation as submicron particles. In this paper, we develop a supersonic spray dryer that enables rapid synthesis of submicron-sized APIs at room temperature. Dispersing gas is accelerated to supersonic velocities in the divergent portion of a de Laval nozzle. The API solution is directly injected in the divergent portion and fully nebulized by impinging high velocity gas and pressure gradients across shocks at the exit of the nozzle. In such a device, we produce crystalline danazol particles with a Sauter mean diameter as small as 188 nm at a production rate up to 200 mg/h. The smallest particles with the narrowest size distributions are formed in overexpanded flows with a shock front close to the nozzle exit. Moreover, we demonstrate the scalability up to 1500 mg/h by increasing the danazol solution concentration; in this case, the Sauter mean diameter of the spray-dried particles increases to 772 nm.

An Intestinal Organ Culture System Uncovers a Role for the Nervous System in Microbe-Immune Crosstalk - Yissachar, Nissan; Zhou, Yan; Ung, Lloyd; Lai, Nicole Y; Mohan, James F; Ehrlicher, Allen; Weitz, David A; Kasper, Dennis L; Chiu, Isaac M; Mathis, Diane; others (Cell, 2017)
Investigation of host-environment interactions in the gut would benefit from a culture system that maintained tissue architecture yet allowed tight experimental control. We devised a microfabricated organ culture system that viably preserves the normal multicellular composition of the mouse intestine, with luminal flow to control perturbations (e.g., microbes, drugs). It enables studying short-term responses of diverse gut components (immune, neuronal, etc.). We focused on the early response to bacteria that induce either Th17 or RORg+ T-regulatory (Treg) cells in vivo. Transcriptional responses partially reproduced in vivo signatures, but these microbes elicited diametrically opposite changes in expression of a neuronal-specific gene set, notably nociceptive neuropeptides. We demonstrated activation of sensory neurons by microbes, correlating with RORg+ Treg induction. Colonic RORg+ Treg frequencies increased in mice lacking TAC1 neuropeptide precursor and decreased in capsaicin-diet fed mice. Thus, differential engagement of the enteric nervous system may partake in bifurcating pro- or anti-inflammatory responses to microbes.

Convection Driven Pull-Down Assays in Nanoliter Droplets using Scaffolded Aptamers - Qu, Xiangmeng; Zhang, Hongbo; Chen, Hong; Aldalbahi, Ali; Li, Li; Tian, Yang; Weitz, David A; Hao Pei (Analytical Chemistry, 2017)
One of the great challenges in cellular studies is to develop a rapid and biocompatible analytical tool for single-cell analysis. We report a rapid, DNA nanostructure-supported aptamer pull-down (DNaPull) assay under convective flux in a glass capillary for analyzing the contents of droplets with nano- or picoliter volumes. We have demonstrated that the scaffolded aptamer can greatly improve the efficiency of target molecules’ pull down. The convective flux allows complete reaction in <5 min, which is an 18-fold improvement compared to purely diffusive flux (traditional model of the stationary case). This established DNaPull assay can serve as a rapid and sensitive analytical platform for analyzing a variety of bioactive molecules, including small molecules [ATP, limit of detecton (LOD) of 1 μM], a drug (cocaine, LOD of 1 μM), and a biomarker (thrombin, LOD of 0.1 nM). Significantly, the designed microfluidic device compartmentalizes live cells into nanoliter-sized droplets to present single-cell samples. As a proof of concept, we demonstrated that cellular molecules (ATP) from a discrete number of HNE1 cells (zero to five cells) lysed inside nanoliter-sized droplets can be analyzed using our DNaPull assay, in which the intracellular ATP level was estimated to be ∼3.4 mM. Given the rapid assay feature and single-cell sample analysis ability, we believe that our analytical platform of convection-driven DNaPull in a glass capillary can provide a new paradigm in biosensor design and will be valuable for single-cell analysis.

Direct Observation of Entropic Stabilization of bcc Crystals Near Melting - Sprakel, Joris; Zaccone, Alessio; Spaepen, Frans; Schall, Peter; Weitz, David A (Physical Review Letters, 2017)
Crystals with low latent heat are predicted to melt from an entropically stabilized body-centered cubic symmetry. At this weakly first-order transition, strongly correlated fluctuations are expected to emerge, which could change the nature of the transition. Here we show how large fluctuations stabilize bcc crystals formed from charged colloids, giving rise to strongly power-law correlated heterogeneous dynamics. Moreover, we find that significant nonaffine particle displacements lead to a vanishing of the nonaffine shear modulus at the transition. We interpret these observations by reformulating the Born-Huang theory to account for nonaffinity, illustrating a scenario of ordered solids reaching a state where classical lattice dynamics fail.

Functional Microcapsules via Thiol- Ene Photopolymerization in Droplet-Based Microfluidics - Amato, Douglas V; Hyomin Lee; Werner, Jörg G; Weitz, David A; Patton, Derek L (ACS applied materials & interfaces, 2017)
Thiol–ene chemistry was exploited in droplet-based microfluidics to fabricate advanced microcapsules with tunable encapsulation, degradation, and thermal properties. In addition, by utilizing the thiol–ene photopolymerization with tunable cross-link density, we demonstrate the importance of monomer conversion on the retention of omniphilic cargo in double emulsion templated microcapsules. Furthermore, we highlight the rapid cure kinetics afforded by thiol–ene chemistry in a continuous flow photopatterning device for hemispherical microparticle production.

An RNA-based signature enables high specificity detection of circulating tumor cells in hepatocellular carcinoma - Kalinich, Mark; Bhan, Irun; Kwan, Tanya T; Miyamoto, David T; Javaid, Sarah; LiCausi, Joseph A; Milner, John D; Hong, Xin; Goyal, Lipika; Sil, Srinjoy; others (Proceedings of the National Academy of Sciences, 2017)
Circulating tumor cells (CTCs) are shed into the bloodstream by invasive cancers, but the difficulty inherent in identifying these rare cells by microscopy has precluded their routine use in monitoring or screening for cancer. We recently described a high-throughput microfluidic CTC-iChip, which efficiently depletes hematopoietic cells from blood specimens and enriches for CTCs with well-preserved RNA. Application of RNA-based digital PCR to detect CTC-derived signatures may thus enable highly accurate tissue lineage-based cancer detection in blood specimens. As proof of principle, we examined hepatocellular carcinoma (HCC), a cancer that is derived from liver cells bearing a unique gene expression profile. After identifying a digital signature of 10 liver-specific transcripts, we used a cross-validated logistic regression model to identify the presence of HCC-derived CTCs in nine of 16 (56%) untreated patients with HCC versus one of 31 (3%) patients with nonmalignant liver disease at risk for developing HCC (P < 0.0001). Positive CTC scores declined in treated patients: Nine of 32 (28%) patients receiving therapy and only one of 15 (7%) patients who had undergone curative-intent ablation, surgery, or liver transplantation were positive. RNA-based digital CTC scoring was not correlated with the standard HCC serum protein marker alpha fetoprotein (P = 0.57). Modeling the sequential use of these two orthogonal markers for liver cancer screening in patients with high-risk cirrhosis generates positive and negative predictive values of 80% and 86%, respectively. Thus, digital RNA quantitation constitutes a sensitive and specific CTC readout, enabling high-throughput clinical applications, such as noninvasive screening for HCC in populations where viral hepatitis and cirrhosis are prevalent.

The microfluidic nebulator: production of sub-micrometer sized airborne drops - Amstad, Esther; Spaepen, Frans; Michael P. Brenner; Weitz, David A (Lab on a Chip, 2017)
Many powders employed in the food and pharmaceutical industries are produced through spray drying because it is a cost efficient process that offers control over the particle size. However, most commercially available spray-driers cannot produce drops with diameters below 1 μm, limiting the size of spray-dried particles to values above 300 nm. We recently developed a microfluidic spray-drier that can form much smaller drops than commercially available spray-driers. This is achieved through a two-step process: first, the microfluidic spray-drier operates in the dripping regime to form 100 μm diameter primary drops in air and, second, subjects them to high shear stresses due to supersonic flow of air to break them into many much smaller secondary drops. In this paper, we describe the two essential steps required to form sub-μm diameter airborne drops inside microfluidic channels. We investigate the influence of the device geometry on the ability to operate the microfluidic spray-drier in the dripping regime. Moreover, we describe how these primary drops are nebulized into many secondary drops that are much smaller than the smallest dimension of the spray-drier channels.

Collective generation of milliemulsions by step-emulsification - Huang, Xing; Eggersdorfer, Max; Wu, Jinrong; Zhao, Chun-Xia; Xu, Zhongbin; Chen, Dong; Weitz, David A (RSC Advances, 2017)
Emulsification is a key step in many processes for the production and functionalization of dispersed liquid systems. Here, we report a versatile and robust device that generates monodisperse milliemulsions by step-emulsification. In contrast to the conventional design in which each channel is physically separated, we use a shallow plateau sandwiched between two parallel glass strips to connect all channels in a microcapillary film (MCF) before emerging in a deep reservoir. Because of the open plateau that connects different channels, the flow tips from neighboring channels may get immediately in contact with each other; this interaction may lead to the relative movement and deformation of the flow tips, to repulsion or even coalescence, enabling droplet generations from different channels to synchronize. By simply tuning the interaction, we achieve Janus droplets, drops of fluids mixed at different ratios and mixed drops of different compositions. The in situ generation of droplets with excellent control is essential for various applications.

Sensitive and predictable separation of microfluidic droplets by size using in-line passive filter - Ding, Ruihua; 丁睿骅; Ung, W. Lloyd; Heyman, John A.; Weitz, David A (Biomicrofluidics, 2017)
<span style='display: inline !important; float: none; background-color: transparent; color: rgb(0, 0, 0); font-family: "Lora",serif; font-size: 20px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;'>Active manipulation of droplets is crucial in droplet microfluidics. However, droplet polydispersity decreases the accuracy of active manipulation. We develop a microfluidic “droplet filter” that accurately separates droplets by size. The droplet filter has a sharp size cutoff and is capable of distinguishing droplets differing in volume by 20%. A simple model explains the behavior of the droplets as they pass through the filter. We show application of the filter in improving dielectric <span style='display: inline !important; float: none; background-color: transparent; color: rgb(0, 0, 0); font-family: "Lora",serif; font-size: 20px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;'> sorting efficiency.

Tandem emulsification for high-throughput production of double emulsions - Eggersdorfer, ML; Zheng, W.; S. Nawar; Mercandetti, C; Ofner, A; Leibacher, I; Koehler, S; Weitz, D. A. (Lab on a Chip, 2017)
Core–shell double emulsions produced using microfluidic methods with controlled structural parameters exhibit great potential in a wide range of applications, but the low production rate of microfluidic methods hinders the exploitation of the capabilities of microfluidics to produce double emulsions with well-defined features. A major obstacle towards the scaled-up production of core–shell double emulsions is the difficulty of achieving robust spatially controlled wettability in integrated microfluidic devices. Here, we use tandem emulsification, a two-step process with microfluidic devices, to scale up the production. With this method, single emulsions are generated in a first device and are re-injected directly into a second device to form uniform double emulsions. We demonstrate the application of tandem emulsification for scalable core–shell emulsion production with both integrated flow focusing and millipede devices and obtain emulsions of which over 90% are single-core monodisperse double emulsion drops. With both mechanisms, the shell thickness can be controlled, so that shells as thin as 3 μm are obtained for emulsions 50 μm in radius.

Microfluidic Fabrication of Colloidal Nanomaterials-encapsulated Microcapsules for Biomolecular Sensing - Xie, Xi; Zhang, Weixia; Abbaspourrad, Alireza; Ahn, Jiyoung; Bader, Andrew; Bose, Suman; Vegas, Arturo; Lin, Jiaqi; Tao, Jun; Hang, Tian; others (Nano Letters, 2017)
Implantable sensors that detect biomarkers in vivo are critical for early disease diagnostics. Although many colloidal nanomaterials have been developed into optical sensors to detect biomolecules in vitro, their application in vivo as implantable sensors is hindered by potential migration or clearance from the implantation site. One potential solution is incorporating colloidal nanosensors in hydrogel scaffold prior to implantation. However, direct contact between the nanosensors and hydrogel matrix has the potential to disrupt sensor performance. Here, we develop a hollow-microcapsule-based sensing platform that protects colloidal nanosensors from direct contact with hydrogel matrix. Using microfluidics, colloidal nanosensors were encapsulated in polyethylene glycol microcapsules with liquid cores. The microcapsules selectively trap the nanosensors within the core while allowing free diffusion of smaller molecules such as glucose and heparin. Glucose-responsive quantum dots or gold nanorods or heparin-responsive gold nanorods were each encapsulated. Microcapsules loaded with these sensors showed responsive optical signals in the presence of target biomolecules (glucose or heparin). Furthermore, these microcapsules can be immobilized into biocompatible hydrogel as implantable devices for biomolecular sensing. This technique offers new opportunities to extend the utility of colloidal nanosensors from solution-based detection to implantable device-based detection.

Core/Shell Nanocomposites Produced by Superfast Sequential Microfluidic Nanoprecipitation - Liu, Dongfei; Zhang, Hongbo; Cito, Salvatore; Fan, Jin; Mäkilä, Ermei M; Salonen, Jarno J; Hirvonen, Jouni; Sikanen, Tiina M; Weitz, David A; Hélder A. Santos (Nano Letters, 2017)
Although a number of techniques exist for generating structured organic nanocomposites, it is still challenging to fabricate them in a controllable, yet universal and scalable manner. In this work, a microfluidic platform, exploiting superfast (milliseconds) time intervals between sequential nanoprecipitation processes, has been developed for high-throughput production of structured core/shell nanocomposites. The extremely short time interval between the sequential nanoprecipitation processes, facilitated by the multiplexed microfluidic design, allows us to solve the instability issues of nanocomposite cores without using any stabilizers. Beyond high throughput production rate (∼700 g/day on a single device), the generated core/shell nanocomposites harness the inherent ultrahigh drug loading degree and enhanced payload dissolution kinetics of drug nanocrystals and the controlled drug release from polymer-based nanoparticles.

Versatile, cell and chip friendly method to gel alginate in microfluidic devices - Hati, A.G.; Bassett, D.C.; Ribe, J.M.; Sikorski, P.; Weitz, D. A.; Stokke, B.T. (Lab on a Chip, 2016)
Alginate is used extensively in microfluidic devices to produce discrete beads or fibres at the microscale. Such structures may be used to encapsulate sensitive cargoes such as cells and biomolecules. On chip gelation of alginate represents a significant challenge since gelling kinetics or physicochemical conditions are not biocompatible. Here we present a new method that offers a hitherto unprecedented level of control over the gelling kinetics and pH applied to the encapsulation of a variety of cells in both bead and fibre geometries. This versatile approach proved straightforward to adjust to achieve appropriate solution conditions required for implementation in microfluidic devices and resulted in highly reliable device operation and very high viability of several different encapsulated cell types for prolonged periods. We believe this method offers a paradigm shift in alginate gelling technology for application in microfluidics.

Water retention against drying with soft-particle suspensions in porous media - Keita, E; Kodger, T. E.; Faure, P; Rodts, S; Weitz, D. A.; Coussot, P (Physical Review E, 2016)
Polymers suspended in granular packings have a significant impact on water retention, which is important for soil irrigation and the curing of building materials. Whereas the drying rate remains constant during a long period for pure water due to capillary flow providing liquid water to the evaporating surface, we show that it is not the case for a suspension made of soft polymeric particles called microgels: The drying rate decreases immediately and significantly. By measuring the spatial water saturation and concentration of suspended particles with magnetic resonance imaging, we can explain these original trends and model the process. In low-viscosity fluids, the accumulation of particles at the free surface induces a recession of the air-liquid interface. A simple model, assuming particle transport and accumulation below the sample free surface, is able to reproduce our observations without any fitting parameters. The high viscosity of the microgel suspension inhibits flow towards the free surface and a drying front appears. We show that water vapor diffusion over a defined and increasing length sets the drying rate. These results and model allow for better controlling the drying and water retention in granular porous materials.

One-pot system for synthesis, assembly, and display of functional single-span membrane proteins on oil–water interfaces - Yunker, Peter J; Asahara, Haruichi; Hung, Kuo-Chan; Landry, Corey; Arriaga, Laura R.; Akartuna, Ilke; Heyman, John; Chong, Shaorong; Weitz, David A (Proceedings of the National Academy of Sciences, 2016)
Single-span membrane proteins (ssMPs) represent approximately one-half of all membrane proteins and play important roles in cellular communications. However, like all membrane proteins, ssMPs are prone to misfolding and aggregation because of the hydrophobicity of transmembrane helices, making them difficult to study using common aqueous solution-based approaches. Detergents and membrane mimetics can solubilize membrane proteins but do not always result in proper folding and functionality. Here, we use cell-free protein synthesis in the presence of oil drops to create a one-pot system for the synthesis, assembly, and display of functional ssMPs. Our studies suggest that oil drops prevent aggregation of some in vitro-synthesized ssMPs by allowing these ssMPs to localize on oil surfaces. We speculate that oil drops may provide a hydrophobic interior for cotranslational insertion of the transmembrane helices and a fluidic surface for proper assembly and display of the ectodomains. These functionalized oil drop surfaces could mimic cell surfaces and allow ssMPs to interact with cell surface receptors under an environment closest to cell–cell communication. Using this approach, we showed that apoptosis-inducing human transmembrane proteins, FasL and TRAIL, synthesized and displayed on oil drops induce apoptosis of cultured tumor cells. In addition, we take advantage of hydrophobic interactions of transmembrane helices to manipulate the assembly of ssMPs and create artificial clusters on oil drop surfaces. Thus, by coupling protein synthesis with self-assembly at the water–oil interface, we create a platform that can use recombinant ssMPs to communicate with cells.

Stable Ultrathin-Shell Double Emulsions for Controlled Release - Zhao, Chun-Xia; Chen, Dong; Hui, Yue; Weitz, David A; Middelberg, Anton PJ (ChemPhysChem, 2016)
Double emulsions are normally considered as metastable systems and this limit in stability restricts their applications. To enhance their stability, the outer shell can be converted into a mechanically strong layer, for example, a polymeric layer, thus allowing improved performance. This conversion can be problematic for food and drug applications, as a toxic solvent is needed to dissolve the polymer in the middle phase and a high temperature is required to remove the solvent. This process can also be highly complex, for example, involving UV initiation of polymeric monomer crosslinking. In this study, we report the formation of biocompatible, water-in-oil-in-water (W/O/W) double emulsions with an ultrathin layer of fish oil. We demonstrate their application for the encapsulation and controlled release of small hydrophilic molecules. Without a trigger, the double emulsions remained stable for months, and the release of small molecules was extremely slow. In contrast, rapid release was achieved by osmolarity shock, leading to complete release within 2 h. This work demonstrates the significant potential of double emulsions, and provides new insights into their stability and practical applications.

Composite alginate gels for tunable cellular microenvironment mechanics - Khavari, Adele; Nydén, Magnus; Weitz, David A; Ehrlicher, Allen J. (Scientific reports, 2016)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="17104" data-gtm-vis-first-on-screen-10482319_401="17104" data-gtm-vis-polling-id-10482319_393="825" data-gtm-vis-polling-id-10482319_401="826" data-gtm-vis-recent-on-screen-10482319_393="36389" data-gtm-vis-recent-on-screen-10482319_401="36390" data-gtm-vis-total-visible-time-10482319_393="3200" data-gtm-vis-total-visible-time-10482319_401="3200" data-title="Abstract" lang="en"> The mechanics of the cellular microenvironment can be as critical as biochemistry in directing cell behavior. Many commonly utilized materials derived from extra-cellular-matrix create excellent scaffolds for cell growth, however, evaluating the relative mechanical and biochemical effects independently in 3D environments has been difficult in frequently used biopolymer matrices. Here we present 3D sodium alginate hydrogel microenvironments over a physiological range of stiffness (E = 1.85 to 5.29 kPa), with and without RGD binding sites or collagen fibers. We use confocal microscopy to measure the growth of multi-cellular aggregates (MCAs), of increasing metastatic potential in different elastic moduli of hydrogels, with and without binding factors. We find that the hydrogel stiffness regulates the growth and morphology of these cell clusters; MCAs grow larger and faster in the more rigid environments similar to cancerous breast tissue (E = 4–12 kPa) as compared to healthy tissue (E = 0.4–2 kpa). Adding binding factors from collagen and RGD peptides increases growth rates, and change maximum MCA sizes. These findings demonstrate the utility of these independently tunable mechanical/biochemistry gels, and that mechanical confinement in stiffer microenvironments may increase cell proliferation.

Probing phenotypic growth in expanding Bacillus subtilis biofilms - Wang, Xiaoling; Koehler, Stephan A.; Wilking, James N.; Sinha, Naveen N.; Cabeen, Matthew T; Srinivasan, Siddarth; Seminara, Agnese; Shmuel Rubinstein; Sun, Qingping; Michael P. Brenner; others (Applied microbiology and biotechnology, 2016)
We develop an optical imaging technique for spatially and temporally tracking biofilm growth and the distribution of the main phenotypes of a Bacillus subtilis strain with a triple-fluorescent reporter for motility, matrix production, and sporulation. We develop a calibration procedure for determining the biofilm thickness from the transmission images, which is based on Beer-Lambert’s law and involves cross-sectioning of biofilms. To obtain the phenotype distribution, we assume a linear relationship between the number of cells and their fluorescence and determine the best combination of calibration coefficients that matches the total number of cells for all three phenotypes and with the total number of cells from the transmission images. Based on this analysis, we resolve the composition of the biofilm in terms of motile, matrix-producing, sporulating cells and low-fluorescent materials which includes matrix and cells that are dead or have low fluorescent gene expression. We take advantage of the circular growth to make kymograph plots of all three phenotypes and the dominant phenotype in terms of radial distance and time. To visualize the nonlocal character of biofilm growth, we also make kymographs using the local colonization time. Our technique is suitable for real-time, noninvasive, quantitative studies of the growth and phenotype distribution of biofilms which are either exposed to different conditions such as biocides, nutrient depletion, dehydration, or waste accumulation.

High-Throughput Step Emulsification for the Production of Functional Materials Using a Glass Microfluidic Device - Ofner, Alessandro; Moore, David G; Rühs, Patrick A; Schwendimann, Pascal; Eggersdorfer, Maximilian; Amstad, Esther; Weitz, David A; Studart, André R (Macromolecular Chemistry and Physics, 2016)
High‐volume production of monodisperse droplets is of importance for industrial applications due to increased emulsion stability, precise control over droplet volumes, and the formation of periodic arranged structures. So far, parallelized microfluidic devices are limited by either their complicated channel geometry or by their chemically or thermally unstable embedding material. This study shows a scalable microfluidic step emulsification chip that enables production of monodisperse emulsions at a throughput of up to 25 mL h−1 in a glass device with 364 linearly parallelized droplet makers. The chemical and thermal stability of such a glass device allows for the preparation of a broad variety of functional particles and microdroplets by using any desired solvent together with nanoparticles, polymers, and hydrogels. Moreover, the microfluidic device can be stringently cleaned for nearly unlimited use and permits the alternating production of oil‐in‐water and water‐in‐oil emulsions. The combined high throughput, chemical and thermal stability offered by our device enables production of monodisperse functional materials for large‐scale applications.

Imaging grain boundary grooves in hard-sphere colloidal bicrystals - Maire, Eric; Redston, Emily; Persson Gulda, Maria; Weitz, DavidA.; Spaepen, Frans (Phys. Rev. E, 2016)
Colloidal particles were sedimented onto patterned glass slides to grow three-dimensional bicrystals with a controlled structure. Three types of symmetric tilt grain boundaries between close-packed face-centered-cubic crystals were produced: Σ5(100),Σ17(100), and Σ3(110). The structure of the crystals and their defects were visualized by confocal microscopy, and characterized by simple geometric measurements, including image difference, thresholding, and reprojection. This provided a quick and straightforward way to detect the regions in which the atoms are mobile. This atomic mobility was higher at the grain boundaries and close to the solid-liquid interface. This method was compared to the more conventional analysis based on the calculation of the local order parameter of the individual particles to identify the interface. This was used in turn to identify the presence of grooves at the grain-boundary–liquid triple junction for every type of grain boundary, except for the twin [Σ3(110)], for which no groove could be detected. Images of these grooves were processed, and the angle linking the grain boundary energy to the solid-liquid interfacial energy was measured. The resulting values of the grain boundary energy were compared to estimates based on the density deficit in the boundary.

One-Step Microfluidic Fabrication of Polyelectrolyte Microcapsules in Aqueous Conditions for Protein Release - Zhang, Liyuan; Cai, Li-Heng; Lienemann, Philipp S; Rossow, Torsten; Polenz, Ingmar; Vallmajo-Martin, Queralt; Ehrbar, Martin; Na, Hui; Mooney, David J; Weitz, David A (Angewandte Chemie, 2016)
We report a microfluidic approach for one‐step fabrication of polyelectrolyte microcapsules in aqueous conditions. Using two immiscible aqueous polymer solutions, we generate transient water‐in‐water‐in‐water double emulsion droplets and use them as templates to fabricate polyelectrolyte microcapsules. The capsule shell is formed by the complexation of oppositely charged polyelectrolytes at the immiscible interface. We find that attractive electrostatic interactions can significantly prolong the release of charged molecules. Moreover, we demonstrate the application of these microcapsules in encapsulation and release of proteins without impairing their biological activities. Our platform should benefit a wide range of applications that require encapsulation and sustained release of molecules in aqueous environments.

Robust scalable high throughput production of monodisperse drops - Amstad, Esther; Chemama, Michael; Eggersdorfer, Maximilian; Arriaga, Laura Rodriguez; Brenner, M.P.; Weitz, David A (Lab on a Chip, 2016)
Monodisperse drops with diameters between 20 μm and 200 μm can be used to produce particles or capsules for many applications such as for cosmetics, food, and biotechnology. Drops composed of low viscosity fluids can be conveniently made using microfluidic devices. However, the throughput of microfluidic devices is limited and scale-up, achieved by increasing the number of devices run in parallel, can compromise the narrow drop-size distribution. In this paper, we present a microfluidic device, the millipede device, which forms drops through a static instability such that the fluid volume that is pinched off is the same every time a drop forms. As a result, the drops are highly monodisperse because their size is solely determined by the device geometry. This makes the operation of the device very robust. Therefore, the device can be scaled to a large number of nozzles operating simultaneously on the same chip; we demonstrate the operation of more than 500 nozzles on a single chip that produces up to 150 mL h−1 of highly monodisperse drops.

Dynamic sound scattering: Field fluctuation spectroscopy with singly scattered ultrasound in the near and far fields - Cowan, M. L.; Page, J. H.; Norisuye, T.; Weitz, D. A. (The Journal of the Acoustical Society of America, 2016)
Dynamic sound scattering (DSS) is a powerful acoustic technique for investigating the motion of particles or other inclusions inside an evolving medium. In DSS, this dynamic information is obtained by measuring the field autocorrelation function of the temporal fluctuations of singly scattered acoustic waves. The technique was initially introduced 15 years ago, but its technical aspects were not adequately discussed then. This paper addresses the need for a more complete account of the method by describing in detail two different implementations of this sound scattering technique, one of which is specifically adapted to a common experimental situation in ultrasonics. The technique is illustrated by the application of DSS to measure the mean square velocity fluctuations of particles in fluidized suspensions, as well as the dynamic velocity correlation length. By explaining the experimental and analytical methods involved in realizing the DSS technique in practice, the use of DSS will be facilitated for future studies of particulate suspension dynamics and particle properties over a wide range of particle sizes and concentrations, from millimeters down to nanometers, where the use of optical techniques is often limited by the opacity of the medium.

Clogging in parallelized tapered microfluidic channels - Massenburg, Sorell S; Amstad, Esther; Weitz, David A (Microfluidics and Nanofluidics, 2016)
Nearly all tubes and pores used to transport solids in fluids, such as arteries and filters, are subject to clogging. The length scales and geometries of these tubes are well defined. In spite of this knowledge, the collective clogging behavior of multiple tubes has not yet been connected to their shapes and sizes. We investigate the clogging behavior of ten parallel tubes, which we model with ten parallel tapered microchannels using poly(styrene) beads to induce clogging events. The clogging behavior depends on the channel geometry as well as the shear stress particles are subjected to. Although our microchannels model filters, our results can be applied to the clogging behavior of a broad range of applications such as the clogging in arteries, inkjets, or xylem in trees.

Fluctuations in the Kinetics of Linear Protein Self-Assembly - Michaels, Thomas CT; Dear, Alexander J; Kirkegaard, Julius B; Saar, Kadi L; Weitz, David A; Knowles, Tuomas P. J. (Physical Review Letters, 2016)
Biological systems are characterized by compartmentalization from the subcellular to the tissue level, and thus reactions in small volumes are ubiquitous in living systems. Under such conditions, statistical number fluctuations, which are commonly negligible in bulk reactions, can become dominant and lead to stochastic behavior. We present here a stochastic model of protein filament formation in small volumes. We show that two principal regimes emerge for the system behavior, a small fluctuation regime close to bulk behavior and a large fluctuation regime characterized by single rare events. Our analysis shows that in both regimes the reaction lag-time scales inversely with the system volume, unlike in bulk. Finally, we use our stochastic model to connect data from small-volume microdroplet experiments of amyloid formation to bulk aggregation rates, and show that digital analysis of an ensemble of protein aggregation reactions taking place under microconfinement provides an accurate measure of the rate of primary nucleation of protein aggregates, a process that has been challenging to quantify from conventional bulk experiments.

Stabilization of the Amorphous Structure of Spray-dried Drug Nanoparticles - Amstad, Esther; Spaepen, Frans A; Weitz, David A (The Journal of Physical Chemistry B, 2016)
The bioavailability of hydrophobic drugs strongly increases if they are formulated as amorphous materials because the solubility of the amorphous phase is much higher than that of the crystal. Moreover, the stability of these particles against crystallization during storage increases with decreasing particle size. Hence, it is advantageous to formulate poorly water soluble drugs as amorphous nanoparticles. The formulation of an amorphous structure is often difficult because many of these drugs have a high propensity to crystallize. This difficulty can be overcome if drugs are spray-dried using a microfluidic nebulator we recently developed. However, these nanoparticles agglomerate when they come in contact with each other, and this compromises the stability of their amorphous structure through crystallization. To improve their stability, we coat the nanoparticles with a sterically stabilizing polymer layer; this can be accomplished by co-spraying them with an excipient. However, this excipient must meet strict solubility limits, which severely limit the choice of polymers. Alternatively, the nanoparticles can be sterically stabilized by spraying them directly into a polymeric matrix; this enables a much wider choice of stabilizing polymers.

Fluorocarbon Oil Reinforced Triple Emulsion Drops - Hyomin Lee; Choi, Chang-Hyung; Abbaspourrad, Alireza; Chris Wesner; Marco Caggioni; Taotao Zhu; Nawar, Saraf; Weitz, DavidA. (Advanced Materials, 2016)
Fluorocarbon oil reinforced triple emulsion drops are prepared to encapsulate a broad range of polar and non‐polar cargoes in a single platform. In addition, it is demonstrated that the fluorocarbon oil within the emulsion drop acts as an effective diffusion barrier, as well as a non‐adhesive layer, enabling highly efficient encapsulation and retention of small molecules and active biomolecules in microcapsules.
Keywords: Emulsions; encapsulation; microcapsules; Microfluidics

Droplet microfluidics: A tool for biology, chemistry and nanotechnology - Mashaghi, Samaneh; Abbaspourrad, Alireza; Weitz, David A; van Oijen, Antoine M (TrAC Trends in Analytical Chemistry, 2016)
<span style="display: inline !important; float: none; background-color: transparent; color: rgb(80, 80, 80); font-family: Arial,Helvetica,Lucida Sans Unicode,Microsoft Sans Serif,Segoe UI Symbol,STIXGeneral,Cambria Math,Arial Unicode MS,sans-serif; font-size: 16px; font-style: normal; font-variant: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-decoration: none; text-indent: 0px; text-transform: none; -webkit-text-stroke-width: 0px; white-space: normal; word-spacing: 0px;">The ability to perform laboratory operations on small scales using miniaturized devices provides numerous benefits, including reduced quantities of reagents and waste as well as increased portability and controllability of assays. These operations can involve reaction components in the solution phase and as a result, their miniaturization can be accomplished through microfluidic approaches. One such approach, droplet microfluidics, provides a high-throughput platform for a wide range of assays and approaches in chemistry, biology and nanotechnology. We highlight recent advances in the application of droplet microfluidics in chip-based technologies, such as single-cell analysis tools, small-scale cell cultures, in-droplet chemical synthesis, high-throughput drug screening, and nanodevice fabrication.

Clonal evolution in patients with chronic lymphocytic leukaemia developing resistance to BTK inhibition - Burger, Jan A; Landau, Dan A; Taylor-Weiner, Amaro; Bozic, Ivana; Zhang, Huidan; Sarosiek, Kristopher; Wang, Lili; Stewart, Chip; Fan, Jean; Hoellenriegel, Julia; others (Nature communications, 2016)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="7689" data-gtm-vis-first-on-screen-10482319_401="7690" data-gtm-vis-has-fired-10482319_393="1" data-gtm-vis-has-fired-10482319_401="1" data-gtm-vis-recent-on-screen-10482319_393="7689" data-gtm-vis-recent-on-screen-10482319_401="7690" data-gtm-vis-total-visible-time-10482319_393="10000" data-gtm-vis-total-visible-time-10482319_401="10000" data-title="Abstract" lang="en"> Resistance to the Bruton’s tyrosine kinase (BTK) inhibitor ibrutinib has been attributed solely to mutations in BTK and related pathway molecules. Using whole-exome and deep-targeted sequencing, we dissect evolution of ibrutinib resistance in serial samples from five chronic lymphocytic leukaemia patients. In two patients, we detect BTK-C481S mutation or multiple PLCG2 mutations. The other three patients exhibit an expansion of clones harbouring del(8p) with additional driver mutations (EP300, MLL2 and EIF2A), with one patient developing trans-differentiation into CD19-negative histiocytic sarcoma. Using droplet-microfluidic technology and growth kinetic analyses, we demonstrate the presence of ibrutinib-resistant subclones and estimate subclone size before treatment initiation. Haploinsufficiency of TRAIL-R, a consequence of del(8p), results in TRAIL insensitivity, which may contribute to ibrutinib resistance. These findings demonstrate that the ibrutinib therapy favours selection and expansion of rare subclones already present before ibrutinib treatment, and provide insight into the heterogeneity of genetic changes associated with ibrutinib resistance.

Microfluidic Fabrication of Pluronic Vesicles with Controlled Permeability - do Nascimento, Débora F; Arriaga, Laura R.; Eggersdorfer, Max; Ziblat, Roy; Marques, Maria de Fátima V; Reynaud, Franceline; Koehler, Stephan A.; Weitz, David A (Langmuir, 2016)
Block copolymers with a low hydrophilic-to-lipophilic balance form membranes that are highly permeable to hydrophilic molecules. Polymersomes with this type of membrane enable the controllable release of molecules without membrane rupture. However, these polymersomes are difficult to assemble because of their low hydrophobicity. Here, we report a microfluidic approach to the production of these polymersomes using double-emulsion drops with ultrathin shells as templates. The small thickness of the middle oil phase enables the attraction of the hydrophobic blocks of the polymers adsorbed at each of the oil/water interfaces of the double emulsions; this results in the dewetting of the oil from the surface of the innermost water drops of the double emulsions and the ultimate formation of the polymersome. This approach to polymersome fabrication enables control of the vesicle size and results in the efficient encapsulation of hydrophilic ingredients that can be released through the polymer membrane without membrane rupture. We apply our approach to the fabrication of Pluronic L121 vesicles and characterize the permeability of their membranes. Furthermore, we show that membrane permeability can be tuned by blending different Pluronic polymers. Our work thus describes a route to producing Pluronic vesicles that are useful for the controlled release of hydrophilic ingredients.

Optimization and development of a universal flow-based microfluidic gradient generator - Xu, Zhongbin; Huang, Xing; Wang, Pengfei; Wang, Huanan; Weitz, David A (Microfluidics and Nanofluidics, 2016)
Generation of concentration gradients of reactive molecules is of fundamental importance for many applications including biology, pharmaceutical and chemical engineering. By numerically simulating the flow behaviour, we reveal the possible factors that cause significant error in the gradients generated by the conventional universal microfluidic gradient generator (MGG) device reported previously. Based on these computational analyses, we optimize the geometrical design of the conventional 2-inlet MGG devices and improve the accuracy of the generated gradients. Moreover, we innovatively propose a 3-inlet MGG design showing desirable accuracy and versatility on creating various gradient profiles using the one single device. We further demonstrate our numerical simulation by fabricating the MGG devices by soft lithography and experimentally produce concentration gradients of diverse power functions. In general, the current study substantially improves the performance of universal MGG devices, which can serve as powerful tools for widespread applications in biology and chemistry.

One-step generation of cell-laden microgels using double emulsion drops with a sacrificial ultra-thin oil shell - Choi, Chang-Hyung; Wang, Huanan; Hyomin Lee; Kim, June Hwan; Zhang, Liyuan; Mao, Angelo; Mooney, David J; Weitz, David A (Lab on a Chip, 2016)
Cell-laden microgels with highly uniform sizes have significant potential in tissue engineering and cell therapy due to their capability to provide a physiologically relevant three-dimensional (3D) microenvironment for living cells. In this work, we present a simple and efficient microfluidic approach to produce monodisperse cell-laden microgels through the use of double emulsion drops with an ultra-thin oil shell as the sacrificial template. Specifically, the thin oil shell in double emulsion spontaneously dewets upon polymerization of the innermost precursor drop and subsequent transfer into an aqueous solution, resulting in direct dispersion of microgels in the aqueous phase. Compared to conventional single emulsion-based techniques for cell encapsulation, this one-step approach prevents prolonged exposure of cells to the oil phase, leading to high-throughput cell encapsulation in microgels without compromising the cell viability. Moreover, this approach allows us to culture cells within a 3D microgel which mimics the extracellular matrix, thus enabling long-term cell functionality. This microfluidic technique represents a significant step forward in high-throughput cell microencapsulation technology and offers a potentially viable option to produce cell-laden microgels for widespread applications in tissue engineering and cell therapies.

Triple Emulsion Drops with An Ultrathin Water Layer: High Encapsulation Efficiency and Enhanced Cargo Retention in Microcapsules - Choi, Chang-Hyung; Hyomin Lee; Abbaspourrad, Alireza; Kim, June Hwan; Fan, Jing; Marco Caggioni; Chris Wesner; Taotao Zhu; Weitz, David A (Advanced Materials, 2016)
Triple emulsion drops with an ultrathin water layer are developed to achieve high encapsulation efficiency of hydrophobic cargo in a hydrophobic polymeric shell, directly dispersed in water. Furthermore, enhanced retention of volatile hydrophobic cargo is achieved by forming a hydrogel network within this water layer that serves as a physical barrier.

Controlled Assembly of Heterotypic cells in a Core-Shell Scaffold: Organ in a Droplet - Chen, Qiushui; Utech, Stefanie; Chen, Dong; Prodanovic, Radivoje M; Lin, Jin-Ming; Weitz, David A (Lab on a Chip, 2016)
This paper reports a droplet-based microfluidic approach to fabricate a large number of monodisperse, portable microtissues, each in an individual drop. We use water–water–oil double emulsions as templates and spatially assemble hepatocytes in the core and fibroblasts in the shell, forming a 3D liver model in a drop.

Injectable Stem Cell-Laden Photocrosslinkable Microspheres Fabricated Using Microfluidics for Rapid Generation of Osteogenic Tissue Constructs - Zhao, Xin; Liu, Shen; Yildirimer, Lara; Zhao, Hong; Ding, Ruihua; Wang, Huanan; Cui, Wenguo; David Weitz (Advanced Functional Materials, 2016)
Direct injection is a minimally invasive method of stem cell transplantation for numerous injuries and diseases. However, despite its promising potential, its clinical translation is difficult due to the low cell retention and engraftment after injection. With high versatility, high‐resolution control and injectability, microfabrication of stem‐cell laden biomedical hydrogels holds great potential as minimally invasive technology. Herein, a strategy of microfluidics‐assisted technology entrapping bone marrow‐derived mesenchymal stem cells (BMSCs) and growth factors in photocrosslinkable gelatin (GelMA) microspheres to ultimately generate injectable osteogenic tissue constructs is presented. Additionally, it is demonstrated that the GelMA microspheres can sustain stem cell viability, support cell spreading inside the microspheres and migration from the interior to the surface as well as enhance cell proliferation. This finding shows that encapsulated cells have the potential to directly and actively participate in the regeneration process. Furthermore, it is found that BMSCs encapsulated in GelMA microspheres show enhanced osteogenesis in vitro and in vivo, associated with a significant increase in mineralization. In short, the proposed strategy can be utilized to facilitate bone regeneration with minimum invasiveness, and can potentially be applied along with other matrices for extended applications.

A mix-and-read drop-based in vitro two-hybrid method for screening high-affinity peptide binders - Cui, Naiwen; Zhang, Huidan; Schneider, Nils; Tao, Ye; Asahara, Haruichi; Sun, Zhiyi; Cai, Yamei; Koehler, Stephan A.; de Greef, Tom FA; Abbaspourrad, Alireza; others (Scientific reports, 2016)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="925" data-gtm-vis-first-on-screen-10482319_401="925" data-gtm-vis-has-fired-10482319_393="1" data-gtm-vis-has-fired-10482319_401="1" data-gtm-vis-recent-on-screen-10482319_393="925" data-gtm-vis-recent-on-screen-10482319_401="925" data-gtm-vis-total-visible-time-10482319_393="10000" data-gtm-vis-total-visible-time-10482319_401="10000" data-title="Abstract" lang="en"> Drop-based microfluidics have recently become a novel tool by providing a stable linkage between phenotype and genotype for high throughput screening. However, use of drop-based microfluidics for screening high-affinity peptide binders has not been demonstrated due to the lack of a sensitive functional assay that can detect single DNA molecules in drops. To address this sensitivity issue, we introduced in vitro two-hybrid system (IVT2H) into microfluidic drops and developed a streamlined mix-and-read drop-IVT2H method to screen a random DNA library. Drop-IVT2H was based on the correlation between the binding affinity of two interacting protein domains and transcriptional activation of a fluorescent reporter. A DNA library encoding potential peptide binders was encapsulated with IVT2H such that single DNA molecules were distributed in individual drops. We validated drop-IVT2H by screening a three-random-residue library derived from a high-affinity MDM2 inhibitor PMI. The current drop-IVT2H platform is ideally suited for affinity screening of small-to-medium-sized libraries (103–106). It can obtain hits within a single day while consuming minimal amounts of reagents. Drop-IVT2H simplifies and accelerates the drop-based microfluidics workflow for screening random DNA libraries, and represents a novel alternative method for protein engineering and in vitro directed protein evolution.

Chapter Fourteen - Methods for Determining the Cellular Functions of Vimentin Intermediate Filaments - Karen M. Ridge; Dale Shumaker; Amélie Robert; Caroline Hookway; Vladimir I. Gelfand; Paul A. Janmey; Jason Lowery; Guo, Ming; Weitz, DavidA.; Edward Kuczmarski; Robert D. Goldman (Intermediate Filament Proteins, 2016)
The type III intermediate filament protein vimentin was once thought to function mainly as a static structural protein in the cytoskeleton of cells of mesenchymal origin. Now, however, vimentin is known to form a dynamic, flexible network that plays an important role in a number of signaling pathways. Here, we describe various methods that have been developed to investigate the cellular functions of the vimentin protein and intermediate filament network, including chemical disruption, photoactivation and photoconversion, biolayer interferometry, soluble bead binding assay, three-dimensional substrate experiments, collagen gel contraction, optical-tweezer active microrheology, and force spectrum microscopy. Using these techniques, the contributions of vimentin to essential cellular processes can be probed in ever further detail.
Keywords: Withaferin A

Drying kinetics driven by the shape of the air/water interface in a capillary channel - Emmanuel Keita; Koehler, Stephan A.; Paméla Faure; Weitz, DavidA.; Philippe Coussot (The European Physical Journal E, 2016)
We look at the drying process in a simple glass channel with dominant capillary effects as is the case in microfluidics. We find drying kinetics commonly observed for confined geometry, namely a constant period followed by a falling rate period. From visualization of the air/water interface with high resolution, we observe that the drying rate decreases without a drying front progression although this is the usually accepted mechanism for confined geometries. We show with FEM that in our specific geometry the falling rate period is due to changes in the shape of the air-water interface at the free surface where most evaporation occurs. Our simulations show that the sensitivity of the drying rate to the shape of the first air-water interface from the sample free surface implies that slight changes of the wetting or pinning conditions can significantly modify the drying rate.

Encapsulation and Enhanced Retention of Fragrance in Polymer Microcapsules - Hyomin Lee; Choi, Chang-Hyung; Abbaspourrad, Alireza; Chris Wesner; Marco Caggioni; Taotao Zhu; Weitz, DavidA. (ACS Applied Materials & Interfaces, 2016)
Fragrances are amphiphilic and highly volatile, all of which makes them a challenging cargo to efficiently encapsulate and retain in microcapsules using traditional approaches. We address these limitations by introducing a new strategy that combines bulk and microfluidic emulsification: a stable fragrance-in-water (F/W) emulsion that is primarily prepared from bulk emulsification is incorporated within a polymer microcapsule via microfluidic emulsification. On the basis of the in-depth study of physicochemical properties of the microcapsules on fragrance leakage, we demonstrate that enhanced retention of fragrance can be achieved by using a polar polymeric shell and forming a hydrogel network within the microcapsule. We further extend the utility of these microcapsules by demonstrating the enhanced retention of encapsulated fragrance in powder state.

Hydrothermal Synthesis and Properties of Hierarchical ZnO and Eu-doped ZnO 3D Structures - Verissimo, C; Abbaspourrad, A.; Sunter, K; F. Capasso; Moshkalev, S; Weitz, D. (une, 2016)

Massively parallel sequencing of single cells by epicPCR links functional genes with phylogenetic markers - Spencer, Sarah J.; Tamminen, Manu V.; Preheim, Sarah P.; Guo, Mira T.; Briggs, Adrian W.; Brito, Ilana L.; Weitz, DavidA.; Pitkanen, Leena K.; Vigneault, Francois; Virta, Marko P. Juhani; Alm, Eric J. (ISME JOURNAL, 2016)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="4000" data-gtm-vis-first-on-screen-10482319_401="4000" data-gtm-vis-polling-id-10482319_393="109" data-gtm-vis-polling-id-10482319_401="110" data-gtm-vis-recent-on-screen-10482319_393="4000" data-gtm-vis-recent-on-screen-10482319_401="4000" data-gtm-vis-total-visible-time-10482319_393="4300" data-gtm-vis-total-visible-time-10482319_401="4300" data-title="Abstract" lang="en"> Many microbial communities are characterized by high genetic diversity. 16S ribosomal RNA sequencing can determine community members, and metagenomics can determine the functional diversity, but resolving the functional role of individual cells in high throughput remains an unsolved challenge. Here, we describe epicPCR (Emulsion, Paired Isolation and Concatenation PCR), a new technique that links functional genes and phylogenetic markers in uncultured single cells, providing a throughput of hundreds of thousands of cells with costs comparable to one genomic library preparation. We demonstrate the utility of our technique in a natural environment by profiling a sulfate-reducing community in a freshwater lake, revealing both known sulfate reducers and discovering new putative sulfate reducers. Our method is adaptable to any conserved genetic trait and translates genetic associations from diverse microbial samples into a sequencing library that answers targeted ecological questions. Potential applications include identifying functional community members, tracing horizontal gene transfer networks and mapping ecological interactions between microbial cells.

Biocompatible fluorinated polyglycerols for droplet microfluidics as an alternative to PEG-based copolymer surfactants - Wagner, Olaf; Thiele, Julian; Weinhart, Marie; Mazutis, Linas; Weitz, David A; Huck, Wilhelm TS; Haag, Rainer (Lab on a Chip, 2016)
In droplet-based microfluidics, non-ionic, high-molecular weight surfactants are required to stabilize droplet interfaces. One of the most common structures that imparts stability as well as biocompatibility to water-in-oil droplets is a triblock copolymer surfactant composed of perfluoropolyether (PFPE) and polyethylene glycol (PEG) blocks. However, the fast growing applications of microdroplets in biology would benefit from a larger choice of specialized surfactants. PEG as a hydrophilic moiety, however, is a very limited tool in surfactant modification as one can only vary the molecular weight and chain-end functionalization. In contrast, linear polyglycerol offers further side-chain functionalization to create custom-tailored, biocompatible droplet interfaces. Herein, we describe the synthesis and characterization of polyglycerol-based triblock surfactants with tailored side-chain composition, and exemplify their application in cell encapsulation and in vitro gene expression studies in droplet-based microfluidics.

Efficient nematode swimming in a shear thinning colloidal suspension - Park, Jin-Sung; Kim, Daeyeon; Shin, Jennifer H.; Weitz, DavidA. (Soft Matter, 2016)
The swimming behavior of a nematode Caenorhabditis elegans (C. elegans) is investigated in a non-Newtonian shear thinning colloidal suspension. At the onset value ([curly or open phi] [similar] 8%), the suspension begins to exhibit shear thinning behavior, and the average swimming speed of worms jumps by approximately 12% more than that measured in a Newtonian solution exhibiting no shear dependent viscosity. In the shear thinning regime, we observe a gradual yet significant improvement in swimming efficiency with an increase in [curly or open phi] while the swimming speed remains nearly constant. We postulate that this enhanced swimming can be explained by the temporal change in the stroke form of the nematode that is uniquely observed in a shear thinning colloidal suspension: the nematode features a fast and large stroke in its head to overcome the temporally high drag imposed by the viscous medium, whose effective viscosity ([small eta]s) is shown to drop drastically, inversely proportional to the strength of its stroke. Our results suggest new insights into how nematodes efficiently maneuver through the complex fluid environment in their natural habitat.

Zinc promotes clot stability by accelerating clot formation and modifying fibrin structure - Henderson, Sara J; Xia, Jing; Huayin Wu; Stafford, Alan R; Leslie, Beverly A.; Fredenburgh, James C; Weitz, David A; Weitz, Jeffrey I.; others (Thrombosis and haemostasis, 2016)
Zinc released from activated platelets binds fibrin(ogen) and attenuates fibrinolysis. Although zinc also affects clot formation, the mechanism and consequences are poorly understood. To address these gaps, the effect of zinc on clot formation and structure was examined in the absence or presence of factor (F) XIII. Zinc accelerated a) plasma clotting by 1.4-fold, b) fibrinogen clotting by 3.5- and 2.3-fold in the absence or presence of FXIII, respectively, c) fragment X clotting by 1.3-fold, and d) polymerisation of fibrin monomers generated with thrombin or batroxobin by 2.5– and 1.8-fold, respectively. Whereas absorbance increased up to 3.3-fold when fibrinogen was clotted in the presence of zinc, absorbance of fragment X clots was unaffected by zinc, consistent with reports that zinc binds to the αC-domain of fibrin(ogen). Scanning electron microscopic analysis revealed a twofold increase in fibre diameter in the presence of zinc and in permeability studies, zinc increased clot porosity by 30-fold with or without FXIII. Whereas FXIII increased clot stiffness from 128 ± 19 Pa to 415 ± 27 Pa in rheological analyses, zinc reduced clot stiffness by 10– and 8.5-fold in the absence and presence of FXIII, respectively. Clots formed in the presence of zinc were more stable and resisted rupture with or without FXIII. Therefore, zinc accelerates clotting and reduces fibrin clot stiffness in a FXIII-independent manner, suggesting that zinc may work in concert with FXIII to modulate clot strength and stability.

The Oxford Handbook of Soft Condensed Matter - Terentjev, Eugene M.; Weitz, DavidA. (Oxford University Press, 2015)
This Handbook serves both as an introduction and an overview of the field of soft condensed matter. The discussion covers topics ranging from the fundamentals of colloid science to the principles and action of surfactants, modern directions of research in liquid crystals, and the key properties of foams. The book also explores the fundamental physics that controls the structure and mechanics of granular matter; how the unusual and often dramatic mechanical properties of concentrated polymer systems are determined by the physics of entanglements; the complex structures formed by block copolymers and the methods of structure analysis; rubber elasticity and new emerging classes of rubber-elastic materials; the physics of polyelectrolytes; the solvent dynamics in polymer gels, in equilibrium and under mechanical stress; the hierarchical structure and characteristics of an extracellular matrix; and the hierarchical structure and resulting physical properties of the cell cytoskeleton. The book concludes with an analysis of the properties of interfaces and membranes.

Collective motion of mammalian cell cohorts in 3D - Sharma, Yasha; Vargas, Diego A; Pegoraro, Adrian F; Lepzelter, David; Weitz, David A; Zaman, Muhammad H. (Integrative Biology, 2015)
Collective cell migration is ubiquitous in biology, from development to cancer; it occurs in complex systems comprised of heterogeneous cell types, signals and matrices, and requires large scale regulation in space and time. Understanding how cells achieve organized collective motility is crucial to addressing cellular and tissue function and disease progression. While current two-dimensional model systems recapitulate the dynamic properties of collective cell migration, quantitative three-dimensional equivalent model systems have proved elusive. To establish such a model system, we study cell collectives by tracking individuals within cell cohorts embedded in three dimensional collagen scaffolding. We develop a custom algorithm to quantify the temporal and spatial heterogeneity of motion in cell cohorts during motility events. In the absence of external driving agents, we show that these cohorts rotate in short bursts, <2 hours, and translate for up to 6 hours. We observe, track, and analyze three dimensional motion of cell cohorts composed of 3–31 cells, and pave a path toward understanding cell collectives in 3D as a complex emergent system.

Crystallization of undercooled liquid fenofibrate - Amstad, Esther; Spaepen, Frans; Weitz, David A (Physical Chemistry Chemical Physics, 2015)
Formulation of hydrophobic drugs as amorphous materials is highly advantageous as this increases their solubility in water and therefore their bioavailability. However, many drugs have a high propensity to crystallize during production and storage, limiting the usefulness of amorphous drugs. We study the crystallization of undercooled liquid fenofibrate, a model hydrophobic drug. Nucleation is the rate-limiting step; once seeded with a fenofibrate crystal, the crystal rapidly grows by consuming the undercooled liquid fenofibrate. Crystal growth is limited by the incorporation of molecules into its surface. As nucleation and growth both entail incorporation of molecules into the surface, this process likely also limits the formation of nuclei and thus the crystallization of undercooled liquid fenofibrate, contributing to the good stability of undercooled liquid fenofibrate against crystallization.

Single-cell ChIP-seq reveals cell subpopulations defined by chromatin state - Rotem, Assaf; Ram, Oren; Shoresh, Noam; Sperling, Ralph A.; Goren, Alon; Weitz, David A; Bernstein, Bradley E (Nature biotechnology, 2015)
<section aria-labelledby="Abs2" data-gtm-vis-first-on-screen-10482319_393="40965" data-gtm-vis-first-on-screen-10482319_401="40965" data-gtm-vis-polling-id-10482319_393="108" data-gtm-vis-polling-id-10482319_401="109" data-gtm-vis-recent-on-screen-10482319_393="40965" data-gtm-vis-recent-on-screen-10482319_401="40965" data-gtm-vis-total-visible-time-10482319_393="5400" data-gtm-vis-total-visible-time-10482319_401="5400" data-title="Abstract" lang="en"> Chromatin profiling provides a versatile means to investigate functional genomic elements and their regulation. However, current methods yield ensemble profiles that are insensitive to cell-to-cell variation. Here we combine microfluidics, DNA barcoding and sequencing to collect chromatin data at single-cell resolution. We demonstrate the utility of the technology by assaying thousands of individual cells and using the data to deconvolute a mixture of ES cells, fibroblasts and hematopoietic progenitors into high-quality chromatin state maps for each cell type. The data from each single cell are sparse, comprising on the order of 1,000 unique reads. However, by assaying thousands of ES cells, we identify a spectrum of subpopulations defined by differences in chromatin signatures of pluripotency and differentiation priming. We corroborate these findings by comparison to orthogonal single-cell gene expression data. Our method for single-cell analysis reveals aspects of epigenetic heterogeneity not captured by transcriptional analysis alone.

Color from hierarchy: Diverse optical properties of micron-sized spherical colloidal assemblies - Vogel, Nicolas; Utech, Stefanie; England, Grant T; Shirman, Tanya; Phillips, Katherine R; Koay, Natalie; Burgess, Ian B; Kolle, Mathias; Weitz, David A; Aizenberg, Joanna (Proceedings of the National Academy of Sciences, 2015)
Materials in nature are characterized by structural order over multiple length scales have evolved for maximum performance and multifunctionality, and are often produced by self-assembly processes. A striking example of this design principle is structural coloration, where interference, diffraction, and absorption effects result in vivid colors. Mimicking this emergence of complex effects from simple building blocks is a key challenge for man-made materials. Here, we show that a simple confined self-assembly process leads to a complex hierarchical geometry that displays a variety of optical effects. Colloidal crystallization in an emulsion droplet creates micron-sized superstructures, termed photonic balls. The curvature imposed by the emulsion droplet leads to frustrated crystallization. We observe spherical colloidal crystals with ordered, crystalline layers and a disordered core. This geometry produces multiple optical effects. The ordered layers give rise to structural color from Bragg diffraction with limited angular dependence and unusual transmission due to the curved nature of the individual crystals. The disordered core contributes nonresonant scattering that induces a macroscopically whitish appearance, which we mitigate by incorporating absorbing gold nanoparticles that suppress scattering and macroscopically purify the color. With increasing size of the constituent colloidal particles, grating diffraction effects dominate, which result from order along the crystal’s curved surface and induce a vivid polychromatic appearance. The control of multiple optical effects induced by the hierarchical morphology in photonic balls paves the way to use them as building blocks for complex optical assemblies—potentially as more efficient mimics of structural color as it occurs in nature.

Isolation and analysis of rare norovirus recombinants from co-infected mice using drop-based microfluidics - Zhang, Huidan; Cockrell, Shelley K.; Kolawole, Abimbola O.; Rotem, Assaf; Serohijos, Adrian WR; Chang, Connie B.; Tao, Ye; Mehoke, Thomas S.; Han, Yulong; Lin, Jeffrey S.; others (Journal of virology, 2015)
Human noroviruses (HuNoVs) are positive-sense RNA viruses that can cause severe, highly infectious gastroenteritis. HuNoV outbreaks are frequently associated with recombination between circulating strains. Strain genotyping and phylogenetic analyses show that noroviruses often recombine in a highly conserved region near the junction of the viral polyprotein (open reading frame 1 [ORF1]) and capsid (ORF2) genes and occasionally within the RNA-dependent RNA polymerase (RdRP) gene. Although genotyping methods are useful for tracking changes in circulating viral populations, they report only the dominant recombinant strains and do not elucidate the frequency or range of recombination events. Furthermore, the relatively low frequency of recombination in RNA viruses has limited studies to cell culture or in vitro systems, which do not reflect the complexities and selective pressures present in an infected organism. Using two murine norovirus (MNV) strains to model coinfection, we developed a microfluidic platform to amplify, detect, and recover individual recombinants following in vitro and in vivo coinfection. One-step reverse transcriptase PCR (RT-PCR) was performed in picoliter drops with primers that identified the wild-type and recombinant progenies and scanned for recombination breakpoints at ∼1-kb intervals. We detected recombination between MNV strains at multiple loci spanning the viral protease, RdRP, and capsid ORFs and isolated individual recombinant RNA genomes that were present at a frequency of 1/300,000 or higher. This study is the first to examine norovirus recombination following coinfection of an animal and suggests that the exchange of RNA among viral genomes in an infected host occurs in multiple locations and is an important driver of genetic diversity.

Label-free single-cell protein quantification using a drop-based mix-and-read system - Abbaspourrad, Alireza; Zhang, Huidan; Tao, Ye; Cui, Naiwen; Asahara, Haruichi; Zhou, Ying; Yue, Dongxian; Koehler, Stephan A.; Ung, W. Lloyd; Heyman, John; others (Scientific reports, 2015)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="880" data-gtm-vis-first-on-screen-10482319_401="880" data-gtm-vis-has-fired-10482319_393="1" data-gtm-vis-has-fired-10482319_401="1" data-gtm-vis-recent-on-screen-10482319_393="11948" data-gtm-vis-recent-on-screen-10482319_401="11948" data-gtm-vis-total-visible-time-10482319_393="10000" data-gtm-vis-total-visible-time-10482319_401="10000" data-title="Abstract" lang="en"> Quantitative protein analysis of single cells is rarely achieved due to technical difficulties of detecting minute amounts of proteins present in one cell. We develop a mix-and-read assay for drop-based label-free protein analysis of single cells. This high-throughput method quantifies absolute, rather than relative, amounts of proteins and does not involve antibody labeling or mass spectrometry.

Microfluidic Generation of Monodisperse, Structurally Homogeneous Alginate Microgels for Cell Encapsulation and 3D Cell Culture - Utech, Stefanie; Prodanovic, Radivoje; Mao, Angelo S; Ostafe, Raluca; Mooney, David J; Weitz, David A (Advanced healthcare materials, 2015)
Recent studies have shown that basic cellular behavior varies significantly between two- and three-dimensional culture systems. To identify the origins of these fundamental differences the design of reliable and precisely controlled environments is essential. While 2D cell culture is a well-established technique, the fabrication of defined three-dimensional culture models is still challenging. We present a new method for the microfluidic generation of a micron-sized three-dimensional cell culture system. We use a triggered ionic crosslink formation to generate highly monodisperse and structurally homogeneous alginate microbeads. Aqueous droplets containing a mixture of alginate and a water-soluble calcium-EDTA complex are formed by droplet-based microfluidics. In their complexed form, the calcium ions are homogenously distributed inside the droplet but not accessible for the crosslinking process. Acid addition is used to trigger the degradation of the complex, releasing calcium ions on demand that can physically crosslink the alginate chains. A homogeneous hydrogel network is thus generated which can be transferred into an aqueous environment without losing its structural integrity. Single cells can be encapsulated into these controlled microenvironments which provide structural support while allowing for continuous nutrient supply. We encapsulate individual mesenchymal stem cells (MSCs) into the microbeads which show the aspired cell growth and proliferation.

Microfluidic Production of Alginate Hydrogel Particles for Antibody Encapsulation and Release - Mazutis, Linas; Vasiliauskas, Remigijus; Weitz, DavidA. (Macromolecular Bioscience, 2015)
Owing to their biocompatibility and reduced side effects, natural polymers represent an attractive choice for producing drug delivery systems. Despite few successful examples, however, the production of monodisperse biopolymer-based particles is often hindered by high viscosity of polymer fluids. In this work, we present a microfluidic approach for production of alginate-based particles carrying encapsulated antibodies. We use a triple-flow micro-device to induce hydrogel formation inside droplets before their collection off-chip. The fast mixing and gelation process produced alginate particles with a unique biconcave shape and dimensions of the mammalian cells. We show slow and fast dissolution of particles in different buffers and evaluate antibody release over time.
Keywords: alginate particles; antibody; droplet microfluidics; drug delivery system

Monodisperse Emulsion Drop Microenvironments for Bacterial Biofilm Growth - Chang, Connie B.; Wilking, James N.; Kim, Shin-Hyun; Shum, Ho Cheung; Weitz, DavidA. (Small, 2015)
In this work, microfluidic technology is used to rapidly create hundreds of thousands of monodisperse double and triple emulsion drops that serve as 3D microenvironments for the containment and growth of bacterial biofilms. The size of these drops, with diameters from tens to hundreds of micrometers, makes them amenable to rapid manipulation and analysis. This is demonstrated by using microscopy to visualize cellular differentiation of Bacillus subtilis biofilm communities within each drop and the bacterial biofilm microstructure. Biofilm growth is explored upon specific interfaces in double and triple emulsions and upon negative and positive radii of curvature. Biofilm attachment of matrix and flagella mutants is studied as well as biofilms of Pseudomonas aeruginosa. This is the first demonstration of biofilms grown in microscale emulsion drops, which serve as both templates and containers for biofilm growth and attachment. These microenvironments have the potential to transform existing high-throughput screening methods for bacterial biofilms.
Keywords: Biofilms; Emulsions; high-throughput; microenvironments; Microfluidics

Perfluoroalkyl-Functionalized Hyperbranched Polyglycerol as Pore Forming Agents and Supramolecular Hosts in Polymer Microspheres - Wagner, Olaf; Zieringer, Maximilian; Duncanson, Wynter J.; Weitz, David A; Haag, Rainer (International journal of molecular sciences, 2015)
Perfluoroalkyl-functionalized, hyperbranched polyglycerols that produce stable microbubbles are integrated into a microfluidic emulsion to create porous microspheres. In a previously-presented work a dendrimer with a perfluorinated shell was used. By replacing this dendrimer core with a hyperbranched core and evaluating different core sizes and degrees of fluorinated shell functionalization, we optimized the process to a more convenient synthesis and higher porosities. The new hyperbranched polyglycerol porogens produced more pores and can be used to prepare microspheres with porosity up to 12% (v/v). The presented preparation forms pores with a perfluoroalkyl-functionalized surface that enables the resulting microspheres to act as supramolecular host systems. The microspheres can incorporate gases into the pores and actives in the polymer matrix, while the perfluoroalkylated pore surface can be used to immobilize perfluoro-tagged molecules onto the pores by fluorous-fluorous interaction.

Rapid, targeted and culture-free viral infectivity assay in drop-based microfluidics - Tao, Ye; Rotem, Assaf; Zhang, Huidan; Chang, Connie B.; Anindita Basu; Kolawole, Abimbola O.; Koehler, Stephan A.; Ren, Yukun; Lin, Jeffrey S.; Pipas, James M.; others (Lab on a Chip, 2015)
A key viral property is infectivity, and its accurate measurement is crucial for the understanding of viral evolution, disease and treatment. Currently viral infectivity is measured using plaque assays, which involve prolonged culturing of host cells, and whose measurement is unable to differentiate between specific strains and is prone to low number fluctuation. We developed a rapid, targeted and culture-free infectivity assay using high-throughput drop-based microfluidics. Single infectious viruses are incubated in a large number of picoliter drops with host cells for one viral replication cycle followed by in-drop gene-specific amplification to detect infection events. Using murine noroviruses (MNV) as a model system, we measure their infectivity and determine the efficacy of a neutralizing antibody for different variants of MNV. Our results are comparable to traditional plaque-based assays and plaque reduction neutralization tests. However, the fast, low-cost, highly accurate genomic-based assay promises to be a superior method for drug screening and isolation of resistant viral strains. Moreover our technique can be adapted to measuring the infectivity of other pathogens, such as bacteria and fungi.

Scalable single-step microfluidic production of single-core double emulsions with ultra-thin shells - Arriaga, LR; Amstad, E.; Weitz, D. A. (Lab on a Chip, 2015)
We report a versatile and robust device for the continuous production of double emulsion drops with very thin shell thicknesses, of about 5% of the radius: for emulsions 50 μm in radius the shells can be as thin as a few micrometers. Importantly, the viscosity of the oil shell can be varied from that of water up to 70 times that of water without compromising device operation. Furthermore, this device can be easily scaled-up as it is made through soft lithography; this may enable the production of industrial quantities of double emulsion drops with ultra-thin shells, which may serve as templates to form capsules with homogeneous shell thicknesses, useful beyond scientific applications.

Unjamming and cell shape in the asthmatic airway epithelium - Park, Jin-Ah; Kim, Jae Hun; Bi, Dapeng; Mitchel, Jennifer A; Qazvini, Nader Taheri; Tantisira, Kelan; Park, Chan Young; McGill, Maureen; Kim, Sae-Hoon; Gweon, Bomi; others (Nature materials, 2015)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="3887" data-gtm-vis-first-on-screen-10482319_401="3887" data-gtm-vis-polling-id-10482319_393="98" data-gtm-vis-polling-id-10482319_401="99" data-gtm-vis-recent-on-screen-10482319_393="3887" data-gtm-vis-recent-on-screen-10482319_401="3887" data-gtm-vis-total-visible-time-10482319_393="4700" data-gtm-vis-total-visible-time-10482319_401="4700" data-title="Abstract" lang="en"> From coffee beans flowing in a chute to cells remodelling in a living tissue, a wide variety of close-packed collective systems—both inert and living—have the potential to jam. The collective can sometimes flow like a fluid or jam and rigidify like a solid. The unjammed-to-jammed transition remains poorly understood, however, and structural properties characterizing these phases remain unknown. Using primary human bronchial epithelial cells, we show that the jamming transition in asthma is linked to cell shape, thus establishing in that system a structural criterion for cell jamming. Surprisingly, the collapse of critical scaling predicts a counter-intuitive relationship between jamming, cell shape and cell–cell adhesive stresses that is borne out by direct experimental observations. Cell shape thus provides a rigorous structural signature for classification and investigation of bronchial epithelial layer jamming in asthma, and potentially in any process in disease or development in which epithelial dynamics play a prominent role.

Whole-Genome Sequencing of a Single Viral Species from a Highly Heterogeneous Sample - Han, Hee-Sun; Cantalupo, Paul G.; Rotem, Assaf; Cockrell, Shelley K.; Carbonnaux, Martial; Pipas, James M.; Weitz, David A (Angewandte Chemie, 2015)
Metagenomic studies suggest that only a small fraction of the viruses that exist in nature have been identified and studied. Characterization of unknown viral genomes is hindered by the many genomes populating any virus sample. A new method is reported that integrates drop‐based microfluidics and computational analysis to enable the purification of any single viral species from a complex mixed virus sample and the retrieval of complete genome sequences. By using this platform, the genome sequence of a 5243 bp dsDNA virus that was spiked into wastewater was retrieved with greater than 96 % sequence coverage and more than 99.8 % sequence identity. This method holds great potential for virus discovery since it allows enrichment and sequencing of previously undescribed viruses as well as known viruses.

Artifact-Free Quantification and Sequencing of Rare Recombinant Viruses by Using Drop-Based Microfluidics - Tao, Ye; Rotem, Assaf; Zhang, Huidan; Cockrell, Shelley K.; Koehler, Stephan A.; Chang, Connie B.; Ung, W. Lloyd; Cantalupo, Paul G.; Ren, Yukun; Lin, Jeffrey S.; Feldman, Andrew B.; Wobus, Christiane E.; et al. (ChemBioChem, 2015)
Recombination is an important driver in the evolution of viruses and thus is key to understanding viral epidemics and improving strategies to prevent future outbreaks. Characterization of rare recombinant subpopulations remains technically challenging because of artifacts such as artificial recombinants, known as chimeras, and amplification bias. To overcome this, we have developed a high‐throughput microfluidic technique with a second verification step in order to amplify and sequence single recombinant viruses with high fidelity in picoliter drops. We obtained the first artifact‐free estimate of in vitro recombination rate between murine norovirus strains MNV‐1 and WU20 co‐infecting a cell (Prec=3.3×10−4±2×10−5) for a 1205 nt region. Our approach represents a time‐ and cost‐effective improvement over current methods, and can be adapted for genomic studies requiring artifact‐ and bias‐free selective amplification, such as microbial pathogens, or rare cancer cells.
Keywords: drop-based microfluidics; error-free genomic amplification; RT-PCR; sequence determination; Viruses

Stress controls the mechanics of collagen networks - Licup, Albert James; Münster, Stefan; Sharma, Abhinav; Sheinman, Michael; Jawerth, Louise M.; Fabry, Ben; Weitz, David A; Mackintosh, Fred C. (Proceedings of the National Academy of Sciences, 2015)
Collagen is the main structural and load-bearing element of various connective tissues, where it forms the extracellular matrix that supports cells. It has long been known that collagenous tissues exhibit a highly nonlinear stress–strain relationship, although the origins of this nonlinearity remain unknown. Here, we show that the nonlinear stiffening of reconstituted type I collagen networks is controlled by the applied stress and that the network stiffness becomes surprisingly insensitive to network concentration. We demonstrate how a simple model for networks of elastic fibers can quantitatively account for the mechanics of reconstituted collagen networks. Our model points to the important role of normal stresses in determining the nonlinear shear elastic response, which can explain the approximate exponential relationship between stress and strain reported for collagenous tissues. This further suggests principles for the design of synthetic fiber networks with collagen-like properties, as well as a mechanism for the control of the mechanics of such networks.

Production of amorphous nanoparticles by supersonic spray-drying with a microfluidic nebulator - Amstad, Esther; Gopinadhan, Manesh; Holtze, Christian; Osuji, Chinedum O.; Michael P. Brenner; Spaepen, Frans; Weitz, David A (Science, 2015)
Amorphous nanoparticles (a-NPs) have physicochemical properties distinctly different from those of the corresponding bulk crystals; for example, their solubility is much higher. However, many materials have a high propensity to crystallize and are difficult to formulate in an amorphous structure without stabilizers. We fabricated a microfluidic nebulator that can produce amorphous NPs from a wide range of materials, even including pure table salt (NaCl). By using supersonic air flow, the nebulator produces drops that are so small that they dry before crystal nuclei can form. The small size of the resulting spray-dried a-NPs limits the probability of crystal nucleation in any given particle during storage. The kinetic stability of the a-NPs—on the order of months—is advantageous for hydrophobic drug molecules.

Soft Poly(dimethylsiloxane) Elastomers from Architecture-Driven Entanglement Free Design - Cai, Li-Heng; Kodger, Thomas E.; Guerra, Rodrigo E.; Pegoraro, Adrian F; Rubinstein, Michael; Weitz, David A (Advanced Materials, 2015)
Soft, solvent‐free poly(dimethylsiloxane) elastomers are fabricated by a one‐step process via crosslinking bottlebrush polymers. The bottlebrush architecture prevents the formation of entanglements, resulting in elastomers with precisely controllable low moduli from 1 to 100 kPa, below the lower limit of traditional elastomers; moreover, the solvent‐free nature enables their negligible adhesiveness compared to commercially available silicone products of similar stiffness.
Keywords: bottlebrush; elastomers; nonsticky; poly(dimethylsiloxane); soft; solvent free

Microfluidic Fabrication and Micromechanics of Permeable and Impermeable Elastomeric Microbubbles - Duncanson, Wynter J.; Kodger, Thomas E.; Babaee, Sahab; Gonzalez, Grant; Weitz, David A; Bertoldi, Katia (Langmuir, 2015)
We use droplet microfluidics to produce monodisperse elastomeric microbubbles consisting of gas encapsulated in a polydimethylsiloxane shell. These microbubbles withstand large, repeated deformations without rupture. We perform μN-scale compression tests on individual microbubbles and find their response to be highly dependent on the shell permeability; during deformation, the pressure inside impermeable microbubbles increases, resulting in an exponential increase in the applied force. Finite element models are used to interpret and extend these experimental results enabling the design and development of deformable microbubbles with a predictable mechanical response. Such microbubbles can be designed to repeatedly transit through the narrow constrictions found in a porous medium functioning as probes of the local pressure.

3D structure of individual nanocrystals in solution by electron microscopy - Park, Jungwon; Elmlund, Hans; Ercius, Peter; Yuk, Jong Min; Limmer, David T.; Chen, Qian; Kim, Kwanpyo; Han, Sang Hoon; Weitz, David A; Zettl, A.; Alivisatos, A. Paul (Science, 2015)
Knowledge about the synthesis, growth mechanisms, and physical properties of colloidal nanoparticles has been limited by technical impediments. We introduce a method for determining three-dimensional (3D) structures of individual nanoparticles in solution. We combine a graphene liquid cell, high-resolution transmission electron microscopy, a direct electron detector, and an algorithm for single-particle 3D reconstruction originally developed for analysis of biological molecules. This method yielded two 3D structures of individual platinum nanocrystals at near-atomic resolution. Because our method derives the 3D structure from images of individual nanoparticles rotating freely in solution, it enables the analysis of heterogeneous populations of potentially unordered nanoparticles that are synthesized in solution, thereby providing a means to understand the structure and stability of defects at the nanoscale.

Direct Observation of Wet Biological Samples by Graphene Liquid Cell Transmission Electron Microscopy - Park, Jungwon; Park, Hyesung; Ercius, Peter; Pegoraro, Adrian F; Xu, Chen; Kim, Jin Woong; Han, Sang Hoon; Weitz, David A (Nano Letters, 2015)
Recent development of liquid phase transmission electron microscopy (TEM) enables the study of specimens in wet ambient conditions within a liquid cell; however, direct structural observation of biological samples in their native solution using TEM is challenging since low-mass biomaterials embedded in a thick liquid layer of the host cell demonstrate low contrast. Furthermore, the integrity of delicate wet samples is easily compromised during typical sample preparation and TEM imaging. To overcome these limitations, we introduce a graphene liquid cell (GLC) using multilayer graphene sheets to reliably encapsulate and preserve biological samples in a liquid for TEM observation. We achieve nanometer scale spatial resolution with high contrast using low-dose TEM at room temperature, and we use the GLC to directly observe the structure of influenza viruses in their native buffer solution at room temperature. The GLC is further extended to investigate whole cells in wet conditions using TEM. We also demonstrate the potential of the GLC for correlative studies by TEM and fluorescence light microscopy imaging.

High-Throughput Single-Cell Labeling (Hi-SCL) for RNA-Seq Using Drop-Based Microfluidics - Rotem, Assaf; Ram, Oren; Shoresh, Noam; Sperling, Ralph A.; Schnall-Levin, Michael; Zhang, Huidan; Anindita Basu; Bernstein, Bradley E; Weitz, David A (PLoS ONE, 2015)
The importance of single-cell level data is increasingly appreciated, and significant advances in this direction have been made in recent years. Common to these technologies is the need to physically segregate individual cells into containers, such as wells or chambers of a micro-fluidics chip. High-throughput Single-Cell Labeling (Hi-SCL) in drops is a novel method that uses drop-based libraries of oligonucleotide barcodes to index individual cells in a population. The use of drops as containers, and a microfluidics platform to manipulate them en-masse, yields a highly scalable methodological framework. Once tagged, labeled molecules from different cells may be mixed without losing the cell-of-origin information. Here we demonstrate an application of the method for generating RNA-sequencing data for multiple individual cells within a population. Barcoded oligonucleotides are used to prime cDNA synthesis within drops. Barcoded cDNAs are then combined and subjected to second generation sequencing. The data are deconvoluted based on the barcodes, yielding single-cell mRNA expression data. In a proof-of-concept set of experiments we show that this method yields data comparable to other existing methods, but with unique potential for assaying very large numbers of cells.

Mechanics and dynamics of reconstituted cytoskeletal systems - Jensen, Mikkel H.; Morris, Eliza J.; Weitz, David A (Biochimica et Biophysica Acta (BBA) - Molecular Cell Research, 2015)
The intracellular cytoskeleton is an active dynamic network of filaments and associated binding proteins that control key cellular properties, such as cell shape and mechanics. Due to the inherent complexity of the cell, reconstituted model systems have been successfully employed to gain an understanding of the fundamental physics governing cytoskeletal processes. Here, we review recent advances and key aspects of these reconstituted systems. We focus on the importance of assembly kinetics and dynamic arrest in determining network mechanics, and highlight novel emergent behavior occurring through interactions between cytoskeletal components in more complex networks incorporating multiple biopolymers and molecular motors.
Keywords: Active soft matter

Membrane-Integrated Glass Capillary Device for Preparing Small-Sized Water-in-Oil-in-Water Emulsion Droplets - Akamatsu, Kazuki; Kanasugi, Shosuke; Nakao, Shin-ichi; Weitz, David A (Langmuir, 2015)
In this study, a membrane-integrated glass capillary device for preparing small-sized water-in-oil-in-water (W/O/W) emulsion droplets is demonstrated. The concept of integrating microfluidics to prepare precise structure-controlled double emulsion droplets with the membrane emulsification technique provides a simple method for preparing small-sized and structure-controlled double emulsion droplets. The most important feature of the integrated device is the ability to decrease droplet size when the emulsion droplets generated at the capillary pass through the membrane. At the same time, most of the oil shell layer is stripped away and the resultant double emulsion droplets have thin shells. It is also demonstrated that the sizes of the resultant double emulsion droplets are greatly affected by both the double emulsion droplet flux through membranes and membrane pore size; when the flux is increased and membrane pore size is decreased, the generated W/O/W emulsion droplets are smaller than the original. In situ observation of the permeation behavior of the W/O/W emulsion droplets through membranes using a high-speed camera demonstrates (1) the stripping of the middle oil phase, (2) the division of the double emulsion droplets to generate two or more droplets with smaller size, and (3) the collapse of the double emulsion droplets. The first phenomenon results in a thinner oil shell, and the second division phenomenon produces double emulsion droplets that are smaller than the original.

Inhibition of Multidrug Resistance of Cancer Cells by Co-Delivery of DNA Nanostructures and Drugs Using Porous Silicon Nanoparticles@Giant Liposomes - Kong, Feng; Zhang, Xu; Zhang, Hongbo; Qu, Xiangmeng; Chen, Dong; Servos, Mark; Mäkilä, Ermei; Salonen, Jarno; Hélder A. Santos; Hai, Mingtan; Weitz, David A (Advanced Functional Materials, 2015)
Biocompatible, multifunctional, stimuli responsive, and high drug loading capacity are key factors for the new generation of drug delivery platforms. However, it is extremely challenging to create such a platform that inherits all these advanced properties in a single carrier. Herein, porous silicon nanoparticles (PSi NPs) and giant liposomes are assembled on a microfluidic chip as an advanced nano‐in‐micro platform (PSi NPs@giant liposomes), which can co‐load and co‐deliver hydrophilic and hydrophobic drugs combined with synthesized DNA nanostructures, short gold nanorods, and magnetic nanoparticles. The PSi NPs@giant liposomes with photothermal and magnetic responsiveness show good biocompatibility, high loading capacity, and controllable release. The hydrophilic thermal oxidized PSi NPs encapsulate hydrophobic therapeutics within the hydrophilic core of the giant liposomes, endowing high therapeutics loading capacity with tuneable ratio and controllable release. It is demonstrated that the DAO‐E A DNA nanostructures have synergism with drugs and importantly they contribute to the significant enhancement of cell death to doxorubicin‐resistant MCF‐7/DOX cells, overcoming the multidrug resistance in the cancer cells. Therefore, the PSi NPs@giant liposomes nano‐in‐micro platform hold great potential for a cocktail delivery of drugs and DNA nanostructures for effective cancer therapy, controllable drug release with tuneable therapeutics ratio, and both photothermal and magnetic dual responsiveness.
Keywords: DNA nanostructures; drug co-delivery; giant liposomes; gold nanorods; porous silicon nanoparticles

Activity-driven fluctuations in living cells - É. Fodor; Guo, M.; N. S. Gov; P. Visco; Weitz, D. A.; F. van Wijland (EPL (Europhysics Letters), 2015)
We propose a model for the dynamics of a probe embedded in a living cell, where both thermal fluctuations and nonequilibrium activity coexist. The model is based on a confining harmonic potential describing the elastic cytoskeletal matrix, which undergoes random active hops as a result of the nonequilibrium rearrangements within the cell. We describe the probe's statistics and we bring forth quantities affected by the nonequilibrium activity. We find an excellent agreement between the predictions of our model and experimental results for tracers inside living cells. Finally, we exploit our model to arrive at quantitative predictions for the parameters characterizing nonequilibrium activity, such as the typical time scale of the activity and the amplitude of the active fluctuations.

Alpha-actinin binding kinetics modulate cellular dynamics and force generation - Ehrlicher, Allen J.; Krishnan, Ramaswamy; Guo, Ming; Bidan, Cécile M.; Weitz, David A; Pollak, Martin R. (Proceedings of the National Academy of Sciences, 2015)
The actin cytoskeleton is a key element of cell structure and movement whose properties are determined by a host of accessory proteins. Actin cross-linking proteins create a connected network from individual actin filaments, and though the mechanical effects of cross-linker binding affinity on actin networks have been investigated in reconstituted systems, their impact on cellular forces is unknown. Here we show that the binding affinity of the actin cross-linker α-actinin 4 (ACTN4) in cells modulates cytoplasmic mobility, cellular movement, and traction forces. Using fluorescence recovery after photobleaching, we show that an ACTN4 mutation that causes human kidney disease roughly triples the wild-type binding affinity of ACTN4 to F-actin in cells, increasing the dissociation time from 29 ± 13 to 86 ± 29 s. This increased affinity creates a less dynamic cytoplasm, as demonstrated by reduced intracellular microsphere movement, and an approximate halving of cell speed. Surprisingly, these less motile cells generate larger forces. Using traction force microscopy, we show that increased binding affinity of ACTN4 increases the average contractile stress (from 1.8 ± 0.7 to 4.7 ± 0.5 kPa), and the average strain energy (0.4 ± 0.2 to 2.1 ± 0.4 pJ). We speculate that these changes may be explained by an increased solid-like nature of the cytoskeleton, where myosin activity is more partitioned into tension and less is dissipated through filament sliding. These findings demonstrate the impact of cross-linker point mutations on cell dynamics and forces, and suggest mechanisms by which such physical defects lead to human disease.

Hybrid Microgels with Thermo-Tunable Elasticity for Controllable Cell Confinement - Hackelbusch, Sebastian; Rossow, Torsten; Steinhilber, Dirk; Weitz, David A; Seiffert, Sebastian (Advanced Healthcare Materials, 2015)
Stimuli‐responsive hydrogels are able to change their physical properties such as their elastic moduli in response to changes in their environment. If biocompatible polymers are used to prepare such materials and if living cells are encapsulated within these networks, their switchability allows the cell–matrix interactions to be investigated with unprecedented consistency. In this paper, thermo‐responsive macro‐ and microscopic hydrogels are presented based on azide‐functionalized copolymers of poly(N‐(2‐hydroxypropyl)‐methacrylamide) and poly(hydroxyethyl methacrylate) grafted with poly(N‐isopropylacrylamide) side chains. Crosslinking of these comb polymers is realized by bio‐orthogonal strain‐promoted azide–alkyne cycloaddition with cyclooctyne‐functionalized poly(ethylene glycol). The resulting hybrid hydrogels exhibit thermo‐tunable elasticity tailored by the polymer chain length and grafting density. This bio‐orthogonal polymer crosslinking strategy is combined with droplet‐based microfluidics to encapsulate living cells into stimuli‐responsive microgels, proving them to be a suitable platform for future systematic stem‐cell research.
Keywords: cell encapsulation; click chemistry; Microfluidics; thermo-responsive materials

Structure and Strength of Flocs of Precipitated Calcium Carbonate Induced by Various Polymers Used in Papermaking - Gaudreault, Roger; Di Cesare, Nicolas; van de Ven, Theo G. M.; Weitz, David A (Industrial & Engineering Chemistry Research, 2015)
Because of persistent economic pressure on cost reduction, inorganic fillers such as precipitated calcium carbonate (PCC) have become increasingly economically attractive in the papermaking process. The increase of filler level in paper can be achieved by adding it to pulp prior to the headbox, either as individual filler particles or as preaggregates, while maintaining paper strength and minimizing their negative impact. Consequently, the floc structure and strength of PCC aggregates was studied using flocculants and dry strength agents, using static light scattering/diffraction (SLS), real time fluorescent video imaging (RTFVI), image analysis, photometric dispersion analysis (PDA), and scanning electron microscopy (SEM). It was found that PEO/cofactor induced PCC aggregates were weaker at high shear and far more irreversible than those induced by the partially hydrolyzed polyvinyl formamide copolymerized with acrylic acid (PVFA/NaAA) or cationic starch. Flocs produced at low polymer dosages were smaller and weaker than those produced at higher dosages. The number of discrete PCC particles in aggregates was measured using real time fluorescent video imaging combined with image analysis. Finally, we speculate that when two scalenohedral crystal type PCC particles aggregate, there is a small effective surface area to bind them, mainly through classical bridging or charge neutralization flocculation. Moreover, additional polymer adsorption results in higher coverage of the external and internal surfaces and prevents further aggregation due to electrosteric repulsion.

Droplet Barcoding for Single-Cell Transcriptomics Applied to Embryonic Stem Cells - Allon M. Klein; Mazutis, Linas; Akartuna, Ilke; Naren Tallapragada; Veres, Adrian; Li, Victor; Peshkin, Leonid; David A. Weitz; Marc W. Kirschner (Cell, 2015)
It has long been the dream of biologists to map gene expression at the single-cell level. With such data one might track heterogeneous cell sub-populations, and infer regulatory relationships between genes and pathways. Recently, RNA sequencing has achieved single-cell resolution. What is limiting is an effective way to routinely isolate and process large numbers of individual cells for quantitative in-depth sequencing. We have developed a high-throughput droplet-microfluidic approach for barcoding the RNA from thousands of individual cells for subsequent analysis by <a href="https://www.sciencedirect.com/topics/biochemistry-genetics-and-molecular-biology/next-generation-sequencing" title="Learn more about Next Generation Sequencing from ScienceDirect's AI-generated Topic Pages">next-generation sequencing. The method shows a surprisingly low noise profile and is readily adaptable to other sequencing-based assays. We analyzed mouse embryonic stem cells, revealing in detail the population structure and the heterogeneous onset of differentiation after <a href="https://www.sciencedirect.com/topics/biochemistry-genetics-and-molecular-biology/leukemia-inhibitory-factor" title="Learn more about Leukemia Inhibitory Factor from ScienceDirect's AI-generated Topic Pages">leukemia inhibitory factor (LIF) withdrawal. The reproducibility of these high-throughput single-cell data allowed us to deconstruct cell populations and infer gene expression relationships.

Highly Parallel Genome-wide Expression Profiling of Individual Cells Using Nanoliter Droplets - Evan Z. Macosko; Anindita Basu; Rahul Satija; James Nemesh; Karthik Shekhar; Melissa Goldman; Itay Tirosh; Allison R. Bialas; Nolan Kamitaki; Emily M. Martersteck; John J. Trombetta; David A. Weitz; et al. (Cell, 2015)
Cells, the basic units of biological structure and function, vary broadly in type and state. Single-cell genomics can characterize cell identity and function, but limitations of ease and scale have prevented its broad application. Here we describe Drop-seq, a strategy for quickly profiling thousands of individual cells by separating them into nanoliter-sized aqueous droplets, associating a different barcode with each cell’s RNAs, and sequencing them all together. Drop-seq analyzes mRNA transcripts from thousands of individual cells simultaneously while remembering transcripts’ cell of origin. We analyzed transcriptomes from 44,808 mouse retinal cells and identified 39 transcriptionally distinct cell populations, creating a molecular atlas of gene expression for known retinal cell classes and novel candidate cell subtypes. Drop-seq will accelerate biological discovery by enabling routine transcriptional profiling at single-cell resolution.

Control of Emergent Properties at a Correlated Oxide Interface with Graphene - Zhou, You; Park, Jungwon; Shi, Jian; Chhowalla, Manish; Park, Hyesung; Weitz, David A; Ramanathan, Shriram (Nano Letters, 2015)
Electrolyte gating of complex oxides enables investigation of electronic phase boundaries and collective response to strong electric fields. The origin of large conductance modulations and associated emergent properties in such field effect structures is a matter of intense study due to competing contributions from electrostatic (charge accumulation) and electrochemical (crystal chemistry changes) effects. Vanadium dioxide (VO2) is a prototypical correlated insulator that shows an insulator-to-metal transition at ∼67 °C and recent studies have noted a vast range of electronic effects in electric double-layer transistors (EDLT). In this study, we demonstrate that the response of electrolyte gated VO2 devices can be deterministically controlled by inserting a monolayer of graphene at the oxide–electrolyte interface. Several electrolytes as well as dopants (such as lithium ions and protons) were employed in EDL transistors to show that graphene serves as an inert barrier that successfully protects the oxide surface from chemical reactions. This monolayer interface has a striking effect on resistance modulation in the vanadium dioxide transistor channel up to several orders of magnitude and enables retention of the insulating phase. The studies allow new insights into the response of correlated insulators in EDLTs and inform design of correlated oxide–2D heterostructures for electronics and sensors.

Anisotropic elasticity of experimental colloidal Wigner crystals - Russell, Emily R.; Spaepen, Frans; Weitz, David A (Phys. Rev. E, 2015)
Colloidal particles interacting via a long-range repulsion can, in contrast to hard-sphere systems, exhibit crystalline ordering at low volume fraction. Here we experimentally investigate the structure and properties of such “colloidal Wigner crystals.” We find a body-centered-cubic crystalline phase at volume fractions of ϕ≳15%, which exhibits large fluctuations of individual particles from their average positions. We determine the three independent crystalline elastic constants and find that these crystals are very compliant and highly anisotropic.

Colloidal Polymers with Controlled Sequence and Branching Constructed from Magnetic Field Assembled Nanoparticles - Bannwarth, Markus B.; Utech, Stefanie; Ebert, Sandro; Weitz, David A; Crespy, Daniel; Landfester, Katharina (ACS Nano, 2015)
The assembly of nanoparticles into polymer-like architectures is challenging and usually requires highly defined colloidal building blocks. Here, we show that the broad size-distribution of a simple dispersion of magnetic nanocolloids can be exploited to obtain various polymer-like architectures. The particles are assembled under an external magnetic field and permanently linked by thermal sintering. The remarkable variety of polymer–analogue architectures that arises from this simple process ranges from statistical and block copolymer-like sequencing to branched chains and networks. This library of architectures can be realized by controlling the sequencing of the particles and the junction points via a size-dependent self-assembly of the single building blocks.

Crystallization and reentrant melting of charged colloids in nonpolar solvents - Kanai, Toshimitsu; Boon, Niels; Lu, Peter J.; Sloutskin, Eli; Schofield, Andrew B.; Smallenburg, Frank; van Roij, René; Dijkstra, Marjolein; Weitz, David A (Phys. Rev. E, 2015)
We explore the crystallization of charged colloidal particles in a nonpolar solvent mixture. We simultaneously charge the particles and add counterions to the solution with aerosol-OT (AOT) reverse micelles. At low AOT concentrations, the charged particles crystallize into body-centered-cubic (bcc) or face-centered-cubic (fcc) Wigner crystals; at high AOT concentrations, the increased screening drives a thus far unobserved reentrant melting transition. We observe an unexpected scaling of the data with particle size, and account for all behavior with a model that quantitatively predicts both the reentrant melting and the data collapse.

Graphene-templated directional growth of an inorganic nanowire - Lee, Won Chul; Kim, Kwanpyo; Park, Jungwon; Koo, Jahyun; Jeong, Hu Young; Lee, Hoonkyung; Weitz, David A; Zettl, Alex; Takeuchi, Shoji (Nature Nanotechnology, 2015)
<section aria-labelledby="Abs2" data-gtm-vis-first-on-screen-10482319_393="1375" data-gtm-vis-first-on-screen-10482319_401="1368" data-gtm-vis-has-fired-10482319_393="1" data-gtm-vis-has-fired-10482319_401="1" data-gtm-vis-recent-on-screen-10482319_393="1374" data-gtm-vis-recent-on-screen-10482319_401="1368" data-gtm-vis-total-visible-time-10482319_393="10000" data-gtm-vis-total-visible-time-10482319_401="10000" data-title="Abstract" lang="en"> Assembling inorganic nanomaterials on graphene is of interest in the development of nanodevices and nanocomposite materials, and the ability to align such inorganic nanomaterials on the graphene surface is expected to lead to improved functionalities, as has previously been demonstrated with organic nanomaterials epitaxially aligned on graphitic surfaces. However, because graphene is chemically inert, it is difficult to precisely assemble inorganic nanomaterials on pristine graphene. Previous techniques based on dangling bonds of damaged graphene, intermediate seed materials and vapour-phase deposition at high temperature have only formed randomly oriented or poorly aligned inorganic nanostructures. Here, we show that inorganic nanowires of gold(I) cyanide can grow directly on pristine graphene, aligning themselves with the zigzag lattice directions of the graphene. The nanowires are synthesized through a self-organized growth process in aqueous solution at room temperature, which indicates that the inorganic material spontaneously binds to the pristine graphene surface. First-principles calculations suggest that this assembly originates from lattice matching and π interaction to gold atoms. Using the synthesized nanowires as templates, we also fabricate nanostructures with controlled crystal orientations such as graphene nanoribbons with zigzag-edged directions.

A high-throughput drop microfluidic system for virus culture and analysis - Fischer, Audrey E.; Wu, Susan K.; Proescher, Jody B. G.; Rotem, Assaf; Chang, Connie B.; Zhang, Huidan; Tao, Ye; Mehoke, Thomas S.; Thielen, Peter M.; Kolawole, Abimbola O.; Smith, Thomas J.; Wobus, Christiane E.; et al. (Journal of Virological Methods, 2015)
High mutation rates and short replication times lead to rapid evolution in RNA viruses. New tools for high-throughput culture and analysis of viral phenotypes will enable more effective studies of viral evolutionary processes. A water-in-oil drop microfluidic system to study virus–cell interactions at the single event level on a massively parallel scale is described here. Murine norovirus (MNV-1) particles were co-encapsulated with individual RAW 264.7 cells in 65 pL aqueous drops formed by flow focusing in 50 μm microchannels. At low multiplicity of infection (MOI), viral titers increased greatly, reaching a maximum 18 h post-encapsulation. This system was employed to evaluate MNV-1 escape from a neutralizing monoclonal antibody (clone A6.2). Further, the system was validated as a means for testing escape from antibody neutralization using a series of viral point mutants. Finally, the replicative capacity of single viral particles in drops under antibody stress was tested. Under standard conditions, many RNA virus stocks harbor minority populations of genotypic and phenotypic variants, resulting in quasispecies. These data show that when single cells are encapsulated with single viral particles under antibody stress without competition from other virions, the number of resulting infectious particles is nearly equivalent to the number of viral genomes present. These findings suggest that lower fitness virions can infect cells successfully and replicate, indicating that the microfluidics system may serve as an effective tool for isolating mutants that escape evolutionary stressors.
Keywords: Microfluidics Murine norovirus Antibody neutralization Evolution

Intermediate filament mechanics in vitro and in the cell: from coiled coils to filaments, fibers and networks - Köster, Sarah; Weitz, David A; Robert D. Goldman; Aebi, Ueli; Herrmann, Harald (Current Opinion in Cell Biology, 2015)
Intermediate filament proteins form filaments, fibers and networks both in the cytoplasm and the nucleus of metazoan cells. Their general structural building plan accommodates highly varying amino acid sequences to yield extended dimeric α-helical coiled coils of highly conserved design. These ‘rod’ particles are the basic building blocks of intrinsically flexible, filamentous structures that are able to resist high mechanical stresses, that is, bending and stretching to a considerable degree, both in vitro and in the cell. Biophysical and computer modeling studies are beginning to unfold detailed structural and mechanical insights into these major supramolecular assemblies of cell architecture, not only in the ‘test tube’ but also in the cellular and tissue context.

Emergent properties of composite semiflexible biopolymer networks - Jensen, Mikkel H.; Morris, Eliza J.; Robert D. Goldman; Weitz, David A (BioArchitecture, 2015)
The semiflexible polymers filamentous actin (F-actin) and intermediate filaments (IF) both form complex networks within the cell, and together are key determinants of cellular stiffness. While the mechanics of F-actin networks together with stiff microtubules have been characterized, the interplay between F-actin and IF networks is largely unknown, necessitating the study of composite networks using mixtures of semiflexible biopolymers. We employ bulk rheology in a simplified in vitro system to uncover the fundamental mechanical interactions between networks of the 2 semiflexible polymers, F-actin and vimentin IF. Surprisingly, co-polymerization of actin and vimentin can produce composite networks either stronger or weaker than pure F-actin networks. We show that this effect occurs through steric constraints imposed by IF on F-actin during network formation and filament crosslinking, highlighting novel emergent behavior in composite semiflexible networks.

Microcapsules for Enhanced Cargo Retention and Diversity - Zieringer, Maximilian A.; Carroll, Nick J.; Abbaspourrad, Alireza; Koehler, Stephan A.; Weitz, David A (Small, 2015)
Prevention of undesired leakage of encapsulated materials prior to triggered release presents a technological challenge for the practical application of microcapsule technologies in agriculture, drug delivery, and cosmetics. A microfluidic approach is reported to fabricate perfluoropolyether (PFPE)‐based microcapsules with a high core‐shell ratio that show enhanced retention of encapsulated actives. For the PFPE capsules, less than 2% leakage of encapsulated model compounds, including Allura Red and CaCl2, over a four week trial period is observed. In addition, PFPE capsules allow cargo diversity by the fabrication of capsules with either a water‐in‐oil emulsion or an organic solvent as core. Capsules with a toluene‐based core begin a sustained release of hydrophobic model encapsulants immediately upon immersion in an organic continuous phase. The major contribution on the release kinetics stems from the toluene in the core. Furthermore, degradable silica particles are incorporated to confer porosity and functionality to the otherwise chemically inert PFPE‐based polymer shell. These results demonstrate the capability of PFPE capsules with large core–shell ratios to retain diverse sets of cargo for extended periods and make them valuable for controlled release applications that require a low residual footprint of the shell material.
Keywords: encapsulation; microcapsules; Microfluidics; perfluoropolyethers; retention

Polyurea Microcapsules in Microfluidics: Surfactant Control of Soft Membranes - Polenz, Ingmar; Weitz, David A; Baret, Jean-Christophe (Langmuir, 2015)
Interfacial polymerization techniques offer a versatile route for microcapsule synthesis. We designed a microfluidic process to synthesize monodisperse polyurea microcapsules (PUMCs); the microcapsules are formed by an interfacial polymerization of isocyanate dissolved in the oil and an amine dissolved in water. We measure the mechanical properties of the capsule as well as transport properties through the membrane using two microfluidic methods. We show that the elasticity and the permeability of the shell are controlled by surfactant additives, added during the synthesis. The control of the nanostructure of the shell by surfactants provides new means to design encapsulation systems with tailored mechanical and physicochemical properties.

Chemically induced coalescence in droplet-based microfluidics - Akartuna, Ilke; Aubrecht, Donald M.; Kodger, Thomas E.; Weitz, David A (Lab Chip, 2015)
We present a new microfluidic method to coalesce pairs of surfactant-stabilized water-in-fluorocarbon oil droplets. We achieve this through the local addition of a poor solvent for the surfactant{,} perfluorobutanol{,} which induces cohesion between droplet interfaces causing them to merge. The efficiency of this technique is comparable to existing techniques providing an alternative method to coalesce pairs of droplets.

Protein Microgels from Amyloid Fibril Networks - Shimanovich, Ulyana; Efimov, Igor; Mason, Thomas O.; Flagmeier, Patrick; Buell, Alexander Kai; Gedanken, Aharon; Linse, Sara; Åkerfeldt, Karin Stigsdotter; Dobson, Christopher M; Weitz, David A; Knowles, Tuomas P. J. (ACS Nano, 2015)
Nanofibrillar forms of proteins were initially recognized in the context of pathology, but more recently have been discovered in a range of functional roles in nature, including as active catalytic scaffolds and bacterial coatings. Here we show that protein nanofibrils can be used to form the basis of monodisperse microgels and gel shells composed of naturally occurring proteins. We explore the potential of these protein microgels to act as drug carrier agents, and demonstrate the controlled release of four different encapsulated drug-like small molecules, as well as the component proteins themselves. Furthermore, we show that protein nanofibril self-assembly can continue after the initial formation of the microgel particles, and that this process results in active materials with network densities that can be modulated in situ. We demonstrate that these materials are nontoxic to human cells and that they can be used to enhance the efficacy of antibiotics relative to delivery in homogeneous solution. Because of the biocompatibility and biodegradability of natural proteins used in the fabrication of the microgels, as well as their ability to control the release of small molecules and biopolymers, protein nanofibril microgels represent a promising class of functional artificial multiscale materials generated from natural building blocks.

Light-Directing Omnidirectional Circularly Polarized Reflection from Liquid-Crystal Droplets - Fan, Jing; Li, Yannian; Bisoyi, Hari Krishna; Zola, Rafael S.; Yang, Deng-ke, Bunning, Timothy J., Weitz, David A., Li, Quan (Angewandte Chemie International Edition, 2014)
Constructing and tuning self‐organized three‐dimensional (3D) superstructures with tailored functionality is crucial in the nanofabrication of smart molecular devices. Herein we fabricate a self‐organized, phototunable 3D photonic superstructure from monodisperse droplets of one‐dimensional cholesteric liquid crystal (CLC) containing a photosensitive chiral molecular switch with high helical twisting power. The droplets are obtained by a glass capillary microfluidic technique by dispersing into PVA solution that facilitates planar anchoring of the liquid‐crystal molecules at the droplet surface, as confirmed by the observation of normal incidence selective circular polarized reflection in all directions from the core of individual droplet. Photoirradiation of the droplets furnishes dynamic reflection colors without thermal relaxation, whose wavelength can be tuned reversibly by variation of the irradiation time. The results provided clear evidence on the phototunable reflection in all directions.

Osmotic-pressure-controlled concentration of colloidal particles in thin-shelled capsules - Kim, Shin-Hyun; Park, Jin-Gyu; Choi, Tae Min; Vinothan N. Manoharan; Weitz, David A (Nature communications, 2014)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="1008" data-gtm-vis-first-on-screen-10482319_401="1077" data-gtm-vis-polling-id-10482319_393="82" data-gtm-vis-polling-id-10482319_401="93" data-gtm-vis-recent-on-screen-10482319_393="1008" data-gtm-vis-recent-on-screen-10482319_401="1077" data-gtm-vis-total-visible-time-10482319_393="5300" data-gtm-vis-total-visible-time-10482319_401="5400" data-title="Abstract" lang="en"> Colloidal crystals are promising structures for photonic applications requiring dynamic control over optical properties. However, for ease of processing and reconfigurability, the crystals should be encapsulated to form ‘ink’ capsules rather than confined in a thin film. Here we demonstrate a class of encapsulated colloidal photonic structures whose optical properties can be controlled through osmotic pressure. The ordering and separation of the particles within the microfluidically created capsules can be tuned by changing the colloidal concentration through osmotic pressure-induced control of the size of the individual capsules, modulating photonic stop band. The rubber capsules exhibit a reversible change in the diffracted colour, depending on osmotic pressure, a property we call osmochromaticity. The high encapsulation efficiency and capsule uniformity of this microfluidic approach, combined with the highly reconfigurable shapes and the broad control over photonic properties, make this class of structures particularly suitable for photonic applications such as electronic inks and reflective displays.

Reply to the ‘Comment on “Wetting-induced formation of controllable monodisperse multiple emulsions in microfluidics”’by J. Guzowski and P. Garstecki, Lab Chip, 2014, 14, DOI: 10.1039/C3LC51229K - Deng, Nan-Nan; Wang, Wei; Ju, Xiao-Jie; Xie, Rui; Weitz, David A; Chu, Liang-Yin (Lab on a Chip, 2014)
A graphical abstract is available for this content.

Platelet bioreactor-on-a-chip - Thon, Jonathan N; Mazutis, Linas; Wu, Stephen; Sylman, Joanna L; Ehrlicher, Allen; Machlus, Kellie R; Feng, Qiang; Lu, Shijiang; Lanza, Robert; Neeves, Keith B; Weitz, David A; Italiano, Joseph E (Blood, 2014)
Jonathan N. Thon1,2,3, Linas Mazutis3,4,5, Stephen Wu1, Joanna L. Sylman6, Allen Ehrlicher4,7, Kellie R. Machlus1,2, Qiang Feng8, Shijiang Lu8, Robert Lanza8, Keith B. Neeves6,9, David A. Weitz4, and Joseph E. Italiano Jr1,2,3,101Department of Medicine, Brigham and Women’s Hospital, Boston, MA; 2Harvard Medical School, Boston, MA; 3Platelet BioGenesis, Chestnut Hill, MA; 4School of Engineering and Applied Sciences, Harvard University, Cambridge, MA; 5Institute of Biotechnology, Vilnius University, Vilnius, Lithuania; 6Department of Chemical and Biological Engineering, Colorado School of Mines, Golden, CO; 7Department of Bioengineering, McGill University, Montreal, Canada; 8Advanced Cell Technologies, Marlborough, MA; 9Department of Pediatrics, University of Colorado, Denver, Aurora, CO; and 10Department of Surgery, Vascular Biology Program, Boston Children’s Hospital, Boston, MAKey PointsWe have developed a biomimetic microfluidic platelet bioreactor that recapitulates bone marrow and blood vessel microenvironments.Application of shear stress in this bioreactor triggers physiological proplatelet production, and platelet release.AbstractPlatelet transfusions total >2.17 million apheresis-equivalent units per year in the United States and are derived entirely from human donors, despite clinically significant immunogenicity, associated risk of sepsis, and inventory shortages due to high demand and 5-day shelf life. To take advantage of known physiological drivers of thrombopoiesis, we have developed a microfluidic human platelet bioreactor that recapitulates bone marrow stiffness, extracellular matrix composition, micro-channel size, hemodynamic vascular shear stress, and endothelial cell contacts, and it supports high-resolution live-cell microscopy and quantification of platelet production. Physiological shear stresses triggered proplatelet initiation, reproduced ex vivo bone marrow proplatelet production, and generated functional platelets. Modeling human bone marrow composition and hemodynamics in vitro obviates risks associated with platelet procurement and storage to help meet growing transfusion needs.Submitted May 9, 2014.Accepted July 8, 2014.© 2014 by The American Society of Hematology

Sorting drops and cells with acoustics: acoustic microfluidic fluorescence-activated cell sorter - Schmid, Lothar; Weitz, David A; Franke, Thomas (Lab Chip, 2014)
We describe a versatile microfluidic fluorescence-activated cell sorter that uses acoustic actuation to sort cells or drops at ultra-high rates. Our acoustic sorter combines the advantages of traditional fluorescence-activated cell (FACS) and droplet sorting (FADS) and is applicable for a multitude of objects. We sort aqueous droplets{,} at rates as high as several kHz{,} into two or even more outlet channels. We can also sort cells directly from the medium without prior encapsulation into drops; we demonstrate this by sorting fluorescently labeled mouse melanoma cells in a single phase fluid. Our acoustic microfluidic FACS is compatible with standard cell sorting cytometers{,} yet{,} at the same time{,} enables a rich variety of more sophisticated applications.

Pattern Formation of Charged Particles in an Electric Field - Lin, Tina; Rubinstein, Shmuel M; Korchev, Andriy; Weitz, David A (Langmuir, 2014)
The application of an electric field to a suspension of charged particles can lead to the formation of patterns due to electrohydrodynamic instabilities which remain poorly understood. We elucidate this behavior by visualizing the dynamics of charged carbon black particles suspended in a nonpolar solvent in response to an electric field. As the particles are transported across a microfluidic channel, an instability occurs in which the initially uniform, rapidly advancing particle front develops fingers. Furthermore, when the direction of the applied field is repeatedly switched, the particles localize into a remarkably well-defined periodic pattern which reflects an interplay between the fingering instability and particle diffusion.

Controlling the Morphology of Polyurea Microcapsules Using Microfluidics - Polenz, Ingmar; Datta, Sujit S.; Weitz, David A (Langmuir, 2014)
We use microfluidics to continuously produce monodisperse polyurea microcapsules (PUMCs) having either aqueous or nonaqueous cores. The microcapsule shells are formed by the reaction between an isocyanate, dissolved in oil, and an amine, dissolved in water, at the surface of oil-in-water or water-in-oil drops immediately as they are formed. Different microcapsule morphologies can be generated using our approach. The thickness of the microcapsule shell increases with an increase in the amine solubility in the oil; this finding provides a simple mechanism by which the PUMC shell thickness can be controlled.

The kitchen as a physics classroom - Rowat, Amy C.; Sinha, Naveen N.; Pia M Sörensen; Otger Campàs; Pere Castells; Daniel Rosenberg; Michael P. Brenner; Weitz, David A (Physics Education, 2014)
Cooking is a tangible, familiar, and delicious tool for teaching physics, which is easy to implement in a university setting. Through our courses at Harvard and UCLA, each year we are engaging hundreds of undergraduate students, primarily non-science majors, in science concepts and the scientific research process. We find that weekly lectures by chefs and professors, paired with edible lab experiments, generate enthusiasm and provide strong motivation for students to learn physics. By the end of the course, students are able to conduct independent scientific research and present their results in a final science fair. Given the considerable broad appeal of food and cooking, the topic could be adapted to other post-secondary as well as secondary-level courses.

Microfluidic Fabrication of Perfluorohexane-Shelled Double Emulsions for Controlled Loading and Acoustic-Triggered Release of Hydrophilic Agents - Duncanson, Wynter J.; Arriaga, Laura R.; Ung, W. Lloyd; Kopechek, Jonathan; Porter, Tyrone; Weitz, David A (Langmuir, 2014)
The ability of low boiling point liquid perfluorocarbons (PFCs) to undergo a phase change from a liquid to a gas upon ultrasound irradiation makes PFC-based emulsions promising vehicles for triggered delivery of payloads. However, loading hydrophilic agents into PFC-based emulsions is difficult due to their insolubility in PFC. Here, we address this challenge by taking advantage of microfluidic technologies to fabricate double emulsions consisting of large aqueous cores and a perfluorohexane (PFH) shell, thus yielding high loading capacities for hydrophilic agents. Using this technology, we efficiently encapsulate a model hydrophilic agent within the emulsions and study its response to ultrasound irradiation. Using a combination of optical and acoustic imaging methods, we observe payload release upon acoustic vaporization of PFH. Our work demonstrates the utility of microfluidic techniques for controllably loading hydrophilic agents into PFH-based emulsions, which have great potential for acoustically triggered release.

Local shear transformations in deformed and quiescent hard-sphere colloidal glasses - Jensen, K. E.; Weitz, D. A.; F. Spaepen (Physical Review E, 2014)
We perform a series of deformation experiments on a monodisperse, hard-sphere colloidal glass while simultaneously following the three-dimensional trajectories of roughly 50000 individual particles with a confocal microscope. In each experiment, we deform the glass in pure shear at a constant strain rate [(1–5)×10−5 s−1] to maximum macroscopic strains (5%–10%) and then reverse the deformation at the same rate to return to zero macroscopic strain. We also measure three-dimensional particle trajectories in an identically prepared quiescent glass in which the macroscopic strain is always zero. We find that shear transformation zones exist and are active in both sheared and quiescent colloidal glasses, revealed by a distinctive fourfold signature in spatial autocorrelations of the local shear strain. With increasing shear, the population of local shear transformations develops more quickly than in a quiescent glass and many of these transformations are irreversible. When the macroscopic strain is reversed, we observe partial elastic recovery, followed by plastic deformation of the opposite sign, required to compensate for the irreversibly transformed regions. The average diameter of the shear transformation zones in both strained and quiescent glasses is slightly more than two particle diameters.

Uncovering the Mechanism of Trapping and Cell Orientation during Neisseria gonorrhoeae Twitching Motility - Zaburdaev, Vasily; Biais, Nicolas; Schmiedeberg, Michael; Eriksson, Jens; Jonsson, Ann-Beth; Sheetz, Michael P.; David A. Weitz (2014)
AbstractNeisseria gonorrheae bacteria are the causative agent of the second most common sexually transmitted infection in the world. The bacteria move on a surface by means of twitching motility. Their movement is mediated by multiple long and flexible filaments, called type IV pili, that extend from the cell body, attach to the surface, and retract, thus generating a pulling force. Moving cells also use pili to aggregate and form microcolonies. However, the mechanism by which the pili surrounding the cell body work together to propel bacteria remains unclear. Understanding this process will help describe the motility of N. gonorrheae bacteria, and thus the dissemination of the disease which they cause. In this article we track individual twitching cells and observe that their trajectories consist of alternating moving and pausing intervals, while the cell body is preferably oriented with its wide side toward the direction of motion. Based on these data, we propose a model for the collective pili operation of N. gonorrheae bacteria that explains the experimentally observed behavior. Individual pili function independently but can lead to coordinated motion or pausing via the force balance. The geometry of the cell defines its orientation during motion. We show that by changing pili substrate interactions, the motility pattern can be altered in a predictable way. Although the model proposed is tangibly simple, it still has sufficient robustness to incorporate further advanced pili features and various cell geometries to describe other bacteria that employ pili to move on surfaces.

Fluctuations in flow produced by competition between apparent wall slip and dilatancy - Larsen, RyanJ.; Kim, Jin-Woong; Zukoski, CharlesF.; Weitz, David A (Rheologica Acta, 2014)
Dense suspensions can exhibit a dramatic stress-induced transition from liquid-like to solid-like behavior. In many materials, the solid-like flow state is characterized by large flow fluctuations and instabilities. Although various experiments have been performed to characterize flow fluctuations, the mechanisms that govern the flow instabilities remain poorly understood. To elucidate these mechanisms, we characterize a system that rapidly fluctuates between two flow states. One of the flow states is dominated by apparent wall slip, and the other is dominated by dilatancy. The dilatant regime occurs at elevated stresses and is associated with reduced wall slip, whereas the wall slip-dominated regime occurs at lower stresses. At stresses that are intermediate between these two regimes, the material fluctuates between the two regimes in a semi-regular fashion. Our analysis of the fluctuations at millisecond timescales shows that fluctuations occur because neither regime is capable of supporting a constant stress in a stable manner. We rationalize our results in terms of the differences in the shear-induced particle pressure between regions that are particle-rich and regions of slip that are particle-depleted.
Keywords: Dilatancy; Flow fluctuations; Normal stress; Shear thickening; Slip velocity; Wall slip

Cross-Kingdom Chemical Communication Drives a Heritable, Mutually Beneficial Prion-Based Transformation of Metabolism - Daniel F. Jarosz; Jessica C.S. Brown; Gordon A. Walker; Manoshi S. Datta; W. Lloyd Ung; Alex K. Lancaster; Rotem, Assaf; Amelia Chang; Gregory A. Newby; David A. Weitz; Linda F. Bisson; Susan Lindquist (Cell, 2014)
Summary In experimental science, organisms are usually studied in isolation, but in the wild, they compete and cooperate in complex communities. We report a system for cross-kingdom communication by which bacteria heritably transform yeast metabolism. An ancient biological circuit blocks yeast from using other carbon sources in the presence of glucose. [GAR+], a protein-based epigenetic element, allows yeast to circumvent this “glucose repression” and use multiple carbon sources in the presence of glucose. Some bacteria secrete a chemical factor that induces [GAR+]. [GAR+] is advantageous to bacteria because yeast cells make less ethanol and is advantageous to yeast because their growth and long-term viability is improved in complex carbon sources. This cross-kingdom communication is broadly conserved, providing a compelling argument for its adaptive value. By heritably transforming growth and survival strategies in response to the selective pressures of life in a biological community, [GAR+] presents a unique example of Lamarckian inheritance.

Microfluidic high-throughput culturing of single cells for selection based on extracellular metabolite production or consumption - Wang, Benjamin L; Ghaderi, Adel; Zhou, Hang; Agresti, Jeremy; Weitz, David A; Fink, Gerald R; Stephanopoulos, Gregory (Nat Biotech, 2014)
Phenotyping single cells based on the products they secrete or consume is a key bottleneck in many biotechnology applications, such as combinatorial metabolic engineering for the overproduction of secreted metabolites. Here we present a flexible high-throughput approach that uses microfluidics to compartmentalize individual cells for growth and analysis in monodisperse nanoliter aqueous droplets surrounded by an immiscible fluorinated oil phase. We use this system to identify xylose-overconsuming Saccharomyces cerevisiae cells from a population containing one such cell per 104 cells and to screen a genomic library to identify multiple copies of the xylose isomerase gene as a genomic change contributing to high xylose consumption, a trait important for lignocellulosic feedstock utilization. We also enriched L-lactate-producing Escherichia coli clones 5,800[times] from a population containing one L-lactate producer per 104D-lactate producers. Our approach has broad applications for single-cell analyses, such as in strain selection for the overproduction of fuels, chemicals and pharmaceuticals.

Microfluidics-assisted engineering of polymeric microcapsules with high encapsulation efficiency for protein drug delivery - Jenni Pessi; Hélder A. Santos; Inna Miroshnyk; JoukoYliruusi; Weitz, David A; Mirza, Sabiruddin (International Journal of Pharmaceutics, 2014)
Abstract In this study, microfluidic technology was employed to develop protein formulations. The microcapsules were produced with a biphasic flow to create water–oil–water (W/O/W) double emulsion droplets with ultrathin shells. Optimized microcapsule formulations containing 1% (w/w) bovine serum albumin (BSA) in the inner phase were prepared with poly(vinyl alcohol), polycaprolactone and polyethylene glycol. All the particles were found to be intact and with a particle size of 23–47 μm. Furthermore, the particles were monodisperse, non-porous and stable up to 4 weeks. The encapsulation efficiency of \{BSA\} in the microcapsules was 84%. The microcapsules released 30% of their content within 168 h. This study demonstrates that microfluidics is a powerful technique for engineering formulations for therapeutic proteins.
Keywords: Drug delivery

Probing the Stochastic, Motor-Driven Properties of the Cytoplasm Using Force Spectrum Microscopy - Guo, Ming; Ehrlicher, Allen J.; Jensen, Mikkel H.; Renz, Malte; Jeffrey R. Moore; Goldman, Robert D.; Lippincott-Schwartz, Jennifer; Mackintosh, Frederick C.; David A. Weitz (Cell, 2014)
Molecular motors in cells typically produce highly directed motion; however, the aggregate, incoherent effect of all active processes also creates randomly fluctuating forces, which drive diffusive-like, nonthermal motion. Here, we introduce force-spectrum-microscopy (FSM) to directly quantify random forces within the cytoplasm of cells and thereby probe stochastic motor activity. This technique combines measurements of the random motion of probe particles with independent micromechanical measurements of the cytoplasm to quantify the spectrum of force fluctuations. Using FSM, we show that force fluctuations substantially enhance intracellular movement of small and large components. The fluctuations are three times larger in malignant cells than in their benign counterparts. We further demonstrate that vimentin acts globally to anchor organelles against randomly fluctuating forces in the cytoplasm, with no effect on their magnitude. Thus, FSM has broad applications for understanding the cytoplasm and its intracellular processes in relation to cell physiology in healthy and diseased states.

Expansion and rupture of charged microcapsules - Datta, Sujit S.; Abbaspourrad, Alireza; Weitz, David A (Mater. Horiz., 2014)
We study the deformations of pH-responsive spherical microcapsules - micrometer-scale liquid drops surrounded by thin{,} solid shells - under the influence of electrostatic forces. When exposed to a large concentration of NaOH{,} the microcapsules become highly charged{,} and expand isotropically. We find that the extent of this expansion can be understood by coupling electrostatics with shell theory; moreover{,} the expansion dynamics is well described by Darcy{'}s law for fluid flow through the microcapsule shell. Unexpectedly{,} however{,} below a threshold NaOH concentration{,} the microcapsules begin to disintegrate{,} and eventually rupture; they then expand non-uniformly{,} ultimately forming large{,} jellyfish-like structures. Our results highlight the fascinating range of behaviors exhibited by pH-responsive microcapsules{,} driven by the interplay between electrostatic and mechanical forces.

Measurement of Flow Velocity and Inference of Liquid Viscosity in a Microfluidic Channel by Fluorescence Photobleaching - Carroll, Nick J.; Jensen, Kaare H.; Parsa, Shima; Holbrook, N Michele; Weitz, David A (Langmuir, 2014)
We present a simple, noninvasive method for simultaneous measurement of flow velocity and inference of liquid viscosity in a microfluidic channel. We track the dynamics of a sharp front of photobleached fluorescent dye using a confocal microscope and measure the intensity at a single point downstream of the initial front position. We fit an exact solution of the advection diffusion equation to the fluorescence intensity recovery curve to determine the average flow velocity and the diffusion coefficient of the tracer dye. The dye diffusivity is correlated to solute concentration to infer rheological properties of the liquid. This technique provides a simple method for simultaneous elucidation of flow velocity and liquid viscosity in microchannels.

A high-throughput cellulase screening system based on droplet microfluidics - Ostafe, Raluca; Prodanovic, Radivoje; Ung, W. Lloyd; Weitz, David A; Fischer, Rainer (Biomicrofluidics, 2014)
A new ultra-high-throughput screening assay for the detection of cellulase activity was developed based on microfluidic sorting. Cellulase activity is detected using a series of coupled enzymes leading to the formation of a fluorescent product that can be detected on a chip. Using this method, we have achieved up to 300-fold enrichments of the active population of cells and greater than 90% purity after just one sorting round. In addition, we proved that we can sort the cellulase-expressing cells from mixtures containing less than 1% active cells.

Fluid breakup during simultaneous two-phase flow through a three-dimensional porous medium - Datta, Sujit S.; Dupin, Jean-Baptiste; Weitz, David A (Physics of Fluids, 2014)
We use confocal microscopy to directly visualize the simultaneous flow of both a wetting and a non-wetting fluid through a model three-dimensional (3D) porous medium. We find that, for small flow rates, both fluids flow through unchanging, distinct, connected 3D pathways; in stark contrast, at sufficiently large flow rates, the non-wetting fluid is broken up into discrete ganglia. By performing experiments over a range of flow rates, using fluids of different viscosities, and with porous media having different geometries, we show that this transition can be characterized by a state diagram that depends on the capillary numbers of both fluids, suggesting that it is controlled by the competition between the viscous forces exerted on the flowing oil and the capillary forces at the pore scale. Our results thus help elucidate the diverse range of behaviors that arise in two-phase flow through a 3D porous medium.

Photoresponsive Monodisperse Cholesteric Liquid Crystalline Microshells for Tunable Omnidirectional Lasing Enabled by a Visible Light-Driven Chiral Molecular Switch - Chen, Lujian; Li, Yannian; Fan, Jing; Bisoyi, Hari Krishna; Weitz, David A; Li, Quan (Advanced Optical Materials, 2014)
A self‐organized, phototunable 3D photonic superstructure is fabricated from a photoresponsive 1D liquid crystal using microfluidics. The resulting microshells are water–oil–water double emulsions, in which the oil phase consists of the photoresponsive liquid crystals. The cholesteric microshells exhibit band‐edge lasing in all directions, and the wavelength of the resultant band‐edge laser is tuned via the pumping laser, causing photoisomerization of the chiral molecular switch.
Keywords: chiral; lasing; Liquid Crystals; Microfluidics; microshells; molecular switches; photoresponse

Ultrathin Shell Double Emulsion Templated Giant Unilamellar Lipid Vesicles with Controlled Microdomain Formation - Arriaga, Laura R.; Datta, Sujit S.; Kim, Shin-Hyun; Amstad, Esther; Kodger, Thomas E.; Monroy, Francisco; Weitz, David A (Small, 2014)
A microfluidic approach is reported for the high-throughput, continuous production of giant unilamellar vesicles (GUVs) using water-in-oil-in-water double emulsion drops as templates. Importantly, these emulsion drops have ultrathin shells; this minimizes the amount of residual solvent that remains trapped within the GUV membrane, overcoming a major limitation of typical microfluidic approaches for GUV fabrication. This approach enables the formation of microdomains, characterized by different lipid compositions and structures within the GUV membranes. This work therefore demonstrates a straightforward and versatile approach to GUV fabrication with precise control over the GUV size, lipid composition and the formation of microdomains within the GUV membrane.
Keywords: giant unilamellar vesicles; lipid membrane; lipid microdomains; lipid vesicles; Microfluidics

Spatial Propagation of Protein Polymerization - Cohen, S. I. A.; Rajah, L.; Yoon, C. H.; Buell, A. K.; White, D. A.; Sperling, R. A.; Vendruscolo, M; Terentjev, E. M.; Dobson, C. M.; Weitz, D. A.; Knowles, T. P. J. (Physical Review Letters, 2014)
We consider the spatial dependence of filamentous protein self-assembly. Through studying the cases where the spreading of aggregated material is dominated either by diffusion or by growth, we derive analytical results for the spatial evolution of filamentous protein aggregation, which we validate against Monte Carlo simulations. Moreover, we compare the predictions of our theory with experimental measurements of two systems for which we identify the propagation as either growth or diffusion controlled. Our results connect the macroscopic observables that characterize the spatial propagation of protein self-assembly with the underlying microscopic processes and provide physical limits on spatial propagation and prionlike behavior associated with protein aggregation.

Mechanism of Calponin Stabilization of Cross-Linked Actin Networks - Mikkel Herholdt Jensen; Eliza J. Morris; Cynthia M. Gallant; Kathleen G. Morgan; David A. Weitz; Jeffrey R. Moore (Biophysical Journal, 2014)
The actin-binding protein calponin has been previously implicated in actin cytoskeletal regulation and is thought to act as an actin stabilizer, but the mechanism of its function is poorly understood. To investigate this underlying physical mechanism, we studied an in vitro model system of cross-linked actin using bulk rheology. Networks with basic calponin exhibited a delayed onset of strain stiffening (10.0% without calponin, 14.9% with calponin) and were able to withstand a higher maximal strain before failing (35% without calponin, 56% with calponin). Using <a href="https://www.sciencedirect.com/topics/biochemistry-genetics-and-molecular-biology/fluorescence-microscopy" title="Learn more about Fluorescence Microscopy from ScienceDirect's AI-generated Topic Pages">fluorescence microscopy to study the mechanics of single actin filaments, we found that calponin increased the flexibility of actin filaments, evident as a decrease in persistence length from 17.6 μm without to 7.7 μm with calponin. Our data are consistent with current models of affine strain behavior in semiflexible polymer networks, and suggest that calponin stabilization of actin networks can be explained purely by changes in single-filament mechanics. We propose a model in which calponin stabilizes actin networks against shear through a reduction of persistence length of individual filaments.

Mobilization of a trapped non-wetting fluid from a three-dimensional porous medium - Datta, Sujit S.; Ramakrishnan, T. S.; Weitz, David A (Physics of Fluids, 2014)
We use confocal microscopy to directly visualize the formation and complex morphologies of trapped non-wetting fluid ganglia within a model 3D porous medium. The wetting fluid continues to flow around the ganglia after they form; this flow is characterized by a capillary number, Ca. We find that the ganglia configurations do not vary for small Ca; by contrast, as Ca is increased above a threshold value, the largest ganglia start to become mobilized and are ultimately removed from the medium. By combining our 3D visualization with measurements of the bulk transport, we show that this behavior can be quantitatively understood by balancing the viscous forces exerted on the ganglia with the pore-scale capillary forces that keep them trapped within the medium. Our work thus helps elucidate the fluid dynamics underlying the mobilization of a trapped non-wetting fluid from a 3D porous medium.

Fabrication of solid lipid microcapsules containing ascorbic acid using a microfluidic technique - Talita A. Comunian; Abbaspourrad, Alireza; Carmen S. Favaro-Trindade; Weitz, David A (Food Chemistry, 2014)
The importance of ascorbic acid (AA) in the human diet has motivated food researchers to develop AA-fortified food products. However, this compound is very unstable. The aim of this work was to produce solid lipid microcapsules (SLMs) loaded with AA using microfluidic technology. The morphology of the SLMs was analysed by optical, scanning electron and confocal microscopy. We determined the encapsulation efficiency, particle size and stability of the encapsulated material. Two different means of enhancing the encapsulation efficiency and stability of AA were demonstrated: a pore blocking method and a micromolecule-chelating agent within the core. The results indicated the enormous potential of the designed vehicle to prevent AA degradation in a food product; additionally, this vehicle could mask the acidic taste of AA.
Keywords: Lipid shell

Double Emulsion Templated Solid Microcapsules: Mechanics And Controlled Release - Datta, Sujit S.; Abbaspourrad, Alireza; Amstad, Esther; Fan, Jing; Kim, Shin-Hyun; Romanowsky, Mark; Shum, Ho Cheung; Sun, Bing Jie; Utada, Andrew S.; Windbergs, Maike; Zhou, Shaobing; Weitz, David A (Advanced Materials, 2014)
We describe how droplet microfluidics can be used to fabricate solid-shelled microcapsules having precisely controlled release behavior. Glass capillary devices enable the production of monodisperse double emulsion drops, which can then be used as templates for microcapsule formation. The exquisite control afforded by microfluidics can be used to tune the compositions and geometrical characteristics of the microcapsules with exceptional precision. We review the use of this approach to fabricate microcapsules that only release their contents when exposed to a specific stimulus – such as a change in temperature, exposure to light, a change in the chemical environment, or an external stress – only after a prescribed time delay, and at a prescribed rate.
Keywords: controlled release; double emulsions; Mechanics; microcapsules; Microfluidics

Identifying directional persistence in intracellular particle motion using Hidden Markov Models - Röding, Magnus; Guo, Ming; Weitz, David A; Rudemo, Mats; Särkkä, Aila (Mathematical Biosciences, 2014)
Particle tracking is a widely used and promising technique for elucidating complex dynamics of the living cell. The cytoplasm is an active material, in which the kinetics of intracellular structures are highly heterogeneous. Tracer particles typically undergo a combination of random motion and various types of directed motion caused by the activity of molecular motors and other non-equilibrium processes. Random switching between more and less directional persistence of motion generally occurs. We present a method for identifying states of motion with different directional persistence in individual particle trajectories. Our analysis is based on a multi-scale turning angle model to characterize motion locally, together with a Hidden Markov Model with two states representing different directional persistence. We define one of the states by the motion of particles in a reference data set where some active processes have been inhibited. We illustrate the usefulness of the method by studying transport of vesicles along microtubules and transport of nanospheres activated by myosin. We study the results using mean square displacements, durations, and particle speeds within each state. We conclude that the method provides accurate identification of states of motion with different directional persistence, with very good agreement in terms of mean-squared displacement between the reference data set and one of the states in the two-state model.
Keywords: Hidden Markov Models; Intracellular transport; Particle tracking; Transport processes

Microfluidic assembly of multistage porous silicon-lipid vesicles for controlled drug release - Herranz-Blanco, Barbara; Arriaga, Laura R.; Makila, Ermei; Correia, Alexandra; Shrestha, Neha; Mirza, Sabiruddin; Weitz, David A; Salonen, Jarno; Hirvonen, Jouni; Santos, Helder A. (Lab on a Chip, 2014)
A reliable microfluidic platform for the generation of stable and monodisperse multistage drug delivery systems is reported. A glass-capillary flow-focusing droplet generation device was used to encapsulate thermally hydrocarbonized porous silicon (PSi) microparticles into the aqueous cores of double emulsion drops, yielding the formation of a multistage PSi-lipid vesicle. This composite system enables a large loading capacity for hydrophobic drugs.

Nutrient depletion in Bacillus subtilis biofilms triggers matrix production - Wenbo Zhang; Seminara, Agnese; Melanie Suaris; Michael P. Brenner; Weitz, David A; Angelini, Thomas E. (New Journal of Physics, 2014)
Many types of bacteria form colonies that grow into physically robust and strongly adhesiveaggregates known as biofilms. A distinguishing characteristic of bacterial biofilms is an extracellular polymeric substance (EPS) matrix that encases the cells and provides physical integrity to the colony. The EPS matrix consists of a large amount of polysaccharide, as well as protein filaments, DNA and degraded cellular materials. The genetic pathways that control the transformation of a colony into a biofilm have been widely studied, and yield a spatiotemporal heterogeneity in EPS production. Spatial gradients in metabolites parallel this heterogeneity in EPS, but nutrient concentration as an underlying physiological initiator of EPS production has not been explored. Here, we study the role of nutrient depletion in EPS production in Bacillus subtilis biofilms. By monitoring simultaneously biofilm size and matrix production, we find that EPS production increases at a critical colony thickness that depends on the initial amount of carbon sources in the medium. Through studies of individual cells in liquid culture we find that EPS production can be triggered at the single-cell level by reducing nutrient concentration. To connect the single-cell assays with conditions in the biofilm, we calculate carbon concentration with a model for the reaction and diffusion of nutrients in the biofilm. This model predicts the relationship between the initial concentration of carbon and the thickness of the colony at the point of internal nutrient deprivation.

Quantifying cell-generated mechanical forces within living embryonic tissues - Campas, Otger; Mammoto, Tadanori; Hasso, Sean; Sperling, Ralph A.; O'Connell, Daniel; Bischof, Ashley G; Maas, Richard; Weitz, David A; Mahadevan, L; Ingber, Donald E (Nat Meth, 2014)
Cell-generated mechanical forces play a critical role during tissue morphogenesis and organ formation in the embryo. Little is known about how these forces shape embryonic organs, mainly because it has not been possible to measure cellular forces within developing three-dimensional (3D) tissues in vivo. We present a method to quantify cell-generated mechanical stresses exerted locally within living embryonic tissues, using fluorescent, cell-sized oil microdroplets with defined mechanical properties and coated with adhesion receptor ligands. After a droplet is introduced between cells in a tissue, local stresses are determined from droplet shape deformations, measured using fluorescence microscopy and computerized image analysis. Using this method, we quantified the anisotropic stresses generated by mammary epithelial cells cultured within 3D aggregates, and we confirmed that these stresses (3.4 nN [mu]m-2) are dependent on myosin II activity and are more than twofold larger than stresses generated by cells of embryonic tooth mesenchyme, either within cultured aggregates or in developing whole mouse mandibles.

The microfluidic post-array device: High throughput production of single emulsion drops - Amstad, E.; Datta, S.S.; Weitz, D. A. (Lab on a Chip, 2014)
We present a microfluidic device that enables high throughput production of relatively monodisperse emulsion drops while controlling the average size. The device consists of a two-dimensional array of regularly-spaced posts. Large drops of a highly polydisperse crude emulsion are input into the device and are successively split by the posts, ultimately yielding a finer emulsion consisting of smaller, and much more monodisperse drops. The size distribution of the resultant emulsion depends only weakly on the viscosities of the input fluids and allows fluids of very high viscosities to be used. The average size and polydispersity of the drops depend strongly on the device geometry enabling both control and optimization. We use this device to produce drops of a highly viscous monomer solution and subsequently solidify them into polymeric microparticles. The production rate of these devices is similar to that achieved by membrane emulsification techniques, yet the control over the drop size is superior; thus these post-array microfluidic devices are potentially useful for industrial applications.

Synchronized reinjection and coalescence of droplets in microfluidics - Lee, Manhee; Collins, Jesse W.; Aubrecht, Donald M.; Sperling, Ralph A.; Solomon, Laura; Ha, Jong-Wook; Yi, Gi-Ra; Weitz, David A; Vinothan N. Manoharan (Lab on a Chip, 2014)
Coalescence of two kinds of pre-processed droplets is necessary to perform chemical and biological assays in droplet-based microfluidics. However, a robust technique to accomplish this does not exist. Here we present a microfluidic device to synchronize the reinjection of two different kinds of droplets and coalesce them, using hydrostatic pressure in conjunction with a conventional syringe pump. We use a device consisting of two opposing T-junctions for reinjecting two kinds of droplets and control the flows of the droplets by applying gravity-driven hydrostatic pressure. The hydrostatic-pressure operation facilitates balancing the droplet reinjection rates and allows us to synchronize the reinjection. Furthermore, we present a simple but robust module to coalesce two droplets that sequentially come into the module, regardless of their arrival times. These re-injection and coalescence techniques might be used in lab-on-chip applications requiring droplets with controlled numbers of solid materials, which can be made by coalescing two pre-processed droplets that are formed and sorted in devices.

The role of vimentin intermediate filaments in cortical and cytoplasmic mechanics - Guo, Ming; Ehrlicher, Allen J.; Mahammad, Saleemulla; Fabich, Hilary; Jensen, Mikkel H.; Moore, Jeffrey R.; Jeffrey J. Fredberg; Robert D. Goldman; Weitz, David A (Biophysical journal, 2013)
The mechanical properties of a cell determine many aspects of its behavior, and these mechanics are largely determined by the cytoskeleton. Although the contribution of actin filaments and microtubules to the mechanics of cells has been investigated in great detail, relatively little is known about the contribution of the third major cytoskeletal component, intermediate filaments (IFs). To determine the role of vimentin IF (VIF) in modulating intracellular and cortical mechanics, we carried out studies using mouse embryonic fibroblasts (mEFs) derived from wild-type or vimentin −/− mice. The VIFs contribute little to cortical stiffness but are critical for regulating intracellular mechanics. Active microrheology measurements using optical tweezers in living cells reveal that the presence of VIFs doubles the value of the cytoplasmic shear modulus to ∼10 Pa. The higher levels of cytoplasmic stiffness appear to stabilize organelles in the cell, as measured by tracking endogenous vesicle movement. These studies show that VIFs both increase the mechanical integrity of cells and localize intracellular components.

Biodegradable core-shell carriers for simultaneous encapsulation of synergistic actives - Windbergs, Maike; Zhao, Yuanjin; Heyman, John; Weitz, David A (Journal of the American Chemical Society, 2013)
Simultaneous encapsulation of multiple active substances in a single carrier is essential for therapeutic applications of synergistic combinations of drugs. However, traditional carrier systems often lack efficient encapsulation and release of incorporated substances, particularly when combinations of drugs must be released in concentrations of a prescribed ratio. We present a novel biodegradable core shell carrier system fabricated in a one-step, solvent-free process on a microfluidic chip; a hydrophilic active (doxorubicin hydrochloride) is encapsulated in the aqueous core, while a hydrophobic active (paclitaxel) is encapsulated in the solid shell. Particle size and composition can be precisely controlled, and core and shell can be individually loaded with very high efficiency. Drug-loaded particles can be dried and stored as a powder. We demonstrate the efficacy of this system through the simultaneous encapsulation and controlled release of two synergistic anticancer drugs using two cancer-derived value for encapsulation of other active cell lines. This solvent-free platform technology is also of high potential ingredients and chemical reagents.

Block-and-break generation of microdroplets with fixed volume - van Steijn, Volkert; Korczyk, Piotr M.; Derzsi, Ladislav; Abate, Adam R.; Weitz, David A; Garstecki, Piotr (Biomicrofluidics, 2013)
We introduce a novel type of droplet generator that produces droplets of a volume set by the geometry of the droplet generator and not by the flow rates of the liquids. The generator consists of a classic T-junction with a bypass channel. This bypass directs the continuous fluid around the forming droplets, so that they can fill the space between the inlet of the dispersed phase and the exit of the bypass without breaking. Once filled, the dispersed phase blocks the exit of the bypass and is squeezed by the continuous fluid and broken off from the junction. We demonstrate the fixed-volume droplet generator for (i) the formation of monodisperse droplets from a source of varying flow rates, (ii) the formation of monodisperse droplets containing a gradation of solute concentration, and (iii) the parallel production of monodisperse droplets. (C) 2013 AIP Publishing LLC. [http://dx.doi.org/10.1063/1.4801637]

Colloidal particles: Crystals, glasses, and gels - Lu, Peter J.; Weitz, David A; Langer, J. S. (Annual Review of Condensed Matter Physics, Vol 4, 2013)
Colloidal particles are microscopic solid particles suspended in a fluid. Colloids are small enough that thermal energy drives their dynamics and ensures equilibration with the suspending fluid; they are also large enough that their positions and motions can be measured precisely using optical methods, such as light scattering and laser-scanning confocal fluorescence microscopy. Colloidal suspensions are a powerful model system for the study of other phenomena in condensed matter physics, where the collective phase behavior of the solid particles mimics that of other condensed systems. We review three classes of interacting colloidal particles, crystals, glasses, and gels, each of which represents fascinating properties of colloidal particles as well as a model for more general types of materials and their behavior.

Controlling release from pH-responsive microcapsules - Abbaspourrad, Alireza; Datta, Sujit S.; Weitz, David A (Langmuir, 2013)
We report a microfluidic approach to produce monodisperse pH-responsive microcapsules with precisely controlled release behavior. The solid microcapsule shells are composed of a biocompatible pH-responsive polymer and robustly encapsulate an active material; however, when exposed to a trigger pH, the shells degrade and ultimately release the microcapsule contents. We control the trigger pH by using polymers that dissolve at different pH values. We independently control the time at which the microcapsule contents are released by carefully controlling the shell thickness. Moreover, we independently control the rate at which the encapsulated contents are released by making hybrid shells composed of a mixture of a pH-responsive polymer and varying proportions of another, solid, pH-unresponsive polymer. This enables us to achieve monodisperse microcapsules that robustly encapsulate an active material, only releasing it when exposed to a desired pH, after a prescribed time delay, and at a prescribed rate.

DNA sequence analysis with droplet-based microfluidics - Abate, Adam R.; Hung, Tony; Sperling, Ralph A.; Mary, Pascaline; Rotem, Assaf; Agresti, Jeremy J.; Weiner, Michael A.; Weitz, David A (Lab on a Chip, 2013)
Droplet-based microfluidic techniques can form and process micrometer scale droplets at thousands per second. Each droplet can house an individual biochemical reaction, allowing millions of reactions to be performed in minutes with small amounts of total reagent. This versatile approach has been used for engineering enzymes, quantifying concentrations of DNA in solution, and screening protein crystallization conditions. Here, we use it to read the sequences of DNA molecules with a FRET-based assay. Using probes of different sequences, we interrogate a target DNA molecule for polymorphisms. With a larger probe set, additional polymorphisms can be interrogated as well as targets of arbitrary sequence.

Drainage in a model stratified porous medium - Datta, Sujit S.; Weitz, David A (Epl, 2013)
We show that when a non-wetting fluid drains a stratified porous medium at sufficiently small capillary numbers Ca, it flows only through the coarsest stratum of the medium; by contrast, above a threshold Ca, the non-wetting fluid is also forced laterally, into part of the adjacent, finer strata. The spatial extent of this partial invasion increases with Ca. We quantitatively understand this behavior by balancing the stratum-scale viscous pressure driving the flow with the capillary pressure required to invade individual pores. Because geological formations are frequently stratified, we anticipate that our results will be relevant to a number of important applications, including understanding oil migration, preventing groundwater contamination, and sub-surface CO2 storage. Copyright (C) EPLA, 2013

Enhanced-throughput production of polymersomes using a parallelized capillary microfluidic device - Kim, Shin-Hyun; Kim, Jin Woong; Kim, Do-Hoon; Han, Sang-Hoon; Weitz, David A (Microfluidics and Nanofluidics, 2013)
We report a parallelized capillary microfluidic device for enhanced production rate of monodisperse polymersomes. This device consists of four independent capillary microfluidic devices, operated in parallel; each device produces monodisperse water-in-oil-in-water (W/O/W) double-emulsion drops through a single-step emulsification. During generation of the double-emulsion drops, the innermost water drop is formed first and it triggers a breakup of the middle oil phase over wide range of flow rates; this enables robust and stable formation of the double-emulsion drops in all drop makers of the parallelized device. Double-emulsion drops are transformed to polymersomes through a dewetting of the amphiphile-laden middle oil phase on the surface of the innermost water drop, followed by the subsequent separation of the oil drop. Therefore, we can make polymersomes with a production rate enhanced by a factor given by the number of drop makers in the parallelized device.

Fabrication and manipulation of polymeric magnetic particles with magnetorheological fluid - Rodriguez-Lopez, Jaime; Shum, Ho Cheung; Elvira, Luis; Montero de Espinosa, Francisco; Weitz, David A (Journal of Magnetism and Magnetic Materials, 2013)
Polymeric magnetic microparticles have been created using a microfluidic device via ultraviolet (UV) polymerization of double emulsions, resulting in cores of magnetorheological (MR) fluids surrounded by polymeric shells. We demonstrate that the resultant particles can be manipulated magnetically to achieve triggered rupture of the capsules. This illustrates the great potential of our capsules for triggered release of active ingredients encapsulated in the polymeric magnetic microparticles. (C) 2012 Elsevier BY. All rights reserved.

Fast dynamics and relaxation of colloidal drops during the drying process using multispeckle diffusing wave spectroscopy - Lee, Jeong Yong; Hwang, Ji Won; Jung, Hyun Wook; Kim, Sung Hyun; Lee, Seong Jae; Yoon, Kisun; Weitz, David A (Langmuir, 2013)
The fast dynamics generated by the Brownian motion of particles in colloidal drops, and the related relaxation during drying, which play key roles in suspension systems, were investigated incorporating multispeckle diffusing wave spectroscopy (MSDWS). MSDWS equipment was implemented to analyze the relaxation properties of suspensions under a nonergodic and nonstationary drying process, which cannot be elucidated by conventional light scattering methods, such as dynamic light scattering and diffusing wave spectroscopy. Rapid particle movement can be identified by the characteristic relaxation time, which is closely related to the Brownian motion due to thermal fluctuations of the particles. In the compacting stage of the drying process, the characteristic relaxation time increased gradually with the drying time because the particles in the colloidal drop were constrained by themselves. Moreover, variations of the initial concentration and particle size considerably affected the complete drying time and characteristic relaxation time, producing a shorter relaxation time for a low concentrated suspension with small particles.

Formation of polymersomes with double bilayers templated by quadruple emulsions - Kim, Shin-Hyun; Nam, Jin; Kim, Jin Woong; Kim, Do-Hoon; Han, Sang-Hoon; Weitz, David A (Lab on a Chip, 2013)
Polymersomes, vesicles composed of bilayer membranes of amphiphilic block-copolymers, are promising delivery vehicles for long-term storage and controlled release of bioactives; enhanced stability of the membrane makes polymersomes potentially useful in a wide range of biological delivery applications by comparison with liposomes. However, unilamellar structure is intrinsically fragile when subjected to external stress. Here, we report a microfluidic approach to produce polymersomes with double bilayers, providing higher stability and lower permeability than unilamellar polymersomes. To achieve this, we developed a new design of a capillary microfluidic device to produce quadruple-emulsion drops which serve as a template for the polymersomes-in-polymersomes. When two bilayers are attracted by depletion in polymersomes-in-polymersomes, the inner polymersomes protrude and bud, forming double bilayers. We confirm these structures are indeed double bilayers using microaspiration and selective doping of the leaflets with nanoparticles. The resultant polymersomes have great potential as highly stable and biocompatible microcarriers for robust encapsulation and storage of bioactives such as drugs, cosmetics and nutrients.

Gas-core triple emulsions for ultrasound triggered release - Chen, Haosheng; Li, Jiang; Wan, Jiandi; Weitz, David A; Stone, Howard A. (Soft Matter, 2013)
Gas-in-oil-in-water-in-oil triple emulsions are fabricated with a microfluidic method. The encapsulating layers can be triggered for release by ultrasound, owing to the gas core. Due to the stability in the atmosphere, the emulsions are polymerized by using UV light outside the device to fabricate compound particles with a gas-in-liquid-in-solid structure.

Hole-shell microparticles from controllably evolved double emulsions - Wang, Wei; Zhang, Mao-Jie; Xie, Rui; Ju, Xiao-Jie; Yang, Chao; Mou, Chuan-Lin; Weitz, David A; Chu, Liang-Yin (Angewandte Chemie-International Edition, 2013)
Hole in one! Hole–shell microparticles (blue, see picture) with controllable structures and flexible internal surfaces have been fabricated from W/O/W emulsions. These microparticles could be used as microcontainers for the controlled capture/release of molecules, microsphere classification/separation, confined cell culture, or as microreactors for catalysis.

Liquid transport facilitated by channels in Bacillus subtilis biofilms - Wilking, James N.; Zaburdaev, Vasily; De Volder, Michael; Losick, Richard; Michael P. Brenner; Weitz, David A (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Many bacteria on earth exist in surface-attached communities known as biofilms. These films are responsible for manifold problems, including hospital-acquired infections and biofouling, but they can also be beneficial. Biofilm growth depends on the transport of nutrients and waste, for which diffusion is thought to be the main source of transport. However, diffusion is ineffective for transport over large distances and thus should limit growth. Nevertheless, biofilms can grow to be very large. Here we report the presence of a remarkable network of well-defined channels that form in wildtype Bacillus subtilis biofilms and provide a system for enhanced transport. We observe that these channels have high permeability to liquid flow and facilitate the transport of liquid through the biofilm. In addition, we find that spatial variations in evaporative flux from the surface of these biofilms provide a driving force for the flow of liquid in the channels. These channels offer a remarkably simple system for liquid transport, and their discovery provides insight into the physiology and growth of biofilms.

Microfluidic fabrication of stable gas-filled microcapsules for acoustic contrast enhancement - Abbaspourrad, Alireza; Duncanson, Wynter J.; Lebedeva, Natalia; Kim, Shin-Hyun; Zhushma, Aleksandr P.; Datta, Sujit S.; Dayton, Paul A.; Sheiko, Sergei S.; Rubinstein, Michael; Weitz, David A (Langmuir, 2013)
We introduce a facile approach for the production of gas-filled microcapsules designed to withstand high pressures. We exploit microfluidics to fabricate water-filled microcapsules that are then externally triggered to become gas-filled, thus making them more echogenic. In addition, the gas-filled microcapsules have a solid polymer shell making them resistant to pressure-induced buckling, which makes them more mechanically robust than traditional prestabilized microbubbles; this should increase the potential of their utility for acoustic imaging of porous media with high hydrostatic pressures such as oil reservoirs.

Microfluidic templated mesoporous silicon-solid lipid microcomposites for sustained drug delivery - Liu, Dongfei; Herranz-Blanco, Barbara; Makila, Ermei; Arriaga, Laura R.; Mirza, Sabiruddin; Weitz, David A; Sandler, Niklas; Salonen, Jarno; Hirvonen, Jouni; Santos, Helder A. (ACS Applied Materials & Interfaces, 2013)
A major challenge for a drug-delivery system is to engineer stable drug carriers with excellent biocompatibility, monodisperse size, and controllable release profiles. In this study, we used a microfluidic technique to encapsulate thermally hydrocarbonized porous silicon (THCPSi) microparticles within solid lipid microparticles (SLMs) to overcome the drawbacks accompanied by THCPSi microparticles. Formulation and process factors, such as lipid matrixes, organic solvents, emulsifiers, and methods to evaporate the organic solvents, were all evaluated and optimized to prepare monodisperse stable SLMs. FTIR analysis together with confocal images showed the clear deposition of THCPSi microparticles inside the monodisperse SLM matrix. The formation of monodisperse THCPSi solid lipid microcomposites (THCPSi SLMCs) not only altered the surface hydrophobicity and morphology of THCPSi microparticles but also remarkably enhanced their cytocompatibility with intestinal (Caco-2 and HT-29) cancer cells. Regardless of the solubility of the loaded therapeutics (aqueous insoluble, fenofibrate and furosemide; aqueous soluble, methotrexate and ranitidine) and the pH values of the release media (1.2, 5.0, and 7.4), the time for the release of 50% of the payloads from THCPSi SLMC was at least 1.3 times longer than that from the THCPSi microparticles. The sustained release of both water-soluble and -insoluble drugs together with a reduced burst-release effect from monodisperse THCPSi SLMC was achieved, indicating the successful encapsulation of THCPSi microparticles into the SLM matrix. The fabricated THCPSi SLMCs exhibited monodisperse spherical morphology, enhanced cytocompatibility, and prolonged both water-soluble and -insoluble drug release, which makes it an attractive controllable drug-delivery platform.

Micron-scale coherence in interphase chromatin dynamics - Zidovska, Alexandra; Weitz, David A; Mitchison, Timothy J. (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Chromatin structure and dynamics control all aspects of DNA biology yet are poorly understood, especially at large length scales. We developed an approach, displacement correlation spectroscopy based on time-resolved image correlation analysis, to map chromatin dynamics simultaneously across the whole nucleus in cultured human cells. This method revealed that chromatin movement was coherent across large regions (4-5 mu m) for several seconds. Regions of coherent motion extended beyond the boundaries of single-chromosome territories, suggesting elastic coupling of motion over length scales much larger than those of genes. These large-scale, coupled motions were ATP dependent and unidirectional for several seconds, perhaps accounting for ATP-dependent directed movement of single genes. Perturbation of major nuclear ATPases such as DNA polymerase, RNA polymerase II, and topoisomerase II eliminated micron-scale coherence, while causing rapid, local movement to increase; i.e., local motions accelerated but became uncoupled from their neighbors. We observe similar trends in chromatin dynamics upon inducing a direct DNA damage; thus we hypothesize that this may be due to DNA damage responses that physically relax chromatin and block long-distance communication of forces.

Microwave dielectric heating of non-aqueous droplets in a microfluidic device for nanoparticle synthesis - Koziej, Dorota; Caspar Floryan; Sperling, Ralph A.; Ehrlicher, Allen J.; Issadore, David; Westervelt, Robert; Weitz, David A (Nanoscale, 2013)
We describe a microfluidic device with an integrated microwave heater specifically designed to dielectrically heat non-aqueous droplets using time-varying electrical fields with the frequency range between 700 and 900 MHz. The precise control of frequency, power, temperature and duration of the applied field opens up new vistas for experiments not attainable by conventional microwave heating. We use a non-contact temperature measurement system based on fluorescence to directly determine the temperature inside a single droplet. The maximum temperature achieved of the droplets is 50 degrees C in 15 ms which represents an increase of about 25 degrees C above the base temperature of the continuous phase. In addition we use an infrared camera to monitor the thermal characteristics of the device allowing us to ensure that heating is exclusively due to the dielectric heating and not due to other effects like non-dielectric losses due to electrode or contact imperfection. This is crucial for illustrating the potential of dielectric heating of benzyl alcohol droplets for the synthesis of metal oxides. We demonstrate the utility of this technology for metal oxide nanoparticle synthesis, achieving crystallization of tungsten oxide nanoparticles and remarkable microstructure, with a reaction time of 64 ms, a substantial improvement over conventional heating methods.

Note: A three-dimensional calibration device for the confocal microscope - Jensen, K. E.; Weitz, D. A.; F. Spaepen (Review of Scientific Instruments, 2013)
Modern confocal microscopes enable high-precision measurement in three dimensions by collecting stacks of 2D (x-y) images that can be assembled digitally into a 3D image. It is difficult, however, to ensure position accuracy, particularly along the optical (z) axis where scanning is performed by a different physical mechanism than in x-y. We describe a simple device to calibrate simultaneously the x, y, and z pixel-to-micrometer conversion factors for a confocal microscope. By taking a known 2D pattern and positioning it at a precise angle with respect to the microscope axes, we created a 3D reference standard. The device is straightforward to construct and easy to use. (C) 2013 American Institute of Physics. [http://dx.doi.org/10.1063/1.4776672]

Nuclear envelope composition determines the ability of neutrophil-type cells to passage through micron-scale constrictions - Rowat, Amy C.; Jaalouk, Diana E.; Zwerger, Monika; Ung, W. Lloyd; Eydelnant, Irwin A.; Olins, Don E.; Olins, Ada L.; Herrmann, Harald; Weitz, David A; Lammerding, Jan (Journal of Biological Chemistry, 2013)
Neutrophils are characterized by their distinct nuclear shape, which is thought to facilitate the transit of these cells through pore spaces less than one-fifth of their diameter. We used human promyelocytic leukemia (HL-60) cells as a model system to investigate the effect of nuclear shape in whole cell deformability. We probed neutrophil-differentiated HL-60 cells lacking expression of lamin B receptor, which fail to develop lobulated nuclei during granulopoiesis and present an in vitro model for Pelger-Huet anomaly; despite the circular morphology of their nuclei, the cells passed through micron-scale constrictions on similar timescales as scrambled controls. We then investigated the unique nuclear envelope composition of neutrophil-differentiated HL-60 cells, which may also impact their deformability; although lamin A is typically down-regulated during granulopoiesis, we genetically modified HL-60 cells to generate a subpopulation of cells with well defined levels of ectopic lamin A. The lamin A-overexpressing neutrophil-type cells showed similar functional characteristics as the mock controls, but they had an impaired ability to pass through micron-scale constrictions. Our results suggest that levels of lamin A have a marked effect on the ability of neutrophils to passage through micron-scale constrictions, whereas the unusual multilobed shape of the neutrophil nucleus is less essential.

One step formation of controllable complex emulsions: From functional particles to simultaneous encapsulation of hydrophilic and hydrophobic agents into desired position - Choi, Chang-Hyung; Weitz, David A; Lee, Chang-Soo (Advanced Materials, 2013)
This article presents a one‐step method for generating complex emulsions that exploits the phase separation of the emulsion droplet generated in the microchannel. This approach easily produces double, triple, quadruple, and Janus emulsions with monodisperse size. These emulsions can be used as useful templates for the synthesis of new functional materials, such as microcapsules, hemispheres, Janus particles and microcarriers that are capable of simultaneously encapsulating hydrophilic and hydrophobic compounds with selective compartmentalization in a one‐step process.

Polymer microcapsules with programmable active release - Abbaspourrad, Alireza; Carroll, Nick J.; Kim, Shin-Hyun; Weitz, David A (Journal of the American Chemical Society, 2013)
We present a new type of microcapsule programmed with a tunable active release mechanism. The capsules are triggered by a plasticizing stimulus that induces a phase change transition of the polymeric membrane from a solid to a fluidized form; thereafter, the cargo is actively driven out of the capsule through a defect at the capsule wall with controllable release kinetics. Tuning the degree of membrane fluidity by tailoring the amount of plasticizing stimulus present allows us to obtain temporal variation of the release kinetics from a subsecond abrupt burst release to a slow sustained release of encapsulant over many minutes. Moreover, we demonstrate tuning of the collective capsule triggering response by adjusting stimulus content, polymer molecular weight, and capsule membrane thickness. For this model system, we use a microfluidic approach to fabricate polystyrene capsules triggered by a toluene stimulus. However, this active release approach is general and is applicable to diverse polymeric capsule systems; this versatility is demonstrated by extension of our trigger-release scheme to capsules fabricated from a rubberlike block copolymer. The utility of our technique further enhances the potential of these active release capsules for practical application.

Polymersomes containing a hydrogel network for high stability and controlled release - Kim, Shin-Hyun; Kim, Jin Woong; Kim, Do-Hoon; Han, Sang-Hoon; Weitz, David A (Small, 2013)
Capillary microfluidic devices are used to prepare monodisperse polymersomes consisting of a hydrogel core and a bilayer membrane of amphiphilic diblock-copolymers. To make polymersomes, water-in-oil-in-water double-emulsion drops are prepared as templates through single-step emulsification in a capillary microfluidic device. The amphiphile-laden middle oil phase of the double-emulsion drop dewets from the surface of the innermost water drop, which contains hydrogel prepolymers; this dewetting leads to the formation of a bilayer membrane. Subsequently, the oil phase completely separates from the innermost water drop, leaving a polymersome. Upon UV illumination of the polymersome, the prepolymers encapsulated within the interior are crosslinked, forming a hydrogel core. The hydrogel network within the polymersomes facilitates sustained release of the encapsulated materials and increases the stability of the polymersomes through the formation of a scaffold to support the bilayer. In addition, this approach provides a facile method to make monodisperse hydrogel particles directly dispersed in water.

Rolling particle lithography by soft polymer microparticles - Di Benedetto, Francesca; Fasano, Vito; Persano, Luana; Maruccio, Claudio; Mele, Elisa; Potente, Giovanni; Weitz, David A; De Lorenzis, Laura; Pisignano, Dario (Soft Matter, 2013)
Elastomeric polymeric microspheres are employed as a direct-writing tool for the continuous delivery of molecular materials. The mechanical properties enabling patterning are investigated and modelled. The proposed approach provides a low cost and versatile lithographic method for transferring features with real-time dynamic control.

Single-cell analysis and sorting using droplet-based microfluidics - Mazutis, Linas; Gilbert, John; Ung, W. Lloyd; Weitz, David A; Griffiths, Andrew D.; Heyman, John A. (Nature Protocols, 2013)
We present a droplet-based microfluidics protocol for high-throughput analysis and sorting of single cells. Compartmentalization of single cells in droplets enables the analysis of proteins released from or secreted by cells, thereby overcoming one of the major limitations of traditional flow cytometry and fluorescence-activated cell sorting. As an example of this approach, we detail a binding assay for detecting antibodies secreted from single mouse hybridoma cells. Secreted antibodies are detected after only 15 min by co-compartmentalizing single mouse hybridoma cells, a fluorescent probe and single beads coated with anti-mouse IgG antibodies in 50-pl droplets. The beads capture the secreted antibodies and, when the captured antibodies bind to the probe, the fluorescence becomes localized on the beads, generating a clearly distinguishable fluorescence signal that enables droplet sorting at similar to 200 Hz as well as cell enrichment. The microfluidic system described is easily adapted for screening other intracellular, cell-surface or secreted proteins and for quantifying catalytic or regulatory activities. In order to screen similar to 1 million cells, the microfluidic operations require 2-6 h; the entire process, including preparation of microfluidic devices and mammalian cells, requires 5-7 d.

Spatial fluctuations of fluid velocities in flow through a three-dimensional porous medium - Datta, Sujit S.; Chiang, H.; Ramakrishnan, T. S.; Weitz, David A (Physical Review Letters, 2013)
We use confocal microscopy to directly visualize the spatial fluctuations in fluid flow through a three-dimensional porous medium. We find that the velocity magnitudes and the velocity components both along and transverse to the imposed flow direction are exponentially distributed, even with residual trapping of a second immiscible fluid. Moreover, we find pore-scale correlations in the flow that are determined by the geometry of the medium. Our results suggest that despite the considerable complexity of the pore space, fluid flow through it is not completely random.

Stimuli-responsive core-shell microcapsules with tunable rates of release by using a depolymerizable poly(phthalaldehyde) membrane - DiLauro, Anthony M.; Abbaspourrad, Alireza; Weitz, David A; Phillips, Scott T. (Macromolecules, 2013)
Flow-focusing microfluidic techniques were used to provide access to core shell microcapsules in which the shell is composed of end tapped poly(phthalaldehydes) that depolymerize completely from head-to-tail in response to fluoride. Microcapsules made from these depolymerizable polymers provide an amplified response to the applied chemical signal, where the rate of the response can be tuned both by varying the length of the polymer and the thickness of the shell wall.

Strain history dependence of the nonlinear stress response of fibrin and collagen networks - Munster, Stefan; Jawerth, Louise M.; Leslie, Beverly A.; Weitz, Jeffrey I.; Fabry, Ben; Weitz, David A (Proceedings of the National Academy of Sciences of the United States of America, 2013)
We show that the nonlinear mechanical response of networks formed from un-cross-linked fibrin or collagen type I continually changes in response to repeated large-strain loading. We demonstrate that this dynamic evolution of the mechanical response arises from a shift of a characteristic nonlinear stress-strain relationship to higher strains. Therefore, the imposed loading does not weaken the underlying matrices but instead delays the occurrence of the strain stiffening. Using confocal microscopy, we present direct evidence that this behavior results from persistent lengthening of individual fibers caused by an interplay between fiber stretching and fiber buckling when the networks are repeatedly strained. Moreover, we show that covalent cross-linking of fibrin or collagen inhibits the shift of the nonlinear material response, suggesting that the molecular origin of individual fiber lengthening may be slip of monomers within the fibers. Thus, a fibrous architecture in combination with constituents that exhibit internal plasticity creates a material whose mechanical response adapts to external loading conditions. This design principle may be useful to engineer novel materials with this capability.

Stress-enhanced gelation: A dynamic nonlinearity of elasticity - Yao, Norman Y.; Broedersz, Chase P.; Depken, Martin; Becker, Daniel J.; Pollak, Martin R.; MacKintosh, Frederick C; Weitz, David A (Physical Review Letters, 2013)
A hallmark of biopolymer networks is their sensitivity to stress, reflected by pronounced nonlinear elastic stiffening. Here, we demonstrate a distinct dynamical nonlinearity in biopolymer networks consisting of filamentous actin cross-linked by alpha-actinin-4. Applied stress delays the onset of relaxation and flow, markedly enhancing gelation and extending the regime of solidlike behavior to much lower frequencies. We show that this macroscopic network response can be accounted for at the single molecule level by the increased binding affinity of the cross-linker under load, characteristic of catch-bond-like behavior. DOI: 10.1103/PhysRevLett.110.018103

Structure and mechanics of fibrin clots formed under mechanical perturbation - Muenster, S.; Jawerth, L. M.; Fabry, B.; Weitz, D. A. (Journal of Thrombosis and Haemostasis, 2013)

Surface functionalized hydrophobic porous particles toward water treatment application - Abbaspourrad, Alireza; Carroll, Nick J.; Kim, Shin-Hyun; Weitz, David A (Advanced Materials, 2013)
A microfluidic-based approach for the fabrication of organic contaminants absorbing core-shell particles is demonstrated. The hydrophobic porous core absorbs oil while the hydrophilic surface enables the particles to be well-dispersed in aqueous solutions. These particles can uptake oil from aqueous solution saturated with oil or via direct contact with oil blobs as depicted in the figure.

Thermally switched release from nanoparticle colloidosomes - Zhou, Shaobing; Fan, Jing; Datta, Sujit S.; Guo, Ming; Guo, Xing; Weitz, David A (Advanced Functional Materials, 2013)
Nanoparticle colloidosomes, whose release can be switched on and off in response to a temperature change, are fabricated. Unlike in other systems, the switchable release does not require the colloidosome shell to deform; it instead occurs due to the adsorption or desorption of a block copolymer, dissolved in the core, at the inner surface of the colloidosome shell, concomitantly blocking or unblocking the pores in the shell. The colloidosomes are prepared using double emulsion templates produced by microfluidics, and are thus highly monodisperse; moreover, they are mechanically stable and consist of biocompatible components, making them suitable for the encapsulation, delivery, and release of a broad range of active materials.

Transport of charged colloids in a nonpolar solvent - Lin, Tina; Kodger, Thomas E.; Weitz, David A (Soft Matter, 2013)
In nonpolar solvents, surfactants stabilize charge through the formation of reverse micelles; this enables the dissociation of charge from the surfaces of particles, thereby charge-stabilizing particle suspensions. We investigate the dynamics of such charged particles by directly visualizing their motion across a microfluidic channel in response to an external electric field. The presence of the reverse micelles has a significant effect on particle motion: in a constant field, the particles initially move, then slow down exponentially, and eventually stop. This is due to the accumulation of reverse micelles at the channel walls, which screens the applied field, leading to the subsequent decay of the internal electric field. The time constant of decay depends on the electrical conductivity of the particle suspension and the width of the channel; this behavior is modeled as an equivalent RC circuit.

Visualizing multiphase flow and trapped fluid configurations in a model three-dimensional porous medium - Krummel, Amber T.; Datta, Sujit S.; Muenster, Stefan; Weitz, David A (Aiche Journal, 2013)
We report an approach to fully visualize the flow of two immiscible fluids through a model three-dimensional (3-D) porous medium at pore-scale resolution. Using confocal microscopy, we directly image the drainage of the medium by the nonwetting oil and subsequent imbibition by the wetting fluid. During imbibition, the wetting fluid pinches off threads of oil in the narrow crevices of the medium, forming disconnected oil ganglia. Some of these ganglia remain trapped within the medium. By resolving the full 3-D structure of the trapped ganglia, we show that the typical ganglion size, as well as the total amount of residual oil, decreases as the capillary number Ca increases; this behavior reflects the competition between the viscous pressure in the wetting fluid and the capillary pressure required to force oil through the pores of the medium. This work thus shows how pore-scale fluid dynamics influence the trapped fluid configurations in multiphase flow through 3-D porous media. (C) 2013 American Institute of Chemical Engineers AIChE J, 59: 1022-1029, 2013

Wetting-induced formation of controllable monodisperse multiple emulsions in microfluidics - Deng, Nan-Nan; Wang, Wei; Ju, Xiao-Jie; Xie, Rui; Weitz, David A; Chu, Liang-Yin (Lab on a Chip, 2013)
Multiple emulsions, which are widely applied in a myriad of fields because of their unique ability to encapsulate and protect active ingredients, are typically produced by sequential drop-formations and drop-encapsulations using shear-induced emulsification. Here we report a qualitatively novel method of creating highly controlled multiple emulsions from lower-order emulsions. By carefully controlling the interfacial energies, we adjust the spreading coefficients between different phases to cause drops of one fluid to completely engulf other drops of immiscible fluids; as a result multiple emulsions are directly formed by simply putting preformed lower-order emulsion drops together. Our approach has highly controllable flexibility. We demonstrate this in preparation of both double and triple emulsions with a controlled number of inner drops and precisely adjusted shell thicknesses including ultra-thin shells. Moreover, this controllable drop-engulfing-drop approach has a high potential in further investigations and applications of microfluidics. Importantly, this innovative approach opens a window to exploit new phenomena occurring in fluids at the microscale level, which is of great significance for developing novel microfluidics.

Control over the Shell Thickness of Core/Shell Drops in Three-Phase Glass Capillary Devices - Vladisavljević, Goran T.; Shum, Ho Cheung; Weitz, DavidA. (UK Colloids 2011: An International Colloid and Surface Science Symposium, 2012)
Monodisperse core/shell drops with aqueous core and poly(dimethylsiloxane) (PDMS) shell of controllable thickness have been produced using a glass microcapillary device that combines co-flow and flow-focusing geometries. The throughput of the droplet generation was high, with droplet generation frequency in the range from 1,000 to 10,000 Hz. The size of the droplets can be tuned by changing the flow rate of the continuous phase. The technique enables control over the shell thickness through adjusting the flow rate ratio of the middle to inner phase. As the flow rate of the middle and inner phase increases, the droplet breakup occurs in the dripping-to-jetting transition regime, with each double emulsion droplet containing two monodisperse internal aqueous droplets. The resultant drops can be used subsequently as templates for monodisperse polymer capsules with a single or multiple inner compartments, as well as functional vesicles such as liposomes, polymersomes and colloidosomes.

Fabrication of Biodegradable Poly(Lactic Acid) Particles in Flow-Focusing Glass Capillary Devices - Vladisavljević, Goran T.; Henry, J. V.; Duncanson, Wynter J.; Shum, Ho C.; Weitz, DavidA. (UK Colloids 2011: An International Colloid and Surface Science Symposium, 2012)
Monodisperse poly(dl-lactic acid) (PLA) particles with a diameter in the range from 12 to 100 $μ$m were fabricated in flow focusing glass capillary devices by evaporation of dichloromethane (DCM) from emulsions at room temperature. The dispersed phase was 5% (w/w) PLA in DCM containing a small amount of Nile red and the continuous phase was 5% (w/w) poly(vinyl alcohol) in reverse osmosis water. Particle diameter was 2.7 times smaller than the size of the emulsion droplet template indicating that the particle porosity was very low. SEM images revealed that the majority of particle pores are in the sub-micron region but in some instances these pores can reach 3 $μ$m in diameter. Droplet diameter was influenced by the flow rates of the two phases and the entry diameter of the collection capillary tube; droplet diameters decreased with increasing values of the flow rate ratio of the dispersed to continuous phase to reach constant minimum values at 40–60% orifice diameter. At flow rate ratios less than 5, jetting can occur, giving rise to large droplets formed by detachment from relatively long jets (~10 times longer than droplet diameter).

The conformational state of actin filaments regulates branching by actin-related protein 2/3 (Arp2/3) complex - Jensen, Mikkel Herholdt; Morris, Eliza J.; Huang, Renjian; Rebowski, Grzegorz; Dominguez, Roberto; Weitz, David A; Moore, Jeffrey R.; Wang, Chih-Lueh Albert (Journal of Biological Chemistry, 2012)
Actin is a highly ubiquitous protein in eukaryotic cells that plays a crucial role in cell mechanics and motility. Cell motility is driven by assembling actin as polymerizing actin drives cell protrusions in a process closely involving a host of other actin-binding proteins, notably the actin-related protein 2/3 (Arp2/3) complex, which nucleates actin and forms branched filamentous structures. The Arp2/3 complex preferentially binds specific actin networks at the cell leading edge and forms branched filamentous structures, which drive cell protrusions, but the exact regulatory mechanism behind this process is not well understood. Here we show using in vitro imaging and binding assays that a fragment of the actin-binding protein caldesmon added to polymerizing actin increases the Arp2/3-mediated branching activity, whereas it has no effect on branch formation when binding to aged actin filaments. Because this caldesmon effect is shown to be independent of nucleotide hydrolysis and phosphate release from actin, our results suggest a mechanism by which caldesmon maintains newly polymerized actin in a distinct state that has a higher affinity for the Arp2/3 complex. Our data show that this new state does not affect the level of cooperativity of binding by Arp2/3 complex or its distribution on actin. This presents a novel regulatory mechanism by which caldesmon, and potentially other actin-binding proteins, regulates the interactions of actin with its binding partners.

Asymmetric functionalization of colloidal dimer particles with gold nanoparticles - Yoon, Kisun; Lee, Daeyeon; Kim, Jin Woong; Kim, Jaeyun; Weitz, David A (Chemical Communications, 2012)
We present a method to asymmetrically functionalize dimer particles with gold nanoparticles. Our method enables the fabrication of asymmetrically functionalized dimer particles on a large scale.

High throughput production of single core double emulsions in a parallelized microfluidic device - Romanowsky, Mark B.; Abate, Adam R.; Rotem, Assaf; Holtze, Christian; Weitz, David A (Lab on a Chip, 2012)
Double emulsions are useful templates for microcapsules and complex particles, but no method yet exists for making double emulsions with both high uniformity and high throughput. We present a parallel numbering-up design for microfluidic double emulsion devices, which combines the excellent control of microfluidics with throughput suitable for mass production. We demonstrate the design with devices incorporating up to 15 dropmaker units in a two-dimensional or three-dimensional array, producing single-core double emulsion drops at rates over 1 kg day(-1) and with diameter variation less than 6%. This design provides a route to integrating hundreds of dropmakers or more in a single chip, facilitating industrial-scale production rates of many tons per year.

Direct visualization of three-dimensional crystallization behavior in microgels - Muluneh, Melaku; Weitz, David A (Physical Review E, 2012)
We use confocal microscopy to study the three-dimensional (3D) structure of colloidal crystals formed by poly(N-isopropylacrylamide)-co-(acrylic acid) microgels of diameter 1.0-1.5 mu m. The confocal images are tracked to locate particle positions in 3D, which are used to compute pair-correlation functions g(r), bond order parameters, and structure factors s(q). We find that the structure remains fcc for a range of charge, size, and concentration of the particles. When the particles are weakly attractive and are at low concentrations, polycrystalline solids result. In addition, owing to the compressibility of the colloids, the crystals display remarkable structural stability when subjected to external stress.

Does size matter? Elasticity of compressed suspensions of colloidal- and granular-scale microgels - Menut, Paul; Seiffert, Sebastian; Sprakel, Joris; Weitz, David A (Soft Matter, 2012)
We investigate the mechanics of dense packing of very small, colloidal-scale, and larger, granular-scale microgel particles. At low particle concentration, thermally induced Brownian motion of the particles is important for the colloidal-scale systems; in contrast, such Brownian motion is irrelevant at particle packing fractions beyond jamming. As a consequence, colloidal and granular systems behave very similarly under these conditions. At sufficiently high compression of the microgel particles, their polymeric nature sets the scale of the osmotic pressure and shear modulus of the whole packing, in direct analogy with macroscopic, continuous polymer gels. This observation suggests that the particulate nature of microgels is inconsequential for their linear elasticity in a highly packed state. In contrast, the particulate nature of the microgels does become essential when the packed suspensions are forced to yield and flow; here, the differences between colloidal-and granular-scale particles are marked.

Protein expression, aggregation, and triggered release from polymersomes as artificial cell-like structures - Martino, Chiara; Kim, Shin-Hyun; Horsfall, Louise; Abbaspourrad, Alireza; Rosser, Susan J.; Cooper, Jonathan; Weitz, David A (Angewandte Chemie-International Edition, 2012)
Bringing droplets to life: A cytoskeletal protein (red dots, see scheme) is expressed in artificial cells composed of biocompatible polymersomes, which encapsulate expression machinery and amino acid building blocks. Release of the expressed proteins can be triggered by a negative osmotic shock.

Characterizing concentrated, multiply scattering, and actively driven fluorescent systems with confocal differential dynamic microscopy - Lu, Peter J.; Giavazzi, Fabio; Angelini, Thomas E.; Zaccarelli, Emanuela; Jargstorff, Frank; Schofield, Andrew B.; Wilking, James N.; Romanowsky, Mark B.; Weitz, David A; Cerbino, Roberto (Physical Review Letters, 2012)
We introduce confocal differential dynamic microscopy (ConDDM), a new technique yielding information comparable to that given by light scattering but in dense, opaque, fluorescent samples of micron-sized objects that cannot be probed easily with other existing techniques. We measure the correct wave vector q-dependent structure and hydrodynamic factors of concentrated hard-sphere-like colloids. We characterize concentrated swimming bacteria, observing ballistic motion in the bulk and a new compressed-exponential scaling of dynamics, and determine the velocity distribution; by contrast, near the coverslip, dynamics scale differently, suggesting that bacterial motion near surfaces fundamentally differs from that of freely swimming organisms.

Non-coalescence of oppositely charged droplets in pH-sensitive emulsions - Liu, Tingting; Seiffert, Sebastian; Thiele, Julian; Abate, Adam R.; Weitz, David A; Richtering, Walter (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Like charges stabilize emulsions, whereas opposite charges break emulsions. This is the fundamental principle for many industrial and practical processes. Using micrometer-sized pH-sensitive polymeric hydrogel particles as emulsion stabilizers, we prepare emulsions that consist of oppositely charged droplets, which do not coalesce. We observe noncoalescence of oppositely charged droplets in bulk emulsification as well as in microfluidic devices, where oppositely charged droplets are forced to collide within channel junctions. The results demonstrate that electrostatic interactions between droplets do not determine their stability and reveal the unique pH-dependent properties of emulsions stabilized by soft microgel particles. The noncoalescence can be switched to coalescence by neutralizing the microgels, and the emulsion can be broken on demand. This unusual feature of the microgel-stabilized emulsions offers fascinating opportunities for future applications of these systems.

Structures, stresses, and fluctuations in the delayed failure of colloidal gels - Lindstrom, Stefan B.; Kodger, Thomas E.; Sprakel, Joris; Weitz, David A (Soft Matter, 2012)
Sample-spanning networks of aggregated colloidal particles have a finite stiffness and deform elastically when subjected to a small shear stress. After some period of creep, these gels ultimately suffer catastrophic failure. This delayed yielding is governed by the association and dissociation dynamics of interparticle bonds and the strand structure of the gel. We derive a model which connects the kinetics of the colloids to the erosion of the strand structure and ultimately to macroscopic failure. Importantly, this model relates time-to-failure of the gel to an applied static stress. Model predictions are in quantitative agreement with experiments. It is predicted that the strand structure, characterized by its mesh size and strand coarseness, has a significant impact on delay time. Decreasing the mesh size or increasing the strand thickness makes colloidal gels more resilient to delayed yielding. The quench and flow history of gels modifies their microstructures. Our experiments show that a slow quenching increases the delay time due to the coarsening of the strands; by contrast, preshear reduces the delay time, which we explain by the increased mesh size as a result of shear-induced fracture of strands.

Skating on a film of air: Drops impacting on a surface - Kolinski, John M; Rubinstein, Shmuel M; Mandre, Shreyas; Michael P. Brenner; Weitz, David A; Mahadevan, L (Physical Review Letters, 2012)
The commonly accepted description of drops impacting on a surface typically ignores the essential role of the air that is trapped between the impacting drop and the surface. Here we describe a new imaging modality that is sensitive to the behavior right at the surface. We show that a very thin film of air, only a few tens of nanometers thick, remains trapped between the falling drop and the surface as the drop spreads. The thin film of air serves to lubricate the drop enabling the fluid to skate on the air film laterally outward at surprisingly high velocities, consistent with theoretical predictions. Eventually this thin film of air breaks down as the fluid wets the surface via a spinodal-like mechanism. Our results show that the dynamics of impacting drops are much more complex than previously thought, with a rich array of unexpected phenomena that require rethinking classic paradigms.

Surface roughness directed self-assembly of patchy particles into colloidal micelles - Kraft, Daniela J.; Ni, Ran; Smallenburg, Frank; Hermes, Michiel; Yoon, Kisun; Weitz, David A; van Blaaderen, Alfons; Groenewold, Jan; Dijkstra, Marjolein; Kegel, Willem K. (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Colloidal particles with site-specific directional interactions, so called "patchy particles", are promising candidates for bottom-up assembly routes towards complex structures with rationally designed properties. Here we present an experimental realization of patchy colloidal particles based on material independent depletion interaction and surface roughness. Curved, smooth patches on rough colloids are shown to be exclusively attractive due to their different overlap volumes. We discuss in detail the case of colloids with one patch that serves as a model for molecular surfactants both with respect to their geometry and their interactions. These one-patch particles assemble into clusters that resemble surfactant micelles with the smooth and attractive sides of the colloids located at the interior. We term these clusters "colloidal micelles". Direct Monte Carlo simulations starting from a homogeneous state give rise to cluster size distributions that are in good agreement with those found in experiments. Important differences with surfactant micelles originate from the colloidal character of our model system and are investigated by simulations and addressed theoretically. Our new "patchy" model system opens up the possibility for self-assembly studies into finite-sized superstructures as well as crystals with as of yet inaccessible structures.

Droplet microfluidics for high-throughput biological assays - Guo, Mira T.; Rotem, Assaf; Heyman, John A.; Weitz, David A (Lab on a Chip, 2012)
Droplet microfluidics offers significant advantages for performing high-throughput screens and sensitive assays. Droplets allow sample volumes to be significantly reduced, leading to concomitant reductions in cost. Manipulation and measurement at kilohertz speeds enable up to 10(8) samples to be screened in one day. Compartmentalization in droplets increases assay sensitivity by increasing the effective concentration of rare species and decreasing the time required to reach detection thresholds. Droplet microfluidics combines these powerful features to enable currently inaccessible high-throughput screening applications, including single-cell and single-molecule assays.

Microfluidic synthesis of advanced microparticles for encapsulation and controlled release - Duncanson, Wynter J.; Lin, Tina; Abate, Adam R.; Seiffert, Sebastian; Shah, Rhutesh K.; Weitz, David A (Lab on a Chip, 2012)
We describe droplet microfluidic strategies used to fabricate advanced microparticles that are useful structures for the encapsulation and release of actives; these strategies can be further developed to produce microparticles for advanced drug delivery applications. Microfluidics enables exquisite control in the fabrication of polymer vesicles and thermosensitive microgels from single and higher-order multiple emulsion templates. The strategies used to create the diversity of microparticle structures described in this review, coupled with the scalability of microfluidics, will enable fabrication of large quantities of novel microparticle structures that have potential uses in controlled drug release applications.

Microfluidic synthesis of monodisperse porous microspheres with size-tunable pores - Duncanson, Wynter J.; Zieringer, Maximilian; Wagner, Olaf; Wilking, James N.; Abbaspourrad, Alireza; Haag, Rainer; Weitz, David A (Soft Matter, 2012)
We use a perfluorinated-dendrimer-dye complex that stabilizes microbubbles as a novel pore-forming agent. We use microfluidics to produce monodisperse emulsions containing a polymer matrix material, a model active, and the perfluorinated complex; upon drying, the emulsions form porous microspheres. This porosity causes the encapsulated model active to be released faster than from non-porous microspheres. Moreover, because of the fluorous features of the pores, we can also attach an additional guest molecule to the pores which is released with a profile that is distinct from that of the encapsulated active. These porous microspheres can encapsulate and controllably release multiple actives; this makes them valuable for applications such as drug delivery and imaging.

Monodisperse gas-filled microparticles from reactions in double emulsions - Duncanson, Wynter J.; Abbaspourrad, Alireza; Shum, Ho Cheung; Kim, Shin-Hyun; Adams, Laura L. A.; Weitz, David A (Langmuir, 2012)
We present a strategy for preparing size-controlled gas-filled microparticles using two aqueous components that chemically react to produce the gas. We use a dual-bore microfluidic device to isolate the reactants of two gas-producing reactions until they are encapsulated in the outer droplet. The reactants in the monodisperse droplets merge and produce the gas bubbles, which are stabilized with a surfactant and form the core of the microparticles. The number and size of the generated gas bubbles are governed by the gas-forming reaction used. Our versatile strategy can be applied to a wide range of gas-producing reactions.

Delayed buckling and guided folding of inhomogeneous capsules - Datta, Sujit S.; Kim, Shin-Hyun; Paulose, Jayson; Abbaspourrad, Alireza; David R. Nelson; Weitz, David A (Physical Review Letters, 2012)
Colloidal capsules can sustain an external osmotic pressure; however, for a sufficiently large pressure, they will ultimately buckle. This process can be strongly influenced by structural inhomogeneities in the capsule shells. We explore how the time delay before the onset of buckling decreases as the shells are made more inhomogeneous; this behavior can be quantitatively understood by coupling shell theory with Darcy's law. In addition, we show that the shell inhomogeneity can dramatically change the folding pathway taken by a capsule after it buckles.

Use of micro-emulsion technology for the directed evolution of antibodies - Buhr, Diane L.; Acca, Felicity E.; Holland, Erika G.; Johnson, Katie; Maksymiuk, Gail M.; Vaill, Ada; Kay, Brian K.; Weitz, David A; Weiner, Michael P.; Kiss, Margaret M. (Methods, 2012)
Affinity reagents, such as antibodies, are needed to study protein expression patterns, sub-cellular localization, and post-translational modifications in complex mixtures and tissues. Phage Emulsion, Secretion, and Capture (ESCape) is a novel micro-emulsion technology that utilizes water-in-oil (W/O) emulsions for the identification and isolation of cells secreting phage particles that display desirable antibodies. Using this method, a large library of antibody-displaying phage will bind to beads in individual compartments. Rather than using biopanning on a large mixed population, phage micro-emulsion technology allows us to individually query clonal populations of amplified phage against the antigen. The use of emulsions to generate microdroplets has the promise of accelerating phage selection experiments by permitting fine discrimination of kinetic parameters for binding to targets. In this study, we demonstrate the ability of phage micro-emulsion technology to distinguish two scFvs with a 300-fold difference in binding affinities (100 nM and 300 pM, respectively). In addition, we describe the application of phage microemulsion technology for the selection of scFvs that are resistant to elevated temperatures. (C) 2012 Published by Elsevier Inc.

Photo- and thermoresponsive polymersomes for triggered release - Amstad, Esther; Kim, Shin-Hyun; Weitz, David A (Angewandte Chemie-International Edition, 2012)
Microfluidics: Thermo‐ and photoresponsive polymersomes are assembled using capillary microfluidic devices. Encapsulants can be selectively released from the thermoresponsive polymersomes if they are incubated at and above temperatures of 40 °C, whereas the photoresponsive polymersomes selectively release encapsulants if illuminated with laser light (see picture; NP=nanoparticle).

Single step emulsification for the generation of multi-component double emulsions - Adams, L. L. A.; Kodger, Thomas E.; Kim, Shin-Hyun; Shum, Ho Cheng; Franke, Thomas; Weitz, David A (Soft Matter, 2012)
We successfully encapsulate two, three, and four different inner drops inside double emulsions by means of a single-step emulsification technique. The microfluidic device fabrication is simple and the emulsification process highly robust. Optical microscopy images of double emulsion generation and of monodisperse double emulsions with discrete numbers of inner drops indicate the achievement of a high level of control with this technique. When the middle fluid transitions from dripping to jetting, two additional variations of double emulsions are produced: highly packed double emulsions and double emulsions with different sizes of inner drops. Finally, we successfully coalesce inner drops confined in a wax shell by applying heat. This demonstrates that these multi-component double emulsions may be useful as micro-reactors.

Experimental validation of plugging during drop formation in a T-junction - Abate, Adam R.; Mary, Pascaline; van Steijn, Volkert; Weitz, David A (Lab on a Chip, 2012)
At low capillary number, drop formation in a T-junction is dominated by interfacial effects: as the dispersed fluid flows into the drop maker nozzle, it blocks the path of the continuous fluid; this leads to a pressure rise in the continuous fluid that, in turn, squeezes on the dispersed fluid, inducing pinch-off of a drop. While the resulting drop volume predicted by this "squeezing'' mechanism has been validated for a range of systems, as of yet, the pressure rise responsible for the actual pinch-off has not been observed experimentally. This is due to the challenge of measuring the pressures in a T-junction with the requisite speed, accuracy, and localization. Here, we present an empirical study of the pressures in a T-junction during drop formation. Using Laplace sensors, pressure probes we have developed, we confirm the central ideas of the squeezing mechanism; however, we also uncover other findings, including that the pressure of the dispersed fluid is not constant but rather oscillates in anti-phase with that of the continuous fluid. In addition, even at the highest capillary number for which monodisperse drops can be formed, pressure oscillations persist, indicating that drop formation in confined geometries does not transition to an entirely shear-driven mechanism, but to a mechanism combining squeezing and shearing.

Measuring the elastic modulus of microgels using microdrops - Abate, Adam R.; Han, Lloyd; Jin, Lihua; Zhigang Suo; Weitz, David A (Soft Matter, 2012)
Two microgel particles are encapsulated in a microdrop having a spherical diameter smaller than the sum of the diameters of the microgels; this causes the microgels to be squeezed together by the oil-water interface of the drop, in turn, making the drop ellipsoidal in shape. By modeling the force applied to the microgels by the drop and equating this to the Hertz contact force of their deformation, we are able to estimate their elastic modulus. By varying the surface tension and shape of the drops, we are able to measure the modulus of the microgels under different loads. This provides a simple technique for quantifying the elasticity of small, deformable objects, including liquid drops, microgels, and cells.

Colloidal gelation of oppositely charged particles - Russell, Emily R.; Sprakel, Joris; Kodger, Thomas E.; Weitz, David A (Soft Matter, 2012)
Colloidal gelation has been extensively studied for the case of purely attractive systems, but little is understood about how colloidal gelation is affected by the presence of repulsive interactions. Here we demonstrate the gelation of a binary system of oppositely charged colloids, in which repulsive interactions compete with attractive interactions. We observe that gelation is controlled by varying the total volume fraction, the interaction strength, and the new tuning parameter of the mixing ratio of the two particle types, and present a state diagram of gelation along all these phase-space coordinates. Contrary to commonly studied purely attractive gels, in which weakly quenched gels are more compact and less tenuous, we find that particles in these binary gels form fewer contacts and the gels become more tenuous as we approach the gel point. This suggests that a different mechanism governs gel formation and ultimate structure in binary gelation: particles are unable to form additional favorable contacts through rearrangements, due to the competition of repulsive interactions between similarly charged colloids and attractive interactions between oppositely charged colloids.

Controlled synthesis of cell-laden microgels by radical-free gelation in droplet microfluidics - Rossow, Torsten; Heyman, John A.; Ehrlicher, Allen J.; Langhoff, Arne; Weitz, David A; Haag, Rainer; Seiffert, Sebastian (Journal of the American Chemical Society, 2012)
Micrometer-sized hydrogel particles that contain living cells can be fabricated with exquisite control through the use of droplet-based microfluidics and bioinert polymers such as polyethyleneglycol (PEG) and hyperbranched polyglycerol (hPG). However, in existing techniques, the microgel gelation is often achieved through harmful reactions with free radicals. This is detrimental for the viability of the encapsulated cells. To overcome this limitation, we present a technique that combines droplet microfluidic templating with bio-orthogonal thiol-ene click reactions to fabricate monodisperse, cell laden microgel particles. The gelation of these microgels is achieved via the nucleophilic Michael addition of dithiolated PEG macro-cross-linkers to acrylated hPG building blocks and does not require any initiator. We systematically vary the microgel properties through the use of PEG linkers with different molecular weights along with different concentrations of macromonomers to investigate the influence of these parameters on the viability and proliferation of encapsulated yeast cells. We also demonstrate the encapsulation of mammalian cells including fibroblasts and lymphoblasts.

Drop formation in non-planar microfluidic devices - Rotem, Assaf; Abate, Adam R.; Utada, Andrew S.; van Steijn, Volkert; Weitz, David A (Lab on a Chip, 2012)
Microfluidic devices can be used to produce single or multiple emulsions with remarkably precise control of both the contents and size of the drops. Since each level of a multiple emulsion is formed by a distinct fluid stream, very efficient encapsulation of materials can be achieved. To obtain high throughput, these devices can be fabricated lithographically, allowing many devices to operate in parallel. However, to form multiple emulsions using a planar microfluidic device, the wettability of its surface must switch from hydrophobic to hydrophilic on the scale of micrometers where the drops are formed; this makes the fabrication of the devices very difficult. To overcome this constraint, we introduce non-planar microfluidic devices with graduated thicknesses; these can make drops even when their wetting properties do not favor drop formation. Nevertheless, the dependence of drop formation on the device geometry, the flow rates and the properties of the fluids, particularly in the case of unfavorable wetting, is very complex, making the successful design of these devices more difficult. Here we show that there exists a critical value of flow of the continuous phase above which drop formation occurs; this value decreases by two orders of magnitude as the wetting to the device wall of the continuous phase improves. We demonstrate how this new understanding can be used to optimize device design for efficient production of double or multiple emulsions.

Emulsion templating of poly(lactic acid) particles: Droplet formation behavior - Vladisavljevic, Goran T.; Duncanson, Wynter J.; Shum, Ho Cheung; Weitz, David A (Langmuir, 2012)
Monodisperse poly(DL-lactic acid) (PLA) particles of diameters between 11 and 121 mu m were fabricated in flow focusing glass microcapillary devices by evaporation of dichloromethane (DCM) from emulsion droplets at room temperature. The dispersed phase was 5% (w/w) PLA in DCM containing 0.1-2 mM Nile Red and the continuous phase was 5% (w/w) poly(vinyl alcohol) in reverse osmosis water. Particle diameter was 2.7 times smaller than the diameter of the emulsion droplet template, indicating very low particle porosity. Monodisperse droplets have only been produced under dripping regime using a wide range of dispersed phase flow rates (0.002-7.2 cm(3).h(-1)), continuous phase flow rates (0.3-30 cm(3).h(-1)), and orifice diameters (50-237 mu m). In the dripping regime, the ratio of droplet diameter to orifice diameter was inversely proportional to the 0.39 power of the ratio of the continuous phase flow rate to dispersed phase flow rate. Highly uniform droplets with a coefficient of variation (CV) below 2% and a ratio of the droplet diameter to orifice diameter of 0.5-1 were obtained at flow rate ratios of 4-25. Under jetting regime, polydisperse droplets (CV > 6%) were formed by detachment from relatively long jets (between 4 and 10 times longer than droplet diameter) and a ratio of the droplet size to orifice size of 2-5.

High-yield cell ordering and deterministic cell-in-droplet encapsulation using Dean flow in a curved microchannel - Kemna, Evelien W. M.; Schoeman, Rogier M.; Wolbers, Floor; Vermes, Istvan; Weitz, David A; van den Berg, Albert (Lab on a Chip, 2012)
In this article high-yield (77%) and high-speed (2700 cells s(-1)) single cell droplet encapsulation is described using a Dean-coupled inertial ordering of cells in a simple curved continuous microchannel. By introducing the Dean force, the particles will order to one equilibrium position after travelling less than 1 cm. We use a planar curved microchannel structure in PDMS to spatially order two types of myeloid leukemic cells (HL60 and K562 cells), enabling deterministic single cell encapsulation in picolitre drops. An efficiency of up to 77% was reached, overcoming the limitations imposed by Poisson statistics for random cell loading, which yields only 37% of drops containing a single cell. Furthermore, we confirm that > 90% of the cells remain viable. The simple planar structure and high throughput provided by this passive microfluidic approach makes it attractive for implementation in lab on a chip (LOC) devices for single cell applications using droplet-based platforms.

Low intensity ultrasound perturbs cytoskeleton dynamics - Mizrahi, Natalya; Zhou, Enhua H.; Lenormand, Guillaume; Krishnan, Ramaswamy; Weihs, Daphne; James P. Butler; Weitz, David A; Jeffrey J. Fredberg; Kimmel, Eitan (Soft Matter, 2012)
Therapeutic ultrasound is widely employed in clinical applications but its mechanism of action remains unclear. Here we report prompt fluidization of a cell and dramatic acceleration of its remodeling dynamics when exposed to low intensity ultrasound. These physical changes are caused by very small strains (10(-5)) at ultrasonic frequencies (10(6) Hz), but are closely analogous to those caused by relatively large strains (10(-1)) at physiological frequencies (10(0) Hz). Moreover, these changes are reminiscent of rejuvenation and aging phenomena that are well-established in certain soft inert materials. As such, we suggest cytoskeletal fluidization together with resulting acceleration of cytoskeletal remodeling events as a mechanism contributing to the salutary effects of low intensity therapeutic ultrasound.

Microfluidic fabrication of water-in-water (w/w) jets and emulsions - Shum, Ho Cheung; Varnell, Jason; Weitz, David A (Biomicrofluidics, 2012)
We demonstrate the generation of water-in-water ( w/w) jets and emulsions by combining droplet microfluidics and aqueous two-phase systems ( ATPS). The application of ATPS in microfluidics has been hampered by the low interfacial tension between typical aqueous phases. The low tension makes it difficult to form w/w droplets with conventional droplet microfluidic approaches. We show that by mechanically perturbing a stable w/w jet, w/w emulsions can be prepared in a controlled and reproducible fashion. We also characterize the encapsulation ability of w/w emulsions and demonstrate that their encapsulation efficiency can be significantly enhanced by inducing formation of precipitates and gels at the w/w interfaces. Our work suggests a biologically and environmentally friendly platform for droplet microfluidics and establishes the potential of w/w droplet microfluidics for encapsulation-related applications. (C) 2012 American Institute of Physics. [doi:10.1063/1.3670365]

Origin of de-swelling and dynamics of dense ionic microgel suspensions - Romeo, Giovanni; Imperiali, Luna; Kim, Jin-Woong; Fernandez-Nieves, Alberto; Weitz, David A (Journal of Chemical Physics, 2012)
A direct consequence of the finite compressibility of a swollen microgel is that it can shrink and deform in response to an external perturbation. As a result, concentrated suspensions of these particles exhibit relaxation dynamics and rheological properties which can be very different with respect to those of a hard sphere suspension or an emulsion. We study the reduction in size of ionic microgels in response to increasing number of particles to show that particle shrinkage originates primarily from steric compression, and that the effect of ion-induced de-swelling of the polymer network is negligible. With increasing particle concentration, the single particle dynamics switch from those typical of a liquid to those of a super-cooled liquid and finally to those of a glass. However, the transitions occur at volume fractions much higher than those characterizing a hard sphere system. In the supercooled state, the distribution of displacements is non-Gaussian and the dependence of the structural relaxation time on volume fraction is describable by a Volger-Fulcher-Tammann function. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.3697762]

Osmotic pressure can regulate matrix gene expression in Bacillus subtilis - Rubinstein, Shmuel M; Kolodkin-Gal, Ilana; Mcloon, Anna; Chai, Liraz; Kolter, Roberto; Losick, Richard; Weitz, David A (Molecular Microbiology, 2012)
Many bacteria organize themselves into structurally complex communities known as biofilms in which the cells are held together by an extracellular matrix. In general, the amount of extracellular matrix is related to the robustness of the biofilm. Yet, the specific signals that regulate the synthesis of matrix remain poorly understood. Here we show that the matrix itself can be a cue that regulates the expression of the genes involved in matrix synthesis in Bacillus subtilis. The presence of the exopolysaccharide component of the matrix causes an increase in osmotic pressure that leads to an inhibition of matrix gene expression. We further show that non-specific changes in osmotic pressure also inhibit matrix gene expression and do so by activating the histidine kinase KinD. KinD, in turn, directs the phosphorylation of the master regulatory protein Spo0A, which at high levels represses matrix gene expression. Sensing a physical cue such as osmotic pressure, in addition to chemical cues, could be a strategy to non-specifically co-ordinate the behaviour of cells in communities composed of many different species.

Osmotic spreading of Bacillus subtilis biofilms driven by an extracellular matrix - Seminara, Agnese; Angelini, Thomas E.; Wilking, James N.; Vlamakis, Hera; Ebrahim, Senan; Kolter, Roberto; Weitz, David A; Michael P. Brenner (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Bacterial biofilms are organized communities of cells living in association with surfaces. The hallmark of biofilm formation is the secretion of a polymeric matrix rich in sugars and proteins in the extracellular space. In Bacillus subtilis, secretion of the exopolysaccharide (EPS) component of the extracellular matrix is genetically coupled to the inhibition of flagella-mediated motility. The onset of this switch results in slow expansion of the biofilm on a substrate. Different strains have radically different capabilities in surface colonization: Flagella-null strains spread at the same rate as wild type, while both are dramatically faster than EPS mutants. Multiple functions have been attributed to the EPS, but none of these provides a physical mechanism for generating spreading. We propose that the secretion of EPS drives surface motility by generating osmotic pressure gradients in the extracellular space. A simple mathematical model based on the physics of polymer solutions shows quantitative agreement with experimental measurements of biofilm growth, thickening, and spreading. We discuss the implications of this osmotically driven type of surface motility for nutrient uptake that may elucidate the reduced fitness of the matrix-deficient mutant strains.

Rapid growth of large, defect-free colloidal crystals - Jensen, K. E.; Pennachio, D.; D. Recht; Weitz, D. A.; F. Spaepen (Soft Matter, 2012)
We demonstrate controlled growth of face-centered cubic (FCC), monodisperse hard-sphere colloidal crystals by centrifugation at up to 3000g onto FCC (100) templates. Such rapid deposition rates often result in an amorphous sediment. Surprisingly, however, growth onto (100) templates results only in single crystals with few or no extended defects. By contrast, deposition onto flat, (111), or (110) templates causes rapid disordering to an amorphous sediment if the dimensionless flux (particle volume fraction x Peclet number) exceeds a critical value. This crystalline-to-amorphous crossover results from the degeneracy of possible stacking positions for these orientations. No such degeneracy exists for growth onto (100). After growth, extended defects can nucleate and grow only if the crystal exceeds a critical thickness that depends on the lattice misfit with the template spacing. The experimental observations of the density of misfit dislocations are accounted for by the Frank-van der Merwe theory, adapted for the depth-dependent variation of lattice spacing and elastic constants that results from the gravitational pressure.

Microgel Suspensions: Fundamentals and Applications - Fernandez‐Nieves, Alberto; Wyss, Hans W.; Mattsson, Johan; Weitz, DavidA. (Wiley-VCH, 2011)
Providing a vital link between chemistry and physics on the nanoscale, this book offers concise coverage of the entire topic in five major sections, beginning with synthesis of microgel particles and continuing with their physical properties. The phase behavior and dynamics of resulting microgel suspensions feature in the third section, followed by their mechanical properties. It concludes with detailed accounts of numerous industrial, commercial and medical applications.

Enhanced encapsulation of actives in self-sealing microcapsules by precipitation in capsule shells - Zhao, Yuanjin; Shum, Ho Cheung; Adams, Laura L. A.; Sun, Bing Jie; Holtze, Christian; Gu, Zhongze; Weitz, David A (Langmuir, 2011)
Microcapsules with core-shell structures are excellent vehicles for the encapsulation of active ingredients; however, the actives often leak out of these structures over time, without observable damage to them. We present a novel approach to enhancing the encapsulation of active ingredients inside microcapsules. We use two components that can form solid precipitates upon mixing and add one each to the microcapsule core and to the continuous phase. The components diffuse through the shell in the same manner as the actives, but upon meeting, they precipitate to form solid particles within the shell; this significantly reduces leakage through the shell of the microcapsules. We show that the reduction in the leakage of actives is due to the blockage of channels or pores that exist in the shell of the capsules by the solid precipitates.

Microfluidic generation of multifunctional quantum dot barcode particles - Zhao, Yuanjin; Shum, Ho Cheung; Chen, Haosheng; Adams, Laura L. A.; Gu, Zhongze; Weitz, David A (Journal of the American Chemical Society, 2011)
We develop a new strategy to prepare quantum dot (QD) barcode particles by polymerizing double-emulsion droplets prepared in capillary microfluidic devices. The resultant barcode particles are composed of stable QD-tagged core particles surrounded by hydrogel shells. These particles exhibit uniform spectral characteristics and excellent coding capability, as confirmed by photoluminescence analyses. By using double-emulsion droplets with two inner droplets of distinct phases as templates, we have also fabricated anisotropic magnetic barcode particles with two separate cores or with a Janus core. These particles enable optical encoding and magnetic separation, thus making them excellent functional barcode particles in biomedical applications.

Biophysical properties of normal and diseased renal glomeruli - Wyss, Hans M.; Henderson, Joel M.; Byfield, Fitzroy J.; Bruggeman, Leslie A.; Ding, Yaxian; Huang, Chunfa; Suh, Jung Hee; Franke, Thomas; Mele, Elisa; Pollak, Martin R.; Miner, Jeffrey H.; Paul A. Janmey; et al. (American Journal of Physiology-Cell Physiology, 2011)
The mechanical properties of tissues and cells including renal glomeruli are important determinants of their differentiated state, function, and responses to injury but are not well characterized or understood. Understanding glomerular mechanics is important for understanding renal diseases attributable to abnormal expression or assembly of structural proteins and abnormal hemodynamics. We use atomic force microscopy (AFM) and a new technique, capillary micromechanics, to measure the elastic properties of rat glomeruli. The Young's modulus of glomeruli was 2,500 Pa, and it was reduced to 1,100 Pa by cytochalasin and latunculin, and to 1,400 Pa by blebbistatin. Cytochalasin or latrunculin reduced the F/G actin ratios of glomeruli but did not disrupt their architecture. To assess glomerular biomechanics in disease, we measured the Young's moduli of glomeruli from two mouse models of primary glomerular disease, Col4a3(-/-) mice (Alport model) and Tg26(HIV/nl) mice (HIV-associated nephropathy model), at stages where glomerular injury was minimal by histopathology. Col4a3(-/-) mice express abnormal glomerular basement membrane proteins, and Tg26(HIV/nl) mouse podocytes have multiple abnormalities in morphology, adhesion, and cytoskeletal structure. In both models, the Young's modulus of the glomeruli was reduced by 30%. We find that glomeruli have specific and quantifiable biomechanical properties that are dependent on the state of the actin cytoskeleton and nonmuscle myosins. These properties may be altered early in disease and represent an important early component of disease. This increased deformability of glomeruli could directly contribute to disease by permitting increased distension with hemodynamic force or represent a mechanically inhospitable environment for glomerular cells.

Nonlinear viscoelasticity of actin transiently cross-linked with mutant alpha-actinin-4 - Yao, Norman Y.; Becker, Daniel J.; Broedersz, Chase P.; Depken, Martin; MacKintosh, Frederick C; Pollak, Martin R.; Weitz, David A (Journal of Molecular Biology, 2011)
Filamentous actin and associated actin binding proteins play an essential role in governing the mechanical properties of eukaryotic cells. They can also play a critical role in disease; for example, mutations in alpha-actinin-4 (Actn4), a dynamic actin cross-linking protein, cause proteinuric disease in humans and mice. Amino acid substitutions strongly affect the binding affinity and protein structure of Actn4. To study the physical impact of such substitutions on the underlying cytoskeletal network, we examine the bulk mechanical behavior of in vitro actin networks cross-linked with wild-type and mutant Actn4. These networks exhibit a complex viscoelastic response and are characterized by fluid-like behavior at the longest timescales, a feature that can be quantitatively accounted for through a model governed by dynamic cross-linking. The elastic behavior of the network is highly nonlinear, becoming much stiffer with applied stress. This nonlinear elastic response is also highly sensitive to the mutations of Actn4. In particular, we observe that actin networks cross-linked with Actn4 bearing the disease-causing K255E mutation are more brittle, with a lower breaking stress in comparison to networks cross-linked with wild-type Actn4. Furthermore, a mutation that ablates the first actin binding site (ABS1) in Actn4 abrogates the network's ability to stress-stiffen is standard nomenclature. These changes in the mechanical properties of actin networks cross-linked with mutant Actn4 may represent physical determinants of the underlying disease mechanism in inherited focal segmental glomerulosclerosis. (C) 2011 Elsevier Ltd. All rights reserved.

Biofilms as complex fluids - Wilking, James N.; Angelini, Thomas E.; Seminara, Agnese; Michael P. Brenner; Weitz, David A (Mrs Bulletin, 2011)
Bacterial biofilms are interface-associated colonies of bacteria embedded in an extracellular matrix that is composed primarily of polymers and proteins. They can be viewed in the context of soft matter physics: the rigid bacteria are analogous to colloids, and the extracellular matrix is a cross-linked polymer gel. This perspective is beneficial for understanding the structure, mechanics, and dynamics of the biofilm. Bacteria regulate the water content of the biofilm by controlling the composition of the extracellular matrix, and thereby controlling the mechanical properties. The mechanics of well-defined soft materials can provide insight into the mechanics of biofilms and, in particular, the viscoelasticity. Furthermore, spatial heterogeneities in gene expression create heterogeneities in polymer and surfactant production. The resulting concentration gradients generate forces within the biofilm that are relevant for biofilm spreading and survival.

Drug dissolution chip (DDC): A microfluidic approach for drug release - Windbergs, Maike; Weitz, David A (Small, 2011)
The first pharmaceutical dissolution testing device for multiparticulate drug delivery systems on a microfluidic chip is presented. This versatile platform technology allows for simultaneous analysis of the drug concentration in the dissolution medium and of the solid parts of the sample immobilized in the device with different analytical techniques. By mimicking the fate of drug release in the human body, this can contribute to the optimization of therapeutic effectiveness during the development of novel drug release systems.

Colloidal glasses - Weitz, David A (Glasses and Grains, 2011)
Classes and granular materials share many features in common: Both can flow under some conditions but form disordered solids under other conditions. The similarity is captured within the jamming phase diagram, which considers how the solid-like state is fluidized with decreasing density, increasing shear stress, and increasing agitation, due to temperature in the case of molecular glasses and to shaking or some other form of agitation in the case of granular materials. Colloidal particles also undergo both jamming and glass transitions. They have the advantage that they are thermalized by temperature and that the particles themselves are large enough to be directly visualized. Thus, the study of the glass transition in colloids can provide an interesting comparison between molecular glasses and granular materials. This paper reviews the properties of colloidal suspensions near the colloidal glass transition, and explores both the glass-like properties and the jamming properties of these materials.

Controllable microfluidic production of multicomponent multiple emulsions - Wang, Wei; Xie, Rui; Ju, Xiao-Jie; Luo, Tao; Liu, Li; Weitz, David A; Chu, Liang-Yin (Lab on a Chip, 2011)
A hierarchical and scalable microfluidic device constructed from a combination of three building blocks enables highly controlled generation of multicomponent multiple emulsions. The number, ratio and size of droplets, each with distinct contents being independently co-encapsulated in the same level, can be precisely controlled. The building blocks are a drop maker, a connector and a liquid extractor; combinations of these enable the scale-up of the device to create higher-order multicomponent multiple emulsions with exceptionally diverse structures. These multicomponent multiple emulsions offer a versatile and promising platform for precise encapsulation of incompatible actives or chemicals, for synergistic delivery and biochemical and chemical reactions, and for engineering multicompartment materials with controlled internal phases.

On-demand drug delivery from self-assembled nanofibrous gels: A new approach for treatment of proteolytic disease - Vemula, Praveen Kumar; Boilard, Eric; Syed, Abdullah; Campbell, Nathaniel R.; Muluneh, Melaku; Weitz, David A; Lee, David M.; Karp, Jeffrey M (Journal of Biomedical Materials Research Part A, 2011)
Local delivery of drugs offers the potential for high local drug concentration while minimizing systemic toxicity, which is often observed with oral dosing. However, local depots are typically administered less frequently and include an initial burst followed by a continuous release. To maximize efficiency of therapy, it is critical to ensure that drug is only released when needed. One of the hallmarks of rheumatoid arthritis, for example, is its variable disease activity consisting of exacerbations of inflammation punctuated by periods of remission. This presents significant challenges for matching localized drug delivery with disease activity. An optimal system would be nontoxic and only release drugs during the period of exacerbation, self-titrating in response to the level of inflammation. We report the development of an injectable self-assembled nanofibrous hydrogel, from a generally recognized as safe material, which is capable of encapsulation and release of agents in response to specific enzymes that are significantly upregulated in a diseased state including matrix metalloproteinases (MMP-2 and MMP-9) and esterases. We show that these self-assembled nanofibrous gels can withstand shear forces that may be experienced in dynamic environments such as joints, can remain stable following injection into healthy joints of mice, and can disassemble in vitro to release encapsulated agents in response to synovial fluid from arthritic patients. This novel approach represents a next-generation therapeutic strategy for localized treatment of proteolytic diseases. (C) 2011 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 97A: 103-110, 2011.

Collective cell guidance by cooperative intercellular forces - Tambe, Dhananjay T.; Hardin, C. Corey; Angelini, Thomas E.; Rajendran, Kavitha; Park, Chan Young; Serra-Picamal, Xavier; Zhou, Enhua H.; Zaman, Muhammad H.; James P. Butler; Weitz, David A; Jeffrey J. Fredberg; Trepat, Xavier (Nature Materials, 2011)
Cells comprising a tissue migrate as part of a collective. How collective processes are coordinated over large multi-cellular assemblies has remained unclear, however, because mechanical stresses exerted at cell-cell junctions have not been accessible experimentally. We report here maps of these stresses within and between cells comprising a monolayer. Within the cell sheet there arise unanticipated fluctuations of mechanical stress that are severe, emerge spontaneously, and ripple across the monolayer. Within that stress landscape, local cellular migrations follow local orientations of maximal principal stress. Migrations of both endothelial and epithelial monolayers conform to this behaviour, as do breast cancer cell lines before but not after the epithelial-mesenchymal transition. Collective migration in these diverse systems is seen to be governed by a simple but unifying physiological principle: neighbouring cells join forces to transmit appreciable normal stress across the cell-cell junction, but migrate along orientations of minimal intercellular shear stress.

Early development drug formulation on a chip: Fabrication of nanoparticles using a microfluidic spray dryer - Thiele, Julian; Windbergs, Maike; Abate, Adam R.; Trebbin, Martin; Shum, Ho Cheung; Foerster, Stephan; Weitz, David A (Lab on a Chip, 2011)
Early development drug formulation is exacerbated by increasingly poor bioavailability of potential candidates. Prevention of attrition due to formulation problems necessitates physicochemical analysis and formulation studies at a very early stage during development, where the availability of a new substance is limited to small quantities, thus impeding extensive experiments. Miniaturization of common formulation processes is a strategy to overcome those limitations. We present a versatile technique for fabricating drug nanoformulations using a microfluidic spray dryer. Nanoparticles are formed by evaporative precipitation of the drug-loaded spray in air at room temperature. Using danazol as a model drug, amorphous nanoparticles of 20-60 nm in diameter are prepared with a narrow size distribution. We design the device with a geometry that allows the injection of two separate solvent streams, thus enabling co-spray drying of two substances for the production of drug co-precipitates with tailor-made composition for optimization of therapeutic efficiency.

Cocktail physics - Sinha, Naveen N.; Weitz, David A (Physics World, 2011)
Many top chefs are well known for taking a more scientific approach to cooking in recent years, and some “mixologists” are now extending the same philosophy to cocktails. Naveen N. Sinha and David A. Weitz explain the theory and techniques behind these increasingly exotic mixed drinks.

Hierarchical porous materials made by drying complex suspensions - Studart, Andre R.; Studer, Julia; Xu, Lei; Yoon, Kisun; Shum, Ho Cheung; Weitz, David A (Langmuir, 2011)
Porous structures containing pores at different length scales are often encountered in nature and are important in many applications. While several processing routes have been demonstrated to create such hierarchical porous materials, most methods either require chemical gelation reactions or do not allow for the desired control of pore sizes over multiple length scales. We describe a versatile and simple approach to produce tailor-made hierarchical porous materials that relies solely on the process of drying. Our results show that simple drying of a complex suspension can lead to the self-assembly of droplets, colloidal particles and molecular species into unique 3D hierarchical porous structures. Using a microfluidic device to produce monodisperse templating droplets of tunable size, we prepared materials with up to three levels of hierarchy exhibiting monodisperse pores ranging from 10 nm to 800 mu m. While the size of macropores obtained after drying is determined by the size of initial droplets, the interconnectivity between macropores is strongly affected by the type of droplet stabilizer (surfactants or particles). This simple route can be used to prepare porous materials of many chemical compositions and has great potential for creating artificial porous structures that capture some of the exquisite hierarchical features of porous biological materials.

Hyperbranched polyglycerols on the nanometer and micrometer scale - Steinhilber, Dirk; Seiffert, Sebastian; Heyman, John A.; Paulus, Florian; Weitz, David A; Haag, Rainer (Biomaterials, 2011)
We report the preparation of polyglycerol particles on different length scales by extending the size of hyperbranched polyglycerols (3 nm) to nanogels (32 nm) and microgels (140 and 220 mu m). We use miniemulsion templating for the preparation of nanogels and microfluidic templating for the preparation of microgels, which we obtain through a free-radical polymerization of hyperbranched polyglycerol decaacrylate and polyethylene glycol-diacrylate. The use of mild polymerization conditions allows yeast cells to be encapsulated into the resultant microgels with cell viabilities of approximately 30%. (C) 2010 Elsevier Ltd. All rights reserved.

Stress enhancement in the delayed yielding of colloidal gels - Sprakel, Joris; Lindstroem, Stefan B.; Kodger, Thomas E.; Weitz, David A (Physical Review Letters, 2011)
Networks of aggregated colloidal particles are solidlike and can sustain an applied shear stress while exhibiting little or no creep; however, ultimately they will catastrophically fail. We show that the time delay for this yielding decreases in two distinct exponential regimes with applied stress. This behavior is universal and found for a variety of colloidal gel systems. We present a bond-rupture model that quantitatively describes this behavior and highlights the role of mesoscopic structures. Our result gives new insight into the nature of yielding in these soft solid materials.

Dewetting-induced membrane formation by adhesion of amphiphile-laden interfaces - Shum, Ho Cheung; Santanach-Carreras, Enric; Kim, Jin-Woong; Ehrlicher, Allen; Bibette, Jerome; Weitz, David A (Journal of the American Chemical Society, 2011)
We introduce an approach for forming bilayer polymer membranes by adhesion of amphiphile-laden interfaces. This adhesion is induced by a reduction of solvent quality for the amphiphilic diblock copolymers through selective evaporation of good solvent in the solvent mixture. By combining this membrane formation mechanism with a double-emulsion-templated approach for vesicle formation, we fabricate monodisperse polymersomes that exhibit excellent membrane uniformity, and structural stability, using a method that has high encapsulation efficiency. Moreover, we also show that the technique is versatile and can be applied to different block copolymers. The ability to direct the assembly of amphiphiles into a membrane creates new opportunities to engineer the structures of vesicles on the level of the individual bilayer leaflets.

Multicompartment polymersomes from double emulsions - Shum, Ho Cheung; Zhao, Yuan-jin; Kim, Shin-Hyun; Weitz, David A (Angewandte Chemie-International Edition, 2011)
Versatile chambers: A microfluidic technique is used to generate polymersomes with multiple compartments using double emulsions with different morphology as templates (see scheme). The polymersomes could be utilized for encapsulation of multiple substances and as reaction vessels that enable triggered reaction with controlled stoichometry of the reactants.

Reduced UV light scattering in PDMS microfluidic devices - Seiffert, Sebastian; Dubbert, Janine; Richtering, Walter; Weitz, David A (Lab on a Chip, 2011)
Microfluidic devices which consist of polydimethylsiloxane ( PDMS) are used extensively for the production of polymer microparticles through the use of droplet templating and on-chip photopolymerization. However, in existing methods, spatial confinement of the photochemical droplet solidification is impaired by UV light scattering inside the PDMS elastomer. We present a technique to load PDMS microfluidic devices with a fluorescent dye that absorbs the scattered UV light and shifts it to longer wavelengths. By this means, the stray light is no longer harmful, and UV exposure can be limited to a desired region on the microfluidic chip.

Direct visualization of pH-dependent evolution of structure and dynamics in microgel suspensions - Muluneh, M.; Sprakel, J.; Wyss, H. M.; Mattsson, J.; Weitz, D. A. (Journal of Physics-Condensed Matter, 2011)
We use 3D confocal microscopy combined with image analysis and particle tracking techniques to study the structure and dynamics of aqueous suspensions of fluorescently labelled p(NIPAm-co-AAc) microgel particles. By adjusting the pH we can tune the interactions between the microgel particles from purely repulsive near neutral pH, to weakly attractive at low pH. This change in the interaction potential has a pronounced effect on the manner in which the suspensions solidify. We directly follow the evolution of the system after a quench from the liquid state to obtain detailed information on the route to kinetic arrest. At low pH and low concentration, dynamic arrest results mainly from crystallization driven by the attraction between particles; crystal nucleation occurs homogeneously throughout the sample and does not appear to be localized to geometric boundaries. Moreover, the growth of crystals is characterized by nucleation-limited kinetics where a rapid growth of crystal domains takes place after a long concentration-dependent lag time. At low pH and high concentration, relaxation of the suspension is constrained and it evolves only slightly, resulting in a disordered solid. At neutral pH, the dynamics are a function of the particle number concentration only; a high concentration leads to the formation of a disordered soft glassy solid.

Controlling droplet incubation using close-packed plug flow - Mary, Pascaline; Abate, Adam R.; Agresti, Jeremy J.; Weitz, David A (Biomicrofluidics, 2011)
Controlling droplet incubation is critical for droplet-based microfluidic applications; however, current techniques are either of limited precision or place strict limits on the incubation times that can be achieved. Here, we present a simple technique to control incubation time by exploiting close-packed plug flow. In contrast to other techniques, this technique is applicable to very short and very long incubation times. (C) 2011 American Institute of Physics. [doi:10.1063/1.3576934]

On-chip background noise reduction for cell-based assays in droplets - Mary, Pascaline; Chen, Angela; Chen, Irwin; Abate, Adam R.; Weitz, David A (Lab on a Chip, 2011)
Droplet-based microfluidics provides an excellent platform for high-throughput biological assays. Each droplet serves as a reaction vessel with a volume as small as a few picolitres. This is an important technology for a high variety of applications. However this technology is restricted to homogeneous assays as it is very difficult to wash reagents from the reaction vessel. To help overcome this limitation, we introduce a method to effectively dilute the content of a droplet while retaining the high throughput. We use electrocoalescence to merge the parent drop with a much larger drop containing only solvent, thereby increasing the volume of the drop by as much as a factor of 14. Three T-junctions then break the larger drop into eight smaller droplets. This dilution and break-up process can be repeated, thus leading to many drops comparable in size to the original one but with much lower concentration of reagents. The system is fully integrated in a PDMS device. To demonstrate its power, we perform a labelling reaction at the surface of the cells by coencapsulating yeast cells expressing S6 peptide tags with the enzyme SFP synthase and the fluorescent substrate CoA 488. After reaction, the droplets are diluted twice using the system and the intensity of their fluorescence is measured. This noise reduction method enables us to more easily distinguish the fluorescence at the surface of a single cell from the fluorescent background inside the droplet.

Control of non-linear elasticity in F-actin networks with microtubules - Lin, Yi-Chia; Koenderink, Gijsje H; MacKintosh, Frederick C; Weitz, David A (Soft Matter, 2011)
We measure the elastic properties of composite cytoskeletal networks consisting of cross-linked actin filaments and microtubules. We show that even a small concentration of microtubules leads to dramatic and qualitative changes in the non-linear elastic properties of the actin filament networks. Specifically, we find that microtubules promote non-linear stiffening of F-actin networks because they are much stiffer than actin filaments and therefore suppress non-uniform strain. This finding may be relevant for interpretation of the mechanical behavior of cells, while also suggesting a new way to reinforce the non-linear elasticity of semiflexible polymer materials.

Highly monodisperse conjugated polymer particles synthesized with drop-based microfluidics - Kuehne, Alexander J. C.; Weitz, David A (Chemical Communications, 2011)
A facile method for preparing highly monodisperse, sub-micrometre conjugated polymer particles is reported. The particles are prepared through emulsification of a conjugated polymer solution on a microfluidic chip followed by solvent evaporation. The particle size is tuned between 150 nm to 2 mu m, by controlling the polymer concentration.

A switchable digital microfluidic droplet dye-laser - Kuehne, Alexander J. C.; Gather, Malte C.; Eydelnant, Irwin A.; Yun, Seok-Hyun; Weitz, David A; Aaron R. Wheeler (Lab on a Chip, 2011)
Digital microfluidic devices allow the manipulation of droplets between two parallel electrodes. These electrodes can act as mirrors generating a micro-cavity, which can be exploited for a droplet dye-laser. Three representative laser-dyes with emission wavelengths spanning the whole visible spectrum are chosen to show the applicability of this concept. Sub-microlitre droplets of laser-dye solution are moved in and out of a lasing site on-chip to down-convert the UV-excitation light into blue, green and red laser-pulses.

Multiple polymersomes for programmed release of multiple components - Kim, Shin-Hyun; Shum, Ho Cheung; Kim, Jin Woong; Cho, Jun-Cheol; Weitz, David A (Journal of the American Chemical Society, 2011)
Long-term storage and controlled release of multiple components while avoiding cross-contamination have potentially important applications for pharmaceuticals and cosmetics. Polymersomes are very promising delivery vehicles but cannot be used to encapsulate multiple independent components and release them in a controlled manner. Here, we report a microfluidic approach to produce multiple polymersomes, or polymersomes-in-polymersome by design, enabling encapsulation and programmed release of multiple components. Monodisperse polymersomes are prepared from templates of double-emulsion drops, which in turn are injected as the innermost phase to form the second level of double-emulsion drops, producing double polymersomes. Using the same strategy, higher-order polymersomes are also prepared. In addition, incorporation of hydrophobic homopolymer into the different bilayers of the multiple polymersomes enables controlled and sequential dissociation of the different bilayer membranes in a programmed fashion. The high encapsulation efficiency of this microfluidic approach, as well as its programmability and the biocompatibility of the materials used to form the polymersomes, will provide new opportunities for practical delivery systems of multiple components.

Observation of spatial propagation of amyloid assembly from single nuclei - Knowles, Tuomas P. J.; White, Duncan A.; Abate, Adam R.; Agresti, Jeremy J.; Cohen, Samuel I. A.; Sperling, Ralph A.; De Genst, Erwin J.; Dobson, Christopher M; Weitz, David A (Proceedings of the National Academy of Sciences of the United States of America, 2011)
The crucial early stages of amyloid growth, in which normally soluble proteins are converted into fibrillar nanostructures, are challenging to study using conventional techniques yet are critical to the protein aggregation phenomena implicated in many common pathologies. As with all nucleation and growth phenomena, it is difficult to track individual nuclei in traditional macroscopic experiments, which probe the overall temporal evolution of the sample, but do not yield detailed information on the primary nucleation step as they mix independent stochastic events into an ensemble measurement. To overcome this limitation, we have developed microdroplet assays enabling us to detect single primary nucleation events and to monitor their subsequent spatial as well as temporal evolution, both of which we find to be determined by secondary nucleation phenomena. By deforming the droplets to high aspect ratio, we visualize in real-time propagating waves of protein assembly emanating from discrete primary nucleation sites. We show that, in contrast to classical gelation phenomena, the primary nucleation step is characterized by a striking dependence on system size, and the filamentous protein self-assembly process involves a highly nonuniform spatial distribution of aggregates. These findings deviate markedly from the current picture of amyloid growth and uncover a general driving force, originating from confinement, which, together with biological quality control mechanisms, helps proteins remain soluble and therefore functional in nature.

One-step emulsification of multiple concentric shells with capillary microfluidic devices - Kim, Shin-Hyun; Weitz, David A (Angewandte Chemie-International Edition, 2011)
Polymeric onions: A facile method to produce monodisperse multiple emulsion drops of high order is developed using a capillary microfluidic device. Coaxial multiphase flows are stabilized by confinement in microcapillary and emulsified to multiple emulsion drops. The breakup of coaxial interfaces, triggered by the core‐drop, facilitates the making of multiple emulsion drops of onionlike configuration.

Amphiphilic crescent-moon-shaped microparticles formed by selective adsorption of colloids - Kim, Shin-Hyun; Abbaspourrad, Alireza; Weitz, David A (Journal of the American Chemical Society, 2011)
We use a microfluidic device to prepare monodisperse amphiphilic particles in the shape of a crescent-moon and use these particles to stabilize oil droplets in water. The microfluidic device is comprised of a tapered capillary in a theta (theta) shape that injects two oil phases into water in a single receiving capillary. One oil is a fluorocarbon, while the second is a photocurable monomer, which partially wets the first oil drop; silica colloids in the monomer migrate and adsorb to the interface with water but do not protrude into the oil interface. Upon UV-induced polymerization, solid particles with the shape of a crescent moon are formed; removal of fluorocarbon oil yields amphiphilic particles due to the selective adsorption of silica colloids. The resultant amphiphilic microparticles can be used to stabilize oil drops in a mixture of water and ethanol; if they are packed to sufficient surface density on the interface of the oil drop, they become immobilized, preventing direct contact between neighboring drops, thereby providing the stability.

Double-emulsion drops with ultra-thin shells for capsule templates - Kim, Shin-Hyun; Kim, Jin Woong; Cho, Jun-Cheol; Weitz, David A (Lab on a Chip, 2011)
We introduce an emulsification technique that creates monodisperse double-emulsion drops with a core-shell geometry having an ultra-thin wall as a middle layer. We create a biphasic flow in a microfluidic capillary device by forming a sheath flow consisting of a thin layer of a fluid with high affinity to the capillary wall flowing along the inner wall of the capillary, surrounding the innermost fluid. This creates double-emulsion drops, using a single-step emulsification, having a very thin fluid shell. If the shell is solidified, its thickness can be small as a hundred nanometres or even less. Despite the small thickness of this shell, these structures are nevertheless very stable, giving them great potential for encapsulation. We demonstrate this by creating biodegradable microcapsules of poly(lactic acid) with a shell thickness of a few tens of nanometres, which are potentially useful for encapsulation and delivery of drugs, cosmetics, and nutrients.

Mechanical strain in actin networks regulates FilGAP and integrin binding to filamin A - Ehrlicher, A. J.; Nakamura, F.; Hartwig, J. H.; Weitz, D. A.; Stossel, T. P. (Nature, 2011)
Mechanical stresses elicit cellular reactions mediated by chemical signals. Defective responses to forces underlie human medical disorders(1-4) such as cardiac failure(5) and pulmonary injury(6). The actin cytoskeleton's connectivity enables it to transmit forces rapidly over large distances(7), implicating it in these physiological and pathological responses. Despite detailed knowledge of the cytoskeletal structure, the specific molecular switches that convert mechanical stimuli into chemical signals have remained elusive. Here we identify the actin-binding protein filamin A (FLNA)(8,9) as a central mechanotransduction element of the cytoskeleton. We reconstituted a minimal system consisting of actin filaments, FLNA and two FLNA-binding partners: the cytoplasmic tail of beta-integrin, and FilGAP. Integrins form an essential mechanical linkage between extracellular and intracellular environments, with beta-integrin tails connecting to the actin cytoskeleton by binding directly to filamin(4). FilGAP is an FLNA-binding GTPase-activating protein specific for RAC, which in vivo regulates cell spreading and bleb formation(10). Using fluorescence loss after photoconversion, a novel, high-speed alternative to fluorescence recovery after photobleaching(11), we demonstrate that both externally imposed bulk shear and myosin-II-driven forces differentially regulate the binding of these partners to FLNA. Consistent with structural predictions, strain increases beta-integrin binding to FLNA, whereas it causes FilGAP to dissociate from FLNA, providing a direct and specific molecular basis for cellular mechanotransduction. These results identify a molecular mechanotransduction element within the actin cytoskeleton, revealing that mechanical strain of key proteins regulates the binding of signalling molecules.

Rheology of attractive emulsions - Datta, Sujit S.; Gerrard, Dustin D.; Rhodes, Travers S.; Mason, Thomas G.; Weitz, David A (Physical Review E, 2011)
We show how attractive interactions dramatically influence emulsion rheology. Unlike the repulsive case, attractive emulsions below random close packing, phi(RCP), can form soft gel-like elastic solids. However, above phi(RCP), attractive and repulsive emulsions have similar elasticities. Such compressed attractive emulsions undergo an additional shear-driven relaxation process during yielding. Our results suggest that attractive emulsions begin to yield at weak points through the breakage of bonds, and, above phi(RCP), also undergo droplet configurational rearrangements.

Microfluidic fabrication of complex-shaped microfibers by liquid template-aided multiphase microflow - Choi, Chang-Hyung; Yi, Hyunmin; Hwang, Sora; Weitz, David A; Lee, Chang-Soo (Lab on a Chip, 2011)
This study presents a simple microfluidic approach to the rapid fabrication of complex-shaped microfibers (e.g., single hollow, double hollow, and microbelt), with highly uniform structures, based on a combination of the spontaneous formation of polymeric jet streams and in situ photopolymerization. Two laminar flows of a photocurable fluid and a liquid template (nonpolymerizing fluid) spontaneously form jet streams in equilibrium states in microfluidic channels because of the minimization of the interfacial energy between the two fluids. The formation of the jet streams strongly depends on the spreading coefficients and the evolution time along the downstream of the microfluidic system. Thus, the simple control of the spreading coefficients can guide microfibers into various shapes. The sizes of the core and shell of the hollow fibers can also be readily manipulated by the flow rates of the polymerizing fluid and the liquid template phase. Asymmetric hollow fibers can also be produced in different evolutionary states in the microfluidic system. The microfluidic approach shown here represents a significant step toward the easy fabrication of microfibers with readily controllable structures and geometries. We anticipate that this novel fabrication approach and the prediction method based on spreading coefficients presented in this work can be applied to produce a wide variety of functional microfibrous materials.

Breakup of double emulsions in constrictions - Chen, Haosheng; Li, Jiang; Shum, Ho Cheung; Stone, Howard A.; Weitz, David A (Soft Matter, 2011)
We report the controlled breakup of double emulsion droplets as they flow through an orifice of a tapered nozzle. The results are summarized in a phase diagram in terms of the droplet-to-orifice diameter ratio and the capillary number. We identify a flow regime where the inner aqueous phase is released.

Reactions in double emulsions by flow-controlled coalescence of encapsulated drops - Chen, Haosheng; Zhao, Yuanjin; Li, Jiang; Guo, Ming; Wan, Jiandi; Weitz, David A; Stone, Howard A. (Lab on a Chip, 2011)
We demonstrate a microfluidic method to first generate double emulsion droplets containing two different inner drops, and to then control the internal coalescence of the encapsulated drops. The advantages of the core-coalescence method are illustrated by fabricating high viscosity particles and by demonstrating the dissolution of cell membranes.

Glass-like dynamics of collective cell migration - Angelini, Thomas E.; Hannezo, Edouard; Trepat, Xavier; Marquez, Manuel; Jeffrey J. Fredberg; Weitz, David A (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Collective cell migration in tissues occurs throughout embryonic development, during wound healing, and in cancerous tumor invasion, yet most detailed knowledge of cell migration comes from single-cell studies. As single cells migrate, the shape of the cell body fluctuates dramatically through cyclic processes of extension, adhesion, and retraction, accompanied by erratic changes in migration direction. Within confluent cell layers, such subcellular motions must be coupled between neighbors, yet the influence of these subcellular motions on collective migration is not known. Here we study motion within a confluent epithelial cell sheet, simultaneously measuring collective migration and subcellular motions, covering a broad range of length scales, time scales, and cell densities. At large length scales and time scales collective migration slows as cell density rises, yet the fastest cells move in large, multicell groups whose scale grows with increasing cell density. This behavior has an intriguing analogy to dynamic heterogeneities found in particulate systems as they become more crowded and approach a glass transition. In addition we find a diminishing self-diffusivity of short-wavelength motions within the cell layer, and growing peaks in the vibrational density of states associated with cooperative cell-shape fluctuations. Both of these observations are also intriguingly reminiscent of a glass transition. Thus, these results provide a broad and suggestive analogy between cell motion within a confluent layer and the dynamics of supercooled colloidal and molecular fluids approaching a glass transition.

Air-bubble-triggered drop formation in microfluidics - Abate, Adam R.; Weitz, David A (Lab on a Chip, 2011)
In microfluidic devices, droplets are normally formed using T-junction or flow focus mechanisms. While both afford a high degree of control over drop formation, they are limited in maximum production rate by the jetting transition. Here, we introduce a new drop formation mechanism that is not limited by jetting, allowing much faster drop production.

Efficient encapsulation with plug-triggered drop formation - Abate, Adam R.; Rotem, Assaf; Thiele, Julian; Weitz, David A (Physical Review E, 2011)
Monodisperse microscale drops formed with microfluidic devices are useful for encapsulating cells, microgel particles, or even additional drops. These techniques are thus useful for applications ranging from high-throughput biology to monodisperse particle and capsule synthesis, which require encapsulation of such objects. However, it is challenging to efficiently encapsulate the objects in all drops; often, the objects are encapsulated inefficiently, resulting in many improperly filled, unusable drops. Here, we describe a phenomenon that allows very efficient encapsulation. We use the inflow of the object to plug the drop maker nozzle; the continued injection of the outer phase pinches off a drop, thereby encapsulating the object; this yields precisely one object encapsulated per drop.

Faster multiple emulsification with drop splitting - Abate, Adam R.; Weitz, David A (Lab on a Chip, 2011)
Microfluidic devices can form emulsions in which the drops have an intricate, controlled structure; however, a challenge is that the droplets are produced slowly, typically only a few millilitres per hour. Here, we present a simple technique to increase the production rate. Using a large drop maker, we produce large drops at a fast volumetric rate; by splitting these drops several times in a splitting array, we create drops of the desired small size. The advantage of this over forming the small drops directly using a small drop maker is that the drops can be formed at much faster rates. This can be applied to the production of single and multiple emulsions.

One-step formation of multiple emulsions in microfluidics - Abate, Adam R.; Thiele, Julian; Weitz, David A (Lab on a Chip, 2011)
We present a robust way to create multiple emulsions with controllable shell thicknesses that can vary over a wide range. We use a microfluidic device to create a coaxial jet of immiscible fluids; using a dripping instability, we break the jet into multiple emulsions. By controlling the thickness of each layer of the jet, we adjust the thicknesses of the shells of the multiple emulsions. The same method is also effective in creating monodisperse emulsions from fluids that cannot otherwise be controllably emulsified, such as, for example, viscoelastic fluids.

Syringe-vacuum microfluidics: A portable technique to create monodisperse emulsions - Abate, Adam R.; Weitz, David A (Biomicrofluidics, 2011)
We present a simple method for creating monodisperse emulsions with microfluidic devices. Unlike conventional approaches that require bulky pumps, control computers, and expertise with device physics to operate devices, our method requires only the microfluidic device and a hand-operated syringe. The fluids needed for the emulsion are loaded into the device inlets, while the syringe is used to create a vacuum at the device outlet; this sucks the fluids through the channels, generating the drops. By controlling the hydrodynamic resistances of the channels using hydrodynamic resistors and valves, we are able to control the properties of the drops. This provides a simple and highly portable method for creating monodisperse emulsions. (C) 2011 American Institute of Physics. [doi: 10.1063/1.3567093]

Synthesis of monodisperse microparticles from non-Newtonian polymer solutions with microfluidic devices - Abate, Adam R.; Kutsovsky, Mikhail; Seiffert, Sebastian; Windbergs, Maike; Pinto, Luis F. V.; Rotem, Assaf; Utada, Andrew S.; Weitz, David A (Advanced Materials, 2011)
Polymer solutions are useful precursors to synthesize microparticles with microfluidic devices, but most polymer solutions are incompatible with microfluidic emulsification due to their non-Newtonian flow characteristics. A technique is presented to form monodisperse particles from such solutions by surrounding them with a chaperoning Newtonian fluid and forcing both to pinch into preparticle drops.

Multicompartment polymersome gel for encapsulation - Shum, Ho Cheung; Weitz, David A (Soft Matter, 2011)
We introduce an approach that combines the concepts of emulsion-templating and dewetting for fabricating polymersomes with a large number of compartments. The resultant polymersome gel behaves as a gel-like solid, but is a true vesicle suspended in an aqueous environment. Due to the thin membranes that separate the compartments, the polymersome gels have a high volume fraction of internal phase for encapsulation of hydrophilic actives; they also provide a large surface area of diblock copolymer membrane for encapsulation of lipophilic actives. Multiple actives can also be encapsulated in the gel without cross-contamination. Our technique represents a simple and versatile bulk approach for fabricating polymersome gels; it does not require the use of any specialized equipment or subsequent polymerization steps to solidify the gel. The resultant polymersome gel is promising as an encapsulating structure as well as a scaffold for tissue engineering.

Novel surface acoustic wave (SAW)-driven closed PDMS flow chamber - Schmid, Lothar; Wixforth, Achim; Weitz, David A; Franke, Thomas (Microfluidics and Nanofluidics, 2011)
In this article, we demonstrate a novel microfluidic flow chamber driven by surface acoustic waves. Our device is a closed loop channel with an integrated acoustic micropump without external fluidic connections that allows for the investigation of small fluid samples in a continuous flow. The fabrication of the channels is particularly simple and uses standard milling and PDMS molding. The micropump consists of gold electrodes deposited on a piezoelectric substrate employing photolithography. We show that the pump generates a pressure-driven Poiseuille flow, investigate the acoustic actuation mechanism, characterize the flow profile for different channel geometries, and evaluate the driving pressure, efficiency and response time of the acoustic micropump. The fast response time of our pump permits the generation of non-stationary flows. To demonstrate the versatility of the device, we have pumped a red blood cell suspension at a physiological rate of 60 beats/min.

Drying of complex suspensions - Xu, Lei; Berges, Alexis; Lu, Peter J.; Studart, Andre R.; Schofield, Andrew B.; Oki, Hidekazu; Davies, Simon; Weitz, David A (Physical Review Letters, 2010)
We investigate the 3D structure and drying dynamics of complex mixtures of emulsion droplets and colloidal particles, using confocal microscopy. Air invades and rapidly collapses large emulsion droplets, forcing their contents into the surrounding porous particle pack at a rate proportional to the square of the droplet radius. By contrast, small droplets do not collapse, but remain intact and are merely deformed. A simple model coupling the Laplace pressure to Darcy's law correctly estimates both the threshold radius separating these two behaviors, and the rate of large-droplet evacuation. Finally, we use these systems to make novel hierarchical structures.

Capillary micromechanics: Measuring the elasticity of microscopic soft objects - Wyss, Hans M.; Franke, Thomas; Mele, Elisa; Weitz, David A (Soft Matter, 2010)
We present a simple method for accessing the elastic properties of microscopic deformable particles. This method is based on measuring the pressure-induced deformation of soft particles as they are forced through a tapered glass microcapillary. It allows us to determine both the compressive and the shear modulus of a deformable object in one single experiment. Measurements on a model system of polyacrylamide microgel particles exhibit good agreement with measurements on bulk gels of identical composition. Our approach is applicable over a wide range of mechanical properties and should thus be a valuable tool for the characterization of a variety of soft and biological materials.

Fabrication of polymersomes using double-emulsion templates in glass-coated stamped microfluidic devices - Thiele, Julian; Abate, Adam R.; Shum, Ho Cheung; Bachtler, Simone; Foerster, Stephan; Weitz, David A (Small, 2010)
The formation of polymersomes from copolymer‐stabilized double emulsions in glass‐coated, PDMS microfluidic devices is described. The device geometry enables separate injection of two organic solvents to form the shell phase of the double emulsion. This allows proper combination of the two solvents, which is essential for forming polymersomes.

Microfluidic melt emulsification for encapsulation and release of actives - Sun, Bing Jie; Shum, Ho Cheung; Holtze, Christian; Weitz, David A (ACS Applied Materials & Interfaces, 2010)
A microfluidic melt emulsification method for encapsulation and release of actives is presented. Using a water-in-oil-in-water (W-O-W) double emulsion template, solid capsules can be formed by freezing the middle shell phase. Actives encapsulated inside the solid shell can be controllably and rapidly released by applying a temperature trigger to melt the shell. The choice of the shell materials can be chosen to accommodate the storage and release temperatures specific to the applications. In addition, we have also demonstrated the same concept to encapsulate multiple actives in multicompartment capsules, which are promising as multifunctional capsules and microreactors.

The shape of a step structure as a design aspect to control droplet generation in microfluidics - Sim, S. P. C.; Kang, T. G.; Yobas, L.; C. Holtze; Weitz, D. A. (Journal of Micromechanics and Microengineering, 2010)
In this paper, silicon-based devices with a step structure integrated at the flow-focusing junction were designed, fabricated and characterized for droplet generation. A two-step silicon etching method was demonstrated to create the step structure. During fabrication, undesirable spikes encountered at the step edge were removed by oxygen plasma ashing and silicon isotropic etching. With this method, two types of step profile (flat and triangular profiles) were fabricated. These two profiles were compared for their differences in droplet-generation behavior. The device with the flat-step profile was found to make larger droplets and at a lower frequency compared to the device with the triangular-step profile. Additionally, polydimethylsiloxan e and glass were tested as capping materials for the devices and the impact of their surface characteristics (hydrophobic and hydrophilic) on the type of droplets (water-in-oil or oil-in-water) formed was investigated.

Corrugated interfaces in multiphase core-annular flow - Shum, Ho Cheung; Sauret, Alban; Fernandez-Nieves, Alberto; Stone, Howard A.; Weitz, David A (Physics of Fluids, 2010)
Microfluidic devices can be used to produce highly controlled and monodisperse double or multiple emulsions. The presence of inner drops inside a jet of the middle phase introduces deformations in the jet, which leads to breakup into monodisperse double emulsions. However, the ability to generate double emulsions can be compromised when the interfacial tension between the middle and outer phases is low, leading to flow with high capillary and Weber numbers. In this case, the interface between the fluids is initially deformed by the inner drops but the jet does not break into drops. Instead, the jet becomes highly corrugated, which prevents formation of controlled double emulsions. We show using numerical calculations that the corrugations are caused by the inner drops perturbing the interface and the perturbations are then advected by the flow into complex shapes. (c) 2010 American Institute of Physics. [doi:10.1063/1.3480561]

Controlled fabrication of polymer microgels by polymer-analogous gelation in droplet microfluidics - Seiffert, Sebastian; Weitz, David A (Soft Matter, 2010)
We fabricate thermo-responsive polymer microgels by combining microfluidic pre-gel emulsification with polymer-analogous gelation. This separates the microgel formation from the polymer synthesis; it combines highly controlled microfluidic templating with the great flexibility of preparative polymer chemistry, allowing each to be controlled independently. We produce monodisperse pre-gel droplets from semidilute solutions of photocrosslinkable poly(N-isopropylacrylamide) precursors. The size and morphology of these droplets can be precisely controlled by the microfluidic emulsification, provided the molecular weight of the precursor is limited. Using polymer-analogous gelation rather than monomer chain-growth gelation yields gels with a higher efficiency of crosslinking and a greater homogeneity on nano- and micrometre scales, as determined by oscillatory shear rheology, static light scattering, and optical microscopy. We also demonstrate the applicability of our method to fabricate microgel particles with well-defined concentrations of functional sites.

Microfluidic fabrication of smart microgels from macromolecular precursors - Seiffert, Sebastian; Weitz, David A (Polymer, 2010)
Stimuli-responsive polymer microgels can be produced with exquisite control using droplet microfluidics; however, in existing methods, the droplet templating is strongly coupled to the material synthesis, because droplet solidification usually occurs through rapid polymerization immediately after the microfluidic droplet formation. This circumstance limits independent control of the material properties and the morphology of the resultant microgel particles. To overcome this limitation, we produce sensitive polymer microgels from pre-fabricated precursor polymers. We use microfluidic devices to emulsify semidilute solutions of crosslinkable poly(N-isopropylacrylamide) and solidify the drops via polymer-analogous gelation. This approach separates the polymer synthesis from the particle gelation and allows each to be controlled independently, thus enabling us to form monodisperse, thermo-responsive microgel particles with well-controlled composition and functionality. In addition, the microfluidic templating allows us to form complex particle morphologies such as hollow gel shells, anisotropic microgels, or multi-layered microgel capsules. (C) 2010 Elsevier Ltd. All rights reserved.

Monodisperse stimuli-responsive colloidosomes by self-assembly of microgels in droplets - Shah, Rhutesh K.; Kim, Jin-Woong; Weitz, David A (Langmuir, 2010)
We introduce a novel and versatile technique to fabricate monodisperse stimuli-responsive colloidosomes using stimuli-responsive microgel particles its building blocks, aqueous droplets as templates, and microfluidic devices to control the assembly. Our colloidosomes exhibit similar to 80% decrease in volume when actuated; thus, they can be of immense potential in applications that require targeted pulsed-release of active materials. The use of microfluidics allows fabrication of extremely monodisperse colloidosomes, Alternatively, our technique can also be combined with bulk emulsification techniques to produce large quantities of colloidosomes for various applications.

High-throughput fluorescence detection using an integrated zone-plate array - Ethan Schonbrun; Abate, Adam R.; Steinvurzel, Paul E.; Weitz, David A; Kenneth B. Crozier (Lab on a Chip, 2010)
Microfluidic devices enable massive parallelization of sample manipulation and delivery, but a similarly parallelized and integrated optical detection system does not yet exist. Standard large numerical aperture wide field or scanning optical systems are not capable of the large field of view and detection sensitivity required to collect fluorescence from parallel arrays of microfluidic devices. Instead, we present a fluorescence measurement platform based on a microfabricated zone-plate array integrated into a parallelized microfluidic device. The zone-plate array is orientated so that a single high numerical aperture zone plate is aligned to read out the fluorescence from each of 64 output channels of a drop-making device. The parallelization of microfluidics and optics produces an integrated system capable of analysis of nearly 200 000 drops per second.

Janus microgels produced from functional precursor polymers - Seiffert, Sebastian; Romanowsky, Mark B.; Weitz, David A (Langmuir, 2010)
Micrometer-sized Janus particles of many kinds can be formed using droplet microfluidics, but in existing methods, the microfluidic templating is strongly coupled to the material synthesis, since droplet solidification occurs through rapid polymerization light after droplet formation. This circumstance limits independent control of the material properties and the morphology of the resultant particles In this paper, we demonstrate a microfluidic technique to produce functional Janus miciogels nom prefabricated, cross-linkable precursor polymers This approach separates the polymer synthesis from the particle gelation, thus allowing the microfluidic droplet templating and the functionalization of the matrix polymer to be performed and controlled in two independent steps We use microfluidic devices to emulsify semidilute solutions of cross-linkable, chemically modified or unmodified poly(N-isopropylacrylamide) precursors and solidify the drops via polymer-analogous gelation The resultant microgel particles exhibit two distinguishable halves which contain most of the modified precursors, and the unmodified matrix polymer separates these materials The spatial distribution of the modified precursors across the particles can be controlled by the flow rates during the microfluidic experiments We also form hollow microcapsules with two different sides (Janus shells) using double emulsion droplets as templates, and we produce Janus microgels that are loaded with a fen magnetic additive which allows remote actuation of the microgels

Smart microgel capsules from macromolecular precursors - Seiffert, Sebastian; Thiele, Julian; Abate, Adam R.; Weitz, David A (Journal of the American Chemical Society, 2010)
Microgel particles and capsules which consist of multiple layers can be fabricated using droplet microfluidics, but in existing methods, emulsion templating forms layers of dissimilar polarity. In this paper, we fabricate functional microgel capsules that consist of two miscible yet distinct layers. We use microfluidic devices to template micrometer-sized drops that are loaded with prepolymerized precursors and solidify them through a polymer-analogous reaction. This allows the particle morphology to be controlled and prevents pronounced interpenetration of the different layers despite their miscibility. We use polyacrylamide and poly(N-isopropylacrylamide) precursors to form thermoresponsive core-shell microparticles and demonstrate their utility for encapsulation and controlled release applications.

Temperature-controlled transitions between glass, liquid, and gel states in dense p-NIPA suspensions - Romeo, Giovanni; Fernandez-Nieves, Alberto; Wyss, Hans M.; Acierno, Domenico; Weitz, David A (Advanced Materials, 2010)
The elastic modulus, G'(p), of concentrated suspensions of thermoresponsive microgel particles highlights transitions between glassy, liquid-like, and gel-like behavior as the temperature is varied Approaching the low critical solution temperature of the particles, T(c) approximate to 29 degrees C, the material undergoes solid-to-liquid transitions even above random close packing and irrespective of particle concentration

Functional patterning of PDMS microfluidic devices using integrated chemo-masks - Romanowsky, Mark B.; Heymann, Michael; Abate, Adam R.; Krummel, Amber T.; Fraden, Seth; Weitz, David A (Lab on a Chip, 2010)
Microfluidic devices can be molded easily from PDMS using soft lithography. However, the softness of the resulting microchannels makes it difficult to photolithographically pattern their surface properties, as is needed for applications such as double emulsification. We introduce a new patterning method for PDMS devices, using integrated oxygen reservoirs fabricated simultaneously with the microfluidic channels, which serve as "chemo-masks". Oxygen diffuses through the PDMS to the nearby channel segments and there inhibits functional polymer growth; by placement of the chemo-masks, we thus control the polymerization pattern. This patterning method is simple, scalable, and compatible with a variety of surface chemistries.

Droplet breakup in flow past an obstacle: A capillary instability due to permeability variations - Protiere, S.; Bazant, M. Z.; Weitz, D. A.; H.A. Stone (Epl, 2010)
In multiphase flow in confined geometries an elementary event concerns the interaction of a droplet with an obstacle. As a model of this configuration we study the collision of a droplet with a circular post that spans a significant fraction of the cross-section of a microfluidic channel. We demonstrate that there exist conditions for which a drop moves completely around the obstacle without breaking, while for the same geometry but higher speeds the drop breaks. Therefore, we identify a critical value of the capillary number above which a drop will break. We explain the results with a one-dimensional model characterizing the flow in the narrow gaps on either side of the obstacle, which identifies a surface-tension-driven instability associated with a variation in the permeability in the flow direction. The model captures the major features of the experimental observations. Copyright (C) EPLA, 2010

Reduction of water evaporation in polymerase chain reaction microfluidic devices based on oscillating-flow - Polini, Alessandro; Mele, Elisa; Sciancalepore, Anna Giovanna; Girardo, Salvatore; Biasco, Adriana; Camposeo, Andrea; Cingolani, Roberto; Weitz, David A; Pisignano, Dario (Biomicrofluidics, 2010)
Producing polymeric or hybrid microfluidic devices operating at high temperatures with reduced or no water evaporation is a challenge for many on-chip applications including polymerase chain reaction (PCR). We study sample evaporation in polymeric and hybrid devices, realized by glass microchannels for avoiding water diffusion toward the elastomer used for chip fabrication. The method dramatically reduces water evaporation in PCR devices that are found to exhibit optimal stability and effective operation under oscillating-flow. This approach maintains the flexibility, ease of fabrication, and low cost of disposable chips, and can be extended to other high-temperature microfluidic biochemical reactors. (C) 2010 American Institute of Physics. [doi: 10.1063/1.3481776]

Biologically templated photocatalytic nanostructures for sustained light-driven water oxidation - Nam, Yoon Sung; Magyar, Andrew P.; Lee, Daeyeon; Kim, Jin-Woong; Yun, Dong Soo; Park, Heechul; Pollom, Thomas S., Jr.; Weitz, David A; Belcher, Angela M (Nature Nanotechnology, 2010)
Over several billion years, cyanobacteria and plants have evolved highly organized photosynthetic systems to shuttle both electronic and chemical species for the efficient oxidation of water(1). In a similar manner to reaction centres in natural photosystems, molecular(2) and metal oxide(3) catalysts have been used to photochemically oxidize water. However, the various approaches involving the molecular design of ligands(4), surface modification(5) and immobilization(6,7) still have limitations in terms of catalytic efficiency and sustainability. Here, we demonstrate a biologically templated nanostructure for visible light-driven water oxidation that uses a genetically engineered M13 virus scaffold to mediate the co-assembly of zinc porphyrins (photosensitizer) and iridium oxide hydrosol clusters (catalyst). Porous polymer microgels are used as an immobilization matrix to improve the structural durability of the assembled nanostructures and to allow the materials to be recycled. Our results suggest that the biotemplated nanoscale assembly of functional components is a promising route to significantly improved photocatalytic water-splitting systems.

Biopolymer network geometries: Characterization, regeneration, and elastic properties - Lindstroem, Stefan B.; Vader, David A.; Kulachenko, Artem; Weitz, David A (Physical Review E, 2010)
We study the geometry of biopolymer networks and effects of the geometry on bulk mechanical properties. It is shown numerically that the physical network geometry can be quantified statistically and regenerated from its statistical description, so that the regenerated network exhibits the same network mechanics as the physical network in the elastic regime. A collagen-I biopolymer network is used for validation. The method enables parametric studies of the network geometry, whose parameters are often difficult to vary independently in experiments.

Divalent cations crosslink vimentin intermediate filament tail domains to regulate network mechanics - Lin, Yi-Chia; Broedersz, Chase P.; Rowat, Amy C.; Wedig, Tatjana; Herrmann, Harald; MacKintosh, Frederick C; Weitz, David A (Journal of Molecular Biology, 2010)
Intermediate filament networks in the cytoplasm and nucleus are critical for the mechanical integrity of metazoan cells. However, the mechanism of crosslinking in these networks and the origins of their mechanical properties are not understood. Here, we study the elastic behavior of in vitro networks of the intermediate filament protein vimentin. Rheological experiments reveal that vimentin networks stiffen with increasing concentrations of Ca2+ and Mg2+, showing that divalent cations act as crosslinkers. We quantitatively describe the elastic response of vimentin networks over five decades of applied stress using a theory that treats the divalent cations as crosslinkers: at low stress, the behavior is entropic in origin, and increasing stress pulls out thermal fluctuations from single filaments, giving rise to a nonlinear response; at high stress, enthalpic stretching of individual filaments significantly modifies the nonlinearity. We investigate the elastic properties of networks formed by a series of protein variants with stepwise tail truncations and find that the last 11 amino acids of the C-terminal tail domain mediate crosslinking by divalent ions. We determined the single-filament persistence length, lP ≈ 0.5 μm, and Young's modulus, Y ≈ 9 MPa; both are consistent with literature values. Our results provide insight into a crosslinking mechanism for vimentin networks and suggest that divalent ions may help regulate the cytoskeletal structure and mechanical properties of cells.

Origins of elasticity in intermediate filament networks - Lin, Yi-Chia; Yao, Norman Y.; Broedersz, Chase P.; Herrmann, Harald; Mackintosh, Fred C.; Weitz, David A (Physical Review Letters, 2010)
Intermediate filaments are common structural elements found in abundance in all metazoan cells, where they form networks that contribute to the elasticity. Here, we report measurements of the linear and nonlinear viscoelasticity of networks of two distinct intermediate filaments, vimentin and neurofilaments. Both exhibit predominantly elastic behavior with strong nonlinear strain stiffening. We demonstrate that divalent ions behave as effective cross-linkers for both networks, and that the elasticity of these networks is consistent with the theory for that of semiflexible polymers.

The role of polymer polydispersity in phase separation and gelation in colloid-polymer mixtures - Lietor-Santos, J. J.; Kim, C.; Lynch, M. L.; Fernandez-Nieves, A.; Weitz, D. A. (Langmuir, 2010)
Mixtures of nonadsorbing polymer and colloidal particles exhibit a range of different morphologies depending, on the particle and polymer concentrations and their relative size ratios. These can be very important for technological applications, where gelation can produce a weak solidlike structure that can help reduce phase separation, extending product shelf life. However, industrial products are typically formulated with polydisperse polymers, and the consequences of this on the phase behavior of the mixture are not known. We investigate the role of polymer polydispersity and show that a small amount of larger polymer in a distribution of nominally much smaller polymer can drastically modify the behavior. It can induce formation of a solidlike gel Structure, abetted by the small polymer, but still allow further evolution of the phase separation process, as is seen with a monodisperse distribution of larger polymer. This coarsening ultimately leads to gravitational collapse. We describe the full phase behavior for polydisperse polymer mixtures and account for the origin of the behavior through Measurements of the structure and dynamics and by comparing to the behavior with monodisperse polymers.

Elasticity of dilatant particle suspensions during flow - Larsen, RyanJ.; Kim, Jin-Woong; Zukoski, CharlesF.; Weitz, David A (Physical Review E, 2010)
Dense suspensions under sufficiently high shear stress can exhibit a dramatic transition to a solidlike state. This is known as extreme shear thickening and is sometimes accompanied by dilatancy. This behavior is contradictory; the material is solidlike but only when flowing. To probe the elasticity of the dilatant state, we measure the transient inertio-elastic oscillations that occur in response to step changes in applied stress. As the volume fraction of solids increases the apparent flow elasticity also increases, and the suspension flows more slowly, approaching an elastic solid, which will support stress statically.

Nanomechanics of vimentin intermediate filament networks - Koester, Sarah; Lin, Yi-Chia; Herrmann, Harald; Weitz, David A (Soft Matter, 2010)
Intermediate filaments are one of three classes of fibrous proteins in the cytoskeleton of eukaryotes, the others being actin filaments and microtubules. The dense filamentous networks and bundles provide important mechanical stability for the cell. Here we directly measure both the structure and mechanical properties of an in vitro model system for intermediate filaments reconstituted from purified vimentin protein at 1 mg mL(-1). We show that the mesh size is on the order of 1 mm, a value that is preserved upon addition of divalent ions. These ions act as effective cross-linkers, further stiffening the network.

Actin filament length tunes elasticity of flexibly cross-linked actin networks - Kasza, K. E.; Broedersz, C. P.; Koenderink, G. H.; Lin, Y. C.; Messner, W.; Millman, E. A.; Nakamura, F.; Stossel, T. P.; MacKintosh, F. C.; Weitz, D. A. (Biophysical Journal, 2010)
Networks of the cytoskeletal biopolymer actin cross-linked by the compliant protein filamin form soft gels that stiffen dramatically under shear stress. We demonstrate that the elasticity of these networks shows a strong dependence on the mean length of the actin polymers, unlike networks with small, rigid cross-links. This behavior is in agreement with a model of rigid filaments connected by multiple flexible linkers.

Fabrication of tunable spherical colloidal crystals immobilized in soft hydrogels - Kanai, Toshimitsu; Lee, Daeyeon; Shum, Ho Cheung; Weitz, David A (Small, 2010)
A method for fabricating gel‐immobilized colloidal crystal spheres using microfluidics is reported. The diffraction color or photonic wavelength of the gel‐immobilized colloidal crystal spheres can be adjusted by varying the particle concentration before gelation and tuned by external stimuli after preparation.

Gel-immobilized colloidal crystal shell with enhanced thermal sensitivity at photonic wavelengths - Kanai, Toshimitsu; Lee, Daeyeon; Shum, Ho Cheung; Shah, Rhutesh K.; Weitz, David A (Advanced Materials, 2010)
A method for fabricating microcapsules with gel-immobilized colloidal crystal shells using microfluidics is reported. The diffraction color or photonic wavelength of the gel-immobilized colloidal crystal shells can be adjusted by varying the particle concentration before gelation and tuned by external stimuli after preparation. The gel-immobilized colloidal crystal shell has a higher sensitivity and wider range in the stop band wavelength than that displayed by a bulk gel.

Axial and lateral particle ordering in finite Reynolds number channel flows - Humphry, Katherine J.; Kulkarni, Pandurang M.; Weitz, David A; Morris, Jeffrey F.; Stone, Howard A. (Physics of Fluids, 2010)
Inertial focusing in a pressure-driven flow refers to the positioning of particles transverse to the mean flow direction that occurs as a consequence of a finite particle Reynolds number. In channels with rectangular cross-sections, and for a range of channel aspect ratios and particle confinement, experimental results are presented to show that both the location and the number of focusing positions depend on the number of particles per unit length along the channel. This axial number density is a function of both the channel cross-section and the particle volume fraction. These results are rationalized using simulations of the particle-laden flow to show the manner in which hydrodynamic interactions set the preferred locations in these confined flows. A criterion is presented for the occurrence of a stepwise transition from one to two or more trains of particles. (c) 2010 American Institute of Physics. [doi:10.1063/1.3478311]

Surface acoustic wave actuated cell sorting (SAWACS) - Franke, T.; Braunmueller, S.; Schmid, L.; Wixforth, A.; Weitz, D. A. (Lab on a Chip, 2010)
We describe a novel microfluidic cell sorter which operates in continuous flow at high sorting rates. The device is based on a surface acoustic wave cell-sorting scheme and combines many advantages of fluorescence activated cell sorting (FACS) and fluorescence activated droplet sorting ( FADS) in microfluidic channels. It is fully integrated on a PDMS device, and allows fast electronic control of cell diversion. We direct cells by acoustic streaming excited by a surface acoustic wave which deflects the fluid independently of the contrast in material properties of deflected objects and the continuous phase; thus the device underlying principle works without additional enhancement of the sorting by prior labelling of the cells with responsive markers such as magnetic or polarizable beads. Single cells are sorted directly from bulk media at rates as fast as several kHz without prior encapsulation into liquid droplet compartments as in traditional FACS. We have successfully directed HaCaT cells (human keratinocytes), fibroblasts from mice and MV3 melanoma cells. The low shear forces of this sorting method ensure that cells survive after sorting.

Shear melting of a colloidal glass - Eisenmann, Christoph; Kim, Chanjoong; Mattsson, Johan; Weitz, David A (Physical Review Letters, 2010)
We use confocal microscopy to explore shear melting of colloidal glasses, which occurs at strains of similar to 0.08, coinciding with a strongly non-Gaussian step size distribution. For larger strains, the particle mean square displacement increases linearly with strain and the step size distribution becomes Gaussian. The effective diffusion coefficient varies approximately linearly with shear rate, consistent with a modified Stokes-Einstein relationship in which thermal energy is replaced by shear energy and the length scale is set by the size of cooperatively moving regions consisting of similar to 3 particles.

Controlled buckling and crumpling of nanoparticle-coated droplets - Datta, Sujit S.; Shum, Ho Cheung; Weitz, David A (Langmuir, 2010)
We introduce a new experimental approach to study the structural transitions of large numbers of nanoparticle-coated droplets as their volume is reduced. We use an emulsion system where the dispersed phase is slightly soluble in the continuous phase. By adding a fixed amount of unsaturated continuous phase, the volume of the droplets can be controllably reduced, causing them to buckle or crumple, thereby becoming nonspherical. The resultant morphologies depend both on the extent of volume reduction and the average droplet size. The buckling and crumpling behavior implies that the droplet surfaces are solid.

Arrested fluid-fluid phase separation in depletion systems: Implications of the characteristic length on gel formation and rheology - Conrad, J. C.; Wyss, H. M.; Trappe, V.; S. Manley; Miyazaki, K.; Kaufman, L. J.; Schofield, A. B.; D. R. Reichman; Weitz, D. A. (Journal of Rheology, 2010)
We investigate the structural, dynamical, and rheological properties of colloid-polymer mixtures in a volume fraction range of phi=0.15-0.35. Our systems are density-matched, residual charges are screened, and the polymer-colloid size ratio is similar to 0.37. For these systems, the transition to kinetically arrested states, including disconnected clusters and gels, coincides with the fluid-fluid phase separation boundary. Structural investigations reveal that the characteristic length, L, of the networks is a strong function of the quench depth: for shallow quenches, L is significantly larger than that obtained for deep quenches. By contrast, L is for a given quench depth almost independent of phi; this indicates that the strand thickness increases with phi. The strand thickness determines the linear rheology: the final relaxation time exhibits a strong dependence on phi, whereas the high frequency modulus does not. We present a simple model based on estimates of the strand breaking time and shear modulus that semiquantitatively describes the observed behavior.

Regulating volume transitions of highly responsive hydrogel scaffolds by adjusting the network properties of microgel building block colloids - Cho, Eun Chul; Kim, Jin-Woong; Hyun, Dong Chun; Jeong, Unyong; Weitz, David A (Langmuir, 2010)
We present a simple method to control the volume change of thermally responsive hydrogel scaffolds, providing a remarkably fast swelling and deswelling response to temperature changes. These scaffolds have 3-dimensional colloidal-network structures which are made from microgel particles while they are above their deswelling transition temperatures. By timing the cross-link density of the microgel particles, we achieve controllable changes of the Volume of the scaffolds in response to temperature. Their fast response rate is determined by the length scale of the unit microgel particles and is not influenced by the properties of the network. The release profile of a model drug (Rhapontin) loaded within the scaffolds can also be regulated by the cross-linking density of the microgel particles. These results offer a new way of fabricating hydrogel scaffolds with tunable matrix geometry and function by adjusting the properties of the unit microgel colloids, without loss or their fast response to temperature change.

Surface-tension-induced synthesis of complex particles using confined polymeric fluids - Choi, Chang-Hyung; Lee, Jinkee; Yoon, Kisun; Tripathi, Anubhav; Stone, Howard A.; Weitz, David A; Lee, Chang-Soo (Angewandte Chemie-International Edition, 2010)
Resolving the tension: Complex particles with various shapes such as bullets, cylinders, discs, hearts, hexagons, and Janus particles can be synthesized by two different surface‐tension‐induced flow sequences (A and B; see picture, scale bars=100 μm). The particles produced by using this approach can be exploited as anisotropic building blocks for the fabrication of complex systems by combination of the two sequences.

Cell migration driven by cooperative substrate deformation patterns - Angelini, Thomas E.; Hannezo, Edouard; Trepat, Xavier; Jeffrey J. Fredberg; Weitz, David A (Physical Review Letters, 2010)
Most eukaryotic cells sense and respond to the mechanical properties of their surroundings. This can strongly influence their collective behavior in embryonic development, tissue function, and wound healing. We use a deformable substrate to measure collective behavior in cell motion due to substrate mediated cell-cell interactions. We quantify spatial and temporal correlations in migration velocity and substrate deformation, and show that cooperative cell-driven patterns of substrate deformation mediate long-distance mechanical coupling between cells and control collective cell migration.

Ultrahigh-throughput screening in drop-based microfluidics for directed evolution - Agresti, Jeremy J.; Antipov, Eugene; Abate, Adam R.; Ahn, Keunho; Rowat, Amy C.; Baret, Jean-Christophe; Marquez, Manuel; Klibanov, Alexander M.; Griffiths, Andrew D.; Weitz, David A (Proceedings of the National Academy of Sciences of the United States of America, 2010)
The explosive growth in our knowledge of genomes, proteomes, and metabolomes is driving ever-increasing fundamental understanding of the biochemistry of life, enabling qualitatively new studies of complex biological systems and their evolution. This knowledge also drives modern biotechnologies, such as molecular engineering and synthetic biology, which have enormous potential to address urgent problems, including developing potent new drugs and providing environmentally friendly energy. Many of these studies, however, are ultimately limited by their need for even-higher-throughput measurements of biochemical reactions. We present a general ultrahigh-throughput screening platform using drop-based microfluidics that overcomes these limitations and revolutionizes both the scale and speed of screening. We use aqueous drops dispersed in oil as picoliter-volume reaction vessels and screen them at rates of thousands per second. To demonstrate its power, we apply the system to directed evolution, identifying new mutants of the enzyme horseradish peroxidase exhibiting catalytic rates more than 10 times faster than their parent, which is already a very efficient enzyme. We exploit the ultrahigh throughput to use an initial purifying selection that removes inactive mutants; we identify similar to 100 variants comparable in activity to the parent from an initial population of similar to 10(7). After a second generation of mutagenesis and high-stringency screening, we identify several significantly improved mutants, some approaching diffusion-limited efficiency. In total, we screen similar to 10(8) individual enzyme reactions in only 10 h, using <150 mu L of total reagent volume; compared to state-of-the-art robotic screening systems, we perform the entire assay with a 1,000-fold increase in speed and a 1-million-fold reduction in cost.

Patterning microfluidic device wettability using flow confinement - Abate, Adam R.; Thiele, Julian; Weinhart, Marie; Weitz, David A (Lab on a Chip, 2010)
We present a simple method to spatially pattern the surface properties of microfluidic devices using flow confinement. Our technique allows surface patterning with micron-scale resolution. To demonstrate its effectiveness, we use it to pattern wettability to form W/O/W and O/W/O double emulsions.

High-throughput injection with microfluidics using picoinjectors - Abate, Adam R.; Hung, Tony; Mary, Pascaline; Agresti, Jeremy J.; Weitz, David A (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Adding reagents to drops is one of the most important functions in droplet-based microfluidic systems; however, a robust technique to accomplish this does not exist. Here, we introduce the picoinjector, a robust device to add controlled volumes of reagent using electro-microfluidics at kilohertz rates. It can also perform multiple injections for serial and combinatorial additions.

Microfluidic sorting with high-speed single-layer membrane valves - Abate, Adam R.; Agresti, Jeremy J.; Weitz, David A (Applied Physics Letters, 2010)
Sorting is one of the most important applications of microfluidic devices; however, current sorters place specific requirements on the density, size, and electrical properties of the objects to be sorted, limiting applicability. We present widely applicable microfluidic sorting. We use high-speed single-layer membrane valves to control flows in a bifurcating channel junction, to direct the paths of objects. This allows sorting at hundreds of hertz. Moreover, since the sorting action is mechanical, it is very widely applicable-to drops, particles, and even living cells. (C) 2010 American Institute of Physics. [doi:10.1063/1.3431281]

Anucleate platelets generate progeny - Schwertz, Hansjoerg; Koester, Sarah; Kahr, Walter H. A.; Michetti, Noemi; Kraemer, Bjoern F.; Weitz, David A; Blaylock, Robert C.; Kraiss, Larry W.; Greinacher, Andreas; Zimmerman, Guy A.; Weyrich, Andrew S. (Blood, 2010)
Platelets are classified as terminally differentiated cells that are incapable of cellular division. However, we observe that anucleate human platelets, either maintained in suspension culture or captured in microdrops, give rise to new cell bodies packed with respiring mitochondria and alpha-granules. Platelet progeny formation also occurs in whole blood cultures. Newly formed platelets are structurally indistinguishable from normal platelets, are able to adhere and spread on extracellular matrix, and display normal signal-dependent expression of surface P-selectin and annexin V. Platelet progeny formation is accompanied by increases in biomass, cellular protein levels, and protein synthesis in expanding populations. Platelet numbers also increase during ex vivo storage. These observations indicate that platelets have a previously unrecognized capacity for producing functional progeny, which involves a form of cell division that does not require a nucleus. Because this new function of platelets occurs outside of the bone marrow milieu, it raises the possibility that thrombopoiesis continues in the bloodstream. (Blood. 2010; 115(18):3801-3809)

A blind spot in confocal reflection microscopy: The dependence of fiber brightness on fiber orientation in imaging biopolymer networks - Jawerth, Louise M.; Muenster, Stefan; Vader, David A.; Fabry, Ben; Weitz, David A (Biophysical Journal, 2010)
We investigate the dependence of fiber brightness on three-dimensional fiber orientation when imaging biopolymer networks with confocal reflection microscopy (CRM) and confocal fluorescence microscopy (CFM). We compare image data of fluorescently labeled type I collagen networks concurrently acquired using each imaging modality. For CRM, fiber brightness decreases for more vertically oriented fibers, leaving fibers above similar to 50 degrees from the imaging plane entirely undetected. As a result, the three-dimensional network structure appears aligned with the imaging plane. In contrast, CFM data exhibit little variation of fiber brightness with fiber angle, thus revealing an isotropic collagen network. Consequently, we find that CFM detects almost twice as many fibers as are visible with CRM, thereby yielding more complete structural information for three-dimensional fiber networks. We offer a simple explanation that predicts the detected fiber brightness as a function of fiber orientation in CRM.

Cross-link-governed dynamics of biopolymer networks - Broedersz, Chase P.; Depken, Martin; Yao, Norman Y.; Pollak, Martin R.; Weitz, David A; MacKintosh, Frederick C (Physical Review Letters, 2010)
Recent experiments show that networks of stiff biopolymers cross-linked by transient linker proteins exhibit complex stress relaxation, enabling network flow at long times. We present a model for the dynamics controlled by cross-links in such networks. We show that a single microscopic time scale for cross-linker unbinding leads to a broad spectrum of macroscopic relaxation times and a shear modulus G similar to omega(1/2) for low frequencies omega. This model quantitatively describes the measured rheology of actin networks cross-linked with alpha-actinin-4 over more than four decades in frequency.

Droplet microfluidics for fabrication of non-spherical particles - Shum, Ho Cheung; Abate, Adam R.; Lee, Daeyeon; Studart, Andre R.; Wang, Baoguo; Chen, Chia-Hung; Thiele, Julian; Shah, Rhutesh K.; Krummel, Amber; Weitz, David A (Macromolecular Rapid Communications, 2010)
We describe new developments for controlled fabrication of monodisperse non-spherical particles using droplet microfluidics. The high degree of control afforded by microfluidic technologies enables generation of single and multiple emulsion droplets. We show that these droplets can be transformed to non-spherical particles through further simple, spontaneous processing steps, including arrested coalescence, asymmetric polymer solidification, polymerization in microfluidic flow, and evaporation-driven clustering. These versatile and scalable microfluidic approaches can be used for producing large quantities of non-spherical particles that are monodisperse in both size and shape; these have great potential for commercial applications.

Elasticity in ionically cross-linked neurofilament networks - Yao, Norman Y.; Broedersz, Chase P.; Lin, Yi-Chia; Kasza, Karen E.; MacKintosh, Frederick C; Weitz, David A (Biophysical Journal, 2010)
Neurofilaments are found in abundance in the cytoskeleton of neurons, where they act as an intracellular framework protecting the neuron from external stresses. To elucidate the nature of the mechanical properties that provide this protection, we measure the linear and nonlinear viscoelastic properties of networks of neurofilaments. These networks are soft solids that exhibit dramatic strain stiffening above critical strains of 30-70%. Surprisingly, divalent ions such as Mg(2+), Ca(2+), and Zn(2+) act as effective cross-linkers for neurofilament networks, controlling their solidlike elastic response. This behavior is comparable to that of actin-binding proteins in reconstituted filamentous actin. We show that the elasticity of neurofilament networks is entropic in origin and is consistent with a model for cross-linked semiflexible networks, which we use to quantify the cross-linking by divalent ions.

Measurement of nonlinear rheology of cross-linked biopolymer gels - Broedersz, Chase P.; Kasza, Karen E.; Jawerth, Louise M.; Muenster, Stefan; Weitz, David A; MacKintosh, Frederick C (Soft Matter, 2010)
One of the hallmarks of biopolymer gels is their nonlinear viscoelastic response to stress, making the measurement of the mechanics of these gels very challenging. Various rheological protocols have been proposed for this; however, a thorough understanding of the techniques and their range of applicability as well as a careful comparison between these methods are still lacking. Using both strain ramp and differential prestress protocols, we investigate the nonlinear response of a variety of systems ranging from extracellular fibrin gels to intracellular F-actin solutions and F-actin cross-linked with permanent and physiological transient linkers. We find that the prestress and strain ramp results agree well for permanently cross-linked networks over two decades of strain rates, while the protocols only agree at high strain rates for more transient networks. Surprisingly, the nonlinear response measured with the prestress protocol is insensitive to creep; although a large applied steady stress can lead to significant flow, this has no significant effect on either the linear or nonlinear response of the system. A simple model is presented to provide insight into these observations.

The micromechanics of three-dimensional collagen-I gels - Stein, Andrew M.; Vader, David A.; Weitz, David A; Sander, Leonard M. (Complexity, 2010)
We study the micromechanics of collagen-I gel with the goal of bridging the gap between theory and experiment in the study of biopolymer networks. Three-dimensional images of fluorescently labeled collagen are obtained by confocal microscopy, and the network geometry is extracted using a 3D network skeletonization algorithm. Each fiber is modeled as an elastic beam that resists stretching and bending, and each crosslink is modeled as torsional spring. The stress-strain curves of networks at three different densities are compared with rheology measurements. The model shows good agreement with experiment, confirming that strain stiffening of collagen can be explained entirely by geometric realignment of the network, as opposed to entropic stiffening of individual fibers. The model also suggests that at small strains, crosslink deformation is the main contributer to network stiffness, whereas at large strains, fiber stretching dominates. As this modeling effort uses networks with realistic geometries, this analysis can ultimately serve as a tool for understanding how the mechanics of fibers and crosslinks at the microscopic level produce the macroscopic properties of the network. (C) 2010Wiley Periodicals, Inc. Complexity 16: 22-28, 2011

Stiffness of the crystal-liquid interface in a hard-sphere colloidal system measured from capillary fluctuations - Ramsteiner, I. B.; Weitz, D. A.; F. Spaepen (Physical Review E, 2010)
Face-centered cubic single crystals of sigma = 1.55 mu m diameter hard-sphere silica colloidal particles were prepared by sedimentation onto (100) and (110) oriented templates. The crystals had a wide interface with the overlaying liquid that was parallel to the template. The location of the interface was determined by confocal microscopic location of the particles, followed by identification of the crystalline and liquid phases by a bond-orientation order parameter. Fluctuations in the height of the interface about its average position were recorded for several hundred configurations. The interfacial stiffness (gamma) over tilde was determined from the slope of the inverse squared Fourier components of the height profile vs the square of the wave number, according to the continuum capillary fluctuation method. The offset of the fit from the origin could quantitatively be accounted for by gravitational damping of the fluctuations. For the (100) interface, (gamma) over tilde = (1.3 +/- 0.3) k(B)T/sigma(2); for the (110) interface, (gamma) over tilde = (1.0 +/- 0.2)k(B)T/sigma(2). The interfacial stiffness of both interfaces was found to be isotropic in the plane. This is surprising for the (110), where crystallography predicts twofold symmetry. Sedimentation onto a (111) template yielded a randomly stacked hexagonal crystal with isotropic (gamma) over tilde = 0.66k(B)T/sigma(2). This value, however, is less reliable than the two others due to imperfections in the crystal.

Strain-Induced Alignment in Collagen Gels - Vader, David; Kabla, Alexandre; Weitz, DavidA.; Mahadevan, Lakshminarayana (PLOS One, 2009)
Collagen is the most abundant extracellular-network-forming protein in animal biology and is important in both natural and artificial tissues, where it serves as a material of great mechanical versatility. This versatility arises from its almost unique ability to remodel under applied loads into anisotropic and inhomogeneous structures. To explore the origins of this property, we develop a set of analysis tools and a novel experimental setup that probes the mechanical response of fibrous networks in a geometry that mimics a typical deformation profile imposed by cells in vivo. We observe strong fiber alignment and densification as a function of applied strain for both uncrosslinked and crosslinked collagenous networks. This alignment is found to be irreversibly imprinted in uncrosslinked collagen networks, suggesting a simple mechanism for tissue organization at the microscale. However, crosslinked networks display similar fiber alignment and the same geometrical properties as uncrosslinked gels, but with full reversibility. Plasticity is therefore not required to align fibers. On the contrary, our data show that this effect is part of the fundamental non-linear properties of fibrous biological networks.

Imaging Techniques for Measuring the Materials Properties of Cells - Kasza, Karen E.; Vader, David; Koester, Sarah; Wang, Ning; Weitz, DavidA. (Live Cell Imaging: A Laboratory Manual, 2009)
The “materials properties” of a biological material include its composition and microscopic structure and the relationship between its structure and its mechanical properties. For living cells, the motor-driven internal motion also significantly impacts the properties, even independently of any remodeling of the cell structure that can occur. These materials properties dictate the passive mechanical response of the material to an applied force. The mechanical properties of cells and tissues are essential for their function and health and affect how cells actively respond to mechanical force in important biological processes, ranging from motility to differentiation and morphogenesis. The mechanical properties of bulk tissues can be determined by traditional rheological techniques that measure the force required to stretch, compress, or shear macroscopic tissue. However, individual cells are too small to be measured by such methods and have highly heterogeneous structures; thus techniques are required that can probe soft materials at the micrometer scale. A variety of microrheological techniques, developed to determine the materials properties of cells, reveal that living cells have materials properties that are quite unusual compared with common inert materials. Cells are active, nonequilibrium materials with a highly nonlinear elasticity. This article presents a subset of microrheological techniques that involve optical imaging of micrometer-sized probes on or within individual cells, describes how to analyze probe motions, and discusses limitations of the techniques.

Functionalized glass coating for PDMS microfluidic devices - Abate, Adam R.; Lee, Daeyeon; Holtze, Christian; Krummel, Amber; Do, Thao; Weitz, DavidA. (Lab-on-a-Chip Technology (Vol. 1): Fabrication and Microfluidics, 2009)
Microfluidic devices can perform multiple laboratory functions on a single, compact, and fully integrated chip. However, fabrication of microfluidic devices is difficult, and current methods, such as glass-etching or soft-lithography in PDMS, are either expensive or yield devices with poor chemical robustness. We introduce a simple method that combines the simple fabrication of PDMS with superior robustness and control of glass. We coat PDMS channels with a functionalized glass layer. The glass coating greatly increases the chemical robustness of the PDMS devices. As a demonstration, we produce emulsions in coated channels using organic solvents. The glass coating also enables surface properties to be spatially controlled. As a demonstration of this control, we spatially pattern the wettability of coated PDMS channels and use the devices to produce double emulsions with fluorocarbon oil.

Flocculation kinetics of precipitated calcium carbonate - Gaudreault, Roger; Di Cesare, Nicolas; Weitz, DavidA.; van de Ven, Theo G. M. (Colloids and Surfaces, 2009)
When the percentage of filler in paper is increased, the optical properties are improved and the production cost lowered. However, fillers weaken paper strength by decreasing the fibre–fibre bonded area. Little is known about the optimum filler floc size or filler floc properties to allow developing optimum paper characteristics. Consequently, the kinetics of aggregation of scalenohedral precipitated calcium carbonate (PCC) filler was studied using various polymers (flocculants, coagulants and dry strength agents). The sodium salt of partially hydrolysed polyvinyl formamide copolymerized with acrylic acid (PVFA/NaAA) or C-starch lead to floc sizes, less sensitive to dosage within a certain range. Results from stability ratios correlate with PCC particle size. The change in particle size measured by photometric dispersion analysis (PDA) correlates well with the change in PCC particle size measured by light scattering/diffraction. Kinetic calculations show the orthokinetic aggregation times to be consistent with the experimental PDA results. The main uncertainty in the orthokinetic times is estimating the effective shear rate. It is proposed that the bridging surface area of PCC particles, the area which can form bonds between PCC particles or aggregates, should be used to study the kinetics of PCC aggregation, and not the total or projected surface area. In polymer induced aggregation, the PCC particle size increases to a plateau value with increasing polymer dosage. Two regions are most pronounced for C-PAM, PVFA/NaAA and A-starch. Region I corresponds to bridging flocculation. Region II is where the particle size reaches a plateau, and not the expected maximum predicted by classical polymer bridging theory or charge neutralisation theory, likely because of a competition between particle aggregation and polymer adsorption.

Droplet-Based Microfluidics for Emulsion and Solvent Evaporation Synthesis of Monodisperse Mesoporous Silica Microspheres - Carroll, Nick; Mendez, Sergio; Edwards, Jeremy; Weitz, DavidA.; Petsev, Dimiter, N. (Structure and Functional Properties of Colloidal Systems, 2009)
The miniaturization of chemical ow and analysis systems has opened up exciting avenues of scien ti c and engineering possibilities. Channels with widths in the tens of micrometer range are referred to as micro uidic devices. Fluidic behavior at the microscale may differ from that at larger scales in that interfacial tension, viscous effects, and energy dissipation can dominate the system. Micro uidics has received much attention in the scienti c community and many excellent reviews have been published [1,2]. A key advantage of micro uidics is the ability to perform experiments and bioassays using miniscule quantities of solution. This provides an economic bene t and is important for certain biosensing applications, experiments requiring single-molecule interrogation (e.g., deoxyribonucleic acid (DNA) sequencing [3,4]), or diffusion-limited regimes. Another benefit is that rapid measurements of these minute quantities can be performed with miniaturized analytical systems [5-7]. In some applications slow or minimal mixing is required, and the laminar ows obtained in microchannels become highly desirable. Water-in-oil emulsions can be formed in micro uidic devices to form a steady stream of monodisperse aqueous droplets with volumes as small as picoliters [8]. The drops can be loaded with reactants to perform chemical reactions of interest [9].

Universal behavior of the osmotically compressed cell and its analogy to the colloidal glass transition - Zhou, E. H.; Trepat, X.; Park, C. Y.; Lenormand, G.; Oliver, M. N.; Mijailovich, S.M.; Hardin, C.; Weitz, D. A.; Butler, J. P.; Fredberg, J. J. (PNAS, 2009)
Mechanical robustness of the cell under different modes of stress and deformation is essential to its survival and function. Under tension, mechanical rigidity is provided by the cytoskeletal network; with increasing stress, this network stiffens, providing increased resistance to deformation. However, a cell must also resist compression, which will inevitably occur whenever cell volume is decreased during such biologically important processes as anhydrobiosis and apoptosis. Under compression, individual filaments can buckle, thereby reducing the stiffness and weakening the cytoskeletal network. However, the intracellular space is crowded with macromolecules and organelles that can resist compression. A simple picture describing their behavior is that of colloidal particles; colloids exhibit a sharp increase in viscosity with increasing volume fraction, ultimately undergoing a glass transition and becoming a solid. We investigate the consequences of these 2 competing effects and show that as a cell is compressed by hyperosmotic stress it becomes progressively more rigid. Although this stiffening behavior depends somewhat on cell type, starting conditions, molecular motors, and cytoskeletal contributions, its dependence on solid volume fraction is exponential in every instance. This universal behavior suggests that compression-induced weakening of the network is overwhelmed by crowding-induced stiffening of the cytoplasm. We also show that compression dramatically slows intracellular relaxation processes. The increase in stiffness, combined with the slowing of relaxation processes, is reminiscent of a glass transition of colloidal suspensions, but only when comprised of deformable particles. Our work provides a means to probe the physical nature of the cytoplasm under compression, and leads to results that are universal across cell type.

Unjamming a Polymer Glass - Weitz, David A (Science, 2009)
Small probes reveal that glass can melt in different ways.

Fabrication of monodisperse toroidal particles by polymer solidification in microfluidics - Wang, Baoguo; Shum, Ho Cheung; Weitz, David A (Chemphyschem, 2009)
Microdoughnuts: Polymer toroidal particles such as the one shown in the left picture have been prepared by a capillary microfluidic technique. Droplets of polymer solution undergo non‐uniform solidification to form the anisotropic polymer particles. By incorporating functional materials inside the polymer network, functional toroidal particles (center and right images) can be tailor‐made for specific applications such as magnetic actuation.

Swelling kinetics of a microgel shell - Wahrmund, Joshua; Kim, Jin-Woong; Chu, Liang-Yin; Wang, Changjie; Li, Yong; Fernandez-Nieves, Alberto; Weitz, David A; Krokhin, Arkadii; Hu, Zhibing (Macromolecules, 2009)
Tanaka's approach to swelling kinetics of a solid gel sphere is extended to a spherical microgel shell. The boundary condition at the inner surface is obtained from the minimization of shear elastic energy. Temporal evolution of a shell is represented in a form of expansion over eigenfunctions of the corresponding diffusion equation. The swelling of Tanaka's solid spherical gel is recovered as a special case of our general Solution if the inner radius approaches zero. In another limiting case of it thin (balloon-like) shell, the set of eigenfunctions is reduced to a single exponential term. In the general case, a solid sphere swells slightly faster than the same sphere with in internal cavity. To test Our theoretical model, we prepared monodisperse poly-N-isopropylacrylamide (PNIPAM) hydrogel shells using a microfluidic device. The temporal dependence of the inner and outer radii of the shell were measured, and the data were fitted to our theoretical model. As a result, we obtained the collective diffusion constants for shrinking and for swelling processes. The obtained values for microgel shells are in excellent agreement with the previous results obtained for submillimeter PNIPAM solid spheres in the same temperature interval. Our model shows that the characteristic swelling time of a gel shell should be proportional to the square of the outer radius not to the thickness of the shell, agreeing with experimental observation.

Physical forces during collective cell migration - Trepat, Xavier; Wasserman, Michael R.; Angelini, Thomas E.; Millet, Emil; Weitz, David A; James P. Butler; Jeffrey J. Fredberg (Nature Physics, 2009)
Fundamental biological processes including morphogenesis, tissue repair and tumour metastasis require collective cell motions(1-3), and to drive these motions cells exert traction forces on their surroundings(4). Current understanding emphasizes that these traction forces arise mainly in 'leader cells' at the front edge of the advancing cell sheet(5-9). Our data are contrary to that assumption and show for the first time by direct measurement that traction forces driving collective cell migration arise predominately many cell rows behind the leading front edge and extend across enormous distances. Traction fluctuations are anomalous, moreover, exhibiting broad non-Gaussian distributions characterized by exponential tails(10-12). Taken together, these unexpected findings demonstrate that although the leader cell may have a pivotal role in local cell guidance, physical forces that it generates are but a small part of a global tug-of-war involving cells well back from the leading edge.

A multi-color fast-switching microfluidic droplet dye laser - Tang, Sindy K. Y.; Li, Zhenyu; Abate, Adam R.; Agresti, Jeremy J.; Weitz, David A; Psaltis, Demetri; George M. Whitesides (Lab on a Chip, 2009)
We describe a multi-color microfluidic dye laser operating in whispering gallery mode based on a train of alternating droplets containing solutions of different dyes; this laser is capable of switching the wavelength of its emission between 580 nm and 680 nm at frequencies up to 3.6 kHz-the fastest among all dye lasers reported; it has potential applications in on-chip spectroscopy and flow cytometry.

Arrested coalescence of particle-coated droplets into nonspherical supracolloidal structures - Studart, Andre R.; Shum, Ho Cheung; Weitz, David A (Journal of Physical Chemistry B, 2009)
Colloidal and supracolloidal structures with anisotropic shape and surface chemistry are potential building blocks for the fabrication of novel materials. Droplets or bubbles are often used as templates for the assembly of particles into supracolloidal structures of spherical shape. Particle-coated droplets or bubbles have recently been shown to also retain nonspherical geometries after deformation, suggesting that the templating approach can also be used to produce supracolloidal structures with anisotropic shape. We show that partially coated droplets generated in a microcapillary device can undergo spontaneous coalescence into stable nonspherical structures. By positioning the droplets into regular arrays before coalescence, we produce anisotropic geometries with well-defined bonding angles between adjacent merged droplets. This approach allows for the fabrication of novel anisotropic supracolloidal structures with deliberately designed shapes.

Double emulsion droplets as microreactors for synthesis of mesoporous hydroxyapatite - Shum, Ho Cheung; Bandyopadhyay, Amit; Bose, Susmita; Weitz, David A (Chemistry of Materials, 2009)
We introduce a novel approach for synthesizing mesoporous hydroxyapatite (HAp, (Ca)(10), (PO(4))(6)(OH)(2)) using double emulsion droplets as microreactors. By using capillary microfluidic techniques, the size and the geometry of the droplet microreactors can be tuned easily. Double emulsion droplets offer the combined advantages of both shielding the reactants and on-demand addition of reactants; this makes them highly versatile microreactors. Such droplet microreactors also enable simple visualization of the HAp formation process as well as control over the porosity in the HAp that is synthesized. Powder formed with our technique demonstrates a remarkable microstructure, as well as significantly enhanced BET specific average surface area and nanoscale porosity. Our results present a novel synthesis approach for controlling the nanoscale porosity and the morphology of inorganic particles using double emulsion droplets.

Janus supraparticles by induced phase separation of nanoparticles in droplets - Shah, Rhutesh K.; Kim, Jin-Woong; Weitz, David A (Advanced Materials, 2009)
Biphasic Janus particles with a precisely tunable internal morphology are fabricated using a novel, versatile, and robust technique. This technique can be used in conjunction with microfluidics to produce monodisperse particles, or can be combined with bulk emulsification techniques to produce large quantities of particles.

Dropspots: A picoliter array in a microfluidic device - Schmitz, Christian H. J.; Rowat, Amy C.; Koester, Sarah; Weitz, David A (Lab on a Chip, 2009)
We present a simple microfluidic device that uses an array of well-defined chambers to immobilize thousands of femtoliter-to picoliter-scale aqueous drops suspended in inert carrier oil. This device enables timelapse studies of large numbers of individual drops, while simultaneously enabling subsequent drop recovery.

Tracking lineages of single cells in lines using a microfluidic device - Rowat, Amy C.; Bird, James C.; Agresti, Jeremy J.; Rando, Oliver J.; Weitz, David A (Proceedings of the National Academy of Sciences of the United States of America, 2009)
Cells within a genetically identical population exhibit phenotypic variation that in some cases can persist across multiple generations. However, information about the temporal variation and familial dependence of protein levels remains hidden when studying the population as an ensemble. To correlate phenotypes with the age and genealogy of single cells over time, we developed a microfluidic device that enables us to track multiple lineages in parallel by trapping single cells and constraining them to grow in lines for as many as 8 divisions. To illustrate the utility of this method, we investigate lineages of cells expressing one of 3 naturally regulated proteins, each with a different representative expression behavior. Within lineages deriving from single cells, we observe genealogically related clusters of cells with similar phenotype; cluster sizes vary markedly among the 3 proteins, suggesting that the time scale of phenotypic persistence is protein-specific. Growing lines of cells also allows us to dynamically track temporal fluctuations in protein levels at the same time as pedigree relationships among the cells as they divide in the chambers. We observe bursts in expression levels of the heat shock protein Hsp12-GFP that occur simultaneously in mother and daughter cells. In contrast, the ribosomal protein Rps8b-GFP shows relatively constant levels of expression over time. This method is an essential step toward understanding the time scales of phenotypic variation and correlations in phenotype among single cells within a population.

Understanding epigenetic regulation: Tracking protein levels across multiple generations of cells - Rowat, A. C.; Weitz, D. A. (European Physical Journal-Special Topics, 2009)
Cells and organisms are remarkably robust: they alter the variety and levels of expressed genes and proteins in response to environmental stimuli, including temperature, chemicals, and the stiffness of their surroundings. Ultimately changes in gene and protein expression can result in a distinct phenotypic state, which in some cases is maintained over multiple generations; the ability to pass on a particular phenotypic state to progeny cells is critical for differentiation. Moreover, epigenetic regulation of phenotype is also thought to provide an evolutionary advantage for a population of cells adapting to a fluctuating environment on faster timescales than the occurrence of genetic mutations. However, simple methods to study patterns of gene and protein expression on multi-generational timescales are sparse. Here we describe a technique to study lineages of single cells over multiple generations using a microfluidic device; this reveals patterns of expression where protein levels are correlated across multiple generations. Such quantitative information of protein expression in the context of pedigree remains hidden when studying the population as an ensemble.

Experimental observation of the crystallization of hard-sphere colloidal particles by sedimentation onto flat and patterned surfaces - Ramsteiner, I. B.; Jensen, K. E.; Weitz, D. A.; F. Spaepen (Physical Review E, 2009)
We present a confocal microscopy study of 1.55 mu m monodisperse silica hard spheres as they sediment and crystallize at the bottom wall of a container. If the particles sediment onto a feature less flat wall, the two bottom layers crystallize simultaneously and layerwise growth follows. If the wall is replaced by a hexagonal template, only layerwise growth occurs. Our results complement earlier numerical simulations and experiments on other colloidal systems.

Short-time self-diffusion of nearly hard spheres at an oil-water interface - Peng, Y.; Chen, W.; Fischer, Th M.; Weitz, D. A.; Tong, P. (Journal of Fluid Mechanics, 2009)
Optical microscopy and multi-particle tracking are used to study hydrodynamic interactions of monodisperse polymethylmethacrylate (PMMA) spheres at a decalin-water interface. The short-time self-diffusion coefficient measured at low surface coverage has the form D(S)(S)(n) = alpha D(0)(1 - beta n), where n is the area fraction Occupied by the particles, and Do is the Stokes-Einstein diffusion coefficient in the bulk suspension of PMMA spheres in decalin. The measured values of a are found to be in good agreement with the numerical calculation for the drag coefficient of interfacial particles. The measured values of P differ from that obtained for bulk suspensions, indicating that hydrodynamic interactions between the particles have interesting new features at the interface.

Molecular basis of filamin A-FilGAP interaction and its impairment in congenital disorders associated with filamin A mutations - Nakamura, Fumihiko; Heikkinen, Outi; Pentikaeinen, Olli T.; Osborn, Teresia M.; Kasza, Karen E.; Weitz, David A; Kupiainen, Olga; Permi, Perttu; Kilpelaeinen, Ilkka; Ylaenne, Jari; Hartwig, John H; Stossel, Thomas P (Plos One, 2009)
Background: Mutations in filamin A (FLNa), an essential cytoskeletal protein with multiple binding partners, cause developmental anomalies in humans. Methodology/Principal Findings: We determined the structure of the 23(rd) Ig repeat of FLNa (IgFLNa23) that interacts with FilGAP, a Rac-specific GTPase-activating protein and regulator of cell polarity and movement, and the effect of the three disease-related mutations on this interaction. A combination of NMR structural analysis and in silico modeling revealed the structural interface details between the C and D beta-strands of the IgFLNa23 and the C-terminal 32 residues of FilGAP. Mutagenesis of the predicted key interface residues confirmed the binding constraints between the two proteins. Specific loss-of-function FLNa constructs were generated and used to analyze the importance of the FLNa-FilGAP interaction in vivo. Point mutagenesis revealed that disruption of the FLNa-FilGAP interface perturbs cell spreading. FilGAP does not bind FLNa homologs FLNb or FLNc establishing the importance of this interaction to the human FLNa mutations. Tight complex formation requires dimerization of both partners and the correct alignment of the binding surfaces, which is promoted by a flexible hinge domain between repeats 23 and 24 of FLNa. FLNa mutations associated with human developmental anomalies disrupt the binding interaction and weaken the elasticity of FLNa/F-actin network under high mechanical stress. Conclusions/Significance: Mutational analysis informed by structure can generate reagents for probing specific cellular interactions of FLNa. Disease-related FLNa mutations have demonstrable effects on FLNa function.

Soft colloids make strong glasses - Mattsson, Johan; Wyss, Hans M.; Fernandez-Nieves, Alberto; Miyazaki, Kunimasa; Hu, Zhibing; Reichman, David R.; Weitz, David A (Nature, 2009)
Glass formation in colloidal suspensions has many of the hallmarks of glass formation in molecular materials(1-5). For hard-sphere colloids, which interact only as a result of excluded volume, phase behaviour is controlled by volume fraction, phi; an increase in phi drives the system towards its glassy state, analogously to a decrease in temperature, T, in molecular systems. When phi increases above phi* approximate to 0.53, the viscosity starts to increase significantly, and the system eventually moves out of equilibrium at the glass transition, phi(g) approximate to 0.58, where particle crowding greatly restricts structural relaxation(1-4). The large particle size makes it possible to study both structure and dynamics with light scattering(1) and imaging(3,4); colloidal suspensions have therefore provided considerable insight into the glass transition. However, hard-sphere colloidal suspensions do not exhibit the same diversity of behaviour as molecular glasses. This is highlighted by the wide variation in behaviour observed for the viscosity or structural relaxation time, tau(alpha), when the glassy state is approached in supercooled molecular liquids(5). This variation is characterized by the unifying concept of fragility(5), which has spurred the search for a 'universal' description of dynamic arrest in glass-forming liquids. For 'fragile' liquids, tau(alpha) is highly sensitive to changes in T, whereas non-fragile, or 'strong', liquids show a much lower T sensitivity. In contrast, hard-sphere colloidal suspensions are restricted to fragile behaviour, as determined by their phi dependence(1,6), ultimately limiting their utility in the study of the glass transition. Here we show that deformable colloidal particles, when studied through their concentration dependence at fixed temperature, do exhibit the same variation in fragility as that observed in the T dependence of molecular liquids at fixed volume. Their fragility is dictated by elastic properties on the scale of individual colloidal particles. Furthermore, we find an equivalent effect in molecular systems, where elasticity directly reflects fragility. Colloidal suspensions may thus provide new insight into glass formation in molecular systems.

Gravitational compression of colloidal gels - Lietor-Santos, J. J.; Kim, C.; Lu, P. J.; Fernandez-Nieves, A.; Weitz, D. A. (European Physical Journal E, 2009)
We study the compression of depletion gels under the influence of a gravitational stress by monitoring the time evolution of the gel interface and the local volume fraction, phi, inside the gel. We find f is not constant throughout the gel. Instead, there is a volume fraction gradient that develops and grows along the gel height as the compression process proceeds. Our results are correctly described by a non-linear poroelastic model that explicitly incorporates the phi-dependence of the gravitational, elastic and viscous stresses acting on the gel.

Nonspherical colloidosomes with multiple compartments from double emulsions - Lee, Daeyeon; Weitz, David A (Small, 2009)
Nonspherical colloidosomes with multiple compartments are generated using water‐in‐oil‐in‐water double emulsions with controlled morphology as templates (see image). Double emulsions are prepared using a glass capillary microfluidic device that provides a precise means to control the number of internal aqueous droplets and the volume ratio of oil and aqueous phases.

Permeability of model stratum corneum lipid membrane measured using quartz crystal microbalance - Lee, Daeyeon; Ashcraft, J. Nathan; Verploegen, Eric; Pashkovski, Eugene; Weitz, David A (Langmuir, 2009)
The stratum corneum (SC) is the outermost layer of the epidermis. Stacked intercellular lipid membranes found in the SC play a crucial role in regulating water transport through the skin. Despite the importance of this role of the SC lipid membranes, only a few studies have presented quantitative methods to measure the permeability of water in SC lipid membranes. In this work, we present a new method to determine the water permeability of a model SC lipid membrane using a quartz crystal microbalance (QCM). We investigate a model SC lipid membrane comprising an equimolar mixture of brain ceramide (CER), cholesterol (CHO), and palmitic acid (PA), and use QCM to determine the diffusivity (D), solubility (S.) and permeability (P) of water vapor in the model SC lipid membrane.

Viscoelastic properties of oxide-coated liquid metals - Larsen, RyanJ.; Dickey, Michael D.; George M. Whitesides; Weitz, David A (Journal of Rheology, 2009)
Many liquid metals exposed to air develop an oxide film on their outer surface. This film is sufficiently solid-like to provide mechanical stability to small liquid metal droplets, yet weak enough to allow the droplets to be malleable. These properties are useful in both micro-electronics and microfluidics; however, little is known about how to characterize them. Here we probe the elastic, yielding, and relaxation properties of oxide-coated gallium and eutectic gallium indium using a rheometer equipped with a parallel-plate geometry. By using parallel plates of different size, we show that surface stresses dominate bulk stresses. These experiments also demonstrate that the apparent elastic properties of the oxide film are highly sensitive to its strain history. Moreover, the apparent elasticity is sensitive to the stresses stored in the oxide skin. We probe these stresses and their time-dependence, with both torque and normal force measurements. We also characterize the time-dependence of the elasticity by observing free vibrations of the rheometer. We rationalize the strain history and time-dependence in terms of oxidation and show that despite this dependence, reproducible elasticity measurements can be obtained due to the ability of shear to produce a state that is independent of the strain history. (C) 2009 The Society of Rheology. [DOI: 10.1122/1.3236517]

An active biopolymer network controlled by molecular motors - Koenderink, Gijsje H; Dogic, Zvonimir; Nakamura, Fumihiko; Bendix, Poul M; MacKintosh, Frederick C; Hartwig, John H; Stossel, Thomas P; Weitz, David A (Proceedings of the National Academy of Sciences of the United States of America, 2009)
We describe an active polymer network in which processive molecular motors control network elasticity. This system consists of actin filaments cross-linked by filamin A (FLNa) and contracted by bipolar filaments of muscle myosin II. The myosin motors stiffen the network by more than two orders of magnitude by pulling on actin filaments anchored in the network by FLNa cross-links, thereby generating internal stress. The stiffening response closely mimics the effects of external stress applied by mechanical shear. Both internal and external stresses can drive the network into a highly nonlinear, stiffened regime. The active stress reaches values that are equivalent to an external stress of 14 Pa, consistent with a 1-pN force per myosin head. This active network mimics many mechanical properties of cells and suggests that adherent cells exert mechanical control by operating in a nonlinear regime where cell stiffness is sensitive to changes in motor activity. This design principle may be applicable to engineering novel biologically inspired, active materials that adjust their own stiffness by internal catalytic control.

Influence of internal capsid pressure on viral infection by phage lambda - Koester, Sarah; Evilevitch, Alex; Jeembaeva, Meerim; Weitz, David A (Biophysical Journal, 2009)
Ejection of the genome from the virus, phage, is the initial step in the infection of its host bacterium. In vitro, the ejection depends sensitively on internal pressure within the virus capsid; however, the in vivo effect of internal pressure on infection of bacteria is unknown. Here, we use microfluidics to monitor individual cells and determine the temporal distribution of lysis due to infection as the capsid pressure is varied. The lysis probability decreases markedly with decreased capsid pressure. Of interest, the average lysis times remain the same but the distribution is broadened as the pressure is lowered.

Filamin A is essential for active cell stiffening but not passive stiffening under external force - Kasza, K. E.; Nakamura, F.; Hu, S.; Kollmannsberger, P.; Bonakdar, N.; Fabry, B.; Stossel, T. P.; Wang, N.; Weitz, D. A. (Biophysical Journal, 2009)
The material properties of a cell determine how mechanical forces are transmitted through and sensed by that cell. Some types of cells stiffen passively under large external forces, but they can also alter their own stiffness in response to the local mechanical environment or biochemical cues. Here we show that the actin-binding protein filamin A is essential for the active stiffening of cells plated on collagen-coated substrates. This appears to be due to a diminished capability to build up large internal contractile stresses in the absence of filamin A. To show this, we compare the material properties and contractility of two human melanoma cell lines that differ in filamin A expression. The filamin A-deficient M2 cells are softer than the filamin A-replete A7 cells, and exert much smaller contractile stresses on the substratum, even though the M2 cells have similar levels of phosphorylated myosin 11 light chain and only somewhat diminished adhesion strength. In contrast to A7 cells, the stiffness and contractility of M2 cells are insensitive to either myosin-inhibiting drugs or the stiffness of the substratum. Surprisingly, however, filamin A is not required for passive stiffening under large external forces.

Nonlinear elasticity of stiff biopolymers connected by flexible linkers - Kasza, K. E.; Koenderink, G. H.; Lin, Y. C.; Broedersz, C. P.; Messner, W.; Nakamura, F.; Stossel, T. P.; MacKintosh, F. C.; Weitz, D. A. (Physical Review E, 2009)
Networks of the biopolymer actin, cross-linked by the compliant protein filamin, form soft gels. They can, however, withstand large shear stresses due to their pronounced nonlinear elastic behavior. The nonlinear elasticity can be controlled by varying the number of cross-links per actin filament. We propose and test a model of rigid filaments decorated by multiple flexible linkers that is in quantitative agreement with experiment. This allows us to estimate loads on individual cross-links, which we find to be less than 10 pN.

Microwave dielectric heating of drops in microfluidic devices - Issadore, David; Humphry, Katherine J.; Brown, Keith A.; Sandberg, Lori; Weitz, David A; Robert M. Westervelt (Lab on a Chip, 2009)
We present a technique to locally and rapidly heat water drops in microfluidic devices with microwave dielectric heating. Water absorbs microwave power more efficiently than polymers, glass, and oils due to its permanent molecular dipole moment that has large dielectric loss at GHz frequencies. The relevant heat capacity of the system is a single thermally isolated picolitre-scale drop of water, enabling very fast thermal cycling. We demonstrate microwave dielectric heating in a microfluidic device that integrates a flow-focusing drop maker, drop splitters, and metal electrodes to locally deliver microwave power from an inexpensive, commercially available 3.0 GHz source and amplifier. The temperature change of the drops is measured by observing the temperature dependent fluorescence intensity of cadmium selenide nanocrystals suspended in the water drops. We demonstrate characteristic heating times as short as 15 ms to steady-state temperature changes as large as 30 degrees C above the base temperature of the microfluidic device. Many common biological and chemical applications require rapid and local control of temperature and can benefit from this new technique.

Suppression of instabilities in multiphase flow by geometric confinement - Humphry, Katherine J.; Ajdari, Armand; Fernandez-Nieves, Alberto; Stone, Howard A.; Weitz, David A (Physical Review E, 2009)
We investigate the effect of confinement on drop formation in microfluidic devices. The presence or absence of drop formation is studied for two immiscible coflowing liquids in a microfluidic channel, where the channel width is considerably larger than the channel height. We show that stability of the inner fluid thread depends on the channel geometry: when the width of the inner fluid is comparable to or larger than the channel height, hydrodynamic instabilities are suppressed, and a stable jet that does not break into drops results; otherwise, the inner fluid breaks into drops, in either a dripping or jetting regime. We present a model that accounts for the data and experimentally exploit this effect of geometric confinement to induce the breakup of a jet at a spatially defined location.

Diffusion through colloidal shells under stress - Guery, J.; Baudry, J.; Weitz, D. A.; Chaikin, P. M.; Bibette, J. (Physical Review E, 2009)
The permeability of solids has long been associated with a diffusive process involving activated mechanism as originally envisioned by Eyring. Tensile stress can affect the activation energy but definitive experiments of the diffusion rate of species through a stressed solid are lacking. Here we use core-shell (liquid core-solid shell) colloidal particles that are sensitive to osmotic pressure to follow the permeation of encapsulated probes at various stresses. We unambiguously show that the tensile stress applied on colloidal shells linearly reduces the local energy barrier for diffusion.

Magneto-mechanical mixing and manipulation of picoliter volumes in vesicles - Franke, Thomas; Schmid, Lothar; Weitz, David A; Wixforth, Achim (Lab on a Chip, 2009)
Superparamagnetic beads in giant unilamellar vesicles are used to facilitate magnetic manipulation, positioning, agitation and mixing of ultrasmall liquid volumes. Vesicles act as leakproof picoliter reaction vessels in an aqueous bulk solution and can be deliberately conveyed by an external magnetic field to a designated position. Upon application of an external magnetic field the beads align to form extended chains. In a rotating magnetic field chains break up into smaller fragments caused by the interplay of viscous friction and magnetic attraction. This process obeys a simple relationship and can be exploited to enhance mixing of the vesicle content and the outer solution or adjacent vesicle volumes exactly at the position of release.

Surface acoustic wave (SAW) directed droplet flow in microfluidics for PDMS devices - Franke, Thomas; Abate, Adam R.; Weitz, David A; Wixforth, Achim (Lab on a Chip, 2009)
We direct the motion of droplets in microfluidic channels using a surface acoustic wave device. This method allows individual drops to be directed along separate microchannel paths at high volume flow rates, which is useful for droplet sorting.

Electrodes on a budget: Micropatterned electrode fabrication by wet chemical deposition - Ebina, Wataru; Rowat, Amy C.; Weitz, David A (Biomicrofluidics, 2009)
Precise patterning of metals is required for diverse microfluidic and microelectro-mechanical system (MEMS) applications ranging from the separation of proteins to the manipulation of single cells and drops of water-in-oil emulsions. Here we present a very simple, inexpensive method for fabricating micropatterned electrodes. We deposit a thin metal layer of controlled thickness using wet chemistry, thus eliminating the need for expensive equipment typically required for metal deposition. We demonstrate that the resulting deposited metal can be used to fabricate functional electrodes: The wet-deposited metal film can sustain patterning by photolithography down to micron-sized features required for MEMS and microfluidic applications, and its properties are suitable for operative electrodes used in a wide range of microfluidic applications for biological studies. (C) 2009 American Institute of Physics. [DOI: 10.1063/1.3224669]

Nucleation and solidification in static arrays of monodisperse drops - Jon F. Edd; Humphry, Katherine J.; Irimia, Daniel; Weitz, David A; Toner, Mehmet (Lab on a Chip, 2009)
The precise measurement of nucleation and non-equilibrium solidification are vital to fields as diverse as atmospheric science, food processing, cryopreservation and metallurgy. The emulsion technique, where the phase under study is partitioned into many droplets suspended within an immiscible continuous phase, is a powerful method for uncovering rates of nucleation and dynamics of phase changes as it isolates nucleation events to single droplets. However, averaging the behavior of many drops in a bulk emulsion leads to the loss of any drop-specific information, and drop polydispersity clouds the analysis. Here we adapt a microfluidic technique for trapping monodisperse drops in planar arrays to characterize solidification of highly supercooled aqueous solutions of glycerol. This system measured rates of nucleation between 10(-5) and 10(-2) pL(-1) s(-1), yielded an ice-water interfacial energy of 33.4 mJ m(-2) between -38 and -35 degrees C, and enabled the specific dynamics of solidification to be observed for over a hundred drops in parallel without any loss of specificity. In addition to the physical insights gained, the ability to observe the time and temperature of nucleation and subsequent growth of the solid phase in static arrays of uniform drops provides a powerful tool to discover thermodynamic protocols that generate desirable crystal structures.

Janus particles templated from double emulsion droplets generated using mcrofluidics - Chen, Chia-Hung; Shah, Rhutesh K.; Abate, Adam R.; Weitz, David A (Langmuir, 2009)
We present a simple microfluidics-based technique to fabricate Janus particles using double-emulsion droplets as templates. Since each half of the particles is templated from a different immiscible fluid, this method enables the formation of particles from two materials with vastly different properties. The use of microfluidics affords excellent control over the size, morphology, and monodispersity of the particles.

Intracellular transport by active diffusion - Brangwynne, Clifford P; Koenderink, Gijsje H; MacKintosh, Frederick C; Weitz, David A (Trends in Cell Biology, 2009)
All substances exhibit constant random motion at the microscopic scale. This is a direct consequence of thermal agitation, and leads to diffusion of molecules and small particles in a liquid. In addition to this nondirected motion, living cells also use active transport mechanisms, such as motor activity and polymerization forces that depend on linear biopolymers and are therefore fundamentally directed in nature. Nevertheless, it has become increasingly clear that such active processes can also drive significant random fluctuations that can appear surprisingly like thermal diffusion of particles, but faster. Here, we discuss recent progress in quantifying this behavior and identifying its origins and consequences. We suggest that it represents an important and biologically tunable mechanism for transport in living cells.

Microfluidic assembly of magnetic hydrogel particles with uniformly anisotropic structure - Chen, Chia-Hung; Abate, Adam R.; Lee, Daeyeon; Terentjev, Eugene M.; Weitz, David A (Advanced Materials, 2009)
Monodisperse magnetic particles are templated from double emulsions formed using sequential flow-focus drop formation. The microfluidic drop formation allows the particles to be formed with high monodispersity and with consistently anisotropic internal structure. This structural anisotropy gives rise to magnetic anisotropy, allowing the particles to be rotated by a magnetic field.

Bacillus subtilis spreads by surfing on waves of surfactant - Angelini, Thomas E.; Roper, Marcus; Kolter, Roberto; Weitz, David A; Michael P. Brenner (Proceedings of the National Academy of Sciences of the United States of America, 2009)
The bacterium Bacillus subtilis produces the molecule surfactin, which is known to enhance the spreading of multicellular colonies on nutrient substrates by lowering the surface tension of the surrounding fluid, and to aid in the formation of aerial structures. Here we present experiments and a mathematical model that demonstrate how the differential accumulation rates induced by the geometry of the bacterial film give rise to surfactant waves. The spreading flux increases with increasing biofilm viscosity. Community associations are known to protect bacterial populations from environmental challenges such as predation, heat, or chemical stresses, and enable digestion of a broader range of nutritive sources. This study provides evidence of enhanced dispersal through cooperative motility, and points to nonintuitive methods for controlling the spread of biofilms.

Fluorescence-activated droplet sorting (FADS): Efficient microfluidic cell sorting based on enzymatic activity - Baret, Jean-Christophe; Miller, Oliver J.; Taly, Valerie; Ryckelynck, Michael; El-Harrak, Abdeslam; Frenz, Lucas; Rick, Christian; Samuels, Michael L.; Hutchison, J. Brian; Agresti, Jeremy J.; Link, Darren R.; Weitz, David A; et al. (Lab on a Chip, 2009)
We describe a highly efficient microfluidic fluorescence-activated droplet sorter (FADS) combining many of the advantages of microtitre-plate screening and traditional fluorescence-activated cell sorting (FACS). Single cells are compartmentalized in emulsion droplets, which can be sorted using dielectrophoresis in a fluorescence-activated manner (as in FACS) at rates up to 2000 droplets s(-1). To validate the system, mixtures of E. coli cells, expressing either the reporter enzyme beta-galactosidase or an inactive variant, were compartmentalized with a fluorogenic substrate and sorted at rates of similar to 300 droplets s(-1). The false positive error rate of the sorter at this throughput was < 1 in 10(4) droplets. Analysis of the sorted cells revealed that the primary limit to enrichment was the co-encapsulation of E. coli cells, not sorting errors: a theoretical model based on the Poisson distribution accurately predicted the observed enrichment values using the starting cell density (cells per droplet) and the ratio of active to inactive cells. When the cells were encapsulated at low density (similar to 1 cell for every 50 droplets), sorting was very efficient and all of the recovered cells were the active strain. In addition, single active droplets were sorted and cells were successfully recovered.

High-order multiple emulsions formed in poly(dimethylsiloxane) microfluidics - A. R. Abate; Weitz, D. A. (Small, 2009)
Multiple emulsions are formed using poly(dimethylsiloxane) microfluidic devices. The single emulsions (see image, left) are formed using a single drop maker with uniform wettability. The double, triple, quadruple, and quintuple emulsions (right) are formed using linear sequences of drop makers with alternating wettability.

Valve-based flow focusing for drop formation - Abate, Adam R.; Romanowsky, Mark B.; Agresti, Jeremy J.; Weitz, David A (Applied Physics Letters, 2009)
Microfluidic devices can produce highly monodisperse drops at kilohertz rates using flow-focus drop formation. We use single-layer membrane valves to control, in real time, the dimensions of the flow-focus drop makers. This allows drop size and frequency to be controlled in real time and without adjusting flow rates.

Beating Poisson encapsulation statistics using close-packed ordering - Abate, Adam R.; Chen, Chia-Hung; Agresti, Jeremy J.; Weitz, David A (Lab on a Chip, 2009)
Loading drops with discrete objects, such as particles and cells, is often necessary when performing chemical and biological assays in microfluidic devices. However, random loading techniques are inefficient, yielding a majority of empty and unusable drops. We use deformable particles that are close packed to insert a controllable number of particles into every drop. This provides a simple, flexible means of efficiently encapsulating a controllable number of particles per drop.

Impact of inlet channel geometry on microfluidic drop formation - A. R. Abate; Poitzsch, A.; Hwang, Y.; Lee, J.; Czerwinska, J.; Weitz, D. A. (Physical Review E, 2009)
We study the impact of inlet channel geometry on microfluidic drop formation. We show that drop makers with T-junction style inlets form monodisperse emulsions at low and moderate capillary numbers and those with Flow-Focus style inlets do so at moderate and high capillary numbers. At low and moderate capillary number, drop formation is dominated by interfacial forces and mediated by the confinement of the microchannels; drop size as a function of flow-rate ratio follows a simple functional form based on a blocking-squeezing mechanism. We summarize the stability of the drop makers with different inlet channel geometry in the form of a phase diagram as a function of capillary number and flow-rate ratio.

Orders-of-magnitude performance increases in GPU-accelerated correlation of images from the International Space Station - Lu, Peter J.; Oki, Hidekazu; Frey, Catherine A.; Chamitoff, Gregory E.; Chiao, Leroy; Fincke, Edward M.; Foale, C. Michael; Magnus, Sandra H.; McArthur, William S., Jr.; Tani, Daniel M.; Whitson, Peggy A.; Williams, Jeffrey N.; et al. (J Real-Time Image Proc, 2009)
We implement image correlation, a fundamental component of many real-time imaging and tracking systems, on a graphics processing unit (GPU) using NVI-DIA's CUDA platform. We use our code to analyze images of liquid-gas phase separation in a model colloid-polymer system, photographed in the absence of gravity aboard the International Space Station (ISS). Our GPU code is 4,000 times faster than simple MATLAB code performing the same calculation on a central processing unit (CPU), 130 times faster than simple C code, and 30 times faster than optimized C++ code using single-instruction, multiple-data (SIMD) extensions. The speed increases from these parallel algorithms enable us to analyze images downlinked from the ISS in a rapid fashion and send feedback to astronauts on orbit while the experiments are still being run.

The Soft Framework of the Cellular Machine - Weitz, DavidA.; Paul A. Janmey (PNAS, 2008)
The mechanical properties of cells are essential in determining a myriad of functions, from mitosis to locomotion. The functional rigidity of a cell is usually thought to result from three interpenetrating networks of filamentous biopolymers: actin microfilaments, microtubules, and intermediate filaments (IF). The mechanical properties of both filamentous actin (F-actin) and microtubule networks have been extensively studied, both directly in cells and in model in vitro systems, consisting of reconstituted networks of purified proteins. The assembly and structures of actin and tubulin polymers, coupled to ATP and GTP hydrolysis, respectively, give rise to fascinating dynamics that have attracted experimentalists, theorists, and modelers for decades, trying to understand their properties and functions. In addition, the diverse molecular motors that run along these tracks are central to much of cell dynamics and vesicle transport. By contrast, intermediate filaments do not hydrolyze nucleotides, do not exhibit structural polarity, and have no motors that run along them. Also, unlike actin and tubulin, which exist in very similar forms in nearly all eukaryotic cells, IF proteins appeared later in evolution and mutated rapidly to form distinct molecular species in different cell types. Some classes of IFs can be genetically ablated in mice without the mice necessarily losing viability and resulting in some cases in a barely discernable phenotype. However, the IFs expressed in epithelial cells, keratin IFs (or KIFs), are required for normal epithelial function, and mutations in these proteins can cause devastating human diseases. In an article in a recent issue of PNAS, Sivaramakrishnan et al. reported on the results of a remarkable study of the micromechanical properties of IF networks that should begin to redress our imbalance in understanding of the mechanics of the different biopolymer networks. These authors show that the KIF networks are essential for the mechanical integrity of the cell, and without them, cells such as alveolar epithelial cells would be helpless to withstand the forces they experience as the lung inflates and stretches them.

Gelation as arrested phase separation in short-ranged attractive colloid-polymer mixtures - Zaccarelli, Emanuela; Lu, Peter J.; Ciulla, Fabio; Weitz, David A; Sciortino, Francesco (Journal of Physics-Condensed Matter, 2008)
We present further evidence that gelation is an arrested phase separation in attractive colloid-polymer mixtures, based on a method combining confocal microscopy experiments with numerical simulations recently established in Lu et al (2008 Nature 453 499). Our results are independent of the form of the interparticle attractive potential and therefore should apply broadly to any attractive particle system with short-ranged, isotropic attractions. We also give additional characterization of the gel states in terms of their structure, inhomogeneous character and local density.

Dynamics of drying in 3D porous media - Xu, Lei; Davies, Simon; Schofield, Andrew B.; Weitz, David A (Physical Review Letters, 2008)
The drying dynamics in three dimensional porous media are studied with confocal microscopy. We observe abrupt air invasions in size from single particle to hundreds of particles. We show that these result from the strong flow from menisci in large pores to menisci in small pores during drying. This flow causes air invasions to start in large menisci and subsequently spread throughout the entire system. We measure the size and structure of the air invasions and show that they are in accord with invasion percolation. By varying the particle size and contact angle we unambiguously demonstrate that capillary pressure dominates the drying process.

Probing nonlinear rheology with inertio-elastic oscillations - Yao, Norman Y.; Larsen, RyanJ.; Weitz, David A (Journal of Rheology, 2008)
Many common materials display significant nonlinear theological properties. Characterizing these properties can be done with a variety of methods. One such method uses inertio-elastic oscillations, which occur naturally in rotational rheometry as a consequence of a material's elasticity and the inertia of the rheometer. These oscillations have primarily been used to characterize linear viscoelastic properties. In addition to allowing for the imposition of stress-biased oscillations on short time scales, we demonstrate that extending this technique to nonlinear deformations provides accurate measurements of nonlinear material properties. Our experiments are performed on fibrin networks, which are well characterized and have dramatic nonlinear properties that are biologically significant. We compare the tangent moduli measurements of inertio-elastic oscillations with three standard methods of nonlinear rheology: forced oscillations about a prestress, a geometric interpretation of large amplitude oscillatory shears, and an extension of the linear viscoelastic moduli to the nonlinear regime. Inertio-elastic oscillations provide an accurate characterization of fibrin's nonlinear properties, and further, our measurements suggest that inertio-elastic oscillations provide the most straightforward method of distinguishing between nonlinear elasticity and dissipation at any given stress. In fact, we find that inertio-elastic oscillations provide the most accurate measurement of the subdominant loss component of our networks. (C) 2008 The Society of Rheology.

Dynamic viscoelasticity of actin cross-linked with wild-type and disease-causing mutant alpha-actinin-4 - Ward, Sabine M. Volkmer; Weins, Astrid; Pollak, Martin R.; Weitz, David A (Biophysical Journal, 2008)
The actin cross-linker alpha-actinin-4 has been found to be indispensable for the structural and functional integrity of podocytes; deficiency or alteration of this protein due to mutations results in kidney disease. To gain insight into the effect of the cross-linker on cytoskeletal mechanics, we studied the macroscopic rheological properties of actin networks cross-linked with wild-type and mutant alpha-actinin-4. The frequency-dependent viscoelasticity of the networks is characterized by an elastic plateau at intermediate frequencies, and relaxation toward fluid properties at low frequencies. The relaxation frequencies of networks with mutant alpha-actinin-4 are an order of magnitude lower than that with the wild-type, suggesting a slower reaction rate for the dissociation of actin and alpha-actinin for the mutant, consistent with a smaller observed equilibrium dissociation constant. This difference can be attributed to an additional binding site that is exposed as a result of the mutation, and can be interpreted as a difference in binding energy barriers. This is further supported by the Arrhenius-like temperature dependence of the relaxation frequencies.

Absolute instability of a liquid jet in a coflowing stream - Utada, Andrew S.; Fernandez-Nieves, Alberto; Gordillo, Jose M.; Weitz, David A (Physical Review Letters, 2008)
Cylindrical liquid jets are inherently unstable and eventually break into drops due to the Rayleigh-Plateau instability, characterized by the growth of disturbances that are either convective or absolute in nature. Convective instabilities grow in amplitude as they are swept along by the flow, while absolute instabilities are disturbances that grow at a fixed spatial location. Liquid jets are nearly always convectively unstable. Here we show that two-phase jets can breakup due to an absolute instability that depends on the capillary number of the outer liquid, provided the Weber number of the inner liquid is >O(1). We verify our experimental observations with a linear stability analysis.

Velocity fluctuations in a low-Reynolds-number fluidized bed - Tee, Shang-You; Mucha, P. J.; Brenner, M.P.; Weitz, D. A. (Journal of Fluid Mechanics, 2008)
The velocity fluctuations of particles in a low-Reynolds-number fluidized bed have important similarities and differences with the velocity fluctuations in a low-Reynolds-number sedimenting suspension. We show that, like sedimentation, the velocity fluctuations in a fluidized bed are described well by the balance between density fluctuations due to Poisson statistics and Stokes drag. However, unlike sedimentation, the correlation length of the fluctuations in a fluidized bed increases with volume fraction. We argue that this difference arises because the relaxation time of density fluctuations is completely different in the two systems.

An algorithm for extracting the network geometry of three-dimensional collagen gels - Stein, Andrew M.; Vader, David A.; Jawerth, Louise M.; Weitz, David A; Sander, Leonard M. (Journal of Microscopy, 2008)
The geometric structure of a biopolymer network impacts its mechanical and biological properties. In this paper, we develop an algorithm for extracting the network architecture of three-dimensional (3d) fluorescently labeled collagen gels, building on the initial work of Wu et al., (2003). Using artificially generated images, the network extraction algorithm is then validated for its ability to reconstruct the correct bulk properties of the network, including fiber length, persistence length, cross-link density, and shear modulus.

Double emulsion templated monodisperse phospholipid vesicles - Shum, Ho Cheung; Lee, Daeyeon; Yoon, Insun; Kodger, Tom; Weitz, David A (Langmuir, 2008)
We present a novel approach for fabricating monodisperse phospholipid vesicles with high encapsulation efficiency using controlled double emulsions as templates. Glass-capillary microfluidics is used to generate monodisperse double emulsion templates. We show that the high uniformity in size and shape of the templates are maintained in the final phospholipid vesicles after a solvent removal step. Our simple and versatile technique is applicable to a wide range of phospholipids.

Microfluidic fabrication of monodisperse biocompatible and biodegradable polymersomes with controlled permeability - Shum, Ho Cheung; Kim, Jin-Woong; Weitz, David A (Journal of the American Chemical Society, 2008)
We describe a versatile technique for fabricating monodisperse polymersomes with biocompatible and biodegradable diblock copolymers for efficient encapsulation of actives. We use double emulsion as a template for the assembly of amphiphilic diblock copolymers into vesicle structures. These polymersomes can be used to encapsulate small hydrophilic solutes. When triggered by an osmotic shock, the polymersomes break and release the solutes, providing a simple and effective release mechanism. The technique can also be applied to diblock copolymers with different hydrophilic-to-hydrophobic block ratios, or mixtures of diblock copolymers and hydrophobic homopolymers. The ability to make polymer vesicles with copolymers of different block ratios and to incorporate different homopolymers into the polymersomes will allow the tuning of polymersome properties for specific technological applications.

Designer emulsions using microfluidics - Shah, Rhutesh K.; Shum, Ho Cheung; Rowat, Amy C.; Lee, Daeyeon; Agresti, Jeremy J.; Utada, Andrew S.; Chu, Liang-Yin; Kim, Jin-Woong; Fernandez-Nieves, Alberto; Martinez, Carlos J.; Weitz, David A (Materials Today, 2008)
We describe new developments for the controlled fabrication of monodisperse emulsions using microfluidics. We use glass capillary devices to generate single, double, and higher order emulsions with exceptional precision. These emulsions can serve as ideal templates for generating well-defined particles and functional vesicles. Polydimethylsiloxane microfluidic devices are also used to generate picoliter-scale water-in-oil emulsions at rates as high as 10 000 drops per second. These emulsions have great potential as individual microvessels in high-throughput screening applications, where each drop serves to encapsulate single cells, genes, or reactants.

Fabrication of monodisperse thermosensitive microgels and gel capsules in microfluidic devices - Shah, Rhutesh K.; Kim, Jin-Woong; Agresti, Jeremy J.; Weitz, David A; Chu, Liang-Yin (Soft Matter, 2008)
We use droplet-based microfluidic techniques to produce monodisperse poly( N-isopropylacrylamide) gel particles in the size range of 10-1000 mu m. Our techniques offer exquisite control over both outer dimensions and inner morphology of the particles. We demonstrate this control by fabricating conventional microgels, microgels with embedded materials and voids, and gel microcapsules with single- and multi-phase cores. These techniques should be applicable for the synthesis of particles and capsules of a variety of chemical compositions and for the generation of higher order "supraparticles'' by directed assembly of colloidal particles in droplets.

Highly anisotropic vorticity aligned structures in a shear thickening attractive colloidal system - Osuji, Chinedum O.; Weitz, David A (Soft Matter, 2008)
Vorticity aligned cylindrical flocs of carbon black particles are formed in steady flow at low shear rates and, strikingly, appear as transient structures in the flow response of gels produced by the quenching of high rate shear thickening flows.

Optimal vein density in artificial and real leaves - Noblin, X.; Mahadevan, L; Coomaraswamy, I. A.; Weitz, D. A.; Holbrook, N. M.; Zwieniecki, M. A. (PNAS, 2008)
The long evolution of vascular plants has resulted in a tremendous variety of natural networks responsible for the evaporatively driven transport of water. Nevertheless, little is known about the physical principles that constrain vascular architecture. Inspired by plant leaves, we used microfluidic devices consisting of simple parallel channel networks in a polymeric material layer, permeable to water, to study the mechanisms of and the limits to evaporation-driven flow. We show that the flow rate through our biomimetic leaves increases linearly with channel density (1/d) until the distance between channels (d) is comparable with the thickness of the polymer layer (5), above which the flow rate saturates. A comparison with the plant vascular networks shows that the same optimization criterion can be used to describe the placement of veins in leaves. These scaling relations for evaporatively driven flow through simple networks reveal basic design principles for the engineering of evaporation-permeation-driven devices, and highlight the role of physical constraints on the biological design or leaves.

Shear thickening and scaling of the elastic modulus in a fractal colloidal system with attractive interactions - Osuji, Chinedum O.; Kim, Chanjoong; Weitz, David A (Physical Review E, 2008)
Dilute oil dispersions of fractal carbon black particles with attractive van der Waals interactions display continuous shear thickening followed by shear thinning at high shear rates. The shear thickening transition occurs at (gamma) over dot(c)approximate to 10(2)-10(3) s(-1) and is driven by hydrodynamic breakup of clusters. Pre-shearing dispersions at shear rates (gamma) over dot>(gamma) over dot(c) produces enhanced-modulus gels where G'similar to sigma(1.5-2)(pre-shear) and is directly proportional to the residual stress in the gel measured at a fixed sample age. The observed data can be accounted for using a simple scaling model for the breakup of fractal clusters under shear stress.

Robust pore size analysis of filamentous networks from three-dimensional confocal microscopy - Mickel, Walter; Muenster, Stefan; Jawerth, Louise M.; Vader, David A.; Weitz, David A; Sheppard, Adrian P.; Mecke, Klaus; Fabry, Ben; Schroeder-Turk, Gerd E. (Biophysical Journal, 2008)
We describe a robust method for determining morphological properties of. lamentous biopolymer networks, such as collagen or other connective tissue matrices, from confocal microscopy image stacks. Morphological properties including pore size distributions and percolation thresholds are important for transport processes, e. g., particle diffusion or cell migration through the extracellular matrix. The method is applied to fluorescently labeled fiber networks prepared from rat-tail tendon and calf-skin collagen, at concentrations of 1.2, 1.6, and 2.4 mg/ml. The collagen fibers form an entangled and branched network. The medial axes, or skeletons, representing the collagen fibers are extracted from the image stack by threshold intensity segmentation and distance-ordered homotopic thinning. The size of the fiuid pores as defined by the radii of largest spheres that fit into the cavities between the collagen fibers is derived from Euclidean distance maps and maximal covering radius transforms of the fluid phase. The size of the largest sphere that can traverse the fluid phase between the collagen fibers across the entire probe, called the percolation threshold, was computed for both horizontal and vertical directions. We demonstrate that by representing the fibers as the medial axis the derived morphological network properties are both robust against changes of the value of the segmentation threshold intensity and robust to problems associated with the point-spread function of the imaging system. We also provide empirical support for a recent claim that the percolation threshold of a fiber network is close to the fiber diameter for which the Euler index of the networks becomes zero.

Gelation of particles with short-range attraction - Lu, Peter J.; Zaccarelli, Emanuela; Ciulla, Fabio; Schofield, Andrew B.; Sciortino, Francesco; Weitz, David A (Nature, 2008)
Nanoscale or colloidal particles are important in many realms of science and technology. They can dramatically change the properties of materials, imparting solid-like behaviour to a wide variety of complex fluids(1,2). This behaviour arises when particles aggregate to form mesoscopic clusters and networks. The essential component leading to aggregation is an interparticle attraction, which can be generated by many physical and chemical mechanisms. In the limit of irreversible aggregation, infinitely strong interparticle bonds lead to diffusion-limited cluster aggregation(3) (DLCA). This is understood as a purely kinetic phenomenon that can form solid-like gels at arbitrarily low particle volume fraction(4,5). Far more important technologically are systems with weaker attractions, where gel formation requires higher volume fractions. Numerous scenarios for gelation have been proposed, including DLCA(6), kinetic or dynamic arrest(4,7-10), phase separation(5,6,11-16), percolation(4,12,17,18) and jamming(8). No consensus has emerged and, despite its ubiquity and significance, gelation is far from understood-even the location of the gelation phase boundary is not agreed on(5). Here we report experiments showing that gelation of spherical particles with isotropic, short-range attractions is initiated by spinodal decomposition; this thermodynamic instability triggers the formation of density fluctuations, leading to spanning clusters that dynamically arrest to create a gel. This simple picture of gelation does not depend on microscopic system-specific details, and should thus apply broadly to any particle system with short- range attractions. Our results suggest that gelation-often considered a purely kinetic phenomenon(4,8-10)-is in fact a direct consequence of equilibrium liquid gas phase separation(5,13-15). Without exception, we observe gelation in all of our samples predicted by theory and simulation to phaseseparate; this suggests that it is phase separation, not percolation(12), that corresponds to gelation in models for attractive spheres.

Double emulsion-templated nanoparticle colloidosomes with selective permeability - Lee, Daeyeon; Weitz, David A (Advanced Materials, 2008)
Nanoparticle colloidosomes, shown in the SEM image, are generated by using water-in-oil-in-water double emulsions as templates. Hydrophobic silica nanoparticles that are dispersed in the oil phase stabilize the double emulsions, and subsequently become the shell of the colloidosomes upon removal of the organic solvent as shown in the figure.

Drop-based microfluidic devices for encapsulation of single cells - Koester, Sarah; Angile, Francesco E.; Duan, Honey; Agresti, Jeremy J.; Wintner, Anton; Schmitz, Christian; Rowat, Amy C.; Merten, Christoph A.; Pisignano, Dario; Griffiths, Andrew D.; Weitz, David A (Lab on a Chip, 2008)
We use microfluidic devices to encapsulate, incubate, and manipulate individual cells in picoliter aqueous drops in a carrier fluid at rates of up to several hundred Hz. We use a modular approach with individual devices for each function, thereby significantly increasing the robustness of our system and making it highly flexible and adaptable to a variety of cell-based assays. The small volumes of the drops enables the concentrations of secreted molecules to rapidly attain detectable levels. We show that single hybridoma cells in 33 pL drops secrete detectable concentrations of antibodies in only 6 h and remain fully viable. These devices hold the promise of developing microfluidic cell cytometers and cell sorters with much greater functionality, allowing assays to be performed on individual cells in their own microenvironment prior to analysis and sorting.

Colloid surfactants for emulsion stabilization - Kim, Jin-Woong; Lee, Daeyeon; Shum, Ho Cheung; Weitz, David A (Advanced Materials, 2008)
Colloid surfactants are fabricated with precisely controlled geometry and used for emulsion stabilization. These amphiphilic dimer particles (left) combine the benefits of emulsion stabilization of particles and the amphiphilicity of molecular surfactants to afford better emulsion stabilization. Remarkably, these colloidal surfactants stabilize not only spherical emulsion droplets but also nonspherical ones (right).

Biocompatible surfactants for water-in-fluorocarbon emulsions - C. Holtze; Rowat, A. C.; Agresti, J. J.; Hutchison, J. B.; Angile, F. E.; Schmitz, C. H. J.; Koster, S.; Duan, H.; Humphry, K. J.; Scanga, R. A.; Johnson, J. S.; Pisignano, D.; et al. (Lab on a Chip, 2008)
Drops of water-in-fluorocarbon emulsions have great potential for compartmentalizing both in vitro and in vivo biological systems; however, surfactants to stabilize such emulsions are scarce. Here we present a novel class of fluorosurfactants that we synthesize by coupling oligomeric perfluorinated polyethers (PFPE) with polyethyleneglycol (PEG). We demonstrate that these block copolymer surfactants stabilize water-in-fluorocarbon oil emulsions during all necessary steps of a drop-based experiment including drop formation, incubation, and reinjection into a second microfluidic device. Furthermore, we show that aqueous drops stabilized with these surfactants can be used for in vitro translation (IVT), as well as encapsulation and incubation of single cells. The compatability of this emulsion system with both biological systems and polydimethylsiloxane (PDMS) microfluidic devices makes these surfactants ideal for a broad range of high-throughput, drop-based applications.

Mechanical response of cytoskeletal networks - Gardel, Margaret L.; Kasza, Karen E.; Brangwynne, Clifford P; Liu, Jiayu; Weitz, David A; Correia, J. J.; Detrich, H. W. (Biophysical Tools for Biologists, Vol 2: In Vivo Techniques, 2008)
The cellular cytoskeleton is a dynamic network of filamentous proteins, consisting of filamentous actin (F-actin), microtubules, and intermediate filaments. However, these networks are not simple linear, elastic solids; they can exhibit highly nonlinear elasticity and athermal dynamics driven by ATP-dependent processes. To build quantitative mechanical models describing complex cellular behaviors, it is necessary to understand the underlying physical principles that regulate force transmission and dynamics within these networks. In this chapter, we review our current understanding of the physics of networks of cytoskeletal proteins formed in vitro. We introduce rheology, the technique used to measure mechanical response. We discuss our current understanding of the mechanical response of F-actin networks, and how the biophysical properties of F-actin and actin cross-linking proteins can dramatically impact the network mechanical response. We discuss how incorporating dynamic and rigid microtubules into F-actin networks can affect the contours of growing microtubules and composite network rigidity. Finally, we discuss the mechanical behaviors of intermediate filaments.

Controlled encapsulation of single-cells into monodisperse picolitre drops - Jon F. Edd; Di Carlo, Dino; Humphry, Katherine J.; Koster, Sarah; Irimia, Daniel; Weitz, David A; Toner, Mehmet (Lab on a Chip, 2008)
Encapsulation of cells within picolitre-size monodisperse drops provides new means to perform quantitative biological studies on a single-cell basis for large cell populations. Variability in the number of cells per drop due to stochastic cell loading is a major barrier to these techniques. We overcome this limitation by evenly spacing cells as they travel within a high aspect-ratio microchannel; cells enter the drop generator with the frequency of drop formation.

Eutectic gallium-indium (EGaIn): A liquid metal alloy for the formation of stable structures in microchannels at room temperature - Dickey, Michael D.; Chiechi, Ryan C.; Larsen, RyanJ.; Weiss, Emily A.; Weitz, David A; George M. Whitesides (Advanced Functional Materials, 2008)
This paper describes the rheological behavior of the liquid metal eutectic gallium-indium (EGaIn) as it is injected into microfluidic channels to form stable microstructures of liquid metal. EGaIn is well-suited for this application because of its theological properties at room temperature: it behaves like an elastic material until it experiences a critical surface stress, at which point it yields and flows readily. These properties allow EGaIn to fill microchannels rapidly when sufficient pressure is applied to the inlet of the channels, yet maintain structural stability within the channels once ambient pressure is restored. Experiments conducted in microfluidic channels, and in a parallel-plate rheometer, suggest that EGaIn's behavior is dictated by the properties of its surface (Predominantly gallium oxide, as determined by Auger measurements); these two experiments both yield approximately the same number for the critical surface stress required to induce EGaIn to flow (similar to 0.5 N/m). This analysis-which shows that the pressure that must be exceeded for EGaIn to flow through a microchannel is inversely proportional to the critical (i.e., smallest) dimension of the channel-is useful to guide future fabrication of microfluidic channels to mold EGaIn into functional microstructures.

Droplet-based microfluidic platforms for the encapsulation and screening of mammalian cells and multicellular organisms - Clausell-Tormos, Jenifer; Lieber, Diana; Baret, Jean-Christophe; El-Harrak, Abdeslam; Miller, Oliver J.; Frenz, Lucas; Blouwolff, Joshua; Humphry, Katherine J.; Koster, Sarah; Duan, Honey; Holtze, Christian; Weitz, David A; et al. (Chemistry & Biology, 2008)
High-throughput, cell-based assays require small sample volumes to reduce assay costs and to allow for rapid sample manipulation. However, further miniaturization of conventional microtiter plate technology is problematic due to evaporation and capillary action. To overcome these limitations, we describe droplet-based microfluidic platforms in which cells are grown in aqueous microcompartments separated by an inert perfluorocarbon carrier oil. Synthesis of biocompatible surfactants and identification of gas-permeable storage systems allowed human cells, and even a Multicellular organism (C. elegans), to survive and proliferate within the microcompartments for several days. Microcompartments containing single cells could be reinjected into a microfluidic device after incubation to measure expression of a reporter gene. This should open the way for high-throughput, cell-based screening that can use >1000-fold smaller assay volumes and has similar to 500x higher throughput than conventional microtiter plate assays.

Highly responsive hydrogel scaffolds formed by three-dimensional organization of microgel nanoparticles - Cho, Eun Chul; Kim, Jin-Woong; Fernandez-Nieves, Alberto; Weitz, David A (Nano Letters, 2008)
We present a robust and straightforward method for fabricating remarkably responsive hydrogel scaffolds consisting of submicron-sized microgel particles. We demonstrate that the microgel particles assemble either through bridging or depletion interactions to yield a structure that swells or deswells at a macroscopic level in much shorter times as compared to a bulk polymer gel of similar characteristics. This approach offers a new way of fabricating functional hydrogel scaffolds with controllable responsiveness to applied stimuli and excellent loading capability for a wide variety of materials, irrespective of chemistry, size, and shape.

Droplet-based microfluidics for emulsion and solvent evaporation synthesis of monodisperse mesoporous silica microspheres - Carroll, Nick J.; Rathod, Shailendra B.; Derbins, Erin; Mendez, Sergio; Weitz, David A; Petsev, Dimiter N. (Langmuir, 2008)
A novel method for the fabrication of monodisperse mesoporous silica particles is suggested. It is based on the formation of well-defined equally sized emulsion droplets using a microfluidic approach. The droplets contain the silica precursor/surfactant solution and are suspended in hexadecane as the continuous oil phase. The solvent is then expelled from the droplets, leading to concentration and micellization of the surfactant. At the same time, the silica solidifies around the surfactant structures, forming equally sized mesoporous particles. The procedure can be tuned to produce well-separated particles or alternatively particles that are linked together. The latter allows us to create 2D or 3D structures with hierarchical porosity.

Cytoplasmic diffusion: Molecular motors mix it up - Brangwynne, Clifford P; Koenderink, Gijsje H; MacKintosh, Frederick C; Weitz, David A (Journal of Cell Biology, 2008)
Random motion within the cytoplasm gives rise to molecular diffusion; this motion is essential to many biological processes. However, in addition to thermal Brownian motion, the cytoplasm also undergoes constant agitation caused by the activity of molecular motors and other nonequilibrium cellular processes. Here, we discuss recent work that suggests this activity can give rise to cytoplasmic motion that has the appearance of diffusion but is significantly enhanced in its magnitude and which can play an important biological role, particularly in cytoskeletal assembly.

Nonequilibrium microtubule fluctuations in a model cytoskeleton - Brangwynne, Clifford P; Koenderink, Gijsje H; MacKintosh, Frederick C; Weitz, David A (Physical Review Letters, 2008)
Biological activity gives rise to nonequilibrium fluctuations in the cytoplasm of cells; however, there are few methods to directly measure these fluctuations. Using a reconstituted actin cytoskeleton, we show that the bending dynamics of embedded microtubules can be used to probe local stress fluctuations. We add myosin motors that drive the network out of equilibrium, resulting in an increased amplitude and modified time dependence of microtubule bending fluctuations. We show that this behavior results from steplike forces on the order of 10 pN driven by collective motor dynamics.

A quantitative analysis of contractility in active cytoskeletal protein networks - Bendix, Paul M.; Koenderink, Glisje H.; Cuvelier, Damien; Dogic, Zvonimir; Koeleman, Bernard N; Brieher, William M; Field, Christine M; Mahadevan, L; Weitz, David A (Biophysical Journal, 2008)
Cells actively produce contractile forces for a variety of processes including cytokinesis and motility. Contractility is known to rely on myosin II motors which convert chemical energy from ATP hydrolysis into forces on actin filaments. However, the basic physical principles of cell contractility remain poorly understood. We reconstitute contractility in a simplified model system of purified F-actin, muscle myosin II motors, and a-actinin cross-linkers. We show that contractility occurs above a threshold motor concentration and within a window of cross-linker concentrations. We also quantify the pore size of the bundled networks and find contractility to occur at a critical distance between the bundles. We propose a simple mechanism of contraction based on myosin filaments pulling neighboring bundles together into an aggregated structure. Observations of this reconstituted system in both bulk and low-dimensional geometries show that the contracting gels pull on and deform their surface with a contractile force of similar to 1 mu N, or similar to 100 pN per F-actin bundle. Cytoplasmic extracts contracting in identical environments show a similar behavior and dependence on myosin as the reconstituted system. Our results suggest that cellular contractility can be sensitively regulated by tuning the (local) activity of molecular motors and the cross-linker density and binding affinity.

Single-layer membrane valves for elastomeric microfluidic devices - A. R. Abate; Weitz, D. A. (Applied Physics Letters, 2008)
We characterize single-layer membrane valves for elastomeric microfluidic devices. The devices are simple to fabricate using standard single-layer softlithography; moreover, they afford continuous control over flow rate. This combines the simplicity of stamped microfluidic devices with the precision control of membrane valves, which we demonstrate by steering objects in the flow using a simple device. (c) 2008 American Institute of Physics.

Glass coating for PDMS microfluidic channels by sol-gel methods - Abate, Adam R.; Lee, Daeyeon; Do, Thao; Holtze, Christian; Weitz, David A (Lab on a Chip, 2008)
Soft lithography using polydimethylsiloxane (PDMS) allows one to fabricate complex microfluidic devices easily and at low cost. However, PDMS swells in the presence of many organic solvents significantly degrading the performance of the device. We present a method to coat PDMS channels with a glass-like layer using sol-gel chemistry. This coating greatly increases chemical resistance of the channels; moreover, it can be functionalized with a wide range of chemicals to precisely control interfacial properties. This method combines the ease of fabrication afforded by soft-lithography with the precision control and chemical robustness afforded by glass.

Photoreactive coating for high-contrast spatial patterning of microfluidic device wettability - Abate, Adam R.; Krummel, Amber T.; Lee, Daeyeon; Marquez, Manuel; Holtze, Christian; Weitz, David A (Lab on a Chip, 2008)
For many applications in microfluidics, the wettability of the devices must be spatially controlled. We introduce a photoreactive sol-gel coating that enables high-contrast spatial patterning of microfluidic device wettability.

Noninvasive Probing of the Spatial Organization of Polymer Chains in Hydrogels Using Fluorescence Resonance Energy Transfer (FRET) - Kong, Hyun J.; Kim, Chan J.; Huebsch, Nathaniel; Weitz, DavidA.; Mooney, David J. (Journal of the American Chemical Society, 2007)
Spatial organization of polymer chains upon ionic or covalent cross-linking to form a hydrogel is examined on the molecular scale using a fluorescent resonance energy transfer (FRET) technique. Minimal changes in the conformation in the polymer chains but significant changes of the intermolecular association of polymer chains are found when polymer chains are cross-linked with a different number of cross-links. This study provides a previously undescribed technique to analyze hydrogel structure in a noninvasive manner.

Strain-rate frequency superposition: A rheological probe of structural relaxation in soft materials - Wyss, Hans M.; Miyazaki, Kunimasa; Mattsson, Johan; Hu, Zhibing; Reichman, David R.; Weitz, David A (Physical Review Letters, 2007)
The rheological properties of soft materials often exhibit surprisingly universal linear and nonlinear features. Here we show that these properties can be unified by considering the effect of the strain-rate amplitude on the structural relaxation of the material. We present a new form of oscillatory rheology, strain-rate frequency superposition (SRFS), where the strain-rate amplitude is fixed as the frequency is varied. We show that SRFS can isolate the response due to structural relaxation, even when it occurs at frequencies too low to be accessible with standard techniques.

Short- and long-range correlated motion observed in colloidal glasses and liquids - Weeks, Eric R.; Crocker, John C.; Weitz, D. A. (Journal of Physics-Condensed Matter, 2007)
We use a confocal microscope to examine the motion of individual particles in a dense colloidal suspension. Close to the glass transition, particle motion is strongly spatially correlated. The correlations decay exponentially with particle separation, yielding a dynamic length scale of O(2-3 sigma) (in terms of particle diameter sigma). This length scale grows modestly as the glass transition is approached. Further, the correlated motion exhibits a strong spatial dependence on the pair correlation function g(r). Motion within glassy samples is weakly correlated, but with a larger spatial scale for this correlation.

Dripping, jetting, drops, and wetting: The magic of microfluidics - Utada, A.S.; Chu, L. Y.; Fernandez-Nieves, A.; Link, D.R.; C. Holtze; Weitz, D. A. (Mrs Bulletin, 2007)
The following article is based on the Symposium X presentation given by David A. Weitz (Harvard University) on April 11, 2007, at the Materials Research Society Spring Meeting in San Francisco. The article describes how simple microfluidic devices can be used to control fluid flow and produce a variety of new materials. Based on the concepts of coaxial flow and hydrodynamically focused flow, used alone or in various combinations, the devices can produce precisely controlled double emulsions (droplets within droplets) and even triple emulsions (double emulsions suspended in a third droplet). These structures, which can be created in a single microfluidic device, have various applications such as encapsulants for drugs, cosmetics, or food additives.

Dripping to jetting transitions in coflowing liquid streams - Utada, Andrew S.; Fernandez-Nieves, Alberto; Stone, Howard A.; Weitz, David A (Physical Review Letters, 2007)
A liquid forced through an orifice into an immiscible fluid ultimately breaks into drops due to surface tension. Drop formation can occur right at the orifice in a dripping process. Alternatively, the inner fluid can form a jet, which breaks into drops further downstream. The transition from dripping to jetting is not understood for coflowing fluid streams, unlike the case of drop formation in air. We show that in a coflowing stream this transition can be characterized by a state diagram that depends on the capillary number of the outer fluid and the Weber number of the inner fluid.

Velocity fluctuations of initially stratified sedimenting spheres - Tee, Shang-You; Mucha, P. J.; Brenner, M.P.; Weitz, D. A. (Physics of Fluids, 2007)
The study of velocity fluctuations in the sedimentation of spheres is complicated by the time evolution of the underlying particle distribution, both at the microscale and in the bulk. We perform a series of experiments and simulations to isolate the effect of an initial, stable stratification in the particle concentration. The directly observed dependence of velocity fluctuations on stratification agrees with a previously obtained scaling theory. (c) 2007 American Institute of Physics.

A Stochastic Model of Glioblastoma Invasion - Stein, Andrew M.; Vader, David A.; Sander, Leonard M.; Weitz, David A (Mathematical Modeling of Biological Systems, Vol I: Cellular Biophysics, Regulatory Networks, Development, Biomedicine, and Data Analysis, 2007)
Glioblastoma is the most malignant form of brain cancer. It is extremely invasive; the mechanisms that govern invasion are not well understood. To better understand the process of invasion, we conducted an in vitro experiment in which a 3D tumor spheroid is implanted into a collagen gel. The paths of individual invasive cells were tracked. These cells were modeled as radially biased, persistent random walkers. The radial velocity bias was found to be 19.6 mu m/hr.

Mixing characterization inside microdroplets engineered on a microcoalescer - Sarrazin, F.; Prat, L.; Di Miceli, N.; Cristobal, G.; Link, D.R.; Weitz, D. A. (Chemical Engineering Science, 2007)
We use a microdevice where microdroplets of reagents are generated and coalesce in a carrier continuous phase. The work focuses on the characterization of the mixing step inside the droplets, in the perspective to use them for chemical kinetic data acquisition. A dye and water are used, and an acid-base instantaneous chemical reaction is monitored thanks to a colored indicator. Acquisitions are done with a high-speed camera coupled to a microscope and a mixing parameter is calculated by image analysis. Different angles of bended channels and different ways of coalescence are compared. It is shown that the homogenization of the droplets can be reached in less than lOms after coalescence. This is achieved by forcing the droplets to coalesce in a "shifted" way, and later by adding 45 degrees angle bends along the channel. (c) 2006 Elsevier Ltd. All rights reserved.

Structural rearrangements that govern flow in colloidal glasses - Schall, Peter; Weitz, David A; Spaepen, Frans (Science, 2007)
Structural rearrangements are an essential property of atomic and molecular glasses; they are critical in controlling resistance to flow and are central to the evolution of many properties of glasses, such as their heat capacity and dielectric constant. Despite their importance, these rearrangements cannot directly be visualized in atomic glasses. We used a colloidal glass to obtain direct three- dimensional images of thermally induced structural rearrangements in the presence of an applied shear. We identified localized irreversible shear transformation zones and determined their formation energy and topology. A transformation favored successive ones in its vicinity. Using continuum models, we elucidated the interplay between applied strain and thermal fluctuations that governs the formation of these zones in both colloidal and molecular glasses.

Target-locking acquisition with real-time confocal (TARC) microscopy - Lu, Peter J.; Sims, Peter A.; Oki, Hidekazu; Macarthur, James B.; Weitz, David A (Optics Express, 2007)
We present a real-time target-locking confocal microscope that follows an object moving along an arbitrary path, even as it simultaneously changes its shape, size and orientation. This Target-locking Acquisition with Realtime Confocal (TARC) microscopy system integrates fast image processing and rapid image acquisition using a Nipkow spinning-disk confocal microscope. The system acquires a 3D stack of images, performs a full structural analysis to locate a feature of interest, moves the sample in response, and then collects the next 3D image stack. In this way, data collection is dynamically adjusted to keep a moving object centered in the field of view. We demonstrate the system's capabilities by target-locking freely-diffusing clusters of attractive colloidal particles, and actively-transported quantum dots (QDs) endocytosed into live cells free to move in three dimensions, for several hours. During this time, both the colloidal clusters and live cells move distances several times the length of the imaging volume. (c) 2007 Optical Society of America

Visualizing the strain field in semiflexible polymer networks: Strain fluctuations and nonlinear rheology of F-actin gels - Liu, J.; Koenderink, G. H.; Kasza, K. E.; MacKintosh, F. C.; Weitz, D. A. (Physical Review Letters, 2007)
We image semiflexible polymer networks under shear at the micrometer scale. By tracking embedded probe particles, we determine the local strain field, and directly measure its uniformity, or degree of affineness, on scales of 2-100 mu m. The degree of nonaffine strain depends upon the polymer length and cross-link density, consistent with theoretical predictions. We also find a direct correspondence between the uniformity of the microscale strain and the nonlinear elasticity of the networks in the bulk.

Viscoelastic properties of microtubule networks - Lin, Yi-Chia; Koenderink, Gijsje H; MacKintosh, Frederick C; Weitz, David A (Macromolecules, 2007)
Micrombules are filamentous protein biopolymers found in eukaryotic cells. They form networks that guide active intracellular transport and support the overall cell structure. Microtubules are very rigid polymers, with persistence lengths as large as a millimeter. As such, they constitute an example of rodlike polymers, whose mechanical and theological properties are as yet poorly understood. We measure the linear and nonlinear viscoelastic properties of isotropic solutions of purified microtubules, as well as networks permanently cross-linked with biotin-NeutrAvidin. In the linear regime both solutions and networks are soft elastic materials with elastic moduli on the order of a few pascals. The elastic moduli show a power-law dependence on tubulin concentration, c(T), with G' similar to c(T)(nu), where v approximate to 1.4 for solutions and increases slightly to nu approximate to 1.6-1.8 for networks. At large deformations, we observe a concentration-dependent yield stress. The rheology of microtubule solutions cannot be explained by the Doi-Edwards model, which treats noninteracting rigid rods. Instead, they show behavior very similar to the permanently cross-linked networks, suggesting the presence of effective cross-linking even in pure microtubule solutions. We develop a simple model based on transient cross-linking interactions between microtubules to interpret the rheological response. We also calculate a lower bound estimate of the strength of this interaction. Our data provide a framework with which to understand the dynamics and mechanics of more physiological networks of microtubules with microtubule-associated cross-linking and motor proteins, and ultimately to understand the role of microtubules in cell mechanics.

A new microrheometric approach reveals individual and cooperative roles for TGF-beta 1 and IL-1 beta in fibroblast-mediated stiffening of collagen gels - Leung, Lester Y.; Tian, David; Brangwynne, Clifford P; Weitz, David A; Tschumperlin, Daniel J. (Faseb Journal, 2007)
The stiffness of the extracellular matrix can profoundly influence cell and tissue behaviors. Thus there is an emerging emphasis on understanding how matrix mechanical environments are established, regulated, and modified. Here we develop a microrheometric assay to measure the mechanical properties of a model extracellular matrix (type I collagen gel) and use it to explore cytokine-induced, cell-mediated changes in matrix mechanical properties. The microrheometric assay uses micron-scale ferrimagnetic beads embedded within collagen gels during fibrillogenesis. The beads are magnetized, then subjected to a twisting field, with the aggregate rotation of the beads measured by a magnetometer. The degree of bead rotation reflects the stiffness of the surrounding matrix. We show that the microscale assay provides stiffness measures for collagen gels comparable to those obtained with standard macroscale rheometry. To demonstrate the utility of the assay for biological discovery, we measure stiffness changes in fibroblast-populated collagen gels exposed to three concentrations of six cytokines over 2 to 14 days. Among the cytokines tested, transforming growth factor-beta 1 and interleukin-1 beta enhanced matrix stiffness, and together exerted cooperative effects on cellular modulation of matrix mechanics. The microrheometry approach developed here should accelerate the discovery of biological pathways orchestrating cellular modulation of matrix mechanics.

Colloidal assembly route for responsive colloidosomes with tunable permeability - Kim, Jin-Woong; Fernandez-Nieves, Alberto; Dan, Nily; Utada, Andrew S.; Marquez, Manuel; Weitz, David A (Nano Letters, 2007)
We present a robust and straightforward approach for fabricating a novel colloiclosome system where colloidal particles are assembled to form colloidal shells on the surface of stimuli-responsive microgel scaffolds. We demonstrate that the structural properties of the colloidal shells can be controlled through the colloidal particle size and modulus, and the state of supporting microgel particles. This technique offers a new way to engineer colloidosomes, enabling fine control over their permeability over a wide range of length scales.

Controlled production of emulsion drops using an electric field in a flow-focusing microfluidic device - Kim, Haejune; Luo, Dawei; Link, Darren; Weitz, David A; Marquez, Manuel; Cheng, Zhengdong (Applied Physics Letters, 2007)
We describe a flexible emulsification method using an electric field to generate droplets in a hydrodynamic-flow-focusing geometry in microchannels. The droplet size is controlled by the ratio of inner and outer flow rates as well as by the electric field. As the voltage increases, the droplet size decreases. A Taylor cone is formed and generates very fine droplets, less than 1 mu m in diameter. Small inner flow rates and high electric fields are required to form a stable Taylor cone in a dc electric field. An ac electric field produces tiny droplets periodically. (C) 2007 American Institute of Physics.

Fabrication of monodisperse gel shells and functional microgels in microfluidic devices - Kim, Jin-Woong; Utada, Andrew S.; Fernandez-Nieves, Alberto; Hu, Zhibing; Weitz, David A (Angewandte Chemie-International Edition, 2007)
Microgel structures such as spherical microgel shells (picture on the upper left) and spherical microgel particles that incorporate quantum dots, magnetic nanoparticles, and polymer microparticles (other images) have been prepared by a capillary microfluidic technique. Because these particles change their volume with changes in temperature, they may find application in, for example, drug delivery.

Gravitational stability of suspensions of attractive colloidal particles - Kim, Chanjoong; Liu, Yaqian; Kuehnle, Angelika; Hess, Stephan; Viereck, Sonja; Danner, Thomas; Mahadevan, L; Weitz, David A (Physical Review Letters, 2007)
Colloidal suspensions are susceptible to gravitationally induced phase separation. This can be mitigated by the formation of a particle network caused by depletion attraction. The effectiveness of this network in supporting the buoyant weight of the suspension can be characterized by its compressional modulus. We measure the compressional modulus for emulsion networks induced by depletion attraction and present a model that quantitatively predicts their gravitational stability. We also determine the relationship between the strength of the depletion attraction and the magnitude of the compressional modulus.

Uniform nonspherical colloidal particles with tunable shapes - Kim, Jin-Woong; Larsen, RyanJ.; Weitz, David A (Advanced Materials, 2007)
A framework for large-scale synthesis of a variety of uniform nonspherical particle types (see figure) is introduced. The technique involves controlling the directionality of phase separations in the seeded-polymerization technique by manipulating the crosslinking density gradients of the dimer seed particles, thus allowing the obtainment of novel nonspherical particle shapes and the production of sufficient quantities to characterize their bulk properties.

The cell as a material - Kasza, Karen E.; Rowat, Amy C.; Liu, Jiayu; Angelini, Thomas E.; Brangwynne, Clifford P; Koenderink, Gijsje H; Weitz, David A (Current Opinion in Cell Biology, 2007)
To elucidate the dynamic and functional role of a cell within the tissue it belongs to, it is essential to understand its material properties. The cell is a viscoelastic material with highly unusual properties. Measurements of the mechanical behavior of cells are beginning to probe the contribution of constituent components to cell mechanics. Reconstituted cytoskeletal protein networks have been shown to mimic many aspects of the mechanical properties of cells, providing new insight into the origin of cellular behavior. These networks are highly nonlinear, with an elastic modulus that depends sensitively on applied stress. Theories can account for some of the measured properties, but a complete model remains elusive.

Novel defect structures in nematic liquid crystal shells - Fernandez-Nieves, A.; Vitelli, V.; Utada, A.S.; Link, D.R.; Marquez, M.; Nelson, D.R.; Weitz, D. A. (Physical Review Letters, 2007)
We use double-emulsion drops to experimentally investigate the defect structures of spherical shells of nematic liquid crystals. We uncover a rich scenario of coexisting defect structures dictated by the unavoidable finite thickness of even the thinnest shell and by the thickness variation around the sphere. These structures are characterized by a varying number of disclination lines and pairs of surface point defects on the inner and outer surfaces of the nematic shell. In the limit of very thick shells the defect structure ultimately merges with that of a bulk nematic liquid crystal drop.

Topological changes in bipolar nematic droplets under flow - Fernandez-Nieves, A.; Link, D.R.; Marquez, M.; Weitz, D. A. (Physical Review Letters, 2007)
Bipolar liquid crystal drops moving inside microchannels exhibit periodic director field transformations due to induced circulating flows inside them. These modifications are characterized by changes in the type of point surface disclinations; they periodically change from splay to bend disclinations, implying the drop changes between bipolar and escaped concentric configurations. Upon stopping the flow, this structure does not relax to the lower energy bipolar configuration; we argue this is due to drop flattening inside the channels.

Controllable monodisperse multiple emulsions - Chu, Liang-Yin; Utada, Andrew S.; Shah, Rhutesh K.; Kim, Jin-Woong; Weitz, David A (Angewandte Chemie-International Edition, 2007)
A drop within a drop within a drop: A microfluidic technique is used to generate highly controlled multiple emulsions (see picture). The high degree of control and scalability afforded by this method makes it a flexible and promising route for engineering designer emulsions and microcapsules with multiphase structures. Moreover, its generality will enable fabrication of novel materials containing complex internal structures.

Monodisperse thermoresponsive microgels with tunable volume-phase transition kinetics - Chu, Liang-Yin; Kim, Jin-Woong; Shah, Rhutesh K.; Weitz, David A (Advanced Functional Materials, 2007)
A facile method to control the volume-phase transition kinetics of thermo-sensitive poly(N-isopropylacrylamide) (PNIPAM) microgels is presented. Monodisperse PNIPAM microgels with spherical voids are prepared using a microfluidic device. The swelling and shrinking responses of these microgels with spherical voids to changes in temperature are compared with those of voidless microgels of the same size and chemical composition prepared using the same microfluidic device. It is shown that the PNIPAM microgels with voids respond faster to changes in temperature as compared with their voidless counterparts. Also, the induced void structure does not have a detrimental effect on the equilibrium volume change of the microgels. Thus, the volume phase transition kinetics of the microgels can be finely tuned by controlling the number and size of the voids. The flexibility, control, and simplicity in fabrication rendered by this approach make these microgels appealing for applications that range from drug delivery systems and chemical separations to chemical/biosensing and actuators.

Force fluctuations and polymerization dynamics of intracellular microtubules - Brangwynne, Clifford P; MacKintosh, F. C.; Weitz, David A (Proceedings of the National Academy of Sciences of the United States of America, 2007)
Microtubules are highly dynamic biopolymer filaments involved in a wide variety of biological processes including cell division, migration, and intracellular transport. Microtubules are very rigid and form a stiff structural scaffold that resists deformation. However, despite their rigidity, inside of cells they typically exhibit significant bends on all length scales. Here, we investigate the origin of these bends using a Fourier analysis approach to quantify their length and time dependence. We show that, in cultured animal cells, bending is suppressed by the surrounding elastic cytoskeleton, and even large intracellular forces only cause significant bending fluctuations on short length scales. However, these lateral bending fluctuations also naturally cause fluctuations in the orientation of the microtubule tip. During growth, these tip fluctuations lead to microtubule bends that are frozen-in by the surrounding elastic network. This results in a persistent random walk of the microtubule, with a small apparent persistence length of approximate to 30 mu m, approximate to 100 times smaller than that resulting from thermal fluctuations alone. Thus, large nonthermal forces govern the growth of microtubules and can explain the highly curved shapes observed in the microtubule cytoskeleton of living cells.

Rheology and microrheology of a microstructured fluid: The gellan gum case - Caggioni, M.; Spicer, P. T.; Blair, D. L.; Lindberg, S. E.; Weitz, D. A. (Journal of Rheology, 2007)
Particle tracking microrheology is used to study the effect of a constant applied shear during gelation of aqueous gellan gum with a monovalent salt. Shear modifies the gellan gum hydrogel microstructure and the bulk rheological properties of the system, depending on whether shear is applied during gelation or afterwards. The microstructure determines the linear elastic response of the gel, as well as the critical strain and stress above which the response becomes nonlinear. Bulk oscillatory rheology is used to study microstructured gellan gum hydrogels at different polymer and salt concentrations. The similarity between our system and concentrated microgel particle suspensions can be explained by considering the microstructured gellan system to be composed of microgel particles whose size is set by the applied shear stress magnitude during gelation. Polymer concentration and ionic strength control the individual microgel particles' elastic properties. We also find the gellan system exhibits an isoenergetic transition from the jammed to un-jammed state when sheared, similar to jammed colloidal systems [C. G. Robertson and X. R. Wang], "Isoenergetic jamming transition in particle-filled systems''.

Bending dynamics of fluctuating biopolymers probed by automated high-resolution filament tracking - Brangwynne, Clifford P; Koenderink, Gijsje H; Barry, Ed; Dogic, Zvonimir; MacKintosh, Frederick C; Weitz, David A (Biophysical Journal, 2007)
Microscope images of. uctuating biopolymers contain a wealth of information about their underlying mechanics and dynamics. However, successful extraction of this information requires precise localization of. lament position and shape from thousands of noisy images. Here, we present careful measurements of the bending dynamics of filamentous ( F-) actin and microtubules at thermal equilibrium with high spatial and temporal resolution using a new, simple but robust, automated image analysis algorithm with subpixel accuracy. We. nd that slender actin. laments have a persistence length of similar to 17 mu m, and display a q(-4) -dependent relaxation spectrum, as expected from viscous drag. Microtubules have a persistence length of several millimeters; interestingly, there is a small correlation between total microtubule length and rigidity, with shorter filaments appearing softer. However, we show that this correlation can arise, in principle, from intrinsic measurement noise that must be carefully considered. The dynamic behavior of the bending of microtubules also appears more complex than that of F-actin, reflecting their higher-order structure. These results emphasize both the power and limitations of light microscopy techniques for studying the mechanics and dynamics of biopolymers.

Spinodal decomposition in a model colloid-polymer mixture in microgravity - Bailey, A. E.; W.C.K. Poon; Christianson, R. J.; Schofield, A. B.; Gasser, U.; Prasad, V.; S. Manley; Segre, P. N.; Cipelletti, L.; Meyer, W. V.; Doherty, M. P.; Sankaran, S.; et al. (Physical Review Letters, 2007)
We study phase separation in a deeply quenched colloid-polymer mixture in microgravity on the International Space Station using small-angle light scattering and direct imaging. We observe a clear crossover from early-stage spinodal decomposition to late-stage, interfacial-tension-driven coarsening. Data acquired over 5 orders of magnitude in time show more than 3 orders of magnitude increase in domain size, following nearly the same evolution as that in binary liquid mixtures. The late-stage growth approaches the expected linear growth rate quite slowly.

Optical manipulation and rotation of liquid crystal drops using high-index fiber-optic tweezers - Abedin, Kazi Sarwar; Kerbage, Charles; Fernandez-Nieves, Alberto; Weitz, David A (Applied Physics Letters, 2007)
We report an optical fiber tweezer based on high-index material for trapping and optical manipulation of microscale particles in water. The use of a high-index material increases the trapping force with respect to the more common silica, through tighter focusing of light. We demonstrate the potential of this simple and versatile device by trapping and rotating nematic liquid crystal drops. We monitor the rotation of the drop by detecting light modulation observed with the same fiber using backscattered light, which exhibits modulation in intensity due to the rotation of the drop; this further extends the capabilities of the fiber tweezers. (c) 2007 American Institute of Physics.

Mechanism for clogging of microchannels - Wyss, Hans M.; Blair, Daniel L.; Morris, Jeffrey F.; Stone, Howard A.; Weitz, David A (Physical Review E, 2006)
We investigate clogging of microchannels at the single-pore level using microfluidic devices as model porous media. The process of clogging is studied at low volume fractions and high flow rates, a technologically important regime. We show that clogging is independent of particle flow rate and volume fraction, indicating that collective effects do not play an important role. Instead, the average number of particles that can pass through a pore before it clogs scales with the ratio of pore to particle size. We present a simple model that accounts for the data.

Buckling and crumpling of drying droplets of colloid-polymer suspensions - Sugiyama, Yoichi; Larsen, RyanJ.; Kim, Jin-Woong; Weitz, David A (Langmuir, 2006)
Spray drying of complex liquids to form solid powders is important in many industrial applications. One of the challenges associated with spray drying is controlling the morphologies of the powders produced; this requires an understanding of how drying mechanics depend on the ingredients and conditions. We demonstrate that the morphology of powders produced by spray drying colloidal polystyrene (PS) suspensions can be significantly altered by changing the molecular weight of dissolved poly(ethylene oxide) (PEO). Samples containing high-molecular-weight PEO produce powders with more crumpled morphologies than those containing low-molecular-weight PEO. Observations of drying droplets suspended by a thin film of vapor suggest that this occurs because the samples with high-molecular-weight PEO buckle earlier in the drying process when the droplets are larger. Earlier buckling times are likely caused by the decreased stability, demonstrated by bulk rheology experiments, of PS particles in the presence of high-molecular-weight PEO at elevated temperatures. We present a consistent picture in which decreased particle stability hastens droplet buckling and leads to more crumpled powder morphologies; this underscores the importance of interparticle forces in determining the buckling of particle-laden droplets.

Microfluidic assembly of homogeneous and janus colloid-filled hydrogel granules - Robert F. Shepherd; Conrad, Jacinta C.; Rhodes, Summer K.; Link, Darren R.; Marquez, Manuel; Weitz, David A; Jennifer A. Lewis (Langmuir, 2006)
The microfluidic assembly of colloid-filled hydrogel granules of varying shape and composition is described. First, drops are formed by shearing a concentrated colloidal microsphere-acrylamide suspension in a continuous oil phase using a sheath-flow device. Both homogeneous and Janus (hemispherically distinct) spheres and disks are produced by confining the assembled drops in microchannels of varying geometry. Next, photopolymerization is carried out shortly after drop breakup to preserve their morphology. Representative wet and dried granules are characterized using fluorescence and scanning electron microscopy, respectively. Our approach offers a facile route for assembling colloid-filled hydrogel granules with controlled shape and composition.

Visualizing dislocation nucleation by indenting colloidal crystals - Schall, P.; Cohen, I.; Weitz, D. A.; F. Spaepen (Nature, 2006)
The formation of dislocations is central to our understanding of yield, work hardening, fracture, and fatigue(1) of crystalline materials. While dislocations have been studied extensively in conventional materials, recent results have shown that colloidal crystals offer a potential model system for visualizing their structure and dynamics directly in real space(2). Although thermal fluctuations are thought to play a critical role in the nucleation of these defects, it is difficult to observe them directly. Nano-indentation, during which a small tip deforms a crystalline film, is a common tool for introducing dislocations into a small volume that is initially defect-free(3-10). Here, we show that an analogue of nano- indentation performed on a colloidal crystal provides direct images of defect formation in real time and on the single particle level, allowing us to probe the effects of thermal fluctuations. We implement a new method to determine the strain tensor of a distorted crystal lattice and we measure the critical dislocation loop size and the rate of dislocation nucleation directly. Using continuum models, we elucidate the relation between thermal fluctuations and the applied strain that governs defect nucleation. Moreover, we estimate that although bond energies between particles are about fifty times larger in atomic systems, the difference in attempt frequencies makes the effects of thermal fluctuations remarkably similar, so that our results are also relevant for atomic crystals.

Nonlinear viscoelasticity of metastable complex fluids - Miyazaki, K.; Wyss, H. M.; Weitz, D. A.; D. R. Reichman (Europhysics Letters, 2006)
Many metastable complex fluids such as colloidal glasses and gels show distinct nonlinear viscoelasticity with increasing oscillatory-strain amplitude; the storage modulus decreases monotonically as the strain amplitude increases whereas the loss modulus has a distinct peak before it decreases at larger strains. We present a qualitative argument to explain this ubiquitous behavior and use mode-coupling theory (MCT) to confirm it. We compare theoretical predictions to the measured nonlinear viscoelasticity in a dense hard-sphere colloidal suspension; reasonable agreement is obtained. The argument given here can be used to obtain new information about linear viscoelasticity of metastable complex fluids from nonlinear strain measurements.

Fluids of clusters in attractive colloids - Lu, P. J.; Conrad, J. C.; Wyss, H. M.; Schofield, A. B.; Weitz, D. A. (Physical Review Letters, 2006)
We show that colloidal particles with attractive interactions induced by a nonadsorbing polymer exhibit a stable phase consisting of a fluid of clusters of particles. This phase persists even in the absence of any long-range repulsion due to charge, contrary to expectations based on simulation and theory. Cluster morphology depends strongly on the range of the interparticle attraction: With a shorter range, clusters are tenuous and branched; with a longer range, they are more compact.

Electric control of droplets in microfluidic devices - Link, D.R.; Grasland-Mongrain, E.; Duri, A.; Sarrazin, F.; Cheng, Z. D.; Cristobal, G.; Marquez, M.; Weitz, D. A. (Angewandte Chemie-International Edition, 2006)
Streamlining microreactors: Electric fields enable the precise manipulation of microreactors in microfluidic channels. One of the key features of such reactors is the ability to combine different chemicals at a precise location to initiate a chemical reaction.

Microrheology probes length scale dependent rheology - Liu, J.; Gardel, M. L.; Kroy, K.; Frey, E.; Hoffman, B. D.; Crocker, J. C.; A. R. Bausch; Weitz, D. A. (Physical Review Letters, 2006)
We exploit the power of microrheology to measure the viscoelasticity of entangled F-actin solutions at different length scales from 1 to 100 mu m over a wide frequency range. We compare the behavior of single probe-particle motion to that of the correlated motion of two particles. By varying the average length of the filaments, we identify fluctuations that dissipate diffusively over the filament length. These provide an important relaxation mechanism of the elasticity between 0.1 and 30 rad/sec.

Synthesis of nonspherical colloidal particles with anisotropic properties - Kim, Jin-Woong; Larsen, RyanJ.; Weitz, David A (Journal of the American Chemical Society, 2006)
We describe a promising and flexible technique for fabricating uniform nonspherical particles with anisotropic phase and surface properties. Our approach is based on the seeded polymerization technique in which monomer-swollen particles are polymerized. The polymerization causes a phase separation to occur, giving rise to two-phase nonspherical particles. We show that the elastic contraction of the swollen polymer particles induced by elevated polymerization temperatures plays an important role in the phase separation. Moreover, chemical anisotropy of nonspherical particles can be obtained by using immiscible polymer pairs and by employing surface treatments. Furthermore, we are able to produce amphiphilic dumbbell particles consisting of two different bulbs: hydrophilic poly (ethylene imine)-coated polystyrene and hydrophobic polystyrene. Controlled geometries of these amphiphilic nonspherical particles will allow a wide range of potential applications, such as engineered colloid surfactants.

Direct imaging of repulsive and attractive colloidal glasses - Laura J. Kaufman; Weitz, David A (Journal of Chemical Physics, 2006)
Coherent anti-Stokes Raman scattering microscopy is performed on glassy systems of poly(methylmethacrylate) colloidal particles in density- and refractive-index-matched solvents. Samples are prepared with varying amounts of linear polystyrene, which induces a depletion driven attraction between the nearly hard-sphere particles. Images collected over several hours confirm the existence of a reentrant glass transition. The images also reveal that the dynamics of repulsive and attractive glasses are qualitatively different. Colloidal particles in repulsive glasses exhibit cage rattling and escape, while those in attractive glasses are nearly static while caged but exhibit large displacements upon (infrequent) cage escape. (c) 2006 American Institute of Physics.

Dewetting instability during the formation of polymersomes from block-copolymer-stabilized double emulsions - Hayward, R. C.; Utada, A.S.; Dan, N.; Weitz, D. A. (Langmuir, 2006)
We investigate the formation of polymer vesicles, or polymersomes, of polystyrene-block-poly(ethylene oxide) diblock copolymers using double emulsion droplets of controlled architecture as templates. To engineer the structure of the polymersomes, it is important to consider the concentration of diblock copolymer in the middle phase of the double emulsion. We describe how the presence of excess polymer can induce a transition from complete wetting to partial wetting of the middle phase, resulting in polymer shells with inhomogeneous thicknesses.

Irreversible shear-activated aggregation in non-Brownian suspensions - Guery, J.; Bertrand, E.; Rouzeau, C.; Levitz, P.; Weitz, D. A.; Bibette, J. (Physical Review Letters, 2006)
We have studied the effect of shear on the stability of suspensions made of non-Brownian solid particles. We demonstrate the existence of an irreversible transition where the solid particles aggregate at remarkably low volume fractions (phi approximate to 0.1). This shear-induced aggregation is dramatic and exhibits a very sudden change in the viscosity, which increases sharply after a shear-dependent induction time. We show that this induction time is related exponentially to the shear rate, reflecting the importance of the hydrodynamic forces in reducing the repulsive energy barrier that prevents the particles from aggregating.

Prestressed F-actin networks cross-linked by hinged filamins replicate mechanical properties of cells - Gardel, M. L.; Nakamura, F.; Hartwig, J. H.; Crocker, J. C.; Stossel, T. P.; Weitz, D. A. (PNAS, 2006)
We show that actin filaments, shortened to physiological lengths by gelsolin and cross-linked with recombinant human filamins (FLNs), exhibit dynamic elastic properties similar to those reported for live cells. To achieve elasticity values of comparable magnitude to those of cells, the in vitro network must be subjected to external prestress, which directly controls network elasticity. A molecular requirement for the strain-related behavior at physiological conditions is a flexible hinge found in FLNa and some FLNb molecules. Basic physical properties of the in vitro filamin-F-actin network replicate the essential mechanical properties of living cells. This physical behavior could accommodate passive deformation and internal organelle trafficking at low strains yet resist externally or internally generated high shear forces.

Stress-dependent elasticity of composite actin networks as a model for cell behavior - Gardel, M. L.; Nakamura, F.; Hartwig, J.; Crocker, J. C.; Stossel, T. P.; Weitz, D. A. (Physical Review Letters, 2006)
Networks of filamentous actin cross-linked with the actin-binding protein filamin A exhibit remarkable strain stiffening leading to an increase in differential elastic modulus by several orders of magnitude over the linear value. The variation of the frequency dependence of the differential elastic and loss moduli as a function of prestress is consistent with that observed in living cells, suggesting that cell elasticity is always measured in the nonlinear regime, and that prestress is an essential control parameter.

Polarization dependent Bragg diffraction and electro-optic switching of three-dimensional assemblies of nematic liquid crystal droplets - Fernandez-Nieves, A.; Link, D.R.; Weitz, D. A. (Applied Physics Letters, 2006)
We report the fabrication of three-dimensional lattices of bipolar nematic liquid crystal droplets. The electro-optic properties of these materials consist of transitions between opaque, Bragg diffracting, and transparent states. These occur continuously at moderate electric (E) fields through bipolar axis rotation of the nematic droplets. An E field applied normal to the hexagonally close packed planes results in a Bragg diffraction pattern that is polarization independent. Application of in-plane fields allows switching between diffracting and transmitting states that depends on the polarization of the incident light.

Dynamics of fracture in drying suspensions - Dufresne, E. R.; Stark, D. J.; Greenblatt, N. A.; Cheng, J. X.; J.W. Hutchinson; Mahadevan, L; Weitz, D. A. (Langmuir, 2006)
We investigate the dynamics of fracture in drying films of colloidal silica. Water loss quenches the nanoparticle dispersions to form a liquid-saturated elastic network of particles that relieves drying-induced strain by cracking. These cracks display intriguing intermittent motion originating from the deformation of arrested crack tips and aging of the elastic network. The dynamics of a single crack exhibits a universal evolution, described by a balance of the driving elastic power with the sum of interfacial power and the viscous dissipation rate of flowing interstitial fluid.

Microscopic structure and elasticity of weakly aggregated colloidal gels - A. D. Dinsmore; Prasad, V.; Wong, I. Y.; Weitz, D. A. (Physical Review Letters, 2006)
We directly probe the microscopic structure, connectivity, and elasticity of colloidal gels using confocal microscopy. We show that the gel is a random network of one-dimensional chains of particles. By measuring thermal fluctuations, we determine the effective spring constant between pairs of particles as a function of separation; this is in agreement with the theory for fractal chains. Long-range attractions between particles lead to freely rotating bonds, and the gel is stabilized by multiple connections among the chains. By contrast, short-range attractions lead to bonds that resist bending, with dramatically suppressed formation of loops of particles.

Fast and slow dynamics of the cytoskeleton - Deng, Linhong; Trepat, Xavier; James P. Butler; Millet, Emil; Morgan, Kathleen G.; Weitz, David A; Jeffrey J. Fredberg (Nature Materials, 2006)
Material moduli of the cytoskeleton (CSK) influence a wide range of cell functions(1-3). There is substantial evidence from reconstituted F-actin gels that a regime exists in which the moduli scale with frequency with a universal exponent of 3/4. Such behaviour is entropic in origin and is attributable to fluctuations in semi flexible polymers driven by thermal forces(4-7), but it is not obvious a priori that such entropic effects are responsible for the elasticity of the CSK. Here we demonstrate the existence of such a regime in the living cell, but only at high frequencies. Fast events scaled with frequency in a manner comparable to semi flexible-polymer dynamics, but slow events scaled with a non-universal exponent that was systematically smaller than 3/4 and probably more consistent with a soft-glass regime(8,9). These findings strongly suggest that at smaller timescales elasticity arises from entropic fluctuations of a semi flexible-filament network, whereas on longer timescales slow (soft-glass-like) dynamics of a different origin prevail. The transition between these two regimes occurred on timescales of the order of 0.01 s, thus setting within the slow glassy regime cellular events such as spreading, crawling, contracting, and invading.

Contribution of slow clusters to the bulk elasticity near the colloidal glass transition - Conrad, Jacinta C.; Dhillon, Param P.; Weeks, Eric R.; Reichman, David R.; Weitz, David A (Physical Review Letters, 2006)
We use confocal microscopy to visualize individual particles near the colloidal glass transition. We identify the most slowly-relaxing particles and show that they form spatially correlated clusters that percolate across the sample. In supercooled fluids, the largest cluster spans the system on short time scales but breaks up on longer time scales. In contrast, in glasses, a percolating cluster exists on all accessible time scales. Using molecular dynamics simulation, we show that these clusters make the dominant contribution to the bulk elasticity of the sample.

Slip, yield, and bands in colloidal crystals under oscillatory shear - Cohen, Itai; Davidovitch, Benny; Schofield, Andrew B.; Michael P. Brenner; Weitz, David A (Physical Review Letters, 2006)
We study dense colloidal crystals under oscillatory shear using a confocal microscope. At large strains the crystals yield and the suspensions form shear bands. The pure harmonic response exhibited by the suspension rules out the applicability of nonlinear rheology models typically used to describe shear banding in other types of complex fluids. Instead, we show that a model based on the coexistence of linearly responding phases of the colloidal suspension accounts for the observed flows. These results highlight a new use of oscillatory measurements in distinguishing the contribution of linear and nonlinear local rheology to a globally nonlinear material response.

Microtubules can bear enhanced compressive loads in living cells because of lateral reinforcement - Brangwynne, C. P.; MacKintosh, F. C.; Kumar, S.; Geisse, N. A.; Talbot, J.; Mahadevan, L; Parker, K. K.; Ingber, D. E.; Weitz, D. A. (Journal of Cell Biology, 2006)
Cytoskeletal microtubules have been proposed to influence cell shape and mechanics based on their ability to resist large-scale compressive forces exerted by the surrounding contractile cytoskeleton. Consistent with this, cytoplasmic microtubules are often highly curved and appear buckled because of compressive loads. However, the results of in vitro studies suggest that microtubules should buckle at much larger length scales, withstanding only exceedingly small compressive forces. This discrepancy calls into question the structural role of microtubules, and highlights our lack of quantitative knowledge of the magnitude of the forces they experience and can withstand in living cells. We show that intracellular microtubules do bear large-scale compressive loads from a variety of physiological forces, but their buckling wavelength is reduced significantly because of mechanical coupling to the surrounding elastic cytoskeleton. We quantitatively explain this behavior, and show that this coupling dramatically increases the compressive forces that microtubules can sustain, suggesting they can make a more significant structural contribution to the mechanical behavior of the cell than previously thought possible.

Dielectrophoretic manipulation of drops for high-speed microfluidic sorting devices - Ahn, K.; Kerbage, C.; Hunt, T. P.; R. M. Westervelt; Link, D.R.; Weitz, D. A. (Applied Physics Letters, 2006)
We demonstrate a high-throughput drop sorter for microfluidic devices that uses dielectrophoretic forces. Microelectrodes underneath a polydimethylsiloxane channel produce forces of more than 10 nN on a water drop in an inert oil, resulting in sorting rates greater than 1.6 kHz. We investigate the dependence of such forces on drop size and flow. Alternate designs with electrodes on either side of a symmetric channel Y junction provide refined control over droplet selection.

Electrocoalescence of drops synchronized by size-dependent flow in microfluidic channels - Ahn, K.; Agresti, J.; Chong, H.; Marquez, M.; Weitz, D. A. (Applied Physics Letters, 2006)
The use of microfluidic devices to control drops of water in a carrier oil is a promising means of performing biological and chemical assays. An essential requirement for this is the controlled coalescence of pairs of drops to mix reagents together. We show that this can be accomplished through electrocoalescence of drops synchronized by size-dependent flow in microfluidic channels. Smaller drops move faster due to the Poiseuille flow, allowing pairs of surfactant-stabilized drops to be brought into contact where they are coalesced with an electric field. We apply this method to an enzyme assay to measure enzyme kinetic constants.

Microrheology - Gardel, M. L.; Valentine, M. T.; Weitz, DavidA. (Microscale Diagnostic Techniques, 2005)

Effect of temperature on carbon-black agglomeration in hydrocarbon liquid with adsorbed dispersant - Won, Y. Y.; Meeker, S. P.; Trappe, V.; Weitz, D. A.; Diggs, N. Z.; Emert, J. I. (Langmuir, 2005)
Suspensions of carbon black in oil, stabilized with adsorbed polyisobutylene succinimide (PIBSI) dispersant, are commonly used as model systems for investigating the soot-handling characteristics of motor oils. The structure of the carbon-black agglomerates changes dramatically with temperature; this results in a concomitant change in the suspension rheology. Linear and nonlinear rheological experiments indicate a large increase of the interparticle attractions as the temperature is raised. To elucidate the origin of this behavior, we investigate the effect of temperature on the stabilizing effect of the dispersant. Measurements of adsorption isotherms of the dispersant on carbon black indicate that there is little variation of the binding energy with temperature. Intrinsic viscosity measurements of PIBSI dispersants in solution clearly exhibit an inverse dependence of the dispersant chain dimension with temperature. These results suggest that the temperature-dependent changes in the chain conformation of the PIBSI dispersant are primarily responsible for the changes in the dispersion rheology, and we propose a simple model to account for these data.

Mechanical properties of Xenopus egg cytoplasmic extracts - Valentine, M. T.; Perlman, Z. E.; Mitchison, T. J.; Weitz, D. A. (Biophysical Journal, 2005)
Cytoplasmic extracts prepared from Xenopus laevis eggs are used for the reconstitution of a wide range of processes in cell biology, and offer a unique environment in which to investigate the role of cytoplasmic mechanics without the complication of preorganized cellular structures. As a step toward understanding the mechanical properties of this system, we have characterized the rheology of crude interphase extracts. At macroscopic length scales, the extract forms a soft viscoelastic solid. Using a conventional mechanical rheometer, we measure the elastic modulus to be in the range of 2 - 10 Pa, and loss modulus in the range of 0.5 - 5 Pa. Using pharmacological and immunological disruption methods, we establish that actin. laments and microtubules cooperate to give mechanical strength, whereas the intermediate. lament cytokeratin does not contribute to viscoelasticity. At microscopic length scales smaller than the average network mesh size, the response is predominantly viscous. We use multiple particle tracking methods to measure the thermal fluctuations of 1 mum embedded tracer particles, and measure the viscosity to be similar to20 mPa-s. We explore the impact of rheology on actin-dependent cytoplasmic contraction, and find that although microtubules modulate contractile forces in vitro, their interactions are not purely mechanical.

Monodisperse double emulsions generated from a microcapillary device - Utada, A.S.; Lorenceau, E.; Link, D.R.; Kaplan, P. D.; H.A. Stone; Weitz, D. A. (Science, 2005)
Double emulsions are highly structured fluids consisting of emulsion drops that contain smaller droplets inside. Although double emulsions are potentially of commercial value, traditional fabrication by means of two emulsification steps leads to very ill-controlled structuring. Using a microcapillary device, we fabricated double emulsions that contained a single internal droplet in a coreshell geometry. We show that the droplet size can be quantitatively predicted from the flow profiles of the fluids. The double emulsions were used to generate encapsulation structures by manipulating the properties of the fluid that makes up the shell. The high degree of control afforded by this method and the completely separate fluid streams make this a flexible and promising technique.

Onset of buckling in drying droplets of colloidal suspensions - Tsapis, N.; Dufresne, E. R.; Sinha, S. S.; Riera, C. S.; J.W. Hutchinson; Mahadevan, L; Weitz, D. A. (Physical Review Letters, 2005)
Minute concentrations of suspended particles can dramatically alter the behavior of a drying droplet. After a period of isotropic shrinkage, similar to droplets of a pure liquid, these droplets suddenly buckle like an elastic shell. While linear elasticity is able to describe the morphology of the buckled droplets, it fails to predict the onset of buckling. Instead, we find that buckling is coincident with a stress-induced fluid to solid transition in a shell of particles at a droplet's surface, occurring when attractive capillary forces overcome stabilizing electrostatic forces between particles.

Glasslike arrest in spinodal decomposition as a route to colloidal gelation - S. Manley; Wyss, H. M.; Miyazaki, K.; Conrad, J. C.; Trappe, V.; Kaufman, L. J.; D. R. Reichman; Weitz, D. A. (Physical Review Letters, 2005)
Colloid-polymer mixtures can undergo spinodal decomposition into colloid-rich and colloid-poor regions. Gelation results when interconnected colloid-rich regions solidify. We show that this occurs when these regions undergo a glass transition, leading to dynamic arrest of the spinodal decomposition. The characteristic length scale of the gel decreases with increasing quench depth, and the nonergodicity parameter exhibits a pronounced dependence on scattering vector. Mode coupling theory gives a good description of the dynamics, provided we use the full static structure as input.

Gravitational collapse of colloidal gels - S. Manley; Skotheim, J. M.; Mahadevan, L; Weitz, D. A. (Physical Review Letters, 2005)
We present a unified framework for understanding the compaction of colloidal gels under their own weight. The dynamics of the collapse are determined by the value of the gravitational stress σ(g), as compared to the yield stress σ(Y) of the network. For σ(g)<σ(Y), gels collapse poroelastically, and their rate of compression decays exponentially in time. For σ(g)>σ(Y), the network eventually yields, leading to rapid settling. In both cases, the rate of collapse is backflow limited, while its overall magnitude is determined by a balance between gravitational stress and network elastic stress.

Time-dependent strength of colloidal gels - S. Manley; Davidovitch, B.; Davies, N. R.; Cipelletti, L.; Bailey, A. E.; Christianson, R. J.; Gasser, U.; Prasad, V.; Segre, P. N.; Doherty, M. P.; Sankaran, S.; Jankovsky, A. L.; et al. (Physical Review Letters, 2005)
Colloidal silica gels are shown to stiffen with time, as demonstrated by both dynamic light scattering and bulk rheological measurements. Their elastic moduli increase as a power law with time, independent of particle volume fraction; however, static light scattering indicates that there are no large-scale structural changes. We propose that increases in local elasticity arising from bonding between neighboring colloidal particles can account for the strengthening of the network, while preserving network structure.

Generation of polymerosomes from double-emulsions - Lorenceau, E.; Utada, A.S.; Link, D.R.; Cristobal, G.; Joanicot, M.; Weitz, D. A. (Langmuir, 2005)
Diblock copolymers are known to spontaneously organize into polymer vesicles. Typically, this is achieved through the techniques of film rehydration or electroformation. We present a new method for generating polymer vesicles from double emulsions. We generate precision water-in-oil-in-water double emulsions from the breakup of concentric fluid streams; the hydrophobic fluid is a volatile mixture of organic solvent that contains dissolved diblock copolymers. We collect the double emulsions and slowly evaporate the organic solvent, which ultimately directs the self-assembly of the dissolved diblock copolymers into vesicular structures. Independent control over all three fluid streams enables precision assembly of polymer vesicles and provides for highly efficient encapsulation of active ingredients within the polymerosomes. We also use double emulsions with several internal drops to form new polymerosome structures.

Glioma expansion in collagen I matrices: Analyzing collagen concentration-dependent growth and motility patterns - Kaufman, L. J.; Brangwynne, C. P.; Kasza, K. E.; Filippidi, E.; Gordon, V. D.; Deisboeck, T. S.; Weitz, D. A. (Biophysical Journal, 2005)
We study the growth and invasion of glioblastoma multiforme (GBM) in three-dimensional collagen I matrices of varying collagen concentration. Phase-contrast microscopy studies of the entire GBM system show that invasiveness at early times is limited by available collagen fibers. At early times, high collagen concentration correlates with more effective invasion. Conversely, high collagen concentration correlates with inhibition in the growth of the central portion of GBM, the multicellular tumor spheroid. Analysis of confocal reflectance images of the collagen matrices quantifies how the collagen matrices differ as a function of concentration. Studying invasion on the length scale of individual invading cells with a combination of confocal and coherent anti-Stokes Raman scattering microscopy reveals that the invasive GBM cells rely heavily on cell-matrix interactions during invasion and remodeling.

Charge stabilization in nonpolar solvents - M. F. Hsu; Dufresne, E. R.; Weitz, D. A. (Langmuir, 2005)
While the important role of electrostatic interactions in aqueous colloidal suspensions is widely known and reasonably well-understood, their relevance to nonpolar suspensions remains mysterious. We measure the interaction potentials of colloidal particles in a nonpolar solvent with reverse micelles. We find surprisingly strong electrostatic interactions characterized by surface potentials, vertical bar e zeta vertical bar, from 2.0 to 4.4 k(B)T and screening lengths, kappa(-1), from 0.2 to 1.4 mu m. Interactions depend on the concentration of reverse micelles and the degree of confinement. Furthermore, when the particles are weakly confined, the values of vertical bar e zeta vertical bar and kappa extracted from interaction measurements are consistent with bulk measurements of conductivity and electrophoretic mobility. A simple thermodynamic model, relating the structure of the micelles to the equilibrium ionic strength, is in good agreement with both conductivity and interaction measurements. Since dissociated ions are solubilized by reverse micelles, the entropic incentive to charge a particle surface is qualitatively changed from aqueous systems, and surface entropy plays an important role.

Self-assembled shells composed of colloidal particles: Fabrication and characterization - M. F. Hsu; M. G. Nikolaides; A. D. Dinsmore; A. R. Bausch; Gordon, V. D.; Chen, X.; J.W. Hutchinson; Weitz, D. A. (Langmuir, 2005)
We construct shells with tunable morphology and mechanical response with colloidal particles that self-assemble at the interface of emulsion droplets. Particles self-assemble to minimize the total interfacial energy, spontaneously forming a particle layer that encapsulates the droplets. We stabilize these layers to form solid shells at the droplet interface by aggregating the particles, connecting the particles with adsorbed polymer, or fusing the particles. These techniques reproducibly yield shells with controllable properties such as elastic moduli and breaking forces. To enable diffusive exchange through the particle shells, we transfer them into solvents that are miscible with the encapsulant. We characterize the mechanical properties of the shells by measuring the response to deformation by calibrated microcantilevers.

Tetrahedral calcite crystals facilitate self-assembly at the air-water interface - Hashmi, S. M.; Wickman, H. H.; Weitz, D. A. (Physical Review E, 2005)
Calcite crystals often nucleate and grow in solutions of calcium carbonate, and these crystallites can become trapped at the air water interface, where they form unusual structures. The most common is a fractal structure, which can extend over a large fraction of the interface, and whose origin is understood in terms of the aggregation of the particles. Much more rarely, a different and entirely unexpected structure is observed: the particles remain well separated on the interface, forming an ordered phase reminiscent of a two-dimensional colloidal crystal. The structure of the crystallites that form this ordered phase is always observed to be tetrahedral, in contrast to the much more common rhombohedral structure of the crystallites that form the fractal phase. We show that the interparticle interaction potential that leads to this ordered phase is a balance between a long-range attractive interaction and a long-range repulsive interaction. The attraction results from gravity-induced capillary forces, while the repulsion results from a dipole-dipole interaction due to the charged surface of the tetrahedral crystals. The interaction potential is estimated from the thermal motion of the particles, and fits to the theoretically expected values suggest that the effective surface charge on the tetrahedral crystals is sigma similar to 0.01 charges/nm(2).

Optically anisotropic colloids of controllable shape - Fernandez-Nieves, A.; Cristobal, G.; Garces-Chavez, V.; Spalding, G. C.; Dholakia, K.; Weitz, D. A. (Advanced Materials, 2005)
Solid spheres, disks, and ellipsoids with micrometer-scale bipolar anisotropic character respond to external electric fields by aligning their mean optical axes parallel to the field. The monodisperse, optically anisotropic colloids (see Figure) are synthesized by photopolymerization of a monodisperse liquid-crystal emulsion after mechanical deformation of the drops.

Microrheology of cross-linked polyacrylamide networks - Dasgupta, B. R.; Weitz, D. A. (Physical Review E, 2005)
Experiments investigating the local viscoelastic properties of a chemically cross-linked polymer are performed on polyacrylamide solutions in the sol and the gel regimes using polystyrene beads of varying sizes and surface chemistry as probes. The thermal motions of the probes are measured to obtain the elastic and viscous moduli of the sample. Probe dynamics are measured using two different dynamic light scattering techniques, diffusing wave spectroscopy (DWS) and quasielastic light scattering (QELS) as well as video-based particle tracking. Diffusing wave spectroscopy probes the short-time dynamics of the scatterers while QELS measures the dynamics at larger times. Video-based particle tracking provides a way to investigate the local environment of the individual probe particles. A combination of all the techniques results in a larger range of frequencies that can be probed compared to conventional bulk measurements while providing local information at the level of individual probes. A modified algebraic form of the generalized Stokes-Einstein equation is used to calculate the frequency-dependent moduli. A comparison of microrheological measurements with bulk rheology exhibits striking similarity, confirming the applicability of microrheology for chemically cross-linked polymeric systems.

Weak correlations between local density and dynamics near the glass transition - Conrad, J. C.; Starr, F. W.; Weitz, D. A. (Journal of Physical Chemistry B, 2005)
We perform experiments on two different dense colloidal suspensions with confocal microscopy to probe the relationship between local structure and dynamics near the glass transition. We calculate the Voronoi volume 19 for our particles and show that this quantity is not a universal probe of glassy structure for all colloidal suspensions. We correlate the Voronoi volume to displacement and find that these quantities are only weakly correlated. We observe qualitatively similar results in a simulation of a polymer melt. These results suggest that the Voronoi volume does not predict dynamical behavior in experimental colloidal suspensions; a purely 44 structural approach based on local single particle volume likely cannot describe the colloidal glass transition.

Cytoskeletal remodelling and slow dynamics in the living cell - Bursac, P.; Lenormand, G.; Fabry, B.; Oliver, M.; Weitz, D. A.; Viasnoff, V.; Butler, J. P.; Fredberg, J. J. (Nature Materials, 2005)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="190892" data-gtm-vis-first-on-screen-10482319_401="190892" data-gtm-vis-polling-id-10482319_393="37" data-gtm-vis-polling-id-10482319_401="38" data-gtm-vis-recent-on-screen-10482319_393="190892" data-gtm-vis-recent-on-screen-10482319_401="190892" data-gtm-vis-total-visible-time-10482319_393="5400" data-gtm-vis-total-visible-time-10482319_401="5400" data-title="Abstract" lang="en"> The cytoskeleton (CSK) is a crowded network of structural proteins that stabilizes cell shape and drives cell motions. Recent studies on the dynamics of the CSK have established that a wide variety of cell types exhibit rheology in which responses are not tied to any particular relaxation times and are thus scale-free<a aria-label="Reference 1" data-test="citation-ref" data-track="click" data-track-action="reference anchor" data-track-label="link" href="https://www.nature.com/articles/nmat1404#ref-CR1" id="ref-link-section-d3005e464" title="Alcaraz, J. et al. Microrheology of human lung epithelial cells measured by atomic force microscopy. Biophys. J. 84, 2071–2079 (2003).">1,<a aria-label="Reference 2" data-test="citation-ref" data-track="click" data-track-action="reference anchor" data-track-label="link" href="https://www.nature.com/articles/nmat1404#ref-CR2" id="ref-link-section-d3005e467" title="Fabry, B. et al. Scaling the microrheology of living cells. Phys. Rev. Lett. 87, 148102 (2001).">2,<a aria-label="Reference 3" data-test="citation-ref" data-track="click" data-track-action="reference anchor" data-track-label="link" href="https://www.nature.com/articles/nmat1404#ref-CR3" id="ref-link-section-d3005e470" title="Desprat, N., Richert, A., Simeon, J. & Asnacios, A. Creep function of a single living cell. Biophys. J. 88, 2224–2233 (2005).">3,<a aria-label="Reference 4" data-test="citation-ref" data-track="click" data-track-action="reference anchor" data-track-label="link" href="https://www.nature.com/articles/nmat1404#ref-CR4" id="ref-link-section-d3005e473" title="Lenormand, G., Millet, E., Fabry, B., Butler, J. & Fredberg, J. Linearity and time-scale invariance of the creep function in living cells. J. R. Soc. Interface 1, 91–97 (2004).">4. Scale-free rheology is often found in a class of materials called soft glasses<a aria-label="Reference 5" data-test="citation-ref" data-track="click" data-track-action="reference anchor" data-track-label="link" href="https://www.nature.com/articles/nmat1404#ref-CR5" id="ref-link-section-d3005e477" title="Sollich, P. Rheological constitutive equation for a model of soft glassy materials. Phys. Rev. E 58, 738–759 (1998).">5, but not all materials expressing scale-free rheology are glassy (see plastics, wood, concrete or some metals for example)<a aria-label="Reference 6" data-test="citation-ref" data-track="click" data-track-action="reference anchor" data-track-label="link" href="https://www.nature.com/articles/nmat1404#ref-CR6" id="ref-link-section-d3005e481" title="Findley, W. N., Lai, J. S. & Onaran, K. Creep and Relaxation of Nonlinear Viscoelastic Materials with an Introduction to Linear Viscoelasticity (Dover Publications, Mineola, New York, 1989).">6. As such, the extent to which dynamics of the CSK might be regarded as glassy remained an open question. Here we report both forced and spontaneous motions of microbeads tightly bound to the CSK of human muscle cells. Large oscillatory shear fluidized the CSK matrix, which was followed by slow scale-free recovery of rheological properties (aging). Spontaneous bead motions were subdiffusive at short times but superdiffusive at longer times; intermittent motions reflecting nanoscale CSK rearrangements depended on both the approach to kinetic arrest and energy release due to ATP hydrolysis. Aging, intermittency, and approach to kinetic arrest establish a striking analogy between the behaviour of the living CSK and that of inert non-equilibrium systems, including soft glasses, but with important differences that are highly ATP-dependent. These mesoscale dynamics link integrative CSK functions to underlying molecular events, and represent an important intersection of topical issues in condensed matter physics and systems biology.

Anomalous diffusion probes microstructure dynamics of entangled F-actin networks - Wong, I. Y.; Gardel, M. L.; D. R. Reichman; Weeks, E. R.; Valentine, M. T.; A. R. Bausch; Weitz, D. A. (Physical Review Letters, 2004)
We study the thermal motion of colloidal tracer particles in entangled actin filament (F-actin) networks, where the particle radius is comparable to the mesh size of the F-actin network. In this regime, the ensemble-averaged mean-squared displacement of the particles is proportional to tau(gamma), where 0

New developments in colloid science - Weitz, D. A.; Russel, W. B. (Mrs Bulletin, 2004)
This introductory article reviews the topics covered in this issue of MRS Bulletin on New Developments in Colloid Science. Colloidal particles have a long history of importance in a broad range of applications in technology and materials processing. They can be made from many different materials and suspended in a wide variety of solvents. The rheological properties of colloidal suspensions have traditionally been of primary concern in their technological applications, and our understanding of these properties continues to evolve. However, new uses of colloidal particles are also emerging. Because they can be produced to a precise size, colloidal particles are now also being used in novel ways as building blocks for engineering completely new materials, including high-precision filters, controlled-porosity substrates, and photonic devices. In addition, new methods are evolving to alter the shape of the particles and create controlled structures with nonspherical particles. New experimental techniques are allowing improved measurement and increased understanding of the structure, properties, and behavior of colloidal suspensions, Significant progress continues to be made, and the potential uses of colloidal particles continue to grow. This issue presents a snapshot summary of recent developments in this field.

Packing in the spheres - Weitz, D. A. (Science, 2004)
To study how objects pack together, physicists have long assumed that the objects are spherical. But this simplifying approximation may be leading researchers astray. As Weitz discusses in his Perspective, the work reported by Doney et al. in the same issue shows that how spheres pack may be the exception rather than the rule. Through a combination of experiments with a large collection of ellipsoidal candies and computer simulations, the researchers discover that a much higher volume can be filled with the ellipsoids than with spheres. Not just a theoretical puzzle, the ways in which objects pack are of vital concern to the shipping and manufacturing industries.

Colloid surface chemistry critically affects multiple particle tracking measurements of biomaterials - Valentine, M. T.; Perlman, Z. E.; Gardel, M. L.; Shin, J. H.; Matsudaira, P.; Mitchison, T. J.; Weitz, D. A. (Biophysical Journal, 2004)
Characterization of the properties of complex biomaterials using microrheological techniques has the promise of providing fundamental insights into their biomechanical functions; however, precise interpretations of such measurements are hindered by inadequate characterization of the interactions between tracers and the networks they probe. We here show that colloid surface chemistry can profoundly affect multiple particle tracking measurements of networks of fibrin, entangled F-actin solutions, and networks of cross-linked F-actin. We present a simple protocol to render the surface of colloidal probe particles protein-resistant by grafting short amine-terminated methoxy-poly(ethylene glycol) to the surface of carboxylated microspheres. We demonstrate that these poly(ethylene glycol)-coated tracers adsorb significantly less protein than particles coated with bovine serum albumin or unmodified probe particles. We establish that varying particle surface chemistry selectively tunes the sensitivity of the particles to different physical properties of their microenvironments. Specifically, particles that are weakly bound to a heterogeneous network are sensitive to changes in network stiffness, whereas protein-resistant tracers measure changes in the viscosity of the fluid and in the network microstructure. We demonstrate experimentally that two-particle microrheology analysis significantly reduces differences arising from tracer surface chemistry, indicating that modifications of network properties near the particle do not introduce large-scale heterogeneities. Our results establish that controlling colloid-protein interactions is crucial to the successful application of multiple particle tracking techniques to reconstituted protein networks, cytoplasm, and cells.

Relating microstructure to rheology of a bundled and cross-linked F-actin network in vitro - Shin, J. H.; Gardel, M. L.; Mahadevan, L; Matsudaira, P.; Weitz, D. A. (PNAS, 2004)
The organization of individual actin filaments into higher-order structures is controlled by actin-binding proteins (ABPs). Although the biological significance of the ABPs is well documented, little is known about how bundling and cross-linking quantitatively affect the microstructure and mechanical properties of actin networks. Here we quantify the effect of the ABP scruin on actin networks by using imaging techniques, cosedimentation assays, multiparticle tracking, and bulk rheology. We show how the structure of the actin network is modified as the scruin concentration is varied, and we correlate these structural changes to variations in the resultant network elasticity.

Visualization of dislocation dynamics in colloidal crystals - Schall, P.; Cohen, I.; Weitz, D. A.; F. Spaepen (Science, 2004)
The dominant mechanism for creating large irreversible strain in atomic crystals is the motion of dislocations, a class of line defects in the crystalline lattice. Here we show that the motion of dislocations can also be observed in strained colloidal crystals, allowing detailed investigation of their topology and propagation. We describe a laser diffraction microscopy setup used to study the growth and structure of misfit dislocations in colloidal crystalline films. Complementary microscopic information at the single-particle level is obtained with a laser scanning confocal microscope. The combination of these two techniques enables us to study dislocations over a range of length scales, allowing us to determine important parameters of misfit dislocations such as critical film thickness, dislocation density, Burgers vector, and lattice resistance to dislocation motion. We identify the observed dislocations as Shockley partials that bound stacking faults of vanishing energy. Remarkably, we find that even on the scale of a few lattice vectors, the dislocation behavior is well described by the continuum approach commonly used to describe dislocations in atomic crystals.

Swollen vesicles and multiple emulsions from block copolymers - Nikova, A. T.; Gordon, V. D.; Cristobal, G.; Talingting, M. R.; D.C. Bell; Evans, C.; Joanicot, M.; Zasadzinski, J. A.; Weitz, D. A. (Macromolecules, 2004)
We engineer novel structures by "stuffing" the aliphatic regions of self-assembled aggregates with hydrophobic homopolymer. These "stuffed" vesicles and multiple emulsions are formed in a one-step process when we rehydrate stuffed films made of amphiphilic block copolymer and hydrophobic homopolymer. Without such homopolymer, this system forms micelles. With homopolymer, vesicles form; varying vesicle membrane thicknesses show that these structures incorporate different amounts of homopolymer. Multiple emulsions, containing more homopolymer than stuffed vesicles, are also fabricated using this single-amphiphile system. The system's incorporation of homopolymer to modify the properties and morphology of the resultant structures is a convenient strategy for preparing self-assembled macromolecular structures with controllable properties.

A model for velocity fluctuations in sedimentation - Mucha, P. J.; Tee, S. Y.; Weitz, D. A.; Shraiman, B. I.; Brenner, M.P. (Journal of Fluid Mechanics, 2004)
We present a model for velocity fluctuations of dilute sedimenting spheres at low Reynolds number. The central idea is that a vertical stratification causes the fluctuations to decrease below those of an independent uniform distribution of particles, such a stratification naturally occurring from the broadening of the sedimentation front. We use numerical simulations, scaling arguments, structure factor calculations, and experiments to show that there is a critical stratification above which the characteristics of the density and velocity fluctuations change significantly. For thin cells, the broadening of the sediment front (and the resulting stratification) is small, so the velocity fluctuations are predicted by independent-Poisson-distribution estimates. In very thick cells, the stratification is significant, leading to persistent decay of the velocity fluctuations for the duration of the experiment. Estimated stratifications quantitatively agree with the simulations, and indicate the likelihood that previous experimental measurements were also affected by stratification. The Velocity fluctuations in sedimentation are therefore not universal but instead depend on both the cell shape and developing stratification.

Limits to gelation in colloidal aggregation - S. Manley; Cipelletti, L.; Trappe, V.; Bailey, A. E.; Christianson, R. J.; Gasser, U.; Prasad, V.; Segre, P. N.; Doherty, M. P.; Sankaran, S.; Jankovsky, A. L.; Shiley, B.; et al. (Physical Review Letters, 2004)
We show that the dynamics of large fractal colloid aggregates are well described by a combination of translational and rotational diffusion and internal elastic fluctuations, allowing both the aggregate size and internal elasticity to be determined by dynamic light scattering. The comparison of results obtained in microgravity and on Earth demonstrates that cluster growth is limited by gravity-induced restructuring. In the absence of gravity, thermal fluctuations ultimately inhibit fractal growth and set the fundamental limitation to the lowest volume fraction which will gel.

Geometrically mediated breakup of drops in microfluidic devices - Link, D.R.; Anna, S. L.; Weitz, D. A.; H.A. Stone (Physical Review Letters, 2004)
Microfluidic technology offers capabilities for the precise handling of small fluid volumes dispersed as droplets. To fully exploit this potential requires simultaneous generation of multiple size droplets. We demonstrate two methods for passively breaking larger drops into precisely controlled daughter drops using pressure-driven flow in simple microfluidic configurations: (i) a T junction and (ii) flow past isolated obstacles. We quantify conditions for breakup at a T junction and illustrate sequential breakup at T junctions for making small drops at high dispersed phase volume fractions.

Dealing with mechanics: Mechanisms of force transduction in cells - Paul A. Janmey; Weitz, DavidA. (Trends in Biochemical Sciences, 2004)
Physical cues, such as forces applied to a cell membrane or the stiffness of materials to which cells adhere, are increasingly recognized as essential determinants of biological function, and mechanical stimuli can be as important as chemical stimuli in determining tissue fate or contributing to pathological states. The physical environment of the cell can act in concert with, or sometimes override, the signals given by proteins and other cellular ligands to change cell morphology, growth rates and transcriptional programs. Recent developments in technology and techniques have facilitated studies of how forces trigger cellular events on the molecular level. As the mechanisms of force transduction are identified, methods and concepts from the physical sciences might become as important as those of biochemistry in elucidating how cells function and how these functions might be altered or corrected in therapeutic and biotechnological contexts.

Rheology of binary colloidal structures assembled via specific biological cross-linking - Hiddessen, A. L.; Weitz, D. A.; Hammer, D. A. (Langmuir, 2004)
The selectivity and range of energies offered by specific biological interactions serve as valuable tools for engineering the assembly of colloidal particles into novel materials. In this investigation, high affinity biological interactions between biotin-coated "A" particles (R-A = 0.475 mum) and streptavidin-coated "B" particles (R-B = 2.75 mum) drive the self-assembly of a series of binary colloidal structures, from colloidal micelles (a large B particle coated by smaller A particles) to elongated chain microstructures (alternating A and B particles), as the relative number of small (A) to large (B) particles (2 less than or equal to N-A/N-B less than or equal to 200) is decreased at a low total volume fraction (10(-4) less than or equal to phi(T) less than or equal to 10(-3)). At a significantly higher total volume fraction (phi(T) greater than or equal to 10(-1)) and a low number ratio (N-A/N-B = 2), the rheological behavior of volume-filling particle networks connected by streptavidin-biotin bonds is characterized. The apparent viscosity (eta) as a function of the shear rate (gamma), measured for networks at phi(T) = 0.1 and 0.2, exhibits shear-rate-dependent flow behavior, and both the apparent viscosity and the extent of shear thinning increase upon an increase of a factor of 2 in the total volume fraction. Micrographs taken before and after shearing show a structural breakdown of the flocculated binary particle network into smaller flocs, and ultimately a fluidlike suspension, with increasing shear rate. Rheological measurements provide further proof that suspension microstructure is governed by specific biomolecular interactions, as control experiments in which the streptavidin molecules on particles were blocked displayed Newtonian flow behavior. This investigation represents the first attempt at measuring the rheology of colloidal suspensions where assembly is driven by biomolecular cross-linking.

A new device for the generation of microbubbles - Gordillo, J. M.; Cheng, Z. D.; Ganan-Calvo, A. M.; Marquez, M.; Weitz, D. A. (Physics of Fluids, 2004)
In this paper we present a new method for the production of bubble-liquid suspensions (from now on BLS) composed of micron-sized bubbles and with gas to liquid volume ratios larger than unity. We show that the BLS gas fraction lambda=Q(g)/Q(l), being Q(g) and Q(l) the flow rates of gas and liquid, respectively, is controlled by a dimensionless parameter which accounts for the ratio of the gas pressure inside the device to the liquid viscous pressure drop from the orifices where the liquid is injected to the exit, where the BLS is obtained. This parameter permits the correct scaling of the BLS gas volume fraction of all the experiments presented. (C) 2004 American Institute of Physics.

Self-assembled polymer membrane capsules inflated by osmotic pressure - Gordon, V. D.; Xi, C.; J.W. Hutchinson; A. R. Bausch; Marquez, M.; Weitz, D. A. (Journal of the American Chemical Society, 2004)
We fabricate and characterize capsules that are composite membranes, made of a polymer network stabilized by adsorption to colloids and inflated by osmotic pressure from internal free polyelectrolyte; here, poly-L-lysine forms the network and inflates the capsules. To assess these capsules' properties and structure, we deform capsules using microcantilevers and use finite element modeling to describe these deformations. Additional experimental tests confirm the model's validity. These capsules' resilient response to mechanical forces indicates that loading and shear should be good triggers for the release of contents via deformation. The osmotic pressure inflating these capsules has the potential to trigger release of contents via deflation in response to changes in the capsules' environment; we demonstrate addition of salt as a trigger for deflating capsules. Because these capsules have a variety of release triggers available and the technique used to fabricate them is very flexible and allows high encapsulation efficiency, these capsules have very high potential for application in many areas.

Elastic behavior of cross-linked and bundled actin networks - Gardel, M. L.; Shin, J. H.; MacKintosh, F. C.; Mahadevan, L; Matsudaira, P.; Weitz, D. A. (Science, 2004)
Networks of cross-linked and bundled actin. laments are ubiquitous in the cellular cytoskeleton, but their elasticity remains poorly understood. We show that these networks exhibit exceptional elastic behavior that reflects the mechanical properties of individual. laments. There are two distinct regimes of elasticity, one reflecting bending of single. laments and a second reflecting stretching of entropic fluctuations of filament length. The mechanical stiffness can vary by several decades with small changes in cross-link concentration, and can increase markedly upon application of external stress. We parameterize the full range of behavior in a state diagram and elucidate its origin with a robust model.

Scaling of F-actin network rheology to probe single filament elasticity and dynamics - Gardel, M. L.; Shin, J. H.; MacKintosh, F. C.; Mahadevan, L; Matsudaira, P. A.; Weitz, D. A. (Physical Review Letters, 2004)
The linear and nonlinear viscoelastic response of networks of cross-linked and bundled cytoskeletal filaments demonstrates remarkable scaling with both frequency and applied prestress, which helps elucidate the origins of the viscoelasticity. The frequency dependence of the shear modulus reflects the underlying single-filament relaxation dynamics for 0.1-10 rad/sec. Moreover, the nonlinear strain stiffening of such networks exhibits a universal form as a function of prestress; this is quantitatively explained by the full force-extension relation of single semiflexible filaments.

Electro-optics of bipolar nematic liquid crystal droplets - Fernandez-Nieves, A.; Link, D.R.; Rudhardt, D.; Weitz, D. A. (Physical Review Letters, 2004)
We directly visualize the response and relaxation dynamics of bipolar nematic liquid crystal droplets to an applied electric field E. Despite strong planar anchoring, there is no critical field for switching. Instead, upon application of E, the surface region first reorients, followed by movement of the disclinations and the bipolar axis. After removing E, elastic forces restore the drop to its original state. The collective electro-optic properties of ordered hexagonal-close-packed monolayers of drops are probed by diffraction experiments confirming the proposed switching mechanism.

Shear-induced configurations of confined colloidal suspensions - Cohen, I.; Mason, T. G.; Weitz, D. A. (Physical Review Letters, 2004)
We show that geometric confinement dramatically affects the shear-induced configurations of dense monodisperse colloidal suspensions; a new structure emerges, where layers of particles buckle to stack in a more efficient packing. The volume fraction in the shear zone is controlled by a balance between the viscous stresses and the osmotic pressure of a contacting reservoir of unsheared particles. We present a model that accounts for our observations and helps elucidate the complex interplay between particle packing and shear stress for confined suspensions.

Electrostatics for exploring the nature of the hydrogen bonding in polyethylene oxide hydration - Aray, Y.; Manuel, M.; Rodriguez, J.; Vega, D.; Simon-Manso, Y.; Coll, S.; Gonzalez, C.; Weitz, D. A. (Journal of Physical Chemistry B, 2004)
Binding between water and models of poly(ethylene oxide), (CH2−CH2−O)n, n = 2−40, has been studied using the topographic features of the electrostatic potential, V(r), and standard density functional theory methods. It was found that, in general, the contour around the minima of the oxygen atoms overlap forming a negative-valued spiral coiled around a positive-valued helix. The positive zone defines a helical groove in the O−C−C−O units where minima lone pairs critical points are located. Topological analysis of the water molecule has also suggested that the attractive electrostatic effect between the positive water O−H zone and the negative PEO lone pairs plays an important role in the hydrogen bonding of the PEO−water system. Thus, the V(r) topology predicts a coil of water molecules around the PEO chain forming hydrogen bonding with two sites of ether oxygens. This coil is formed in such a way that more water molecules accumulate on the cavities surrounding the poly(ethylene oxide)'s oxygen atoms where the minima of the negative zone are located.

Shake-gels: Shear-induced gelation of laponite-PEO mixtures - Zebrowski, J.; Prasad, V.; Zhang, W.; Walker, L. M.; Weitz, D. A. (Colloids and Surfaces a-Physicochemical and Engineering Aspects, 2003)
Suspensions of clay particles (laponite), mixed with poly(ethylene oxide) (PEO) undergo a dramatic shear thickening when subjected to vigorous shaking, which transforms them from a low viscosity fluid into a 'shake-gel', a solid with elasticity sufficient enough to support its own weight. The shake-gel is reversible, relaxing back to a fluid with a relaxation time that is strongly dependent on PEO concentration. Shake-gels are observed for PEO concentrations slightly below the threshold for complete saturation of the laponite particles by the polymer. Light scattering measurements confirm that the PEO is adsorbed on the surface of the laponite particles, and suggests that shear induces a bridging between the colloidal particles, resulting in a gel network which spans the system. Desorption of the polymer reduces the bridging and thus relaxes the network. (C) 2002 Elsevier Science B.V. All rights reserved.

Direct lung delivery of para-aminosalicylic acid by aerosol particles - Tsapis, N.; Bennett, D.; O'Driscoll, K.; Shea, K.; Lipp, M. M.; Fu, K.; Clarke, R. W.; Deaver, D.; Yamins, D.; J. Wright; Peloquin, C. A.; Weitz, D. A.; et al. (Tuberculosis, 2003)
Para-aminosalicylic acid (PAS), a tuberculostatic agent, was formulated into large porous particles for direct delivery into the lungs via inhalation. These particles possess optimized physical properties for deposition throughout the respiratory tract, a drug loading of 95% by weight and physical stability over 4 weeks at elevated temperatures. Upon insufflation in rats, PAS concentrations were measured in plasma, lung lining fluid and homogenized whole lung tissue. Systemic drug concentrations peaked at 15 min, with a maximum plasma concentration of 11+/-1 mug/ml. The concentration in the lung lining fluid was 148 +/- 62 mug/ml at 15 min. Tissue concentrations were 65 +/- 20 mug/ml at 15 min and 3.2 +/- 0.2 mug/ml at 3 h. PAS was cleared within 3 h from the lung lining fluid and plasma but was still present at therapeutic concentrations in the lung tissue. These results suggest that inhalation delivery of PAS can potentially allow for a reduction in total dose delivered while providing for higher local and similar peak systemic drug concentrations as compared to those obtained upon oral PAS dosing. Similar particles could potentially be used for the delivery of additional anti-tuberculosis agents such as rifampicin, aminoglucosides or fluoroquinolones. (C) 2003 Elsevier Ltd. All rights reserved.

Phase switching of ordered arrays of liquid crystal emulsions - Rudhardt, D.; Fernandez-Nieves, A.; Link, D.R.; Weitz, D. A. (Applied Physics Letters, 2003)
We report a fabrication method for producing interference-based electro-optic phase gratings that switch between diffracting and transparent states. The phase grating consists of a hexagonal-close-packed array of monodisperse emulsion drops of nematic liquid crystal, embedded in a polymer matrix. Monodisperse droplet size allows for fast switching at low electric fields. (C) 2003 American Institute of Physics.

Microscopic origin of light scattering in tissue - Popp, A. K.; Valentine, M. T.; Kaplan, P. D.; Weitz, D. A. (Applied Optics, 2003)
A newly designed instrument, the static light-scattering (SLS) microscope, which combines light microscopy with SLS, enables us to characterize local light-scattering patterns of thin tissue sections. Each measurement is performed with an illumination beam of 70-mum diameter. On these length scales, tissue is not homogeneous. Both structural ordering and small heterogeneities contribute to the scattering signal. Raw SLS data consist of a two-dimensional intensity distribution map I(theta, phi), showing the dependence of the scattered intensity I on the scattering angle theta and the azimuthal angle D. In contrast to the majority of experiments and to simulations that consider only the scattering angle, we additionally perform an analysis of the azimuthal dependence I(phi). We estimate different contributions to the azimuthal scattering variation and show that a significant fraction of the azimuthal amplitude is the result of tissue structure. As a demonstration of the importance of the structure-dependent part of the azimuthal signal, we show that this function of the scattered light alone can be used to classify tissue types with surprisingly high specificity and sensitivity. (C) 2003 Optical Society of America.

Universal features of the fluid to solid transition for attractive colloidal particles - Prasad, V.; Trappe, V.; A. D. Dinsmore; Segre, P. N.; Cipelletti, L.; Weitz, D. A. (Faraday Discussions, 2003)
Attractive colloidal particles can exhibit a fluid to solid phase transition if the magnitude of the attractive interaction is sufficiently large, if the volume fraction is sufficiently high, and if the applied stress is sufficiently small. The nature of this fluid to solid transition is similar for many different colloid systems, and for many different forms of interaction. The jamming phase transition captures the common features of these fluid to solid translations, by unifying the behavior as a function of the particle volume fraction, the energy of interparticle attractions, and the applied stress. This paper describes the applicability of the jamming state diagram, and highlights those regions where the fluid to solid transition is still poorly understood. It also presents new data for gelation of colloidal particles with an attractive depletion interaction, providing more insight into the origin of the fluid to solid transition.

Engineering asymmetric vesicles - Pautot, S.; Frisken, B. J.; Weitz, D. A. (PNAS, 2003)
Vesicles are bilayers of lipid molecules enclosing a fixed volume of aqueous solution. Ubiquitous in cells, they can be produced in vitro to study the physical properties of biological membranes and for use in drug delivery and cosmetics. Biological membranes are, in fact, a fluid mosaic of lipids and other molecules; the richness of their chemical and mechanical properties in vivo is often dictated by an asymmetric distribution of these molecules. Techniques for vesicle preparation have been based on the spontaneous assembly of lipid bilayers, precluding the formation of such asymmetric structures. Partial asymmetry has been achieved only with chemical methods greatly restricting the study of the physical and chemical properties of asymmetric vesicles and their use in potential applications for drug delivery. Here we describe the systematic engineering of unilamellar vesicles assembled with two independently prepared monolayers; this process produces asymmetries as high as 95%. We demonstrate the versatility of our method by investigating the stability of the asymmetry. We also use it to engineer hybrid structures comprised of an inner leaflet of diblock copolymer and an independent lipid outer leaflet.

Production of unilamellar vesicles using an inverted emulsion - Pautot, S.; Frisken, B. J.; Weitz, D. A. (Langmuir, 2003)
We investigate a method for the controlled assembly of unilamellar vesicles consisting of bilayers assembled one leaflet at a time. We use water-in-oil emulsions stabilized by the material for the inner leaflet and produce vesicles by passing the water droplets through a second oil-water interface, where they become coated with the outer leaflet. We have used this technique to form vesicles from lipids, mixed lipid and surfactant systems, and diblock copolymers. The stability of lipid-stabilized emulsions limits the range of sizes that can be produced and the vesicle yield; nevertheless, there are several advantages with this emulsion-based technique: It is possible to make unilamellar vesicles with sizes ranging from 100 nm to 1 mum. Moreover, the process allows for efficient encapsulation and ensures that the contents of the vesicles remain isolated from the continuous aqueous phase. To illustrate possible applications of this technique, we demonstrate the use of vesicles as microreactors where we polymerize actin through the addition of magnesium and show that the polymerization kinetics are unaffected by the encapsulation.

Spontaneous formation of lipid structures at oil/water lipid interfaces - Pautot, S.; Frisken, B. J.; Cheng, J. X.; Xie, X. S.; Weitz, D. A. (Langmuir, 2003)
We report the spontaneous formation of emulsion droplets and multilamellar concentric onions when a water drop is immersed into dodecane containing phospholipids. We show that the origin of the spontaneous emulsification is the formation of a semierystalline multilamellar film at the dodecane-water interface, which swells with water, shedding the emulsion and onion droplets. We use coherent anti-Stokes Raman scattering microscopy to determine that the shell of the onion structures is composed of partially hydrated concentric bilayers, and the core is composed of lipids, water, and dodecane.

Like-charged particles at liquid interfaces - Reply - M. G. Nikolaides; A. R. Bausch; M. F. Hsu; A. D. Dinsmore; Brenner, M.P.; C. Gay; Weitz, D. A. (Nature, 2003)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="401" data-gtm-vis-first-on-screen-10482319_401="471" data-gtm-vis-polling-id-10482319_393="66" data-gtm-vis-polling-id-10482319_401="77" data-gtm-vis-recent-on-screen-10482319_393="401" data-gtm-vis-recent-on-screen-10482319_401="471" data-gtm-vis-total-visible-time-10482319_393="5000" data-gtm-vis-total-visible-time-10482319_401="5000" data-title="Abstract" lang="en"> Our experiment provides a clear measure of the interactions between charged particles at fluid–fluid interfaces and demonstrates that there can be a long-range attractive interaction between such particles.

Dynamics of weakly aggregated colloidal particles - Kilfoil, M. L.; Pashkovski, E. E.; Masters, J. A.; Weitz, D. A. (Philosophical Transactions of the Royal Society of London Series A, 2003)
We discuss the behaviour of the dynamics of colloidal particles with a weak attractive interparticle interaction that is induced through the addition of polymer to the solvent. We briefly review the description of their behaviour in terms of the jamming phase diagram, which parametrized the fluid-to-solid transition due to changes in volume fraction, attractive energy or applied stress. We focus on a discussion of ageing of the solid gels formed by these colloid-polymer mixtures. They exhibit a delayed collapse induced by gravity. The time evolution of the height of the sediment exhibits an unexpected scaling behaviour, suggesting a universal nature to this delayed collapse. We complement these measurements of the scaling of the collapse with microscopic investigations of the evolution of the structure of the network using confocal microscopy. These results provide new insight into the origin of this ageing behaviour.

Synthesis of voltage-sensitive fluorescence signals from three-dimensional myocardial activation patterns - Hyatt, C. J.; Mironov, S. F.; Wellner, M.; Berenfeld, O.; Popp, A. K.; Weitz, D. A.; Jalife, J.; Pertsov, A. M. (Biophysical Journal, 2003)
Voltage-sensitive fluorescent dyes are commonly used to measure cardiac electrical activity. Recent studies indicate, however, that optical action potentials (OAPs) recorded from the myocardial surface originate from a widely distributed volume beneath the surface and may contain useful information regarding intramural activation. The first step toward obtaining this information is to predict OAPs from known patterns of three-dimensional (3-D) electrical activity. To achieve this goal, we developed a two-stage model in which the output of a 3-D ionic model of electrical excitation serves as the input to an optical model of light scattering and absorption inside heart tissue. The two-stage model permits unique optical signatures to be obtained for given 3-D patterns of electrical activity for direct comparison with experimental data, thus yielding information about intramural electrical activity. To illustrate applications of the model, we simulated surface fluorescence signals produced by 3-D electrical activity during epicardial and endocardial pacing. We discovered that OAP upstroke morphology was highly sensitive to the transmural component of wave front velocity and could be used to predict wave front orientation with respect to the surface. These findings demonstrate the potential of the model for obtaining useful 3-D information about intramural propagation.

Measuring the mechanical stress induced by an expanding multicellular tumor system: A case study - Gordon, V. D.; Valentine, M. T.; Gardel, M. L.; Andor-Ardo, D.; Dennison, S.; Bogdanov, A. A.; Weitz, D. A.; Deisboeck, T. S. (Experimental Cell Research, 2003)
Rapid volumetric growth and extensive invasion into brain parenchyma are hallmarks of malignant neuroepithelial tumors in vivo. Little is known, however, about the mechanical impact of the growing brain tumor on its microenvironment. To better understand the environmental mechanical response, we used multiparticle tracking methods to probe the environment of a dynamically expanding, multicellular brain tumor spheroid that grew for 6 days in a three-dimensional Matrigel-based in vitro assay containing 1.0-mum latex beads. These beads act as reference markers for the gel, allowing us to image the spatial displacement of the tumor environment using high-resolution time-lapse video microscopy. The results show that the volumetrically expanding tumor spheroid pushes the gel outward and that this tumor-generated pressure propagates to a distance greater than the initial radius of the tumor spheroid. Intriguingly, beads near the tips of invasive cells are displaced inward, toward the advancing invasive cells. Furthermore, this localized cell traction correlates with a marked increase in total invasion area over the observation period. This case study presents evidence that an expanding microscopic tumor system exerts both significant mechanical pressure and significant traction on its microenvironment. (C) 2003 Elsevier Science (USA). All rights reserved.

Local order in a supercooled colloidal fluid observed by confocal microscopy - Gasser, U.; Schofield, A.; Weitz, D. A. (Journal of Physics: Condensed Matter, 2003)
The local order in a supercooled monodisperse colloidal fluid is studied by direct imaging of the particles with a laser scanning confocal microscope. The local structure is analysed with a bond order parameter method, which allows one to discern simple structures that are relevant in this system. As expected for samples that crystallize eventually, a large fraction of the particles are found to sit in surroundings with dominant face-centred cubic or hexagonally close-packed character. Evidence for local structures that contain fragments of icosahedra is found, and, moreover, the icosahedral character increases with volume fraction phi, which indicates that it might play an important role at volume fractions near the glass transition.

Microrheology of entangled F-actin solutions - Gardel, M. L.; Valentine, M. T.; Crocker, J. C.; A. R. Bausch; Weitz, D. A. (Physical Review Letters, 2003)
We measure the viscoelasticity of entangled F-actin over length scales between 1 and 100 mum using one- and two-particle microrheology, and directly identify two distinct microscopic contributions to the elasticity. Filament entanglements lead to a frequency-independent elastic modulus over an extended frequency range of 0.01-30 rad/sec; this is probed with one-particle microrheology. Longitudinal fluctuations of the filaments increase the elastic modulus between 0.1 and 30 rad/sec at length scales up to the filament persistence length; this is probed by two-particle microrheology.

Flow and fracture in drying nanoparticle suspensions - Dufresne, E. R.; Corwin, E. I.; Greenblatt, N. A.; J. Ashmore; Wang, D. Y.; A. D. Dinsmore; Cheng, J. X.; Xie, X. S.; J.W. Hutchinson; Weitz, D. A. (Physical Review Letters, 2003)
Drying aqueous suspensions of monodisperse silica nanoparticles can fracture in remarkable patterns. As the material solidifies, evenly spaced cracks invade from the drying surface, with individual cracks undergoing intermittent motion. We show that the growth of cracks is limited by the advancement of the compaction front, which is governed by a balance of evaporation and flow of fluid at the drying surface. Surprisingly, the macroscopic dynamics of drying show signatures of molecular-scale fluid effects.

Universal non-diffusive slow dynamics in aging soft matter - Cipelletti, L.; Ramos, L.; S. Manley; Pitard, E.; Weitz, D. A.; Pashkovski, E. E.; Johansson, M. (Faraday Discussions, 2003)
We use conventional and multispeckle dynamic light scattering to investigate the dynamics of a wide variety of jammed soft materials, including colloidal gels, concentrated emulsions, and concentrated surfactant phases. For all systems, the dynamic structure factor f (q, t) exhibits a two-step decay. The initial decay is due to the thermally activated diffusive motion of the scatterers, as indicated by the q(-2) dependence of the characteristic relaxation time, where q is the scattering vector. However, due to the constrained motion of the scatterers in jammed systems, the dynamics are arrested and the initial decay terminates in a plateau. Surprisingly, we find that a final, ultraslow decay leads to the complete relaxation of f (q, t), indicative of rearrangements on length scales as large as several microns or tens of microns. Remarkably, for all systems the same very peculiar form is found for the final relaxation of the dynamic structure factor: f (q, t) similar to exp [ (t /tau(s))(p)], with p approximate to 1.5 and t(s) similar to q(-1), thus suggesting the generality of this behavior. Additionally, for all samples the final relaxation slows down with age, although the aging behavior is found to be sample dependent. We propose that the unusual ultraslow dynamics are due to the relaxation of internal stresses, built into the sample at the jamming transition, and present simple scaling arguments that support this hypothesis.

Ordering of water molecules between phospholipid bilayers visualized by coherent anti-Stokes Raman scattering microscopy - Cheng, J. X.; Pautot, S.; Weitz, D. A.; Xie, X. S. (PNAS, 2003)
We demonstrate ordered orientation of the hydration water at the surface of phospholipid bilayers by use of coherent anti-Stokes Raman scattering (CARS) microscopy, a highly sensitive vibrational imaging method recently developed. We investigated negatively charged POPS (1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-L-serine) and neutral POPC (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine) multilamellar onions dispersed in deuterated dodecane. The imaging contrast based on the CARS signal from the H2O stretching vibration shows a clear dependence on the excitation field polarization. Our results provide direct experimental evidence that water molecules close to the phospholipid bilayer surface are ordered with the symmetry axis along the direction normal to the bilayer. Moreover, the amount of ordered water molecules depends on the lipid polar group. The spectral profile for the interlamellar water shows that the water molecules bound to the bilayer surface are less hydrogen-bonded and exhibit a higher vibrational frequency than bulk water.

Grain boundary scars and spherical crystallography - A. R. Bausch; Bowick, M.J.; Cacciuto, A.; A. D. Dinsmore; M. F. Hsu; Nelson, D.R.; M. G. Nikolaides; Travesset, A.; Weitz, D. A. (Science, 2003)
We describe experimental investigations of the structure of two-dimensional spherical crystals. The crystals, formed by beads self-assembled on water droplets in oil, serve as model systems for exploring very general theories about the minimum-energy configurations of particles with arbitrary repulsive interactions on curved surfaces. Above a critical system size we find that crystals develop distinctive high-angle grain boundaries, or scars, not found in planar crystals. The number of excess defects in a scar is shown to grow linearly with the dimensionless system size. The observed slope is expected to be universal, independent of the microscopic potential.

Size-dependent intracellular immunotargeting of therapeutic cargoes into endothelial cells - Wiewrodt, R.; Thomas, A. P.; Cipelletti, L.; Christofidou-Solomidou, M.; Weitz, D. A.; Feinstein, S. I.; Schaffer, D.; Albelda, S. M.; Koval, M.; Muzykantov, V.R. (Blood, 2002)
Cell-selective intracellular targeting is a key element of more specific and safe enzyme, toxin, and gene therapies. Endothelium poorly internalizes certain candidate carriers for vascular immunotargeting, such as antibodies to platelet endothelial cell adhesion molecule 1 (PECAM-1). Conjugation of poorly internalizable antibodies with streptavidin (SA) facilitates the intracellular uptake. Although both small and large (100-nm versus 1000-nm diameter) anti-PECAM/SA-beta galactosidase (SA-beta-gal) conjugates bound selectively to PECAM-expressing cells, only small conjugates showed intracellular accumulation of active P-gal. To study whether size of the conjugates controls the uptake, a series of anti-PECAM/SA and anti-PECAM/bead conjugates ranging from 80 nm to 5 mum in diameter were produced. Human umbilical vein endothelial cells and PECAM-transfected mesothelioma cells internalized 80- to 350-nm anti-PECAM conjugates, but not conjugates larger than 500 nm. Further, size controls intracellular targeting of active therapeutic cargoes in vitro and in vivo. Small anti-PECAM/DNA conjugates transfected target cells in culture 5-fold more effectively than their large counterpart (350- versus 4200-nm diameter). To evaluate the practical significance of the size-controlled subcellular addressing, we coupled glucose oxidase (GOX) to anti-PECAM and antithrombomodulin. Both types of conjugates had equally high pulmonary uptake after intravenous injection in mice, yet only small (200- to 250-nm), not large (600- to 700-nm), GOX conjugates caused profound oxidative vascular injury in the lungs, presumably owing to intracellular generation of H2O2. Thus, engineering of affinity carriers of specific size permits intracellular delivery of active cargoes to endothelium in vitro and in vivo, a paradigm useful for the targeting of drugs, genes, and toxins. (C) 2002 by The American Society of Hematology.

Properties of cage rearrangements observed near the colloidal glass transition - Weeks, E. R.; Weitz, D. A. (Physical Review Letters, 2002)
We use confocal microscopy to study particle motion in colloidal systems. Near the glass transition, motion is inhibited, as particles spend time trapped in transient "cages" formed by neighboring particles. We measure the cage sizes and lifetimes, which, respectively, shrink and grow as the glass transition approaches. Cage rearrangements are more prevalent in regions with lower concentrations and higher disorder. Neighboring rearranging particles typically move in parallel directions, although a nontrivial fraction moves in antiparallel directions, usually from particle pairs with initial separations corresponding to local maxima and minima of the pair correlation function g(r), respectively.

Subdiffusion and the cage effect studied near the colloidal glass transition - Weeks, E. R.; Weitz, D. A. (Chemical Physics, 2002)
The dynamics of a glass-forming material slow greatly near the glass transition, and molecular motion becomes inhibited. We use confocal microscopy to investigate the motion of colloidal particles near the colloidal glass transition. As the concentration in a dense colloidal suspension is increased, particles become confined in transient cages formed by their neighbors. This prevents them from diffusing freely throughout the sample. We quantify the properties of these cages by measuring temporal anticorrelations of the particles' displacements. The local cage properties are related to the subdiffusive rise of the mean square displacement: over a broad range of time scales, the mean square displacement grows slower than linearly in time. (C) 2002 Elsevier Science B.V. All rights reserved.

Trojan particles: Large porous carriers of nanoparticles for drug delivery - Tsapis, N.; Bennett, D.; Jackson, B.; Weitz, D. A.; Edwards, D. A. (PNAS, 2002)
We have combined the. drug release and delivery potential of nanoparticle (NP) systems with the ease of flow, processing, and aerosolization potential of large porous particle (LPP) systems by spray drying solutions of polymeric and nonpolymeric NPs into extremely thin-walled macroscale structures. These hybrid LPPs exhibit much better flow and aerosolization properties than the NPs; yet, unlike the LPPs, which dissolve in physiological conditions to produce molecular constituents, the hybrid LPPs dissolve to produce NPs, with the drug release and delivery advantages associated with NP delivery systems. Formation of the large porous NP (LPNP) aggregates occurs via a spray-drying process that ensures the drying time of the sprayed droplet is sufficiently shorter than the characteristic time for redistribution of NPs by diffusion within the drying droplet, implying a local Peclet number much greater than unity. Additional control over LPNPs physical characteristics is achieved by adding other components to the spray-dried solutions, including sugars, lipids, polymers, and proteins. The ability to produce LPNPs appears to be largely independent of molecular component type as well as the size or chemical nature of the NPs.

Nonuniversal velocity fluctuations of sedimenting particles - Tee, S. Y.; Mucha, P. J.; Cipelletti, L.; S. Manley; Brenner, M.P.; Segre, P. N.; Weitz, D. A. (Physical Review Letters, 2002)
Velocity fluctuations in sedimentation are studied to investigate the origin of a hypothesized universal scale [P. N. Segre, E. Herbolzheimer, and P. M. Chaikin, Phys. Rev. Lett. 79, 2574 (1997)]. Our experiments show that fluctuations decay continuously in time for sufficiently thick cells, never reaching steady state. Simulations and scaling arguments suggest that the decay arises from increasing vertical stratification of particle concentration due to spreading of the sediment front. The results suggest that the velocity fluctuations in sedimentation depend sensitively on cell geometry.

Rheology of defect networks in cholesteric liquid crystals - Ramos, L.; Zapotocky, M.; Lubensky, T.C.; Weitz, D. A. (Physical Review E, 2002)
The rheological properties of cholesteric liquid crystals containing networks of defects are investigated. A network of linear defects of the "oily-streak" type is stabilized when colloidal particles are dispersed into the cholesteric liquid crystals. This network converts the rheological response of a presheared cholesteric liquid crystal from fluidlike to solidlike and leads to the formation of a "defect-mediated" solid. The frequency-dependent complex shear modulus G(*)(omega) is measured, for samples with and without inclusions, in both the linear and nonlinear viscoelastic regimes. The linear elastic response mediated by the defect network is discussed in terms of a model analogous to the theories of rubber elasticity. All our data for G(*)(omega) are fitted to a simplified theoretical form, and the values and variations of the fitting parameters, in the various regimes investigated, are discussed in terms of the properties of defect structure present in the samples. Similar rheological properties are expected to arise from particle-stabilized oily-streak defect networks in layered systems such as smectic-A and lyotropic L(alpha) phases.

Electric-field-induced capillary attraction between like-charged particles at liquid interfaces - M. G. Nikolaides; A. R. Bausch; M. F. Hsu; A. D. Dinsmore; Brenner, M.P.; Weitz, D. A.; C. Gay (Nature, 2002)
Nanometre- and micrometre-sized charged particles at aqueous interfaces are typically stabilized by a repulsive Coulomb interaction. If one of the phases forming the interface is a nonpolar substance ( such as air or oil) that cannot sustain a charge, the particles will exhibit long-ranged dipolar repulsion(1); if the interface area is confined, mutual repulsion between the particles can induce ordering(2) and even crystallization(3,4). However, particle ordering has also been observed in the absence of area confinement(5), suggesting that like-charged particles at interfaces can also experience attractive interactions(6). Interface deformations are known to cause capillary forces that attract neighbouring particles to each other, but a satisfying explanation for the origin of such distortions remains outstanding(7,8). Here we present quantitative measurements of attractive interactions between colloidal particles at an oil - water interface and show that the attraction can be explained by capillary forces that arise from a distortion of the interface shape that is due to electrostatic stresses caused by the particles' dipolar field. This explanation, which is consistent with all reports on interfacial particle ordering so far, also suggests that the attractive interactions might be controllable: by tuning the polarity of one of the interfacial fluids, it should be possible to adjust the electrostaticstresses of the system and hence the interparticle attractions.

Electro-optic response and switchable Bragg diffraction for liquid crystals in colloid-templated materials - Mach, P.; Wiltzius, P.; Megens, M.; Weitz, D. A.; Lin, K. H.; Lubensky, T.C.; Yodh, A. G. (Physical Review E, 2002)
We report optical switching studies on nematic liquid crystal incorporated into structures based on self-assembled colloids. We compare the electro-optic responses of liquid crystal imbibed into colloid-templated polymers, liquid crystal imbibed in the interstitial space of colloid crystals, and conventional polymer-dispersed liquid crystals. We characterize the Bragg diffraction of our templated liquid-crystal/polymer composites as a function of electric field and measure switching times. The response of liquid crystal in connected networks differs qualitatively from that of liquid crystal in isolated cavities.

Switchable Bragg diffraction from liquid crystal in colloid-templated structures - Mach, P.; Wiltzius, P.; Megens, M.; Weitz, D. A.; Lin, K. H.; Lubensky, T.C.; Yodh, A. G. (Europhysics Letters, 2002)
We have incorporated nematic liquid crystal into periodic, polymer host structures templated from self-assembled colloids. Using these composite materials, we demonstrate the first electrically switchable three-dimensional Bragg diffraction. The switchable beam deflection is potentially useful for non-mechanical beam steering and optical beam splitting devices. We compare the electro-optic response of our templated liquid-crystal/polymer composites with conventional polymer-dispersed liquid crystals (PDLCs). Our data reveal a qualitatively different and faster response for liquid crystal distributed within a connected cavity network, as compared to isolated liquid-crystal droplets within a polymer matrix.

Colloidosomes: Selectively permeable capsules composed of colloidal particles - A. D. Dinsmore; M. F. Hsu; M. G. Nikolaides; Marquez, M.; A. R. Bausch; Weitz, D. A. (Science, 2002)
We present an approach to fabricate solid capsules with precise control of size, permeability, mechanical strength, and compatibility. The capsules are fabricated by the self-assembly of colloidal particles onto the interface of emulsion droplets. After the particles are locked together to form elastic shells, the emulsion droplets are transferred to a fresh continuous-phase fluid that is the same as that inside the droplets. The resultant structures, which we call "colloidosomes", are hollow, elastic shells whose permeability and elasticity can be precisely controlled. The generality and robustness of these structures and their potential for cellular immunoisolation are demonstrated by the use of a variety of solvents, particles, and contents.

Direct imaging of three-dimensional structure and topology of colloidal gels - A. D. Dinsmore; Weitz, D. A. (Journal of Physics-Condensed Matter, 2002)
We present novel measurements of the structure of colloidal gels. Using confocal microscopy, we obtain the precise three-dimensional positions of a large number of particles. We develop quantitative descriptions of the topology of the gel, including the number of bonds per particle, the chemical or bond fractal dimension, the number of flexible pivot points and other topological parameters that describe the chainlike structure. We investigate the dependence of these parameters on the particle volume fraction and the strength of the attraction that holds the particles together. While all samples have approximately the same fractal and chemical dimensions, we find that gels formed with stronger attraction or larger volume fraction have fewer bonds per particle, more filamentous chains and a greater number of flexible pivot points. Finally, we discuss the topological results in the context of the gel's elasticity. Measurements of the elastic constants of individual chainlike segments are explained with a simple model. The distribution of elastic constants, however, has a general form that is not understood.

Diffusing acoustic wave spectroscopy - Cowan, M. L.; Jones, I. P.; Page, J. H.; Weitz, D. A. (Physical Review E, 2002)
We have developed a technique in ultrasonic correlation spectroscopy called diffusing acoustic wave spectroscopy (DAWS). In this technique, the motion of the scatterers (e.g., particles or inclusions) is determined from the temporal fluctuations of multiply scattered sound. In DAWS, the propagation of multiply scattered sound is described using the diffusion approximation, which allows the autocorrelation function of the temporal field fluctuations to be related to the dynamics of the multiply scattering medium. The expressions relating the temporal field autocorrelation function to the motion of the scatterers are derived, focusing on the types of correlated motions that are most likely to be encountered in acoustic measurements. The power of this technique is illustrated with ultrasonic data on fluidized suspensions of particles, where DAWS provides a sensitive measure of the local relative velocity and strain rate of the suspended particles over a wide range of time and length scales. In addition, when combined with the measurements of the rms velocity of the particles using dynamic sound scattering, we show that DAWS can be used to determine the spatial extent of the correlations in the particle velocities, thus indirectly measuring the particle velocity correlation function. Potential applications of diffusing acoustic wave spectroscopy are quite far reaching, ranging from the ultrasonic nondestructive evaluation of the dynamics of inhomogeneous materials to geophysical studies of mesoscopic phenomena in seismology.

Microrheology of polyethylene oxide using diffusing wave spectroscopy and single scattering - Dasgupta, B. R.; Tee, S. Y.; Crocker, J. C.; Frisken, B. J.; Weitz, D. A. (Physical Review E, 2002)
Experiments investigating the local viscoelastic properties of a simple uncross-linked flexible polymer are performed on polyethylene oxide solutions in the semidilute regime using polystyrene beads of varying sizes and surface chemistry as probes. We measure the thermal motions of the beads to obtain the elastic and viscous moduli of our sample. Two different dynamic light scattering techniques, diffusing wave spectroscopy and quasielastic light scattering (QELS), are used to determine the dynamics of the probe particles. Diffusing wave spectroscopy probes the short time dynamics of the scatterers while QELS or single scattering measures the dynamics at larger times. This results in a larger frequency overlap of the data obtained from the microrheological techniques with the data obtained from the conventional bulk measurements. The moduli are estimated using a modified algebraic form of the generalized Stokes-Einstein equation. Comparison of microrheology with,bulk measurements shows excellent similarity confirming the applicability of this method for simple, uncross-linked polymeric systems.

Tracking the dynamics of single quantum dots: Beating the optical resolution twice - A. R. Bausch; Weitz, D. A. (Journal of Nanoparticle Research, 2002)
Using particle tracking routines the location of single point light sources can be determined with an accuracy of a few nanometers. By using quantum dots (QDs) emitting at different wavelengths, the measurement of the distance between these point light sources, which are closer than the optical resolution of 200 nm, was achieved. The nanocrystals have major advantages over conventional chromophores in higher quantum yield, more photostability, and the possibility of different emission wavelengths by an excitation with a single wavelength. The colocalization of two single QDs at the least distance of 40 nm can be measured with a standard deviation of 5 nm and a time resolution of 117 ms using one excitation wavelength.

Memories of paste - Weitz, D. A. (Nature, 2001)
Pastes are not the simple materials they appear to be. It seems they have a 'memory': after a force has been applied, they recover and move back in the opposite direction.

Investigating the microenvironments of inhomogeneous soft materials with multiple particle tracking - Valentine, M. T.; Kaplan, P. D.; Thota, D.; Crocker, J. C.; Gisler, T.; Prud'homme, R. K.; Beck, M.; Weitz, D. A. (Physical Review E, 2001)
We develop a multiple particle tracking technique for making precise., localized measurements of the mechanical microenvironments of inhomogeneous materials. Using video microscopy, we simultaneously measure the Brownian dynamics of roughly one hundred fluorescent tracer particles embedded in a complex medium and interpret their motions in terms of local viscoelastic response. To help overcome the inherent statistical limitations due to the finite imaging volume and limited imaging times, we develop statistical techniques and analyze the distribution of particle displacements in order to make meaningful comparisons of individual particles and thus characterize the diversity and properties of the microenvironments. The ability to per-form many local measurements simultaneously allows more precise measurements even in systems that evolve in time. We show several examples of inhomogeneous materials to demonstrate the flexibility of the technique and learn new details of the mechanics of the microenvironments that small particles explore. This technique extends other microrheological methods to allow simultaneous measurements of large numbers of probe particles, enabling heterogeneous samples to be studied more effectively.

Microscope-based static light-scattering instrument - Valentine, M. T.; Popp, A. K.; Weitz, D. A.; Kaplan, P. D. (Optics Letters, 2001)
We describe a new design for a microscope-based static light-scattering instrument that provides simultaneous high-resolution images and static light-scattering data. By correlating real space images with scattering patterns, we can interpret measurements from heterogeneous samples, which we illustrate by using biological tissue. (C) 2001 Optical Society of America.

Microscope-based static light-scattering instrument enables precise measurements of heterogeneous materials - Valentine, M. T.; Popp, A. K.; Kaplan, P. D.; Weitz, D. A. (Optics & Photonics News, 2001)

Jamming phase diagram for attractive particles - Trappe, V.; Prasad, V.; Cipelletti, L.; Segre, P. N.; Weitz, D. A. (Nature, 2001)
A wide variety of systems, including granular media, colloidal suspensions and molecular systems, exhibit non-equilibrium transitions from a fluid-like to a solid-like state, characterized solely by the sudden arrest of their dynamics. Crowding or jamming of the constituent particles traps them kinetically, precluding further exploration of the phase space(1). The disordered fluid-like structure remains essentially unchanged at the transition. The jammed solid can be refluidized by thermalization, through temperature or vibration, or by an applied stress. The generality of the jamming transition led to the proposal(2) of a unifying description, based on a jamming phase diagram. It was further postulated that attractive interactions might have the same effect in jamming the system as a confining pressure, and thus could be incorporated into the generalized description. Here we study experimentally the fluid-to-solid transition of weakly attractive colloidal particles, which undergo markedly similar gelation behaviour with increasing concentration and decreasing thermalization or stress. Our results support the concept of a jamming phase diagram for attractive colloidal particles, providing a unifying link between the glass transition(3), gelation(4,5) and aggregation(6-8).

An effective gravitational temperature for sedimentation - Segre, P. N.; Liu, F.; Umbanhowar, P.; Weitz, D. A. (Nature, 2001)
The slow sedimentation of suspensions of solid particles in a fluid results in complex phenomena that are poorly understood. For a low volume fraction (phi) of particles, long-range hydrodynamic interactions result in surprising spatial correlations(1) in the velocity fluctuations; these are reminiscent of turbulence, even though the Reynolds number is very low(2-4). At higher values of phi, the behaviour of sedimentation remains unclear; the upward backflow of fluid becomes increasingly important, while collisions and crowding further complicate inter-particle interactions(5-8). Concepts from equilibrium statistical mechanics could in principle be used to describe the fluctuations and thereby provide a unified picture of sedimentation, but one essential ingredient-an effective temperature that provides a mechanism for thermalization-is missing. Here we show that the gravitational energy of fluctuations in particle number can act as an effective temperature. Moreover, we demonstrate that the high-phi behaviour is in fact identical to that at low phi, provided that the suspension viscosity and sedimentation velocity are scaled appropriately, and that the effects of particle packing are included.

Glasslike kinetic arrest at the colloidal-gelation transition - Segre, P. N.; Prasad, V.; Schofield, A. B.; Weitz, D. A. (Physical Review Letters, 2001)
We show that gelation of weakly attractive colloids is remarkably similar to the colloidal glass transition. Like the glass transition, dynamic light scattering functions near gelation scale with scattering vector, and exhibits a two-step decay with a power-law divergence of the final decay time. Like the glass transition, static light scattering does not change upon gelation. These results suggest that, like the glass transition, gelation results from kinetic arrest due to crowding of clusters, and that both gelation and the glass transition are manifestations of a more general jamming transition.

Patterned colloidal coating using adhesive emulsions - Ramos, L.; Weitz, D. A. (Langmuir, 2001)

The effect of solvent and ions on the structure and rheological properties of guar solutions - Gittings, M. R.; Cipelletti, L.; Trappe, V.; Weitz, D. A.; In, M.; Lal, J. (Journal of Physical Chemistry A, 2001)
We study the effect of isopropyl alcohol (IPA) and various salts (sodium chloride, sodium thiocyanate, sodium carbonate, and urea) on the rheological behavior and the conformation of aqueous guar solutions. Ultralow angle light scattering, conventional light scattering, and neutron scattering are used to probe the structure of guar over length scales spanning 5 decades, from a few angstroms to several tens of microns. Although both IPA and salts worsen solvent conditions, their effect is very different. Isopropyl alcohol promotes the formation of a network of large-scale structures via intermolecular associations, thus increasing dramatically the elastic response of guar solutions. Salts. on the contrary, affects guar on a local scale, leading to a more collapsed chain configuration, thus to a lower effective volume fraction and to reduced viscosity.

Real-space imaging of nucleation and growth in colloidal crystallization - Gasser, U.; Weeks, E. R.; Schofield, A.; Pusey, P. N.; Weitz, D. A. (Science, 2001)
Crystallization of concentrated colloidal suspensions was studied in real space with laser scanning confocal microscopy. Direct imaging in three dimensions allowed identification and observation of both nucleation and growth of crystalline regions, providing an experimental measure of properties of the nucleating crystallites. By following their evolution, we identified critical nuclei, determined nucleation rates, and measured the average surface tension of the crystal-liquid interface. The structure of the nuclei was the same as the bulk solid phase, random hexagonal close-packed, and their average shape was rather nonspherical, with rough rather than faceted surfaces.

Three-dimensional confocal microscopy of colloids - A. D. Dinsmore; Weeks, E. R.; Prasad, V.; Levitt, A. C.; Weitz, D. A. (Applied Optics, 2001)
Confocal microscopy is used in the study of colloidal gels, glasses, and binary fluids. We measure the three-dimensional positions of colloidal particles with a precision of approximately 50 nm (a small fraction of each particle's radius) and with a time resolution sufficient for tracking the thermal motions of several thousand particles at once. This information allows us to characterize the structure and the dynamics of these materials in qualitatively new ways, for example, by quantifying the topology of chains and clusters of particles as well as by measuring the spatial correlations between particles with high mobilities. We describe our experimental technique and describe measurements that complement the results of light scattering. (C) 2001 Optical Society of America.

Three-dimensional direct imaging of structural relaxation near the colloidal glass transition - Weeks, E. R.; Crocker, J. C.; Levitt, A. C.; Schofield, A.; Weitz, D. A. (Science, 2000)
Confocal microscopy was used to directly observe three-dimensional dynamics of particles in colloidal supercooled fluids and colloidal glasses. The fastest particles moved cooperatively; connected clusters of these mobile particles could be identified: and the cluster size distribution, structure, and dynamics were investigated. The characteristic cluster size grew markedly in the supercooled fluid as the glass transition was approached, in agreement with computer simulations; at the glass transition, however, there was a sudden drop in their size. The clusters of fast-moving particles were largest near the alpha-relaxation time scale for supercooled colloidal fluids, but were also present, albeit with a markedly different nature, at shorter beta-relaxation time scales, in both supercooled fluid and glass colloidal phases.

Simultaneous imaging and light scattering from biological tissues - Valentine, M. T.; Popp, A. K.; Weitz, D. A.; Kaplan, P. D.; Osa, O. S. A. (Biomedical Optical Spectroscopy and Diagnostics, 2000)
Using a microscope capable of simultaneous imaging and static light scattering, we measure the optical properties of different tissues. We correlate the scattering patterns to local structures and heterogeneities.

Monodisperse emulsion generation via drop break off in a coflowing stream - Umbanhowar, P. B.; Prasad, V.; Weitz, D. A. (Langmuir, 2000)
We describe an experimental technique for the production of highly monodisperse emulsions (with minimum achievable polydispersities <3%). The phase to be dispersed is introduced into a coflowing, surfactant-laden continuous phase via a tapered capillary. Drops detach from the capillary when the streamwise forces exceed the force due to interfacial tension. Drop size is a function of the capillary tip diameter, the velocity of the continuous phase, the extrusion rate, and the viscosities and interfacial tension of the two phases. Emulsions composed of a variety of fluids and with drop sizes ranging from 2 to 200 mu m have been produced using this technique.

Scaling of the viscoelasticity of weakly attractive particles - Trappe, V.; Weitz, D. A. (Physical Review Letters, 2000)
The rheological data of weakly attractive colloidal particles are shown to exhibit a surprising scaling behavior as the particle volume fraction, phi, or the strength of the attractive interparticle interaction, U, are varied. There is a critical onset of a solid network as either phi or U increase above critical values. For all solidlike samples, both the frequency-dependent linear viscoelastic moduli, and the strain-rate dependent stress can be scaled onto universal master curves. A model of a solid network interspersed in a background fluid qualitatively accounts for this behavior.

Diffusing acoustic wave spectroscopy of fluidized suspensions - Page, J. H.; Cowan, M. L.; Weitz, D. A. (Physica B, 2000)
The velocity fluctuations and local strain rate in a fluidized suspension of particles are investigated using the new ultrasonic technique of diffusing acoustic wave spectroscopy. DAWS probes the relative motion of the particles at very short length scales down to the inter-particle separation, and allows the spatial correlations of the velocity fluctuations to be probed by varying the transport mean free path of the diffusing ultrasonic waves. Our results demonstrate the power of this ultrasonic technique to probe the dynamics of sedimenting particles at larger length scales and Reynolds numbers than can be achieved by light scattering methods. (C) 2000 Elsevier Science B.V. All rights reserved.

Rheology of F-actin solutions determined from thermally driven tracer motion - Mason, T. G.; Gisler, T.; Kroy, K.; Frey, E.; Weitz, D. A. (Journal of Rheology, 2000)
We report measurements of the frequency-dependent complex shear modulus of semidilute F-actin solutions based on optical observations of the thermally excited motion of monodisperse tracer microspheres. Because the tracer spheres cause incident laser light to be strongly scattered, we determine their average motion using diffusing wave spectroscopy. From the measured mean square displacement, we extract the retardation spectrum of the actin solution using st regularized fit based on a discretized model involving a linear superposition of harmonically bound Brownian particles. At an actin concentration of C = 1.2 mg/ml and for microspheres of radius a = 0.8 mu m, we find that the complex modulus exhibits a dominant low frequency plateau modulus and a high frequency rise with the loss modulus dominating above a crossover frequency. Over a limited range of frequencies well above the crossover frequency, the magnitude of the high frequency storage modulus G'(omega) is consistent with the power law scaling omega(3/4). The observed gradual crossover appears to be at odds with previous theoretical predictions, but it corresponds to a simple structure of the retardation spectrum. (C) 2000 The Society of Rheology. [S0148-6055(00)00904-4].

Entropically driven colloidal crystallization on patterned surfaces - Lin, K. H.; Crocker, J. C.; Prasad, V.; Schofield, A.; Weitz, D. A.; Lubensky, T.C.; Yodh, A. G. (Physical Review Letters, 2000)
We investigate the self-assembly of colloidal spheres on periodically patterned templates. The surface potentials and the surface phases are induced entropically by the presence of dissolved, nonadsorbing polymers. A rich variety of two-dimensional fluidlike and solidlike phases was observed to form on template potentials with both one- and two-dimensional symmetry. The same methodology was then used to nucleate an oriented single fee crystal more than 30 layers thick. The general approach provides a new route for directed self-assembly of novel mesoscopic structures.

Assembly of binary colloidal structures via specific biological adhesion - Hiddessen, A. L.; Rodgers, S. D.; Weitz, D. A.; Hammer, D. A. (Langmuir, 2000)
We present a novel approach to the fabrication of binary colloidal materials where specific biomolecular cross-linking drives the self-assembly of bidisperse colloidal suspensions. In particular, we have employed low-affinity immune system carbohydrate-selectin interactions to mediate the heterotypic assembly of binary colloidal structures. Using small (0.94 mum) and larger (5.5 mum) diameter particles coated with complementary chemistry, we show that a progressive series of structures, such as colloidal micelles (a large particle coated with smaller particles), colloidal clusters, rings, and elongated chains, can be made by decreasing the number fraction, N-A/N-B, Of Small (A) to large (B) particles (200 greater than or equal to N-A/N-B greater than or equal to 2) at low total volume fraction (phir = 10(-4)-10(-3)). The assembly is due to specific molecular interactions, as control experiments in which the molecules are blocked or eliminated do not lead to the assembly of these structures. The size of the structures can be modulated by time or total volume fraction. Currently, our methods employ high molecular surface densities, such that the structures result from kinetically trapped, diffusion-limited assembly. Ultimately, with the ability to control the strength of the interaction (using different chemistries and molecular surface densities) as well as the lengths of the molecular tethering arms, particle number densities, and physical properties of the colloidal components, this colloidal assembly driven by specific interactions should yield new materials with many potential technological applications including optical filters, sensors, and separation media.

Structure of guar in solutions of H2O and D2O: An ultra-small-angle light-scattering study - Gittings, M. R.; Cipelletti, L.; Trappe, V.; Weitz, D. A.; In, M.; Marques, C. (Journal of Physical Chemistry B, 2000)
We examine the structure of guar as a function of concentration in both H2O and D2O using several different scattering techniques. The range of scattering vectors spans 5 decades (143 cm(-1) < q < 10.3 x 10(6) cm(-1)), providing insight into the supramolecular and local, organization of the chains. This allows us to directly characterize the large-scale aggregate structure of the guar, which can be on the order of 100 mu m. The aggregates are most likely loosely interconnected with single chains and other aggregates, and the structure and organization are critical in determining solution viscoelastic properties. The solubility is poorer in D2O, as evidenced by larger aggregates, higher scattering intensities, a slightly higher fractal dimension, and a sublinear concentration dependence of the intensity. Aggregates were found in dilute neutral guar solutions as well as in cationic guar solutions (in H2O), whether screened or unscreened. The presence of aggregates at all concentrations for neutral and charged guar indicates the difficulty in determining a molecular weight of the guar molecule.

Two-point microrheology of inhomogeneous soft materials - Crocker, J. C.; Valentine, M. T.; Weeks, E. R.; Gisler, T.; Kaplan, P. D.; Yodh, A. G.; Weitz, D. A. (Physical Review Letters, 2000)
We demonstrate a novel method for measuring the microrheology of soft viscoelastic media, based on cross correlating the thermal motion of pairs of embedded tracer particles. The method does not depend on the exact nature of the coupling between the tracers and the medium, and yields accurate rheological data for highly inhomogeneous materials. We demonstrate the accuracy of this method with a guar solution, for which other microscopic methods fail due to thr polymer's mesoscopic inhomogeneity. Measurements in an F-actin solution suggest conventional microrheology measurements may not reflect the true bulk behavior.

Velocity fluctuations in fluidized suspensions probed by ultrasonic correlation spectroscopy - Cowan, M. L.; Page, J. H.; Weitz, D. A. (Physical Review Letters, 2000)
Velocity fluctuations in a fluidized suspension of particles are investigated using two new ultrasonic correlation spectroscopies: diffusing acoustic wave spectroscopy and dynamic sound scattering. These techniques probe both the local strain rate and rms velocity of the particles, providing important information about the spatial extent of velocity correlations. Our results demonstrate the power of these techniques to probe particle dynamics of fluidized suspensions, and suggest that the velocity correlations are essentially independent of Reynolds numbers for Re-p < 1.

Universal aging features in the restructuring of fractal colloidal gels - Cipelletti, L.; S. Manley; Ball, R. C.; Weitz, D. A. (Physical Review Letters, 2000)
We use multispeckle dynamic light scattering to measure the dynamic structure factor, f(q, tau), of gels formed by aggregation of colloids. Although the gel is an elastic solid, f(q, tau) nearly completely decays on long time scales, with an unusual form, f(q, tau) similar to exp{-(tau/tau(f))(mu)}, with mu approximate to 1.5 and with tau(f) proportional to q(-1) A model for restructuring of the gel with aging correctly accounts for this behavior. Aging leads to a dramatic increase in tau(f) however, all data can be scaled on a single master curve, with tau(f) asymptotically growing linearly with age. This behavior is strikingly similar to that predicted for aging in disordered glassy systems, offering convincing proof of the universality of these concepts.

Energy Velocity of Diffusing Waves in Strongly Scattering Media – Reply - Schriemer, H. P.; Cowan, M. L.; Page, J. H.; Seng, Ping; Liu, Zhengyou; Weitz, D. A. (Physical Review Letters, 1999)
A Reply to the Comment by C. M. Soukoulis et al.

Light-scattering microscope - Kaplan, Peter D.; Trappe, Veronique; Weitz, DavidA. (Applied Optics, 1999)
We demonstrate a new design for a light-scattering microscope that is convenient to use and that allows simultaneous imaging and light scattering. The design is motivated by the growing use of thermal fluctuations to probe the viscoelastic properties of complex inhomogeneous environments. We demonstrate measurements of an optically nonergodic sample, one of the most challenging light-scattering applications.

Particle-stabilized defect gel in cholesteric liquid crystals - Zapotocky, M.; Ramos, L.; Poulin, P.; Lubensky, T.C.; Weitz, D. A. (Science, 1999)
Dispersions of colloidal particles in cholesteric liquid crystals form an unusual solid by stabilizing a network of linear defects under tension in the ideal layered structure of the cholesteric. The large length scales of the cholesteric liquid crystals allowed direct observation of the network structure, and its properties were correlated with rheological measurements of elasticity. This system serves as a model for a class of solids formed when particles are mixed with layered materials such as thermotropic and lyotropic smectic liquid crystals and block copolymers.

Wave transport in random media: The ballistic to diffusive transition - Zhang, Z. Q.; Jones, I. P.; Schriemer, H. P.; Page, J. H.; Weitz, D. A.; Sheng, P. (Physical Review E, 1999)
The character of wave transport through a strongly scattering medium, excited by a pulsed plane-wave source, is investigated as a function of sample thickness over the range from about one to 13 mean free paths. To examine the behavior theoretically, we perform a first-principles calculation of both the frequency correlation function of the transmitted field and the time-domain profile of the transmitted intensity. These quantities are investigated experimentally using an ultrasonic technique, which allows us to separate the ballistic and scattered components of the total transmitted field, and hence to measure the scattered component unambiguously in thin samples. For sample thicknesses greater than about four mean free paths, we find good agreement between our theory, the diffusion approximation, and our experimental: data for both the frequency correlation function and the intensity time profile. In thinner samples, there are systematic differences between theory and experiment. To characterize the transition from ballistic to diffusive behavior in thin samples, we focus on the arrival time of the peak in the scattered component of the transmitted intensity; unexpectedly we find that the scattered peak arrival time exhibits an abrupt crossover between ballistic and diffusive behavior when the ratio of sample thickness to mean free path, L/l, is approximately equal to 3. Excellent agreement is obtained between our theory and experiment for this crossover behavior over the entire range of sample thicknesses investigated. [S1063-651X(99)12009-9].

Surfactant-mediated two-dimensional crystallization of colloidal crystals - Ramos, L.; Lubensky, T.C.; Dan, N.; Nelson, P.; Weitz, D. A. (Science, 1999)
Colloidal particles can form unexpected two-dimensional ordered colloidal crystals when they interact with surfactants of the opposite charge. Coulomb interactions Lead to self-limited adsorption of the particles on the surface of vesicles formed by the surfactants. The adsorbed particles form ordered but fluid rafts on the vesicle surfaces, and these ultimately form robust two-dimensional crystals. This use of attractive Coulomb interaction between colloidal particles and surfactant structures offers a potential new route to self-assembly of ordered colloidal structures.

From colloidal aggregation to spinodal decomposition in sticky emulsions - Poulin, P.; Bibette, J.; Weitz, D. A. (European Physical Journal B, 1999)
Aggregation mechanisms of emulsions at high initial volume fractions (phi(0) >. 0.01) is studied using light scattering. We use emulsion droplets which can be made unstable towards aggregation by a temperature quench. For deep quenches and 0.1 > phi(0) > 0.01, the aggregation mechanism is identified as diffusion-limited cluster aggregation (DLCA). An ordering of the clusters, which is reflected by a peak in the scattering intensity, is shown to result from the intercluster separation, exhibiting different scaling than that observed at lower volume fractions. This manifests an increasing similarity to spinodal decomposition observed as phi(0) is increased. For bo > 0.1 and shallow quenches, different mechanisms, closer to spinodal decomposition, are observed. These results allow the subtle boundaries between DLCA and spinodal decomposition to be explored.

Diffusive transport of acoustic waves in strongly scattering media - Page, J. H.; Jones, I. P.; Schriemer, H. P.; Cowan, M. L.; Sheng, P.; Weitz, D. A. (Physica B, 1999)
The diffusive transport of multiply scattered ultrasonic waves is investigated experimentally and theoretically in a simple system consisting of glass beads in water. New experimental results are presented using a novel method for measuring the frequency correlation function of the transmitted acoustic field. The wave diffusion coefficient D is found to vary strongly with frequency when the wavelength is comparable to the size of the scatterers, reflecting a substantial slowing down of wave propagation when the scattering is strongest. The results are interpreted using a model based on a spectral function approach that gives good agreement with experiment. (C) 1999 Elsevier Science B.V. All rights reserved.

Viscoelasticity of depletion-induced gels in emulsion-polymer systems - A. Meller; Gisler, T.; Weitz, D. A.; Stavans, J. (Langmuir, 1999)
Using rheometry and light scattering, we have studied the viscoelasticity of gels formed by the kinetically arrested phase separation in an emulsion-polymer mixture; to prevent the gels From collapsing under their own weight, we have used an isopycnic solvent. At constant osmotic pressure (set by the polymer concentration) and droplet volume fractions phi well, above the gelation transition, we find the elastic modulus to increase roughly linearly with phi, indicating an entropic elasticity based on the cluster packing.

Interactions between surfactant-coated surfaces in hydrocarbon liquids containing functionalized polymer dispersant - Giasson, S.; Weitz, D. A.; Israelachvili, J. N. (Colloid and Polymer Science, 1999)
The forces and viscosity between calcium benzene sulfonate surfactant-coated mica surfaces in various hydrocarbon liquids containing a polyamine-functionalized hydrocarbon polymer (M-W approximate to 8000) have been measured using the surface forces apparatus technique. The polymer is found to adsorb to the substrate surfaces by displacing the surfactant layer, and to produce forces that are monotonically repulsive. The forces have a maximum range of 50-100 nm (>3R(H)), indicating that tails play a particularly important role in the interaction of this relatively low molecular weight polymer. The forces become steeply repulsive below about 10 nm (similar to 0.6R(H)), at which point a "hardwall" repulsion comes in that can sustain pressures greater than 100 atm. Thin-film viscosity measurements indicate that the far-field positions of the slipping planes Delta(H) depend on the shear rate, showing that significant shear thinning/thickening effects occur within the outermost tail regions of the adsorbed layers during shear. The position of the slipping plane, or hydrodynamic layer thickness Delta(H), varies from 0.6R(H) to 2R(H) away from each surface (mica and surfactant-coated mica surfaces). Beyond the hydrodynamic layer the far-field fluid viscosity is the same as that of the bulk polymer solution. At separations below D = 2 Delta(H) the viscosity increases as each polymer layer is compressed. The static forces exhibited various time- and history-dependent effects, which further indicate that a number of different relaxation/equilibration processes are operating simultaneously in this complex multicomponent system. The results reveal that the interactions of tails of functionally adsorbed polymers play a more important role than previously thought. This is especially true in this study where the adsorbed polymers are of low molecular weight and where the tails may represent the largest fraction of interacting segments.

Scaling of the microrheology of semidilute F-actin solutions - Gisler, T.; Weitz, D. A. (Physical Review Letters, 1999)
The viscoelasticity of actin networks is probed over an extended range of frequencies using microrheology techniques, where the thermal motion of small beads in the network is measured using diffusing-wave spectroscopy. Despite large sample-to-sample variations, the data exhibit an unexpected scaling behavior and can all be collapsed onto a single master curve, indicative of a surprising universality in the elastic properties. The scaled data provide a precise measure of the average behavior of the actin networks and indicate that at high frequencies omega, the shear modulus, increases as omega(3/4).[S0031-9007(99)08465-3].

Strain hardening of fractal colloidal gels - Gisler, T.; Ball, R.; Weitz, D. A. (Physical Review Letters, 1999)
We report on experiments on the rheology of gels formed by diffusion-limited aggregation of neutrally buoyant colloidal particles. These gels form very weak solids, with the elastic modulus, G'(omega), larger than the loss modulus, G "(omega), and with both G'(omega) and G "(omega) exhibiting only a very weak frequency dependence. Upon small but finite strains gamma < 0.45 the elastic modulus increases roughly exponentially with gamma(2). We explain the observed strain hardening with the highly nonlinear elastic response of the rigid backbone of the gel to elongational deformation.

Emulsion glasses: A dynamic light-scattering study - Gang, H.; Krall, A. H.; Cummins, H. Z.; Weitz, D. A. (Physical Review E, 1999)
A liquid-glass transition was observed experimentally in a new system, an oil-in-water emulsion. Dynamic light scattering was employed to obtain the intermediate scattering function f(q,t) for a range of volume fractions phi and scattering vectors q. The results are compared with predictions of the mode coupling theory. While the usual idealized version of the theory provides accurate fits to the data on the Liquid side of the transition, fits for volume fractions near the transition and in the glass phase were found to require the extended version, presumably due to an additional decay mechanism related to the deformability of the oil droplets. [S1063-651X(99)04901-6].

Ultralow-angle dynamic light scattering with a charge coupled device camera based multispeckle, multitau correlator - Cipelletti, L.; Weitz, D. A. (Review of Scientific Instruments, 1999)
We use a charge coupled device (CCD) camera and a multi-tau software correlator to measure dynamic light scattering (DLS) at many angles simultaneously, from 0.07 degrees to 5.1 degrees. Real-time autocorrelation functions are calculated by averaging both over time and over CCD pixels, each corresponding to a different coherence area. In order to cover the wide spectrum of decay times associated with the large range of accessible angles, we adopt the multitau scheme, where the correlator channel spacing is quasilogarithmic rather than linear. A detailed analysis is presented of the effects of dark noise, stray light, and finite pixel area, and methods to correct the data for these effects are developed, making a CCD camera a viable alternative for a DLS detector. We test the apparatus on a dilute suspension of colloidal particles. Very good agreement is found between the particle radius derived from the CCD data, and that obtained with a conventional DLS setup. (C) 1999 American Institute of Physics. [S0034-6748(99)05008-X].

Electrostatic repulsion of positively charged vesicles and negatively charged objects - Aranda-Espinoza, H.; Chen, Y.; Dan, N.; Lubensky, T.C.; Nelson, P.; Ramos, L.; Weitz, D. A. (Science, 1999)
A positively charged, mixed bilayer vesicle in the presence of negatively charged surfaces (for example, colloidal particles) can spontaneously partition into an adhesion zone of definite area and another zone that repels additional negative objects, Although the membrane itself has nonnegative charge in the repulsive zone, negative counterions on the interior of the vesicle spontaneously aggregate there and present a net negative charge to the exterior. Beyond the fundamental result that oppositely charged objects can repel, this mechanism helps to explain recent experiments on surfactant vesicles.

Inverted and multiple nematic emulsions - Poulin, P.; Weitz, D. A. (Physical Review E, 1998)
We investigate experimentally the structures that form when small colloidal particles are suspended in a nematic solvent. These structures are anisotropic, and their formation is driven by interactions arising from the orientational elasticity of the nematic solvent. By using inverted and multiple nematic emulsions composed of water droplets dispersed in a thermotropic liquid crystal, we identify the nature of these interactions, and demonstrate that they can be controlled by the anchoring of the liquid crystal molecules at the surfaces of the droplets. When the anchoring is normal, the droplets form linear chains, suggesting a long-range dipole-dipole attraction between the particles. By contrast, the interactions are repulsive at short range, and prevent contact of the droplets, thereby stabilizing them against coalescence. When the anchoring is planar, the droplets generate distortions that have a quadrupolar character. The resultant elastic interactions lead to more compact, but still anisotropic, clusters.

Internal dynamics and elasticity of fractal colloidal gels - Krall, A. H.; Weitz, D. A. (Physical Review Letters, 1998)
The dynamic structure factor of fractal colloidal gels is shown to exhibit a stretched exponential decay to a finite plateau with an exponent of about 0.7. The value of the plateau depends on both initial particle volume fraction phi(0) and scattering wave vector. We show that this behavior results from the contribution of internal elastic modes of many length scales, and present a model which accounts for the data. From the observed plateau we determine that the very small elastic modulus scales as G similar to phi(0)(3.9), in agreement with predictions, and with direct mechanical measurements.

Rotational diffusion of monodisperse liquid crystal droplets - P. Hsu; Poulin, P.; Weitz, D. A. (Journal of Colloid and Interface Science, 1998)
We have prepared monodisperse suspensions of nematic liquid crystal droplets in water. The droplets are stabilized by polyvinyl alcohol, a polymer that induces planar anchoring of the liquid crystal molecules at the surface of the droplets. The resultant particles exhibit strong optical anisotropy while having a spherical shape. As a consequence, the light scattering from the particles contains a strong depolarized component. We report a simple application of this feature by performing dynamic light scattering experiments to measure the rotational diffusion of colloidal spheres in a dilute suspension. (C) 1998 Academic Press.

Tracer microrheology in complex fluids - Gisler, T.; Weitz, D. A. (Current Opinion in Colloid & Interface Science, 1998)
Recent results suggest that the motion of colloidal particles can be interpreted in terms of the viscoelasticity of the surrounding medium. New experimental techniques to extend these probe measurements and new methods for data interpretation have been developed.

Diffusion in a different direction - Weitz, D. A. (Nature, 1997)
Diffusion of particles or molecules in a fluid is an essential manifestation of thermal energy. It is seen in the familiar brownian motion of dust particles in a fluid or a gas, and it ensures the mixing of different molecules in a fluid. So mixing, at the shortest length scales, results from diffusion rather than convection. This is behind a standard method for measuring molecular diffusion coefficients: a sharp concentration gradient is established between two fluids, and the decay of this gradient as the two fluids mix determines the diffusion coefficient of one fluid in the second. Observers look in a direction perpendicular to the gradient (that is, with the interface edge-on), and the results are interpreted assuming a smooth relaxation of the concentration gradient. But that may not be valid: on page 262 of this issue, a team from Milan report unexpected spatial fluctuations in the concentration of two fluids mixing by diffusion.

Energy velocity of diffusing waves in strongly scattering media - Schriemer, H. P.; Cowan, M. L.; Page, J. H.; Sheng, P.; Liu, Z. Y.; Weitz, D. A. (Physical Review Letters, 1997)
Measurements of the diffusive transport of multiply scattered ultrasonic waves show that the energy velocity is very similar in magnitude and frequency dependence to the group velocity. Our data are accurately described using a theoretical model that accounts for the renormalization of scattering by the coupling between neighboring scatterers, quantitatively predicting the scattering delay that causes the strong frequency dependence of these velocities seen in our experiments. This gives a unified physical picture of the velocities of energy transport by both diffusive and ballistic waves.

Direct measurement of colloidal forces in an anisotropic solvent - Poulin, P.; Cabuil, V.; Weitz, D. A. (Physical Review Letters, 1997)
We present a new method to measure attractive interactions between colloidal particles, and determine the nature of the attraction between particles suspended in a nematic liquid crystal, We confine droplets filled with ferrofluid to a thin layer and apply a magnetic field to induce dipole moments that drive the droplets apart. When the field is removed, the attractive interactions pull the droplets back together. The force is determined from the velocity because the motion is viscously damped. We confirm the dipolar character of the interaction between droplets in a nematic solvent.

Novel colloidal interactions in anisotropic fluids - Poulin, P.; Stark, H.; Lubensky, T.C.; Weitz, D. A. (Science, 1997)
Small water droplets dispersed in a nematic liquid crystal exhibit a novel class of colloidal interactions, arising from the orientational elastic energy of the anisotropic host fluid. These interactions include a short-range repulsion and a long-range dipolar attraction, and they lead to the formation of anisotropic chainlike structures by the colloidal particles, The repulsive interaction can lead to novel mechanisms for colloid stabilization.

Classical wave propagation in strongly scattering media - Page, J. H.; Schriemer, H. P.; Jones, I. P.; Sheng, P.; Weitz, D. A. (Physica A, 1997)
The transport of classical waves in strongly scattering media is investigated using ultrasonic techniques, allowing us to measure both the ballistic and scattered components of the wave field. We fmd that the ballistic propagation is dramatically slowed down by scattering resonances, although the group velocity remains well-defined. The propagation of the scattered waves is also strongly affected by resonant scattering, and is shown to be well described by using the diffusion approximation. A model based on the generalized coherent potential approximation gives a quantitative explanation of the experimental data.

Diffusing-wave-spectroscopy measurements of viscoelasticity of complex fluids - Mason, T. G.; Gang, H.; Weitz, D. A. (Journal of the Optical Society of America A, 1997)
We present a new use of dynamic light scattering that permits the determination of the viscoelastic behavior of a complex fluid. By describing the motion of a scattering particle in a viscoelastic medium in terms of a generalized Langevin equation with a memory function, we relate the time evolution of its mean-square displacement to the frequency-dependent storage and loss moduli of the medium. The utility of this technique is illustrated through the application of diffusing-wave spectroscopy to probe the viscoelastic behavior of two complex fluids. The properties of a concentrated suspension of colloidal particles interacting as hard spheres are shown to be strongly influenced by the incipient colloidal glass transition, which leads to an extended range of frequencies over which they behave like an elastic solid. Similar elasticity is observed in a compressed emulsion, resulting in this case from the additional interfacial energy of the deformed droplets. In both cases diffusing-wave spectroscopy is used to measure the frequency dependence of the storage and loss moduli, and these results are compared with those from mechanical measurements. Besides providing a purely optical method for measuring mechanical properties, this technique provides new insight into the origin of the viscoelastic behavior.

Osmotic pressure and viscoelastic shear moduli of concentrated emulsions - Mason, T. G.; Lacasse, M. D.; Grest, G. S.; Levine, D.; Bibette, J.; Weitz, D. A. (Physical Review E, 1997)
We present an experimental study of the frequency omega dependence and volume fraction phi dependence of the complex shear modulus G*(omega,phi) of monodisperse emulsions which have been concentrated by an osmotic pressure Pi. At a given phi, the elastic storage modulus G'(omega)=Re[G*(omega)] exhibits a low-frequency plateau G'(p), dominating the dissipative loss modulus G''(omega)=Im[G*(omega)] which exhibits a minimum. Above a critical packing fraction phi(c), we find that both Pi(phi) and G'(p)(phi) increase quasilinearly, scaling as (phi-phi(c))(mu), where phi(c) approximate to phi(c)(rcp), the volume fraction of a random close packing of spheres, and mu is an exponent close to unity. To explain this result, we develop a model of disordered droplets which interact through an effective repulsive anharmonic potential, based on results obtained for a compressed droplet. A simulation based on this model yields a calculated static shear modulus G and osmotic pressure Pi that are in excellent agreement with the experimental values of G'(p) and Pi.

Dynamics of density fluctuations in colloidal gels - Krall, A. H.; Huang, Z; Weitz, D. A. (Physica A, 1997)
We use dynamic light scattering to measure the dynamic structure factor of density fluctuations occurring in colloidal suspensions that have attained a quiescent state long after aggregation. We find a stretched-exponential decay to a finite plateau. Our interpretation of the arrested decay is that these systems are gels, i.e., systems possessing a finite elastic modulus G. We develop a theory for the internal elastic modes of a fractal cluster and use it to derive G and the arrested, stretched-exponential behavior of colloidal gel dynamics. Good agreement between experiment and theory is obtained.

Monodisperse Emulsions: Properties and Uses - Mason, T. G.; Krall, A. H.; Gang, H.; Bibette, J.; Weitz, D. A. (Encyclopedia of Emulsion Technology, 1996)

Materials - Foams flow by stick and slip - Weitz, D. A. (Nature, 1996)

Group velocity in strongly scattering media - Page, J. H.; Sheng, P.; Schriemer, H. P.; Jones, I.; Jing, X. D.; Weitz, D. A. (Science, 1996)
Investigation of the ballistic propagation of acoustic waves through a resonantly scattering, Inhomogeneous medium indicates that although the ballistic signal remains coherent with the incident pulse, it is nevertheless strongly affected by scattering resonances. These resonances cause considerable frequency dispersion and substantially reduce the phase and group velocities. The experimental data are quantitatively described by a theoretical model that correctly accounts for the coupling between the resonant scatterers, leading to an effective renormalization of the scattering within the medium. This approach; resolves a long-standing problem in the definition of the group velocity in strongly scattering materials.

Rheology of complex fluids measured by dynamic light scattering - Mason, T. G.; Gang, H.; Weitz, D. A. (Journal of Molecular Structure, 1996)
We introduce a method for using dynamic light scattering to measure the frequency-dependent linear viscoelastic moduli of complex fluids. The technique exploits the fluctuation dissipation theorem, which relates the relaxation of thermal excitations of a probe particle to the viscoelastic properties of the surrounding medium. The relaxation of the thermal excitations of probe particles are determined by measuring the time evolution of the mean square displacement using dynamic light scattering. A Langevin equation with a time-dependent damping term is used to relate this mean square displacement to the dynamic shear modulus of the medium. This method probes the linear viscoelastic moduli over a much larger frequency range than traditional mechanical means, and in particular, easily extends their measurement to much higher frequencies.

Yielding and flow of monodisperse emulsions - Mason, T. G.; Bibette, J.; Weitz, D. A. (Journal of Colloid and Interface Science, 1996)
We have measured the yield transition of monodisperse emulsions as the volume fraction, phi, and droplet radius, alpha, are varied. We study the crossover from the perturbative shear regime, which reflects the linear viscoelastic properties, to the steady shear regime, which reflects nonlinear, plastic flow. For small oscillatory strains of peak amplitude gamma, the peak stress, tau, is linearly proportional to gamma. As the strain is increased, the stress becomes nonlinear in gamma at the yield strain, gamma(y). The phi dependence of gamma(y) is independent of alpha and exhibits a minimum near the critical volume fraction, phi(c) approximate to 0.635, associated with the random close packing of monodisperse spheres. We show that the yield stress, tau(y), increases dramatically as the volume fraction increases above phi(c); tau(y) also scales with the Laplace pressure, sigma/alpha, where sigma is the interfacial tension. For comparison, we also determine the steady shear stress over a wide range of strain rates, gamma. Below phi approximate to 0.70, the flow is homogeneous throughout the sample, while for higher phi, the emulsion fractures resulting in highly inhomogeneous flow along the fracture plane. Above phi approximate to 0.58, the steady shear stress exhibits a low strain rate plateau which corresponds with the yield stress measured with the oscillatory technique. Moreover, tau(y) exhibits a robust power law dependence on gamma with exponents decreasing with phi, varying from 2/3 to 1/2. Below phi approximate to 0.58, associated with the colloidal glass transition, the plateau stress disappears entirely, suggesting that the equilibrium glassy dynamics are important in identifying the onset of the yield behavior. (C) 1996 Academic Press, Inc.

Anomalous viscous loss in emulsions - Liu, A. J.; Ramaswamy, S.; Mason, T. G.; Gang, H.; Weitz, D. A. (Physical Review Letters, 1996)
We propose a model for concentrated emulsions based on the speculation that a macroscopic shear strain does not produce an affine deformation in the randomly close-packed droplet structure. The model yields an anomalous contribution to the complex dynamic shear modulus that varies as the square root of frequency. We test this prediction using a novel light scattering technique to measure the dynamic shear modulus, and directly observe the predicted behavior over six decades of frequency and a wide range of volume fractions.

Model for the elasticity of compressed emulsions - Lacasse, M. D.; Grest, G. S.; Levine, D.; Mason, T. G.; Weitz, D. A. (Physical Review Letters, 1996)
We present a new model to describe the unusual elastic properties of compressed emulsions. The response of a single droplet under compression is investigated numerically for different Wigner-Seitz cells. The response is softer than harmonic, and depends on the coordination number of the droplet. Using these results, we propose a new effective interdroplet potential which is used to determine the elastic response of a monodisperse collection of disordered droplets as a function of volume fraction. Our results are in excellent agreement with recent experiments. This suggests that anharmonicity together with disorder are responsible for the quasilinear increase of G and Pi observed at phi(c).

Scaling of transient hydrodynamic interactions in concentrated suspensions - Reply - Weitz, D. A.; Ladd, A. J. C. (Physical Review Letters, 1995)
A Reply to the Comment by E. G. D. Cohen and I. M. de Schepper.

Adsorption and desorption of a wetting fluid in vycor studied by acoustic and optical techniques - Page, J. H.; Liu, J.; Abeles, B.; Herbolzheimer, E.; Deckman, H. W.; Weitz, D. A. (Physical Review E, 1995)
We study the adsorption and desorption of hexane in porous Vycor, as the ambient vapor pressure is varied, through sorption isotherm, ultrasonic velocity and attenuation, and light scattering measurements. On adsorption, we show that the fluid fills the pore space uniformly until capillary condensation occurs; however, small, randomly distributed, vapor bubbles remain, as detected by a large increase in the attenuation of the ultrasound. On desorption, the mismatch in the index of refraction between the empty pores and the surrounding filled pores leads to intense scattering of light that reveals the presence of long-range correlations in the pore space. These correlations have a fractal dimension of 2.6, which is very near the value predicted for invasion percolation. Finally, we also investigate the time dependence of the changes in the adsorbed fluid mass and use these measurements to identify three distinct regimes with vastly differing mechanisms for mass transport. The results presented here provide information on the differences in pore-space correlations on filling and drainage, and highlight the critical role of the connectivity of the pores to the surface in determining the desorption behavior.

Experimental test of the diffusion-approximation for multiply scattered sound - Page, J. H.; Schriemer, H. P.; Bailey, A. E.; Weitz, D. A. (Physical Review E, 1995)
We have critically tested the application of the diffusion approximation to describe the propagation of ultrasonic waves through a random, strongly scattering medium. The transmission of short ultrasonic pulses has been measured through a concentrated suspension of glass beads immersed in water. The transmitted sound field is found to exhibit temporal fluctuations with a period determined by the width of the incident pulse. Provided that appropriate boundary conditions are used to account for the reflectivity of the interfaces, the time dependence of the ensemble-averaged transmitted intensity is shown to be well described by the diffusion equation. This enables us to determine both the diffusion coefficient for the sound waves as well as the inelastic absorption rate. The consistency of these results is established by varying the experimental geometry; while the transmitted pulse shape changes markedly, the values for the diffusion coefficient and absorption rate obtained through a description using the diffusion approximation remain unchanged. We have also measured the absolute transmitted intensity of the sound as the sample thickness is varied; this provides an accurate measure of the transport mean free path and thus also the energy transport velocity. These results convincingly demonstrate the validity of using the diffusion approximation to describe the propagation of sound waves through strongly scattering media.

Linear viscoelasticity of colloidal hard-sphere suspensions near the glass-transition - Mason, T. G.; Weitz, D. A. (Physical Review Letters, 1995)
The frequency-dependent viscoelastic shear modulus of concentrated suspensions of colloidal hard spheres is shown to be strongly modified as the volume fraction approaches the glass transition. The elastic or storage component, G', becomes larger than the viscous or loss component, G''. The frequency dependence of G' develops a plateau while that of G'' develops a minimum. We propose a physical model to account for these data, using a description of the glasslike behavior based on mode-coupling theory, and a description of the high-frequency behavior based on hydrodynamic flow calculations.

Optical measurements of frequency-dependent linear viscoelastic moduli of complex fluids - Mason, T. G.; Weitz, D. A. (Physical Review Letters, 1995)
We present a novel experimental method to measure linear viscoelastic moduli of complex fluids using dynamic light scattering. A generalized Langevin equation is used to relate the mean square displacement of a probe particle to the storage and loss moduli of the bulk complex fluid. We confirm the experimental validity of this technique by comparing the light scattering results with mechanical measurements for several complex fluids. This method probes the moduli over a greatly extended frequency range and provides significant new insight into the elastic susceptibility of complex fluids.

Elasticity of compressed emulsions - Mason, T. G.; Bibette, J.; Weitz, D. A. (Physical Review Letters, 1995)
The elastic shear modulus of monodisperse emulsions is shown to exhibit a universal dependence on droplet volume fraction phi when scaled by the Laplace pressure of the droplets, increasing as phi(phi - phi(c)). where phi(c) approximate to 0.635, the value of random close packing of solid spheres. Surprisingly the osmotic pressure required to compress the emulsions to increase phi is nearly the same as the shear modulus over a large range of volume fraction, while the bulk osmotic modulus differs significantly. Models based on the structural disorder of the emulsions are discussed to account for these data.

Experimental evidence for the divergence of a transport coefficient in a quasi-2-dimensional fluid - Lin, B. H.; Rice, S. A.; Weitz, D. A. (Physical Review E, 1995)
We report experimental evidence for the divergence of the collective diffusion coefficient in a quasi-two-dimensional fluid. The system studied is a monolayer of nearly monodisperse self-assembled disks of the diblock copolymer polystyrene-b-polymethylmethacrylate, supported in the air/water interface, and the method used to measure the collective diffusion coefficient is dynamic evanescent wave light scattering. In all cases studied, in a system of interacting particles the collective diffusion coefficient, which depends on the sum of the time integrals of the velocity autocorrelation and crosscorrelation functions for all pairs of particles, is proportional to the self-diffusion coefficient. It has been predicted that the self-diffusion coefficient of a two-dimensional fluid does not exist, i.e., that the apparent self-diffusion coefficient defined by the time integral of the velocity autocorrelation function diverges as t→∞, implying that so, also, will the collective diffusion coefficient of a two-dimensional fluid. Our experimental data are consistent with this qualitative expectation and they also agree with the asymptotic dependence on time (t→∞), wave vector (Q→0), and surface density of the self-diffusion coefficient of a two-dimensional fluid predicted by Yuan and Oppenheim [H.H.-H. Yuan and I. Oppenheim, Physica 90A, 1 (1978); 90A, 21 (1978); 90A, 561 (1978)].

Temporal and spatial dependence of hydrodynamic correlations - Simulation and experiment - Ladd, A. J. C.; Gang, H.; Zhu, J. X.; Weitz, D. A. (Physical Review E, 1995)
Time-dependent hydrodynamic interactions in a colloidal suspension of hard spheres are studied, both experimentally and through computer simulation. The focus is on the behavior at small wave vectors, which directly probes the temporal evolution of hydrodynamic interactions between nearby particles. The computer simulations show that the time-dependent diffusion coefficient has the same functional form for all wave vectors, with a single characteristic scaling time for each length scale and for each volume fraction. Wave-vector-averaged effective diffusion coefficients, measured experimentally using diffusing wave spectroscopy, also scale to the same functional form. In this case, the scaling time is dependent on both volume fraction and particle size; it decreases sharply with decreasing particle radius, reflecting the greater contribution from smaller wave vectors that is contained in the scattering from the smaller particles. For a direct comparison of simulation and experiment, we simulate the experimentally observed correlation functions, by averaging the wavevector-dependent computer-simulation data with the weighting appropriate to the experimental technique. Although the overall scaling is similar, there are quantitative differences in the simulated and measured relaxation times. We suggest these differences are due to the compressibility of the suspension, and that the resultant pressure waves make an unexpectedly significant contribution to the hydrodynamic interactions.

Time-dependent collective diffusion of colloidal particles - Ladd, A. J. C.; Gang, H.; Zhu, J. X.; Weitz, D. A. (Physical Review Letters, 1995)
We use a combination of numerical simulations and laboratory experiments to study the time-dependent collective diffusion coefficient D(q, t) in concentrated colloidal suspensions. At short times, the particle configuration is frozen, and D(q, t) probes the temporal and spatial evolution of hydrodynamic interactions, via their effects on the particle velocities. We find that D(q, t) exhibits a surprising scaling behavior, with a single, q-dependent relaxation time, suggesting that the suspension behaves as an effective medium for hydrodynamic interactions over a wide range of length scales and time scales.

The density of aggregated polystyrene spheres - Huang, Z; Krall, A. H.; Weitz, D. A. (Journal of Colloid and Interface Science, 1995)
We show that density measurements can provide an alternative method for determining the number and species of ions adsorbed onto colloidal particles. We cause charge-stabilized colloidal dispersions of polystyrene spheres to aggregate by adding various salts. The solvents are mixtures of H2O and D2O in which the colloids are neutrally buoyant after aggregation, which we verify by centrifugation of the samples, By this method we are able to determine the density of the aggregated colloids. We find that the density depends on the species of salt added to initiate the aggregation and can be calculated on the assumption that a cation of the added salt binds with each ionizable group on the surface of the colloidal particles. (C) 1995 Academic Press, Inc.

Thermal fluctuations of the shapes of droplets in dense and compressed emulsions - Gang, H.; Krall, A. H.; Weitz, D. A. (Physical Review E, 1995)
We generalize the theory of diffusing-wave spectroscopy (DWS) to include the effects of fluctuations of the amplitudes of the scattered fields. Thus DWS can be used to probe the internal dynamics of flexible particles. We study the thermally induced shape fluctuations of monodisperse emulsion droplets as a function of the droplet volume fraction phi. We find that a droplet's mean-squared deviation from spherical shape increases with phi, while the characteristic rate of relaxation of the shape deformations decreases with phi. Our generalization of the theory of DWS allows us to measure the autocorrelation function of the fluctuating amplitude of the field scattered from a droplet. We use fluid dynamics and scattering theory to calculate this autocorrelation function theoretically for an isolated droplet. The significant contribution of many independent modes of deformation results in a distinctly nonexponential relaxation. The measured behavior agrees with the theory as phi approaches zero. At higher values of phi throughout the range of colloidal liquids we find a surprising scaling behavior, which implies that particle interactions bring about the enhancement and slowing down of shape fluctuations without altering the spectrum of excited deformation modes. We relate the form of the scaling function to the particle radial distribution function. In ''compressed'' emulsions with phi as high as 0.8, shape fluctuations may be the only dynamical behavior that can occur. We suggest that in these systems the amplitude of the shape fluctuations is related to the emulsion's elastic modulus.

Diffusing-wave spectroscopy and interferometry - Weitz, D. A.; Pine, D.J. (MRS Bulletin, 1994)

Shape fluctuations of interacting fluid droplets - Gang, H.; Krall, A. H.; Weitz, D. A. (Physical Review Letters, 1994)
We study the thermally induced shape fluctuations of monodisperse emulsion droplets. The very small amplitude of these fluctuations is clearly resolved by diffusing wave spectroscopy and a theory is derived to describe the measured data. We measure the dependence of the fluctuations on droplet volume fraction φ, thereby directly probing the interplay between droplet interactions and droplet flexibility. The characteristic relaxation frequency of the fluctuations is found to decrease with increasing φ, while their amplitude increases.

Foams - Durian, D. J.; Weitz, D. A. (Kirk-Othmer Encyclopedia of Chemical Technology, 1993)

Dynamic Correlations of Multiply Scattered Light from Strongly Interacting Suspension - Zhu, J. X.; Weitz, D. A.; Klein, R. (Photonic Band Gaps and Localization, 1993)
The scattering of a coherent light source, such as a laser, from any random medium invariably results in a far field scattering pattern consisting of light and dark regions, called a speckle pattern. If the scattering medium changes in time, as for example will happen if the scattering particles move, then the speckle pattern also changes in time, reflecting this motion. The analysis of the intensity fluctuations of a single speckle spot can provide information about the dynamics of the scattering medium, and this form of light scattering is called dynamic light scattering (DLS), or quasielastic light scattering. The traditional DLS experiment entails the measurement of the temporal autocorrelation function of the intensity fluctuations of a speckle spot, and for singly scattered light, the time constant of the decay of this correlation function can be related to the dynamics of the scattering system through knowledge of the scattering wave vector, q. This is a well developed form of light scattering spectroscopy, and traditional DLS has found many applications in the study of the dynamics of a wide variety of systems.

Sound-propagation in suspensions of solid spheres - L. Ye; Liu, J.; Sheng, P.; Weitz, D. A. (Physical Review E, 1993)
We measure the dispersion of the longitudinal sound waves in a suspension of solid spheres using Brillouin scattering. We fmd two distinct propagating longitudinal modes when the wavelength of the sound becomes comparable to the sphere diameter. The higher-frequency mode has a velocity intermediate between those of the pure solid and pure liquid phases, and its velocity increases with increasing solid volume fraction. The dispersion curve of this mode has distinct gaps, and the group velocity goes to zero near these gaps. We interpret this mode as a compressional ''citation which propagates through both the liquid and the solid, as expected for a composite medium. The gaps in the dispersion curve result from the very large scattering of the excitation by the spheres, and occur at frequencies where the scattering from a single, isolated sphere is predicted to be a maximim due to a resonance in the sphere. By contrast, the lower-frequency mode has a velocity that is less than those in either the pure solid or the pure fluid. We interpret this mode as a surface acoustic excitation, which propagates between adjacent spheres by means of the exponentially decaying portion of the excitation in the fluid at the surface of the spheres. A summary of a theoretical treatment is also presented.

Sound-propagation in colloidal systems - L. Ye; Liu, J.; Sheng, P.; Huang, J. S.; Weitz, D. A. (Journal De Physique IV, 1993)
We study the propagation of sound in complex colloidal systems. By combining Brillouin scattering with ultrasonic techniques, we measure the dispersion in the acoustic propagation over three decades in frequency. Acoustic propagation is sensitive to the bulk compressibility of the medium, and probes new structural and dynamic properties of the colloidal system. We study two colloidal systems. The first is a system of inverted micelles or microemulsions, where the droplet size is significantly smaller than the wavelength of the sound. By measuring the dispersion of the sound velocity as a function of droplet volume fraction, we identify an increased rigidity of the system at high frequencies. The increase in the modulus scales as (phi - phi(c))tau, where phi is the volume fraction of droplets and phi(c) is a critical volume fraction. This is consistent with rigidity percolation. The second system we study consists of a suspension of hard sphere colloids whose diameter is comparable to the wavelength of sound. We measure the dispersion curve for the phonons in this system at different volume fractions of spheres. A new acoustic excitation is found when the wavelength of the sound is comparable to the sphere diameter. This acoustic excitation possesses unusual properties and is attributed to a surface excitation that can propagate coherently between adjacent spheres.

Diffusing-Wave Spectroscopy: The technique and some applications - Weitz, D. A.; Zhu, J. X.; Durian, D. J.; Gang, H.; Pine, D.J. (Physica Scripta, 1993)
We discuss the entension of dynamic light scattering to very strongly scattering media, where the propagation of light is described by the diffusion approximation, allowing the distribution of the light paths to be determined. The temporal evolution of the length of each of these paths, due to the dynamics of the scattering medium, is calculated, and an expression for the temporal autocorrelation function of the intensity fluctuations of the scattered light is obtained. This relates the measured decay of the autocorrelation function to the dynamics of the medium. This technique is called diffusing wave spectroscopy (DWS). To extend its utility, we consider the consequences of interactions between the scattering particles on the light scattering. To illustrate its applications, we consider several examples of new physics that can be investigated using DWS. We study the transient nature of hydrodynamic interactions between a particle and the surrounding fluid. We are able to probe the decay of the velocity correlation function of the particles, and we demonstrate its algebraic decay, with a t(-3/2) rime dependence. We also show that the time-dependent self diffusion coefficient exhibits an unexpected scaling behavior, whereby all the data, from samples of different volume fractions, can be scaled onto a single curve. Finally, we discuss the applications of DWS to the study of the dynamics of foams, and show how it can be used to probe the rearrangement of the bubbles within the foam as they coarsen.

Pore-space correlations in capillary condensation in vycor - Page, J. H.; Liu, J.; Abeles, B.; Deckman, H. W.; Weitz, D. A. (Physical Review Letters, 1993)
We use ultrasonic attenuation and light scattering to study spatial correlations in the pores of Vycor on filling and draining with hexane. On filling, the hexane initially adsorbs uniformly, but when capillary condensation occurs, vapor microbubbles are formed and persist until the sample is completely full. However, no long-range correlations of the bubbles are observed. By contrast, on drainage, the empty pores exhibit long-range correlations with a fractal dimension of 2.6. This results from the pore connectivity, suggesting that this behavior can be modeled by invasion percolation.

Coherent crystallography of shear-aligned crystals of hard-sphere colloids - Liu, J.; Weitz, D. A.; Ackerson, B. J. (Physical Review E, 1993)
The structure of colloidal crystals formed from suspensions of hard-sphere colloids is studied. The samples are contained in a thin cell. By rocking the samples, we are able to form shear-aligned colloidal crystals with extended, long-range order. The aligned crystals persist after the shear ceases, enabling us to use laser-light crystallography to determine their structure. We observe an unusual ordering, wherein the structure is a nearly perfect single twin of a face-centered cubic crystal, with crystals of different twins formed on each side of the cell. We exploit the coherence of the laser source to observe a speckle-like fluctuation of the intensity in the Bragg peaks. However, this fluctuation occurs only in one scattering direction, and therefore reflects a remnant disorder in the stacking of the hcp planes. We introduce a simple model which accounts for both the nature of the disorder in the stacking as well as the specklelike fluctuations. Our observation of this speckle also confirms recent predictions.

Static and dynamic evanescent-wave light-scattering-studies of diblock copolymers adsorbed at the air-water-interface - Lin, B. H.; Rice, S. A.; Weitz, D. A. (Journal of Chemical Physics, 1993)
We report the results of static and dynamic evanescent wave light scattering studies of a monolayer of a diblock copolymer, polystyrene-b-polymethylmethacrylate (PS-b-PMMA) with weight averaged molecular weights (M(w)) of 880 000:290 000 supported at the air/water interface. Our studies probe the interfacial structural and dynamic proper-ties of the monolayer on a length scale which is a fraction of the wavelength of light. The static light scattering studies were carried out as a function of polymer surface coverage and temperature; we also report some preliminary data for the dependence of the static structure function on the relative molecular weights of the PS and PMMA blocks. The complementary dynamic light scattering studies were carried out only as a function of surface coverage. Our data suggest that, upon spreading in the air/water interface, PS-b-PMMA (880:290 K) copolymers form thin disklike aggregates containing about 240 molecules. These data are consistent with a model in which each such aggregate is a ''furry disk'' with a dense core consisting of a layer of collapsed PS blocks atop a thin layer of extended PMMA blocks on the water surface and a brushlike boundary of extended PMMA blocks. The data show that the furry disks diffuse freely when the surface coverage is small, but when the surface coverage is large, they are immobile. Our data also suggest that the furry disks can aggregate to form even larger ''islands'' of disks with an extension greater than 20 mum. The static structure function of the assembly of furry disks is well described, over a wide range of surface coverage, by the structure factor of a two-dimensional hard disk fluid modulated by a two-dimensional hard disk form factor.

Structure of adhesive emulsions - Bibette, J.; Mason, T. G.; Hu, G.; Weitz, D. A.; Poulin, P. (Langmuir, 1993)
We study oil in water emulsions when the interaction between the droplets becomes strongly adhesive, causing them to stick together. However, the droplets still retain their integrity and do not coalesce. By using emulsions with droplets that are monodisperse in size, we are able to clearly observe their structure when the emulsions become adhesive. We show that the structure of strongly adhesive emulsions reflects a complex interplay among the strength of the adhesion, the droplet volume fraction, phi, and the time evolution of the adhesion. Initially, strong adhesion of the droplets leads to the formation of an emulsion gel. Moreover, the gel possesses a well-defined characteristic length scale, d(c), as evidenced by an intense ring of small angle light scattering. The characteristic length scale decreases as the droplet volume fraction increases. At low phi, the structure of the emulsion gel is fractal on length scales shorter than d(c), and the measured fractal dimension suggests that the gelation mechanism is controlled by diffusion-limited cluster aggregation. However, at higher phi, the short range structure is more compact, rather than fractal, and a different mechanism must be responsible for the gelation. If the strength of the adhesion is increased still further, the droplets become more deformed, resulting in massive restructuring of the emulsion gel. The structure fractures into independent, more compact flocs, eliminating the overall rigidity of the emulsion gel. These results help rationalize some of the diverse structures that are observed upon flocculation of the more usually studied polydisperse emulsions.

Scaling of transient hydrodynamic interactions in concentrated suspensions - Zhu, J. X.; Durian, D. J.; Muller, J.; Weitz, D. A.; Pine, D.J. (Physical Review Letters, 1992)
The mean-square displacement [DELTA-r2(tau)] of particles in concentrated suspensions is measured at times sufficiently short to observe the transient nature of hydrodynamic interactions. For all volume fractions-phi, the velocity autocorrelation function decays as a power law R(tau) is similar to tau–3/2. A remarkable scaling with phi is observed for the time-dependent self-diffusion coefficient D(s)(tau) = [DELTA-r2(tau)]/6-tau: If D(s)(tau) is scaled by its asymptotic value and if time is scaled by a viscous time inversely proportional to the shear viscosity of the suspension, all the data fall onto a single master curve.

Kinetically induced ordering in gelation of emulsions - Bibette, J.; Mason, T. G.; Gang, H.; Weitz, D. A. (Physical Review Letters, 1992)
We report the formation of a solid gel network from purely liquid emulsion droplets. The gel remains rigid at droplet volume fractions as low as 10(-3). The gelation process is identified as diffusion-limited cluster aggregation. We find a surprising order in the gel structure. This ordering is induced by the aggregation kinetics, which result in an unexpected spatial correlation between the growing clusters, ensuring that the network is formed from clusters of nearly equal size and spacing.

Stability-criteria for emulsions - Bibette, J.; Morse, D. C.; Witten, T. A.; Weitz, D. A. (Physical Review Letters, 1992)
The coalescence of monodisperse silicone oil-in-water emulsions stabilized with sodium dodecyl sulfate has been studied. We report the existence of a sharp destabilization threshold, controlled by surfactant chemical potential, osmotic pressure, and droplet diameter, at which the rate of coalescence increases dramatically. We present evidence that the stability of the emulsions can be characterized by two microscopic parameters: a minimum stable value of the surfactant chemical potential and a maximum value of the pressure exerted upon a droplet-droplet interface.

Scaling in Colloid Aggregation - Weitz, D. A.; Lin, M. Y.; Huang, J. S.; Witten, T. A.; Sinha, S. K.; Gethner, J.S.; Ball, R. C. (Scaling Phenomena in Disordered Systems, 1991)
We study the aggregation of aqueous gold colloids and apply modern scaling methods to interpret our results. We find that there are two regimes of aggregation, each with different rate-limiting physics, depending on the sticking probability of the individual colloidal particles. Each regime is distinguished by the fractal dimension of the resultant clusters, the aggregation dynamics and the cluster-mass distribution. The two regimes are diffusion-limited cluster aggregation and reaction-limited aggregation; and the two represent the two limiting universality classes for kinetic cluster-cluster aggregation.

Internal-reflection of diffusive light in random-media - Zhu, J. X.; Pine, D.J.; Weitz, D. A. (Physical Review A, 1991)
The consequences of internal reflection of multiply scattered light at the boundaries of disordered media are studied. We show that the effect of internal reflection due to index mismatch can be quantitatively accounted for with a single parameter by incorporating a reflection coefficient into the boundary condition for the diffusive light. We measure the angular correlation functions in transmission and reflection at different thicknesses for both high- and low-index mismatch. By including the effect of internal reflection, we are able to obtain consistent quantitative agreement between experiment and theory. Extensions to other experiments including diffusing-wave spectroscopy, coherent backscattering, frequency correlations, and pulse propagation are discussed.

Sound-propagation in sodium di-2-ethyl-hexylsulfosuccinate micelles and microemulsions - L. Ye; Weitz, D. A.; Sheng, P.; Huang, J. S. (Physical Review A, 1991)
We present the results of a systematic study of the propagation of sound in sodium di-2-ethyl-hexylsulfosuccinate (AOT) micelles and microemulsions. The dispersion in the sound velocity upsilon is determined over three and a half decades in frequency by using both ultrasonic and Brillouin-scattering techniques. The dispersion in the sound velocity is also measured as a function of the volume fraction phi of micelles or microemulsions. In addition, we measure the dependence of the sound velocity dispersion on the linear hydrocarbon chain length of the solvent molecules, and on the size of the microemulsion droplets. A consistent physical picture emerges that accounts for all of the results. The sound velocity in the micelle or microemulsion phases is greater than that in the solvent, leading to the observed increase of upsilon with phi. In addition, due to the overlapping of the surfactant tails, there is a weak, short-range attractive interaction between the droplets, causing them to form short-lived, extended networks. These networks can support shear, leading to a further increase in upsilon at higher phi, provided the frequency of the sound is sufficiently high that the instantaneous networks remain intact over the period of the sound wave. This results in the additional frequency dispersion in upsilon at high phi. The strength of the attractive interaction, and hence the dispersion in the sound velocity, depends on the chain length of the solvent molecule and the diameter of the microemulsion droplet. The use of an effective-medium model is critical in confirming the validity of the physical picture. The effective-medium model includes the contribution of a shear modulus of one of the phases and can account for the phi dependence of upsilon for all the systems. The shape of the full Rayleigh-Brillouin spectra is shown to be describable by a formalism that includes the relaxation of the extended networks. Finally, since the micelle or microemulsion networks cannot support shear unless they extend across the whole system, we show that the additional shear modulus contributed by the droplet phase exhibits scaling behavior when the volume fraction exceeds a critical value defined by the rigidity percolation threshold. This allows us to measure both the critical volume fraction and the exponent for rigidity percolation. However, since this additional shear modulus only occurs at high frequency, this effect is an example of dynamic rigidity percolation.

Universality laws in coagulation - Weitz, D. A.; Lin, M. Y.; Lindsay, H. M. (Chemometrics and Intelligent Laboratory Systems, 1991)
We show that the process of irreversible, kinetic colloid aggregation exhibits universal behavior, independent of the detailed chemical nature of the colloidal particles. Modern methods of statistical physics, applied to a kinetic growth process, provide a good basis to model the observed behavior. Two limiting regimes of colloid aggregation are identified: rapid aggregation, limited solely by the diffusion of the growing clusters; and slow aggregation, limited by the reaction rate that leads to the formation of bonds between the clusters. In each regime the cluster structure is fractal, with fractal dimension d(f) approximately 1.8 for diffusion-limited clusters and d(f) approximately 2.1 for reaction-limited clusters. A scaling method is used to compare dynamic light scattering data obtained from completely different colloids aggregated under the two limiting conditions. These data provide a critical comparison of the behavior of the different colloids, and confirm the universality of each limiting regime of colloid aggregation.

Multiple light-scattering probes of foam structure and dynamics - Durian, D. J.; Weitz, D. A.; Pine, D.J. (Science, 1991)
The structure and dynamics of three-dimensional foams are probed quantitatively by exploiting the strong multiple scattering of light that gives foams their familiar white color. Approximating the propagation of light as a diffusion process, transmission measurements provide a direct probe of the average bubble size. A model for dynamic light scattering is developed that can be used to interpret temporal fluctuations in the intensity of multiply scattered light. The results identify previously unrecognized internal dynamics of the foam bubbles. These light-scattering techniques are direct, noninvasive probes of bulk foams and therefore should find wide use in the study of their properties.

Scaling behavior in shaving cream - Durian, D. J.; Weitz, D. A.; Pine, D.J. (Physical Review A, 1991)
The coarsening of a three-dimensional foam is studied with multiple light-scattering techniques. Scaling behavior is observed with the average bubble diameter growing in time as t(z) where z = 0.45 /- 0.05. Changes in the packing conditions during coarsening give rise to a dynamical process that also exhibits temporal scaling. Neighboring bubbles undergo sudden structural rearrangement events at a rate per unit volume that decays as t(-y) where y = 2.0 /- 0.2.

The length scale dependence of viscosity approaching the glass-transition in glycerol - Dixon, P. K.; Nagel, S. R.; Weitz, D. A. (Journal of Chemical Physics, 1991)
We measure the viscosity of glycerol by using photon correlation spectroscopy to observe the Brownian motion of small (∼100 nm) polystyrene spheres. By comparing the viscositymeasured with different size spheres, we can measure the length scale dependence of the viscosity as the liquid is cooled towards the glass. In contrast to published reports, we observe no spatial dispersion in the viscosity.

Dynamic Rigidity Percolation in Inverted AOT Micellar Solutions - Huang, J. S.; L. Ye; Weitz, D. A.; Sheng, P.; Bhattacharya, S.; Higgins, M.J. (Progress in Colloid & Polymer Science, 1990)
We use ultrasonic techniques and Brillouin scattering to study the elastic response of AOT surfactant solutions. This micellar solution features a short-range attractive interaction between the droplets. We find behavior consistent with a dynamic rigidity percolation wherein clusters that span the system can form in the solution at surfactant volume fractions above Φ ≈ 0.16. The percolation clusters contribute a real shear modulus causing an increase in the sound velocity if the frequency is higher than the characteristic relaxation rate of the cluster (∼108 Hz). By contrast, at low frequencies the solution behaves as an effective medium with isolated micelle aggregates imbedded in the oil continuum, and the anomalous contribution of the shear modulus disappears. This experiment provides a unique measurement of the scaling of the elastic properties for a percolating system. In particular, the rigidity exponent is found to be τ′ ⋍ 2.5, consistent with the theoretical predictions.

Theory of Scattering from Colloidal Aggregates - Klein, R.; Weitz, D. A.; Lin, M. Y.; Lindsay, H. M.; Ball, R. C.; Meakin, P. (Progress in Colloid and Polymer Science, 1990)
Static and dynamic light scattering are major experimental tools to study colloidal aggregates. The theoretical methods for a proper analysis of such experiments are reviewed. It is shown how several interrelated features of the aggregation process determine the experimentally accessible quantities. These features are the structure of the clusters as characterized by their fractal dimension and their anisotropies and the shape of the cluster mass distribution. Using computer-generated clusters, obtained under the conditions of diffusion-limited and of reaction-limited cluster aggregation, and using results for the cluster mass distribution obtained from the Smoluchowski equation for irreversible growth, the static scattering intensity and the correlation function of quasi-elastic light scattering are calculated. The latter is shown to depend sensitively on rotational diffusion processes and on the cluster mass distribution. Finally, it is shown how the growth kinetics can be extracted from the angle dependence of the first cumulant.

Diffusing-wave spectroscopy in a shear-flow - Wu, X. L.; Pine, D.J.; Chaikin, P. M.; Huang, J. S.; Weitz, D. A. (J. Opt. Soc. Am. B 7, 1990)
We present a new technique for measuring velocity gradients for laminar shear flow, using dynamic light scattering in the strongly multiple-scattering regime. We derive temporal autocorrelation functions for multiply scattered light, taking into account particle displacements arising from deterministic shear flow and random Brownian motion. The laminar shear flow and Brownian motion are characterized by the relaxation rates [see link for figures], respectively, where [see link for figures] is the mean shear rate of the scatterers, k0 = 2πn/λ is the wave number in the scattering medium, l* is the transport mean free path of the photons, and D is the diffusion coefficient of the scatterers. We obtain excellent agreement between theory and experiment over a wide range of shear rates, [see link for range]. In addition, the autocorrelation function for forward scattering is independent of the scattering properties of the medium and depends only on the mean shear rate and sample thickness when τS is much less than τB. Thus the mean shear rate can be simply determined by a single measurement.

Hydrodynamic interactions in concentrated suspensions - Qiu, X.; Wu, X. L.; Xue, J. Z.; Pine, D.J.; Weitz, D. A.; Chaikin, P. M. (Physical Review Letters, 1990)
We study the effects of hydrodynamic interactions on the diffusion of hard spheres in concentrated suspensions. Using a multiple-light-scattering technique that measures the early-time behavior, we find Deff/D0=1-(1.86±0.07)φ, where φ is the volume fraction of spheres, Deff is the effective diffusion coefficient, and D0 is the free-particle diffusion coefficient. This agrees with the linear φ term calculated theoretically for short-time self-diffusion. The short-time diffusion coefficient is also found to be continuous across the freezing transition.

Diffusing-wave spectroscopy: Dynamic light scattering in the multiple scattering limit - Pine, D.J.; Weitz, D. A.; Zhu, J. X.; Herbolzheimer, E. (Journal De Physique, 1990)
Dynamic light scattering is extended to optically thick (opaque) media which exhibit a very high degree of multiple scattering. This new technique, called diffusing-wave spectroscopy (DWS), exploits the diffusive nature of the transport of light in strongly scattering media to relate the temporal fluctuations of the multiply scattered light to the motion of the scatterers. A simple theory of DWS, based on the diffusion approximation for the transport of light, is developed to calculate the temporal electric field autocorrelation functions of the multiply scattered light. Two important scattering geometries are treated : transmission and backscattering. The theory is compared to experimental measurements of Brownian motion of submicron-diameter polystyrene spheres in aqueous suspension. The agreement between theory and experiment is excellent. The limitations of the photon diffusion approximation and the polarization dependence of the autocorrelation functions are discussed for the backscattering measurements. The effects of absorption of light and particle polydispersity are also incorporated into the theory and verified experimentally. It is also shown how DWS can be used to obtain information about the mean size of the particles which scatter light.

Novel acoustic excitations in suspensions of hard-sphere colloids - Liu, J.; L. Ye; Weitz, D. A.; Ping, S. (Physical Review Letters, 1990)
We use Brillouin scattering to measure the longitudinal-phonon dispersion curves for a suspension of hard-sphere colloids. Two distinct propagating acoustic excitations are observed when the wavelength of the sound is comparable to, or smaller than, the size of the spheres. One excitation has a velocity intermediate between that of the fluid and the solid phases and is interpreted as an acoustic wave propagating through the composite medium of fluid and solid spheres. The second has a velocity slower than both that of the solid and that of the fluid phase and is interpreted as a coupled interfacial, or Stoneley, wave.

The structure of fractal colloidal aggregates of finite extent - Lin, M. Y.; Klein, R.; Lindsay, H. M.; Weitz, D. A.; Ball, R. C.; Meakin, P. (Journal of Colloid and Interface Science, 1990)
The structure of fractal colloid aggregates formed in both the diffusion- and the reaction-limited regimes is studied by static light scattering experiments. The crossover region of the structure factor of the clusters is measured, and the effects of the finite extent of the fractal structure on the scattering are investigated. The polydispersity of the cluster mass distribution markedly changes the shape of the measured scattering intensity. A form for the structure factor obtained from computer-generated clusters is found to describe the colloidal aggregates very well, for both regimes. Other available models for the crossover region are also discussed. In addition, the effects of the optical plasma resonance in the case of metallic colloids and the effects of cluster restructuring on the static scattering are discussed.​​​​​​

Universal diffusion-limited colloid aggregation - Lin, M. Y.; Lindsay, H. M.; Weitz, D. A.; Klein, R.; Ball, R. C.; Meakin, P. (J. Phys.: Condensed Matter, 1990)
The authors study the process of diffusion-limited colloid aggregation (DLCA) using both static and dynamic light scattering. Static light scattering is used to measure the fractal dimension of the clusters as well as their structure factor, which is found to be in good agreement with that obtained from calculation using computer-generated clusters. Dynamic light scattering is used to probe both translational and rotational diffusion motion of the clusters. A method to separate their respective contributions is developed, allowing a quantitative determination of the average hydrodynamic radius. In addition, they determine the ratio of the hydrodynamic radius to the radius of gyration for individual aggregates, and find beta =0.93. A method is developed to scale all the dynamic light scattering data onto a single master curve, whose shape is sensitive to key features of the DLCA process. Good agreement is found between the prediction of the shape of the master curve and that obtained from experiments. Using several completely different colloids, they find that the shape of their master curves are identical, their fractal dimensions are identical and their aggregation kinetics are identical. This provides strong evidence of the universality of the DLCA regime of colloid aggregation.

Universal reaction-limited colloid aggregation - Lin, M. Y.; Lindsay, H. M.; Weitz, D. A.; Ball, R. C.; Klein, R.; Meakin, P. (Physical Review A, 1990)
We study slow, or reaction-limited, colloid aggregation (RLCA) with both static and dynamic light scattering and develop a self-consistent interpretation of the results. Static light scattering is used to determine the fractal dimension of the clusters and the cutoff mass of the power-law cluster-mass distribution. Using this same cutoff cluster mass, we can predict the shape of the temporal autocorrelation function measured by dynamic light scattering. Good agreement with experiments is obtained provided the effects of rotational diffusion are included. In addition, we determine the ratio of the hydrodynamic radius to the radius of gyration of individual RLCA clusters and find β=1.0. A scaling method is used for the q-dependent first cumulants of the temporal autocorrelation functions to obtain a single master curve for data obtained at different times in the aggregation process. The shape of this master curve is very sensitive to several key features of the process of reaction-limited colloid aggregation. It allows us to unambiguously determine the exponent for the power-law cluster-mass distribution, τ=1.5±0.05. Furthermore, we show that the master curves for three completely different colloids, gold, silica, and polystyrene, are indistinguishable. In addition, the fractal dimensions of their RLCA clusters, as measured by static light scattering, are all df=2.1±0.05, while the aggregation kinetics for each colloid are exponential. This demonstrates that reaction-limited colloid aggregation is universal, independent of the detailed chemical nature of the colloid system.

Dynamics and coarsening in 3-dimensional foams - Durian, D. J.; Weitz, D. A.; Pine, D.J. (Journal of Physics-Condensed Matter, 1990)
We show that diffusing-wave spectroscopy can be used as a non-invasive probe of the bulk properties of three-dimensional foams. A new picture accounting for the origin of the temporal fluctuations of multiply scattered light is developed and corroborated with direct observations through a microscope. Our interpretation and measurements yield the growth law for the coarsening of foam bubbles and new insight into their dynamics.

Dynamical Correlations of Multiply Scattered Light - Pine, D.J.; Weitz, D. A.; Maret, G.; Wolf, P.E.; Herbolzheimer, E.; Chaikin, P. M. (Scattering and Localization of Classical Waves in Random Media, 1989)
Motion of particles in optically dense media gives rise to temporal fluctuations in the intensity of multiply scattered light. We show that useful information about the dynamics of the scatterers can be obtained from measurements of the temporal autocorrelation functions of these fluctuations in the multiply scattered light. We develop a phenomenological theory, which models the transport of light as a random walk between scatterers, and obtain explicit expressions for the autocorrelation functions for several experimental geometries. These expressions are compared with experiments probing the dynamics of colloidal suspensions and are shown to be in excellent agreement with the data. The dependence of the autocorrelation functions on the experimental geometry provides a powerful means of exploring the particle dynamics over vastly different length and time scales. Thus, this technique extends the conventional single scattering technique of Dynamic Light Scattering to the multiple scattering regime. We call this new technique Diffusing Wave Spectroscopy (DWS). We illustrate the power of DWS by applying it to measure the particle size in concentrated suspensions and to study the diffusion of particles in porous media and the flow of particles under shear. In addition, we show that DWS can be extended to study the dynamics of interacting colloids by including the consequences of the correlations between the particle positions and velocities. DWS can also be used to study the nature of the transport of light in disordered systems and, in particular, the limitations of using a continuum diffusion approximation. To exploit this, we show that other quantities, such as the angular dependence of the coherent backscattering cone and the absorption dependence of the incoherent backscattering intensity, depend on the distribution of light paths through the sample in the same way as the temporal autocorrelation functions obtained in backscattering.

Dynamic rigidity percolation in inverted micelles - L. Ye; Weitz, D. A.; Sheng, P.; Bhattacharya, S.; Huang, J. S.; Higgins, M.J. (Physical Review Letters, 1989)
Inverted micelles are found to exhibit marked viscoelasticity with a pronounced dependence on volume fraction. The frequency dependence, measured using both ultrasonic and Brillouin techniques, reflects the dynamics of the interactions between the micelles. At low frequencies they behave as isolated spheres, while at high frequencies they behave as an instantaneous connected network. The rigidity of this network exhibits power-law scaling with volume fraction, consistent with rigidity percolation.

Nondiffusive brownian-motion studied by diffusing-wave spectroscopy - Weitz, D. A.; Pine, D.J.; Pusey, P. N.; Tough, R. J. A. (Physical Review Letters, 1989)
On a short time scale, Brownian particles undergo a transtion from the initial ballistic trajectories to diffusive motion. Hydrodynamic interactions with the surrounding fluid lead to a complex time dependence of this transition. We directly probe this transition for colloidal particles by measuring the autocorrelation function of multiply scattered, transmitted light. We show that a quantitative interpretation is possible because the transport of the light is diffusive, resolving a conflict in previous measurements.

Polarization memory of multiply scattered-light - MacKintosh, F. C.; Zhu, J. X.; Pine, D.J.; Weitz, D. A. (Physical Review B, 1989)
Light backscattered from an optically dense random medium is shown to exhibit a pronounced polarization dependence. An unexpected memory of the incident circular polarization of multiply scattering light arises because the wave’s helicity is randomized less rapidly than is its direction. A simple model is developed to account for the observed polarization dependence of the intensity and temporal correlations of the intensity fluctuations of backscattered light.

Structure and anisotropy of colloid aggregates - Lindsay, H. M.; Klein, R.; Weitz, D. A.; Lin, M. Y.; Meakin, P. (Physical Review A, 1989)
We study the complex, disordered structure of clusters formed by several kinetic aggregation processes. By expanding the structure factor into spherical harmonics, detailed information about both the structure and anisotropy of the clusters at all length scales is obtained. The scaling of the expansion terms with cluster mass and order of the expansion is investigated. For cluster-cluster aggregates, we find that the fractal dimension, which reflects the scaling of the orientationally averaged structure, also describes the scaling of the spherical harmonics, which reflect the anisotropies of the structure. By contrast, clusters formed by single-particle diffusion-limited aggregation do not appear to exhibit the same degree of scale invariance. Cluster-cluster aggregates are found to exhibit considerably more anisotropy than those formed by single-particle diffusion. The consequences of the anisotropies for quasielastic light scattering experiments are discussed.

Universality in colloid aggregation - Lin, M. Y.; Lindsay, H. M.; Weitz, D. A.; Ball, R. C.; Klein, R.; Meakin, P. (Nature, 1989)
<section aria-labelledby="Abs1" data-gtm-vis-first-on-screen-10482319_393="593" data-gtm-vis-first-on-screen-10482319_401="632" data-gtm-vis-polling-id-10482319_393="849" data-gtm-vis-polling-id-10482319_401="850" data-gtm-vis-recent-on-screen-10482319_393="17532" data-gtm-vis-recent-on-screen-10482319_401="17532" data-gtm-vis-total-visible-time-10482319_393="9100" data-gtm-vis-total-visible-time-10482319_401="9100" data-title="Abstract" lang="en"> THE aggregation of colloidal particles is of fundamental importance in colloid science and its applications. The recent application of scaling concepts1,2 has resulted in a much deeper understanding of the structure of colloidal aggregates and the kinetics of their formation. Two distinct, limiting regimes of irreversible colloid aggregation have been identified3. Diffusion-limited colloid aggregation occurs when there is negligible repulsive force between the colloidal particles, so that the aggregation rate is limited solely by the time taken for clusters to encounter each other by diffusion. Reaction-limited colloid aggregation occurs when there is still a substantial, but not insurmountable, repulsive force beween the particles, so that the aggregation rate is limited by the time taken for two clusters to overcome this repulsive barrier by thermal activation. These regimes correspond to the limiting cases of rapid and slow colloid aggregation that have long been recognized in colloid science4. An intriguing possibility suggested by recent work is that each of these limiting regimes of colloid aggregation is universal, independent of the chemical details of the particular colloid system. Here we investigate the aggregation of three chemically different colloidal systems under both diffusion-limited and reaction-limited aggregation conditions. A scaling analysis of light-scattering data is used to compare the behaviour and provides convincing experimental evidence that the two regimes of aggregation are indeed universal.

Universality of fractal aggregates as probed by light scattering - Lin, M. Y.; Lindsay, H. M.; Weitz, D. A.; Ball, R. C.; Klein, R.; Meakin, P. (Proceedings of the Royal Society of London Series A, Mathematical and Physical Sciences, 1989)
Fractal colloid aggregates are studied with both static and dynamic light scattering. The dynamic light scattering data are scaled onto a single master curve, whose shape is sensitive to the structure of the aggregates and their mass distribution. By using the structure factor determined from computer-simulated aggregates, and including the effects of rotational diffusion, we predict the shape of the master curve for different cluster distributions. Excellent agreement is found between our predictions and the data for the two limiting regimes, diffusion-limited and reaction-limited colloid aggregation. Furthermore, using data from several completely different colloids, we find that the shapes of the master curves are identical for each regime. In addition, the cluster fractal dimensions and the aggregation kinetics are identical in each regime. This provides convincing experimental evidence of the universality of these two regimes of colloid aggregation.

Diffusing wave spectroscopy - Pine, D.J.; Weitz, D. A.; Chaikin, P. M.; Herbolzheimer, E. (Physical Review Letters, 1988)
We obtain useful information from the intensity autocorrelations of light scattered from systems which exhibit strong multiple scattering. A phenomenological model, which exploits the diffusive nature of the transport of light, is shown to be in excellent agreement with experimental data for several different scattering geometries. The dependence on geometry provides an important experimental control over the time scale probed. We call this technique diffusing wave spectroscopy, and illustrate its utility by studying diffusion in a strongly interacting colloidal glass.

Effect of rotational diffusion on quasielastic light-scattering from fractal colloid aggregates - Lindsay, H. M.; Klein, R.; Weitz, D. A.; Lin, M. Y.; Meakin, P. (Physical Review A, 1988)
We examine the contribution of rotational diffusion to quasielastic light scattering (QELS) from fractal colloid aggregates, both theoretically and experimentally. Rotational diffusion makes a substantial contribution to QELS when the size of the clusters is large compared with the inverse of the scattering wave vector, due to the anisotropy of the clusters at all length scales smaller than the cluster size. We evaluate the rotational contributions to QELS by performing a multipole expansion of the light scattered from computer-simulated clusters. Experimentally, rotational contributions are observed through measurement of the wave-vector dependence of the first cumulant. We find excellent agreement between cumulants calculated through our multipole-expansion technique and those obtained in our experimental measurements.

Optical properties of aggregate clusters - Chen, Z.; Sheng, P.; Weitz, D. A.; Lindsay, H. M.; Lin, M. Y.; Meakin, P. (Physical Review B, 1988)
We examine the optical properties of aggregate clusters and consider the effects of multiple scattering. The long-range fractal correlations can modify the mean index of refraction of the clusters, but multiple scattering has no effect on the wave-vector dependence of the scattering. By contrast, the short-range correlations inherent in a connected cluster lead to high-order multipole interactions which cannot be treated with a mean-field approach. These are shown to determine the wavelength dependence of the absorption and depolarized scattering from metallic clusters in good accord with experiment.

Viscous Fingering Instabilities in Porous Media - Stokes, J. P.; Weitz, D. A.; Ball, R. C.; Kushnick, A. P. (NATO ASI Series, 1987)
We study patterns formed by the viscous fingering instability in a porous media. When the displacing fluid preferentially wets the medium, the finger width is much larger than the pore size and, when normalized by the square root of the permeability, is found to scale with capillary number as Ca−1/2. While traditional theories based on Hele-Shaw geometry give this dependence for the most unstable wavelength, they are unable to explain the magnitude of the finger. We consider here the effect of a velocity dependent capillary pressure in addition to the more conventional static term, and suggest that it may control the scaling of the finger width on Ca. We demonstrate the existence of this dynamic capillary pressure, which offers new insight into the basic physics of the motion of a fluid interface in porous media.

Effect of Rotational Diffusion on Quasi-Elastic Light Scattering from Fractal Clusters - Lindsay, H. M.; Klein, R.; Weitz, D. A.; Lin, M. Y.; Meakin, P. (NATO ASI Series, 1987)
The aggregation of colloids is of substantial interest both fundamentally and practically. The level of interest has risen in recent years with the observation that colloidal aggregates are often well characterized as scale-invariant, or fractal, objects, providing a quantitative description of the structure of these random, irregular clusters.1–4 The consequences of the scale invariance on light scattering from the clusters has been widely exploited. In static light scattering, the dependence of the scattering intensity on the scattering wave vector q allows a convenient way of determining the fractal dimension of the clusters, while Quasi-Elastic Light Scattering (QELS) has proved useful in monitoring the kinetics of the aggregation process. The combination of the scale-invariant structures of the aggregates and the power-law distributions which often occur leads to elegant scaling behavior of the dynamic light scattering.5,6 For the large clusters (qRg ≳1) often found in aggregation, rotational diffusion can play an important role in determining the decay of the autocorrelation of the scattered light measured in QELS. While scaling arguments have been used to account for the contribution of rotational diffusion, it is nonetheless important to determine this effect more quantitatively.

Dynamic capillary-pressure in porous-media: Origin of the viscous-fingering length scale - Weitz, D. A.; Stokes, J. P.; Ball, R. C.; Kushnick, A. P. (Physical Review Letters, 1987)
We measure the velocity dependence of the capillary pressure, ΔPc(v), between two fluids in a porous medium. At zero velocity, the interface is pinned, and a critical ΔPc must be achieved before the interface moves. For nonzero velocities, there is an additional dynamic component to ΔPc, which scales as v12 when a wetting fluid displaces a nonwetting fluid. We suggest that this dynamic component of ΔPc can stabilize viscous fingers, and obtain excellent agreement with experiment.

Weitz, Lin, Lindsay, and Huang respond - Weitz, D. A.; Lin, M. Y.; Lindsay, H. M.; Huang, J. S. (Physical Review Letters, 1987)

Comment on "Hydrodynamic behavior of fractal aggregates" - Pusey, P. N.; Rarity, J. G.; Klein, R.; Weitz, D. A. (Physical Review Letters, 1987)
A Comment on the Letter by P. Wiltzius, Phys. Rev. Lett. 58, 710 (1987).

Properties of fractal colloid aggregates - Lindsay, H. M.; Lin, M. Y.; Weitz, D. A.; Sheng, P.; Chen, Z.; Klein, R.; Meakin, P. (Faraday Discussions, 1987)
We study the influence of the fractal structure on the physical properties of colloidal gold aggregates. The optical properties are strongly influenced by both the long- and the short-range correlations of the aggregate structure, as well as the electronic plasma resonance of the gold particles. The absorption of the aggregates is dominated by the electromagnetic interaction between nearest-neighbour particles. The angular dependence of the polarized scattering reflects the long-range fractal correlations of the particles in the clusters, while that of the depolarized scattering reflects the short-range correlations of the local field corrections. The fractal structure also affects dynamic light scattering, so that rotational diffusion effects play an important role in the decay of the autocorrelation function. Finally, we show that the very tenuous nature of the fractal structure makes the aggregates quite susceptible to deformation under shear stress.

Competition between shear-melting and taylor instabilities in colloidal crystals - Dimeglio, J. M.; Weitz, D. A.; Chaikin, P. M. (Physical Review Letters, 1987)
We study the onset of the Taylor instability for colloidal crystals in a narrow-gap Couette Cell. There is a natural competition between the radial flow required for Taylor rolls and the resistance to such motion caused by the anisotropy of the flowing solid. A new, combined Taylor–shear-melting instability is found at rotation rates above those expected for the formation of rolls, but below the shear rate required for shear melting in the absence of the Taylor instability. The control parameter for the shear melting transition appears to be a critical shear stress rather than the shear rate.

Universal kinetics in reaction-limited aggregation - Ball, R. C.; Weitz, D. A.; Witten, T. A.; Leyvraz, F. (Physical Review Letters, 1987)
Reaction-limited cluster aggregation is modeled with the kinetic rate (Smoluchowski) equations, using a kernel determined intrinsically by the clusters fractal geometry. The kernel scales with cluster mass as M1Mλ−12 (M1≫M2), and Mλ1 (M1≊M2), with λ=1 in three dimensions, resulting in exponential kinetics and a cluster mass distribution CM∼M−τ, with τ=(3/2), in excellent accord with experiments. The singular nature of this solution forces the adjustment of the cluster fractal dimension, df, thereby determining its value.

Dynamic scaling of cluster-mass distributions in kinetic colloid aggregation - Weitz, D. A.; Lin, M. Y. (Physical Review Letters, 1986)
The cluster-mass distributions produced in the kinetic aggregation of aqueous gold colloids are measured over an extended range of masses for two limiting kinetic regimes, diffusion-limited (DLA) and reaction-limited (RLA) aggregation. Markedly different distributions are found, with DLA having a peaked distribution, while RLA has a power-law distribution. In both cases the distributions are shown to exhibit dynamic scaling, as has recently been predicted. The data are interpreted with the Smoluchowski equations, and are used to determine the form of the appropriate kernel for each regime.

Interfacial stability of immiscible displacement in a porous-medium - Stokes, J. P.; Weitz, D. A.; J. P. Gollub; Dougherty, A.; Robbins, M. O.; Chaikin, P. M.; Lindsay, H. M. (Physical Review Letters, 1986)
We study patterns formed by the viscous fingering instability in a porous medium. The wetting properties of the medium have a profound influence on the width of the individual fingers and consequently on the shape of the overall pattern. If the displaced fluid preferentially wets the medium, the finger width is comparable to the pore size, independent of other parameters. In contrast, if the displacing fluid preferentially wets the medium, the finger width is much larger than the pore size, and, when normalized by the square root of the permeability, is found to scale with the capillary number approximately as N−12Ca.

Structure of aggregated gold colloids - Dimon, P.; Sinha, S. K.; Weitz, D. A.; Safinya, C. R.; Smith, G. S.; Varady, W. A.; Lindsay, H. M. (Physical Review Letters, 1986)
We report a high-resolution, small-angle x-ray study of aggregated gold colloids over the range 0.0003 to 0.08 Å−1. We are able to fit our data with a simple model that correctly accounts for nonfractal short-range order with a crossover to long-range fractal correlations. This provides new information on the structure of real aggregates, and new insight into the aggregation processes which lead to their formation.

Colloidal aggregation revisited - new insights based on fractal structure and surface-enhanced raman-scattering - Weitz, D. A.; Lin, M. Y.; Sandroff, C. J. (Surface Science, 1985)
We have examined both the structure and surface chemistry of gold clusters formed by the kinetic aggregation of colloidal gold particles. The highly disordered, ramified aggregates can be very accurately described as self-similar or fractal objects with a fractal dimension equal to 1.75. Spectroscopic studies performed with surface-enhanced Raman scattering (SERS), clearly indicate that colloidal gold surfaces are highly heterogeneous, consisting both of donor and acceptor sites which can be identified as Au(0) and Au(I). respectively. Aggregation occurs when negatively charged species are displaced from the gold surface by more strongly bound molecular adsorhates, with the rate determined by the nature and concentration of the displacing species. The new insights afforded by the fractal description of the structure of the aggregates and the SERS probe of the chemical nature of the colloid surface should lead to a more complete understanding of the basic mechanisms of colloid aggregation. This potential is illustrated with a quantitative description of the dynamics of aggregate growth measured by dynamic light scattering.​​​​​​

Limits of the fractal dimension for irreversible kinetic aggregation of gold colloids - Weitz, D. A.; Huang, J. S.; Lin, M. Y.; Sung, J. (Physical Review Letters, 1985)
We show that there are two regimes of irreversible, kinetic aggregation of aqueous colloids, determined by the short-range interparticle potential, through its control of the sticking probability upon approach of two particles. Each regime has different rate-limiting physics, aggregation dynamics, and cluster-mass distributions, and results in clusters with different fractal dimensions. These results set limits on the fractal dimension, df, for gold aggregates of 1.75<~df<~2.05(±0.05).

Periodic structures in driven colloidal crystals - Weitz, D. A.; Dozier, W. D.; Chaikin, P. M. (Journal de Physique, 1985)
The large lattice spacings in colloidal crystals produce elastic constants ~ 1010 less than conventional solids. It is therefore easy to study flow properties at stress/elastic constant ratios higher than previously available. The highly nonlinear plastic flow regime studied in oscillating and steady state flow yields periodic patterns. These patterns correspond to alternating regions of ordered crystallites which are mirror image structures. The pattern observed in oscillatory flow in a tube is also unusual in that the core is liquid while at larger radius one finds a solid on the tube wall. This traditionally unstable configuration may be the result of an anomalous stress-rate relation at the fluid-solid boundary. Experiments in couette geometry produce vertical stripes which correspond to coherent motion of dislocations at the boundaries separating two mirror image structures. The stripes move in the direction opposite from the rotation of the inner cylinder, at velocities close to the transverse sound velocity.

High-pressure conductivity and structure of HMTSF-TCNQ - King, H. E.; Tozer, S. W.; Safinya, C. R.; Stokes, J. P.; Weitz, D. A.; Bloch, A. N.; Cowan, D. O. (Molecular Crystals and Liquid Crystals, 1985)
Four-probe resistivity measurements on organic conductors have been extended to 6 GPa. The organic metal HMTSF-TCNO appears to undergo a phase transition to a three-dimen-sionaliy ordered conducting state near 4 GPa. X-ray and Raman scattering confirm the transition. Unexpectedly, the degree of charge transfer in HMTSF-TCNO is relatively insensitive to pressure.

Self-Similar Structures and the Kinetics of Aggregation of Gold Colloids - Weitz, D. A.; Huang, J. S. (Kinetics of Aggregation and Gelation, 1984)
We show that the clusters formed by the irreversible aggregation of uniform aqueous gold colloids exhibit dilation symmetry and are well described as fractals with a Hausdorff or fractal dimension of ~1.75. The detailed structure of the clusters is studied with transmission electron microscopy, and is confirmed with small angle neutron scattering. The value of the fractal dimension obtained is in excellent agreement with that predicted by theory and computer simulation for cluster-cluster aggregation. We also discuss preliminary measurements of the kinetics of aggregation, which indicate that there are two limiting regimes with substantially different behavior. One is dominated by the particle-particle sticking time leading to relatively slow growth initially, but an increasing rate of growth as the aggregation proceeds. In contrast, the other is dominated by the diffusion time for clusters to collide leading to much faster aggregation, but with a decreasing rate of growth as the aggregation proceeds.

Dynamics of diffusion-limited kinetic aggregation - Weitz, D. A.; Huang, J. S.; Lin, M. Y.; Sung, J. (Physical Review Letters, 1984)
We study the dynamics of diffusion-limited cluster-cluster aggregation of aqueous colloids using quasielastic light scattering. Scaling behavior is found for the dependence of the mean cluster size on both time and initial concentration, and limits are placed on the scaling exponents of the cluster mass distribution. The fractal nature of the resultant clusters directly affects the exponents, illustrating the inherent relationship between the dynamic and static properties of kinetic aggregation processes.

Fractal structures formed by kinetic aggregation of aqueous gold colloids - Weitz, D. A.; Oliveria, M. (Physical Review Letters, 1984)
We use transmission-electron micrographs to study the structure formed by the irreversible kinetic aggregation of uniformly sized aqueous gold colloids. The structures are highly ramified and exhibit a scale invariance that is well described as a fractal with a Hausdorff dimension of ∼ 1.75. This value is in excellent agreement with recent computer simulations of diffusion-limited aggregation when the clusters themselves are allowed to aggregate.

Electrodynamics at rough metal-surfaces - photochemistry and luminescence of adsorbates near metal-island films - Garoff, S.; Weitz, D. A.; Alvarez, M. S.; Gersten, J. I. (Journal of Chemical Physics, 1984)
Detailed measurements of the photochemical and photophysical properties of an adsorbate on discontinuous metal‐island films are used to explore the unusual electrodynamics near rough metal surfaces. Several aspects of the properties have been measured: the magnitude the temporal decay of the fluorescence, the shape and temporal evolution of the fluorescence spectrum, and the effects on the spectrum of a photochemical hole‐burning process. Dramatic increases in the fluorescent decay rate and decreases in the photochemical reaction rate as well as systematic spectral shifts of the emission of molecules experiencing the different electrodynamic environments on the island film are observed. These results reveal the strong effects of the coupling between the adsorbate and the plasma resonances localized on the islands of the film. We model our results using the electrodynamic picture which has successfully described many aspects of surface‐enhanced Raman scattering and other optical processes on island films. The excellent agreement between this model and our results suggests that an important feature of the electrodynamics at these rough metal surfaces is the dipolar character of the couplings between the surface, the adsorbate, and the optical fields.

Luminescent and photochemical properties of molecules near rough metal-surfaces - Garoff, S.; Weitz, D. A.; Alvarez, M. S. (Journal of Luminescence, 1984)
The unusual luminescent and photochemical properties of molecules near rough metal surfaces have been measured and used to ellucidate the electrodynamics at these interfaces.

Laser desorption mass-spectrometry of surface-adsorbed molecules - Fletcher, R. A.; Chabay, I.; Weitz, D. A.; Chung, J. C. (Chemical Physics Letters, 1984)
The role of the electronic-plasma-resonance absorption of surface microstructure in the visible and UV pulsed laser desorption of adsorbates on a silver surface is examined. It is shown that the surface microstructure aids in the absorption of a significant fraction of the laser radiation and can lead to a relatively gentle thermal desorption of molecular monolayers absorbed on the metal. This substantially increases the sensitivity and selectivity of time-of-flight mass spectrometry in the analysis of adsorbates on the metal surface.

Electromagnetically Induced Changes in Intensities, Spectra and Temporal Behavior of Light Scattering from Molecules on Silver Island Films - Garoff, S.; Weitz, D. A.; Alvarez, M. S.; Chung, J. C. (J. Phys. Colloques, 1983)
The electrodynamic interactions which lead to surface-enhanced Raman scattering (SERS) also lead to dramatic changes in the intensities, spectra, and temporal behavior of the fluorescent emission of adsorbates on rough metal surfaces. Spectral shifts of the fluorescence of adsorbates on island films have been observed (a) by examining the emission from adsorbates on different substrates, (b) by a "photochemical holeburning" method, and (c) by measuring the temporal evolution of the fluorescent spectrum at very short times after laser excitation. The observed changes can be accounted for within the framework of the electromagnetic theory of SERS generalized to include the details of molecular resonances and relaxed emission processes.

Surface-enhanced Raman scattering by molecules adsorbed on aqueous copper colloids - Creighton, J.A.; Alvarez, M. S.; Weitz, D. A.; Garoff, S.; Kim, M.W. (J. Phys. Chem., 1983)

Charge transfer from tetrathiafulvalene to silver and gold surfaces studied by surface-enhanced Raman scattering - Sandroff, C. J.; Weitz, D. A.; Chung, J. C.; Herschbach, D.R. (J. Phys. Chem., 1983)

A comparison of raman-scattering, resonance raman-scattering, and fluorescence from molecules adsorbed on silver island films - Weitz, D. A.; Garoff, S.; Gersten, J. I.; Nitzan, A. (Journal of Electron Spectroscopy and Related Phenomena, 1983)
The enhancement of Raman scattering (RS), resonance Raman scattering (RRS), and fluorescence from molecules adsorbed on silver-island films is reported. A heirarchy of enhancements is found: 105 for RS, 103 for RRS, and 0.1–10 for fluorescence, depending on the quantum yield of the free molecule. Using the framework of the electromagnetic theory of surface-enhanced Raman scattering, generalized to treat molecular resonance phenomena, we develop a unified picture of the role of the surface plasmon resonances, and the surface-induced damping, in the light scattering processes. The observed heirarchy of enhancements is shown to have important spectroscopic consequences.

The enhancement of raman-scattering, resonance raman-scattering, and fluorescence from molecules adsorbed on a rough silver surface - Weitz, D. A.; Garoff, S.; Gersten, J. I.; Nitzan, A. (Journal of Chemical Physics, 1983)
The enhancements of normal Raman scattering, resonance Raman scattering, and fluorescence from molecules adsorbed on identical, well‐characterized, silver‐island films are reported. The enhancement arises from the electromagnetic interaction between the molecules and the electronic plasma resonance of the silver islands. A hierarchy of enhancement ratios is found, with typical values of 105 for RS, 103 for RRS and 10−1 to 10 for fluorescence, depending on the quantum yield of the molecular fluorescence. A model, developed on heuristic grounds and substantiated using the density matrix formalism, describes the light scattering processes and the effects of the plasma resonance. This model presents a unified picture of the surface‐induced enhancement effects and is consistent with the experimental values. The comparison of all the forms of optical scattering leads to a complete determination of the role of the plasma resonances in the various portions of the scattering process. The excitation of the electronic plasma resonance results in an increased local field at the molecules leading to an increased excitation or absorption rate. Similarly, the excitation of the plasma resonance by the molecular emission dipole results in an increase in the radiative decay rate. However, the electromagnetic coupling of the molecule to the plasma resonance also adds an additional damping channel which can result in a reduction of the absorption or excitation rate as well as the emission yield. The resultant balance of these processes leads to the hierarchy in the measured enhancements. The hierarchy of enhancements is also shown to have important spectroscopic consequences.

Inelastic Mie Scattering from Rough Metal Surfaces - Weitz, D. A.; Gramila, T. J.; Genack, A.Z. (Surface Enhanced Raman Scattering, 1982)
One of the most widely debated questions concerning surface-enhanced Raman scattering (SERS) is the nature of the surface morphology required to obtain the large enhancements. While it is generally agreed that surface roughness is important, the specific nature of this roughness, and its exact role in the enhancement has been a subject of considerable debate. In this chapter, we discuss experimental results that address this question directly. We study an extremely low frequency Raman mode which we attribute to Raman scattering (RS) from the rough metal surface itself.1,2 From the low frequency Raman scattering we can determine the nature of the roughness which contributes to SERS. From the anomalous behavior of this Raman scattering, we can determine the role of this roughness in the large enhancement of the RS cross section of adsorbed molecules.

Excitation-spectra of surface-enhanced raman-scattering on silver-island films - Weitz, D. A.; Garoff, S.; Gramila, T. J. (Optics Letters, 1982)
Both the spectral dependence and the magnitude of the excitation spectra of surface-enhanced Raman scattering are found to be quantitatively related to the absorption spectra for silver-island films. This relationship is maintained even when the local electromagnetic enhancement at the islands is varied by coating the film with a layer of absorbing dye molecules. The results illustrate a simple experimental way to determine independently the role of the electronic plasma resonances in the enhancement process on these films and shed new insights into the details of the electromagnetic interactions responsible for surface-enhanced Raman scattering.

Fluorescent lifetimes of molecules on silver-island films - Weitz, D. A.; Garoff, S.; Hanson, C. D.; Gramila, T. J.; Gersten, J. I. (Optics Letters, 1982)
The fluorescence of molecules on silver-island films exhibits nonexponential decay and is several orders of magnitude more rapid than on a silica surface, while the total emission intensity is slightly increased. This behavior results from the electromagnetic coupling between the fluorescing molecules and the plasmon resonances of the silver islands. We obtain good agreement with a model that uses the same theory for the electromagnetic coupling as has been used to account for surface-enhanced Raman scattering.

Spectroscopy of adsorbed molecules using silver-island films - Weitz, D. A.; Garoff, S.; Alvarez, M. S.; Chung, J. C. (Applied Physics B-Photophysics and Laser Chemistry, 1982)

Photochemistry of molecules adsorbed on silver-island films: effects of the spatially inhomogeneous environment - Garoff, S.; Weitz, D. A.; Alverez, M. S. (Chemical Physics Letters, 1982)
We have examined how the photochemical reaction rate of molecules absorbed at rough silver surfaces is affected by the same strong electrodynamic interactions which lead to surface-enhanced Raman scattering. We probe the effects of the spatial variation of the electrodynamic interactions across the island film.

Fluorescent lifetimes and yields of molecules adsorbed on silver-island films - Weitz, D. A.; Garoff, S.; Hanson, C. D.; Gramila, T. J.; Gersten, J. I. (Journal of Luminescence, 1981)
When molecules are adsorbed on silver island films, their fluorescent lifetimes are found to be shortened by about three orders of magnitude and their decay is found to be non-exponential in time. This behavior is a result of the electro-magnetic interaction between the molecules and the silver islands. The emission process of the molecule-island system can be quite efficient, and the increased radiative rate can lead to an improved effective quantum yield for adsorbates on silver-island films.

Optical-absorption resonances of dye-coated silver-island films - Garoff, S.; Weitz, D. A.; Gramila, T. J.; Hanson, C. D. (Optics Letters, 1981)
We have used Mie theory to account for the features of the transmission spectra of dye-coated silver-island films. The unusual behavior of the spectra arises from the effect of the dispersion and damping of the optical response of the absorbing coating on the structural resonances of the silver islands. Our modeling indicates that the power dissipation in the dye coating is enhanced compared with the dissipation of dye deposited on a nonresonant structure. These results help elucidate the excitation mechanisms of Raman and fluorescent emission of adsorbates at rough silver interfaces.

Role of roughness in surface-enhanced raman-scattering - Weitz, D. A.; Gramila, T. J.; Genack, A.Z.; Gersten, J. I. (Journal of the Optical Society of America, 1980)

Anomalous low-frequency raman-scattering from rough metal-surfaces and the origin of surface-enhanced raman-scattering - Weitz, D. A.; Gramila, T. J.; Genack, A.Z.; Gersten, J. I. (Physical Review Letters, 1980)
Anomalous, low-frequency Raman scattering from localized acoustic vibrations of roughness features on a metal surface are observed. The observed mode frequency shifts with excitation frequency and with the index of refraction of the surrounding medium. The shifts arise from resonant laser excitation of localized dipolar plasmons. This resonant optical coupling is a key to the phenomenon of enhanced Raman scattering from molecules adsorbed on rough metal surfaces.

Nuclear-quadrupole optical hole burning in the stoichiometric material eup5o14 - R. M. Macfarlane; Shelby, R. M.; Genack, A.Z.; Weitz, D. A. (Optics Letters, 1980)
Hole burning, which is attributed to optical pumping of nuclear-quadrupole levels, has been observed in the stoichiometric rare-earth compound, EuP5O14. The long lifetime of these holes (∼60 min) implies slow nuclear-spin flip-flop rates. The small magnetic moment of Eu3+ has prevented conventional magnetic-resonance measurements on Eu3+ compounds, but hole burning provides a sensitive method for the optical detection of nuclear-magnetic resonance and nuclear-quadrupole resonance. We have used hole burning and optically detected nuclear-quadrupole resonance to determine quadrupole splittings in the ground (7F0) and excited (5D0) states.

Coherent transients by optical-phase switching - dephasing in LaCL3-Pr3+ - Genack, A.Z.; Weitz, D. A.; R. M. Macfarlane; Shelby, R. M.; Schenzle, A. (Physical Review Letters, 1980)
A novel coherent transient effect is observed following a rapid shift in the relative phase of an exciting laser and sample polarization. An analytical expression is derived for the signal which is a sum of exponentially decaying terms with characteristic times involving both T1 and T2. Phase switching is a powerful approach to the study of optical relaxation and is applied here to measure dephasing in LaCl3: Pr3+.

Inelastic mie scattering from rough metal-surfaces - theory and experiment - Gersten, J. I.; Weitz, D. A.; Gramila, T. J.; Genack, A.Z. (Physical Review B, 1980)
A theory for inelastic Mie scattering from rough metal surfaces or metal sols is proposed. A resonant excitation of a localized dipolar plasmon can enhance the cross section, and experimental data relating to the phenomenon in silver and copper are presented. Two distinct effects are noted. One is inelastic light scattering from the rough metal surface or bare metal sol. The other is related to Reyleigh scattering from adsorbed molecules as modified by the presence of the substrate. Both involve frequency shifts determined by the characteristic mechanical vibrations of the metal. A striking feature of this inelastic Mie scattering is that for a distribution of particle sizes and shapes the frequency shift changes as the incident laser frequency is changed or as the index of refraction of the surrounding medium is changed. Inelastic Mie scattering is shown to yield important information on the surface roughness required for the observation of surface-enhanced Raman scattering.

Very low-frequency surface enhanced raman-scattering - Genack, A.Z.; Weitz, D. A.; Gramila, T. J. (Surface Science, 1980)
We have observed Raman spectra of a very low frequency mode involving surface adsorbed molecules. Scattering from this mode appears to be sensitive to adsorbate orientation. With pyrazine as the adsorbate, the frequency shifts with electrochemical voltage, possibly because of changes in orientation of the molecule on the surface. With pyridine as the adsorbate, we find that the frequency of the peak in the scattered light intensity increases linearly with excitation frequency, suggesting that light is resonantly scattered from the surface adsorbed species.​​​​​​

Capacitive-mesh output couplers for optically pumped far-infrared lasers - Weitz, D. A.; Skocpol, W. J.; Tinkham, M. (Optics Letters, 1978)
The use of capacitive-mesh output couplers for optically pumped far-infrared molecular lasers has been extended throughout the far-infrared spectrum, between 42 μm and 1.2 mm, and the optimum grid constants have been found for several lines. At shorter wavelengths, performance has been improved by the use of a novel hybrid capacitive-mesh hole output coupler.

Characterization of niobium point contacts showing Josephson effects in far infrared - Weitz, D. A.; Skocpol, W. J.; Tinkham, M. (Journal of Applied Physics, 1978)
The high‐frequency behavior of niobium cat‐whisker point contacts has been studied using radiation from an optically pumped far‐infrared laser. When the point contacts are classified on the basis of their high‐frequency performance, their dc I‐V curves fall into recognizable groups. We find that the ac Josephson effect has a strong correlation with the gap‐related structure on the I‐V curve, but none at all with the apparent excess current observed in all the contacts. For high‐performance junctions, these and other features of the I‐V curves are very reproducible from contact to contact, allowing a comparison with the available theories. The experimental evidence seems to suggest that our point contacts are best modeled as extremely small metallic constrictions.

Far-infrared frequency-dependence of the AC Josephson effect in niobium point contacts - Weitz, D. A.; Skocpol, W. J.; Tinkham, M. (Physical Review B, 1978)
We have measured the far-infrared frequency dependence of the strength of the ac Josephson effect in Nb cat-whisker point contacts, which have consistent and reproducible behavior and minimal extrinsic high-frequency limitations due to capacitance and heating. We monitor the constant-voltage Josephson steps induced on the dc I−V curves by an optically pumped far-infrared laser at fundamental frequencies corresponding to voltages from ∼0.2 to ∼2 times the energy-gap voltage. At all the frequencies studied, we find that the shape of the power dependence of the step amplitudes is fit reasonably well by Werthamer's frequency-dependent theory for tunnel junctions in the voltage-bias approximation. However, the observed magnitude of the steps is considerably less than predicted by the theory. By fitting to the I−V curves of the steps, we find that some of this discrepancy can be accounted for by heating-enhanced noise rounding. The remaining discrepancies (of the order of a factor of 2) are attributed to departures from a voltage bias at low frequencies and, tentatively, to the effects of the Ginzburg-Landau relaxation time at higher voltages. Our data confirm the expected intrinsic roll off of the strength of the ac Josephson effect above the energy gap.

High-frequency behavior of ideal superconducting point contacts - Weitz, D. A.; Skocpol, W. J.; Tinkham, M. (Physical Review Letters, 1978)
We have studied niobium point contacts which are very consistent and reproducible from junction to junction, in both their dc and high-frequency behavior. We find a strong correlation between the sharpness of the gap structure and the ac Josephson effect, and we present the first quantitative measurements of the far-infrared frequency dependence of the Josephson effect above the energy gap. The measured I−V curves are also compared with available theoretical models.

Properties of Josephson point-contact far-infrared detectors - Weitz, D. A.; Skocpol, W. J.; Tinkham, M. (Infrared Physics, 1978)
The far-infrared (FIR) properties of niobium cat-whisker point contacts were studied using radiation from an optically pumped FIR laser. The reproducible behaviour of junctions with excellent high-frequency performance allowed a measurement of the FIR frequency dependence of the strength of the a.c. Josephson effect. The shape of the laser-induced steps was used to measure the effective noise temperatures, which increase with bias voltage in agreement with a heating model of metallic constrictions. The high-quality junctions were tested as frequency-selective, incoherent FIR detectors, with the d.c. bias in the vicinity of the incipient laser step. The response was found to be linear in the laser power, and the best measured responsivity at 604 GHz was 2 × 105 V/W, while the best noise equivalent power was 10p−13 W/Hz, with a 450 Hz chopping frequency. The NEP is limited by the voltage noise in the junction, which was found to have an approximately  frequency dependence. The detector performance is degraded considerably at higher FIR frequencies. Also studied was the low-laser-power behaviour of the I–V curves near the critical current, which may be of importance for mixing applications with external local oscillators.

Niobium point-contact Josephson-junction behavior at 604 gHz - Weitz, D. A.; Skocpol, W. J.; Tinkham, M. (Applied Physics Letters, 1977)
We have measured the ac Josephson effect in Nb point contactsat 604 GHz (496 μm). We find the coupling of the far‐infrared radiation to the point contact to depend in a simple manner on the resistance of the contact. The behavior of the high‐resistance point contacts (50⩽R⩽200 Ω) is very reproducible, allowing a quantitative comparison of the data to the frequency‐dependent Werthamer theory. We also account for the effects of noise and heating and compare these to Tinkham’s heating theory.

Wavelength Measurements of C-13 O-16 Laser Transitions - Johns, J. W. C.; Mckellar, A. R.; Weitz, D. (Journal of Molecular Spectroscopy, 1974)
Wavelength measurements of 160 13C16O laser lines in the range from 1500 to 1900 cm−1 have been made with a conventional grating spectrometer. The accuracy of the measurements is about ±0.003 cm−1. Although more precise measurements of these lines will ultimately be made using microwave beating techniques, the present results should be of interest for the determination of improved molecular constants for CO and especially for the various spectroscopic applications of the CO laser.

Delayed Electroluminescence Quenching in Anthracene - Bradley, L.L.T.; Schwob, H.P.; Weitz, D. A.; Williams, D.F. (Molecular Crystals and Liquid Crystals, 1973)
Observations of the transient behaviour of electroluminescence in sublimation flakes have shown that quenching of the delayed electro-luminescence component by the carriers themselves becomes important at high currents. The results show quenching is of the same order as observed for carrier quenching of optically produced triplet excitons. No quenching was observed in thick crystals though carrier densities of the same order are present. This is presumably due to the difference in recombination zone width which may be larger in these thick crystals.

The Variation of the Carrier Recombination Region with Carrier Density in Anthracene Crystals - Schwob, H.P.; Weitz, D. A.; Williams, D.F. (Molecular Crystals and Liquid Crystals, 1973)
The time dependence of slow electroluminescence has been used as an experimental probe for studying the physical characteristics of the recombination region in anthracene. Under conditions where two injecting contacts are used, and neither carrier is trapped to a large extent, the recombination zone is found to occupy approximately 0.3 of the crystal volume for current densities of 10−5-10−8 amps cm−2. When forced hole injection is used, the recombination volume at low currents decreases, particularly at low temperatures. This decrease in recombination volume is discussed in terms of carrier trapping and filament formation.